한국의 대학생을 대상으로 한 성교육 프로그램에 관한 통합적 고찰 - 신혜원; 이정민; 민혜영 (한국간호교육학회지, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:E8QDFIDD
Keywords: _C:Korea XKOR; _C:Korea; Republic KOR; _C:Uganda UGA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Zero-rating educational content in low- and middle-income countries - McBurnie, Chris; Adam, Taskeen; Kaye, Thomas; Haßler, Björn (2020)
EdTechHub.Source: 2405685:F4PCMTZB EdTechHub.Source: 2405685:F4PCMTZB KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3784940 2129771:4W3D35BT 2339240:7VJMDZGM 2339240:RSJNXIC6 2405685:DX5RMV6U 2405685:F4PCMTZB
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; LP: English; _C:Afghanistan AFG; _C:Benin BEN; _C:Botswana BWA; _C:Burkina Faso BFA; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Egypt EGY; _C:Ghana GHA; _C:India IND; _C:Jamaica JAM; _C:Jordan JOR; _C:Kenya KEN; _C:Korea (Republic of) KOR; _C:Korea XKOR; _C:Liberia LBR; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nigeria NGA; _C:Paraguay PRY; _C:Rwanda RWA; _C:Senegal SEN; _C:Somalia SOM; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _bjoern_cv; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Zambia: An overview of formal education - Masaiti, Gift; Chita, Joseph (Education in East and Central Africa, 2014)
Publisher: Bloomsbury London
Keywords: ⛔ No DOI found

Youth unemployment in resource-rich Sub-Saharan Africa: A critical review - Ackah-Baidoo, Patricia (The Extractive Industries and Society, 2016)
This paper critically reviews the youth unemployment crisis in resource-rich Sub-Saharan Africa. Although the region has experienced continuous and a seemingly limitless ﬂow of investment in all types of extractive industries in recent decades, this growth has not directly translated into signiﬁcant poverty reduction. Its overdependence on natural resources economically seems to have had a negative impact on socioeconomic development overall, generating very few jobs for youth and exacerbating existing unemployment crises. The paper uses Ghana, one the region’s top mineral-rich countries, as a case study to explore these issues further.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.exis.2015.11.010 10/gf62j7 2129771:5IQB689N 2317526:V2TDX9MD
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; CLL:en; _C:Ghana GHA; __C:filed:1; publicImportV1

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTechHub.Source: 2405685:VX7UW757 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3874247 2129771:LBII97HZ 2339240:FT2TLP7Q 2339240:J7DSQVEZ 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Bhutan BTN; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Colombia COL; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Congo; Republic COG; _C:El Salvador SLV; _C:France FRA; _C:Kenya KEN; _C:Kyrgyzstan KGZ; _C:Lebanon LBN; _C:Maldives MDV; _C:Mexico MEX; _C:Nepal NPL; _C:Nigeria NGA; _C:Peru PER; _C:Sierra Leone SLE; _C:Somaliland XSMLD; _C:South Africa ZAF; _C:South Sudan SSD; _C:Spain ESP; _C:Sudan SDN; _C:Zimbabwe ZWE; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-dode

Worldreader | Sierra Leone - Worldreader (2020)
Worldreader brings digital reading to schools in Sierra Leone in partnership with the Klintworth Family Foundation.
Library Catalog: www.worldreader.org KerkoCite.ItemAlsoKnownAs: 2129771:2EGLUVQQ 2405685:FHAMLZRG
Keywords: _C:Sierra Leone SLE

Work-integrated learning for TVET lecturers: Articulating industry and college practices - Bijl, André van der; Taylor, Vanessa (Journal of Vocational, Adult and Continuing Education and Training, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:UVFWWSSX 2317526:CCAQJSZP
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:LOW; -RRQ:M:final; C:South Africa; RRQ:other; __C:filed:1; publicImportV1; ⛔ No DOI found

Women's access to agricultural technologies in rice production and processing hubs: A comparative analysis of Ethiopia, Madagascar and Tanzania - Achandi, Esther L.; Mujawamariya, Gaudiose; Agboh-Noameshie, Afiavi R.; Gebremariam, Shewaye; Rahalivavololona, Njaka; Rodenburg, Jonne; Rahalivavololona, Njaka; Rodenburg, Jonne; Rodenburg, Jonne (Journal of Rural Studies, 2018)
© 2018 Elsevier Ltd This study presents results from a farmer survey conducted with 560 rice farmers from 27 villages spread over five hubs (concentration areas of rice production and processing) in three different countries in Eastern Africa (Ethiopia, Tanzania and Madagascar). The main research objective was to assess women's access to rice technologies and constraints to adoption of technologies. Constraints were analyzed over five different categories: (1) institutional (2) access to agricultural inputs, (3) technology-contextual, (4) household and socio-cultural and (5) extension. Key providers of extension were public (government), Non-Governmental Organizations (NGOs) and international organizations. Our study identifies that the overarching constraints to technology adoption are institutional and cultural impediments and related to the mode of delivery of extension services. Furthermore, the Focus Group Discussions (FGD) with the women, revealed that empowerment of women in decision making at the household level can enhance women's access and engagement in better farming practices suggested under extension advisory services. This is specifically true where women are able to overcome the hurdles of acquisition of extension training and access to the improved technologies.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jrurstud.2018.03.011 10/gf62jz 2129771:7UPXJXRQ 2317526:HEL4WL56
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:eastern Africa; C:Ethiopia; C:Madagascar; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:access; F:women; P:agricultural; P:culture; P:production; P:services; P:technology; R:focus groups; R:survey; T:Training; __C:filed:1; publicImportV1

Wnioski z międzynarodowych doświadczeń w wykorzystywaniu tablic interaktywnych - rola doskonalenia zawodowego we wprowadzaniu nowych technologii do szkół - Hennessy, Sara; London, Laura; Dzierzgowski, Jan (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:ES3KSIUM
Keywords: _C:Australia AUS; _C:Mexico MEX; _C:Tanzania TZA; _C:United Kingdom GBR; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

‘Without Education You Can Never Become President’: Teenage Pregnancy and Pseudo-empowerment in Post-Ebola Sierra Leone - Menzel, Anne (Journal of Intervention and Statebuilding, 2019)
This article analyses the emergence of ‘teenage pregnancy’ as a new policy focus in post-Ebola Sierra Leone and explores how Sierra Leoneans interpret the problem of ‘teenage pregnancy’. I argue that the new policy focus is not indicative of changing or new problems. Rather, ‘teenage pregnancy’ has created opportunities for donors and the Government of Sierra Leone to continue cooperation in gender politics. At the same time, Sierra Leoneans are clearly concerned about ‘teenage pregnancy’, and many agree with sensitization campaigns that responsibilize young women and girls while downplaying structural factors that render them vulnerable to arrangements involving transactional sex.
Publisher: Routledge _eprint: https://doi.org/10.1080/17502977.2019.1612992 KerkoCite.ItemAlsoKnownAs: 10.1080/17502977.2019.1612992 2129771:S4K2JMQ3 2129771:VERU8P94 2405685:MKDQ3K53
Keywords: Sierra Leone; _C:Sierra Leone SLE; aid and development; gender politics; neoliberalism; sexual violence; teenage pregnancy

Who has what? Assessing who has access to what devices in the education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris; Adam, Taskeen; Allier-Gagneur, Zoe (Open Development & Education, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:LABCYNPR 2129771:P36LQR3G 2129771:QIX7PIBG 2129771:T6Q8K4IR 2339240:CFWFBGB5 2405685:JMDCGPBJ 2405685:LQY8MDMV 2486141:342IZ4L3
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _C:Ghana GHA; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:x

Where it's needed most: Quality professional development for all teachers - Burns, M.; Lawrie, J. (Inter-Agency Network for Education in Emergencies, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:7944FCFC 2129771:T2JI2EYX 2405685:XABT3JHM
Keywords: C:Fragile contexts; _C:Afghanistan AFG; _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Brazil BRA; _C:Cambodia KHM; _C:Canada CAN; _C:Central African Republic CAF; _C:Chile CHL; _C:Colombia COL; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Ethiopia ETH; _C:France FRA; _C:Gambia GMB; _C:Ghana GHA; _C:Guatemala GTM; _C:Guinea GIN; _C:Guinea-Bissau GNB; _C:Haiti HTI; _C:Honduras HND; _C:India IND; _C:Indonesia IDN; _C:Iraq IRQ; _C:Japan JPN; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Mali MLI; _C:Mexico MEX; _C:Myanmar MMR; _C:Nepal NPL; _C:Netherlands NLD; _C:New Zealand NZL; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:Singapore SGP; _C:Somalia SOM; _C:Somaliland XSMLD; _C:South Africa ZAF; _C:South Sudan SSD; _C:State of Palestine PSE; _C:Sudan SDN; _C:Switzerland CHE; _C:Syrian Arab Republic SYR; _C:Tanzania TZA; _C:Thailand THA; _C:Tunisia TUN; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Yemen YEM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6530321 10.53832/edtechhub.0095 2129771:G2ULWZXN 2405685:8GN4RWMR
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

What matters most for education management information systems: A framework paper - Abdul-Hamid, Husein (2014)
Publisher: World Bank Group, Washington, DC KerkoCite.ItemAlsoKnownAs: 2129771:C4JC4EQI
Keywords: _C:Antigua and Barbuda ATG; _C:Australia AUS; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Benin BEN; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:Djibouti DJI; _C:Dominica DMA; _C:Ethiopia ETH; _C:Ghana GHA; _C:Grenada GRD; _C:Guinea GIN; _C:India IND; _C:Indonesia IDN; _C:Japan JPN; _C:Jordan JOR; _C:Liberia LBR; _C:Malawi MWI; _C:Malaysia MYS; _C:Mali MLI; _C:Mozambique MOZ; _C:Nicaragua NIC; _C:Nigeria NGA; _C:Pakistan PAK; _C:Philippines PHL; _C:Saint Kitts and Nevis KNA; _C:Saint Vincent and the Grenadines VCT; _C:Senegal SEN; _C:State of Palestine PSE; _C:Sudan SDN; _C:Thailand THA; _C:Tunisia TUN; _C:Turkey TUR; _C:Uganda UGA; _C:United States USA; _C:Yemen YEM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

What impact do climate conditions in classrooms have on teachers? - Koomar, Saalim (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912313 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1129 ZenodoArchiveConcept: 10912312
Keywords: _publish; _r:AddedByMyEducationEvidence

What are the impacts and cost-effectiveness of strategies to improve performance of untrained and under-trained teachers in the classroom in developing countries?: systematic review - Orr, David; Westbrook, Jo; Pryor, John; Durrani, Naureen; Sebba, Judy; Adu-Yeboah, Christine; others (EPPI-Centre, Social Science Research Unit, Institute of Education, University of London, 2013)
KerkoCite.ItemAlsoKnownAs: 2129771:9YW97PKU 2129771:F4Q5DIY8 2129771:LZYDA4UF 2405685:YAT9NL4R 2486141:LAE22MA6 261495:XSK2293Z
Keywords: C:Low- and middle-income countries; STC-TLC; _C:Afghanistan AFG; _C:Algeria DZA; _C:Angola AGO; _C:Antigua and Barbuda ATG; _C:Argentina ARG; _C:Armenia ARM; _C:Australia AUS; _C:Azerbaijan AZE; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Barbados BRB; _C:Belize BLZ; _C:Benin BEN; _C:Bhutan BTN; _C:Bolivia BOL; _C:Botswana BWA; _C:Brazil BRA; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Central African Republic CAF; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Costa Rica CRI; _C:Cuba CUB; _C:Djibouti DJI; _C:Dominica DMA; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Federated States of Micronesia FSM; _C:Fiji FJI; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Grenada GRD; _C:Guatemala GTM; _C:Guinea GIN; _C:Guyana GUY; _C:Haiti HTI; _C:Honduras HND; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Ivory Coast CIV; _C:Jamaica JAM; _C:Japan JPN; _C:Jordan JOR; _C:Kazakhstan KAZ; _C:Kenya KEN; _C:Kiribati KIR; _C:Korea XKOR; _C:Kosovo XKSVO; _C:Kyrgyzstan KGZ; _C:Laos LAO; _C:Lebanon LBN; _C:Lesotho LSO; _C:Liberia LBR; _C:Libya LBY; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Maldives MDV; _C:Mali MLI; _C:Marshall Islands MHL; _C:Mauritania MRT; _C:Mauritius MUS; _C:Mexico MEX; _C:Mongolia MNG; _C:Montenegro MNE; _C:Morocco MAR; _C:Mozambique MOZ; _C:Myanmar MMR; _C:Namibia NAM; _C:Nepal NPL; _C:Netherlands NLD; _C:Nicaragua NIC; _C:Niger NER; _C:Nigeria NGA; _C:Oman OMN; _C:Pakistan PAK; _C:Palau PLW

West African Senior School Certificate Examination: Sierra Leone Results Analysis - Ministry of Basic and Secondary Education (2022)
KerkoCite.ItemAlsoKnownAs: 2129771:P4P34Q78 2339240:2WY3SC9N 2405685:YKA8Y8DM
Keywords: _C:Sierra Leone SLE

Vulnerability, partnerships and the pursuit of survival: Urban livelihoods and apprenticeship contracts in a West African City - Hanson, Kobena (GeoJournal, 2005)
This paper analyses local level apprenticeship contracts and networks to highlight informal urban livelihoods within the context of socio-economic vulnerability and wider contemporary changes taking place in Koforidua, Ghana. It does so by specifically examining the complex entanglements of interpersonal relationships that characterize apprenticeship contracts within which home-based entrepreneurs and artisans in Koforidua engage in to sustain both current livelihoods, as well as to shore themselves against socio-economic vulnerability triggered in part by adjustment. As a result of the changing geography of the city, network entanglements, comprising resilient ties and egalitarian relations, have become vital to urban livelihoods in this community. However, apprenticeship contracts and the networks they engender can be a double-edged sword. For instance, demands of reciprocity or support from co-network members, neighbours and family, can be so taxing that some individuals opt out of the network. This tension notwithstanding, this paper contends that apprenticeship contracts and the network spaces they create have created a new social cohesion and community that transcend the traditionally known spaces of social support, i.e. ethnic ties, family ties or even institutional support. © Springer 2005.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10708-005-7915-1 10/cjzk3k 2129771:QJBKZ3W3 2129771:W58GJ244 2317526:CDMIR86U 2317526:XVHN9P2E
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; CA:AandC; CCZ:Ghana; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:artist; P:economy; P:measurement; P:social; T:Lehrlingsausbildung; Z:Apprenticeship contracts; Z:Micro-enterprises; Z:Social networks; Z:Socio-economic vulnerability; Z:Urban livelihoods; _C:Ghana GHA; publicImportV1

Voices Confined to Classrooms: The Marginalised Status of Teachers in Curriculum Development in Lusaka, Zambia - Mwanza, Christine (2018)

Vocational Education and Training through Open and Distance Learning: World review of distance education and open learning - Moran, L; Rumble, G (2004)
The world needs workers with more and better skills. Conventional apprenticeships and old methods of professional training are not providing enough skilled workers, so governments, companies and colleges are all using open and distance learning to fill these gaps. This unique international review of experience looks at the policies needed in both the private and the public sector for effective vocational education and training at all levels – from basic skills to continuing professional education. It goes on to examine the new roles of information and communication technologies, establishing what we know about their performance, and identifying the choices to be made in applying technologies to vocational education and training. The book will help senior institutional managers and policy makers to understand and appreciate: • the role distance education can play in increasing skills levels in young people and the existing workforce; • the potential advantages and disadvantages of using technology, and therefore make better-informed choices about technology use; • how to integrate distance education with traditional educational models and approaches.
KerkoCite.ItemAlsoKnownAs: 2129771:26J6H6AI 2317526:754E3R6X
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:policy; P:measurement; P:media; P:teacher education; Q:ICT; Q:ODEL; Q:distance education; Q:distance learning; Q:educational technology; Q:open learning; T:Ausbildung; T:Educação Profissional Técnica de Nível Médio; T:Educação profissionalizante; T:Fortbildung; T:Lehrlingsausbildung; T:TVET; T:continuing education; T:work-based learning; publicImportV1; ⛔ No DOI found

Vocational education and training in Sub-Saharan Africa: current situation and development - Eicker, F; Haseloff, G; Lennartz, B (W. Bertelsmann Verlag GmbH & Co. KG, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:DJ6ESH6T 2129771:FKBCF6JJ 2317526:GAA92EKQ 2317526:IJ4BRW4E
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; A:Sub-Saharan Africa; C:Namibia; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; P:economy; P:teachers; Q:higher education; T:Educação profissionalizante; T:TVET; T:in-service TVET; publicImportV1

Vocational education and training in southern Africa: a comparative study - Akoojee, Salim; Gewer, Anthony; McGrath, Simon A. (2005)
Introduction This volume is intended to develop and share knowledge within the southern African region regarding the challenges faced by vocational education and training (VET) systems and the responses to these challenges. Some of these challenges arise out of the history of VET in the region, whilst others relate to current international discourses about VET. The field of VET in southern Africa has been badly neglected. It is very difficult to find an article in the international journals on the topic, and it is even less likely that it will have been written by a national of the region, based at one of its research institutions. VET has also attracted little attention in the policy community for more than a decade, given the donor fascination with basic education since the World Conference on Education for All in 1990 (McGrath 2002). However, VET can play an important role in supporting social and economic development goals, and major VET policy reforms and the creation of new institutions are either underway or planned in all seven countries under study in this book. Therefore, it is my intention in this introduction to illuminate the nature of some of these changes, their origins and their likelihood of success. In so doing, I will show how VET is an important policy nexus – located as it is between economic and educational policy, between the state and the market, and between concerns with poverty and growth. Before this volume turns to examine this complexity through an exploration of the experiences of seven countries (Botswana, Lesotho, Mauritius, Mozambique, Namibia, South Africa and Swaziland), it is important to locate these national and contemporary debates in the historical evolution of ideas about VET. In so doing, I will look at both internal trends within Africa and the impact of external ideas.
KerkoCite.ItemAlsoKnownAs: 2129771:PRN4YC58 2317526:2ETPJUUU
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; AA:Africa; Southern; C:Botswana; C:Lesotho; C:Mauritius; C:Mozambique; C:Namibia; C:South Africa; C:eSwatini; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:Q; CT:T; Q:ICT; T:TVET; Vocational education; publicImportV1

Vocational Education and Training for Sustainability in South Africa: The Role of Public and Private Provision - McGrath, Simon; Akoojee, Salim (International Journal of Educational Development, 2009)
Written in the twilight of the Mbeki Presidency, this paper considers the role that skills development has in the sustainability of the South African political-economic project. It explores some of the disarticulations of public policy and argues that these both undermine public sector delivery and open up opportunities for private provision to be, under certain circumstances, more responsive to the challenges of national development. We argue that there is a possibility that the state could work more smartly with both sets of providers. Crucially, however, this would necessitate working more smartly within itself. This was a major plank of the Mbeki strategy but it has failed conspicuously with regard to the Education-Labour relationship. Whether a new President can achieve a radical reworking of this relationship may be an important indicator of the viability of any new development project. (Contains 1 table.)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2008.09.008 10/bnnh2c 2129771:L24MHEVT 2317526:PHJKJ53J
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:attitude; F:pay; F:policy; P:economy; P:social; T:TVET; Z:Economic Development; Z:Educational Development; Z:Foreign Countries; Z:Political Attitudes; Z:Politics; Z:Presidents; Z:Public Policy; Z:Public Sector; Z:Role; Z:Skill Development; Z:Sustainable Development; Z:Vocational Education; publicImportV1

Vocational education and training for development: A policy in need of a theory? - McGrath, Simon (International Journal of Educational Development, 2012)
The current decade has seen a significant return of interest in vocational education and training (VET) amongst the international policy community. This rise in policy and programmatic interest in VET's role in development, however, stands in contrast to the state of the academic debate. Whilst there have continued to be both policy and academic developments in VET in OECD countries; in the South there has been a paucity of VET research and little in the way of theoretical exploration. Rather, the academic orthodoxy in the international education and development field is dismissive of VET's possible contribution. Given the return of the policy interest in VET for development, and the possibilities of a broader vision of education–development relations beyond 2015, when the MDGs end, it is time to revisit the role of VET in development from an explicitly theoretical stance. In this article, I argue that the current approach to VET is grounded in an outmoded model of development, whilst the academic critique of VET in developing countries is clearly long outdated. In contrast, I examine the implications for VET of recent trends in thinking about development through the exploration of three particular theoretical approaches: human rights, capabilities and integrated human development. I conclude by considering the purposes, natures and possibilities of VET as a means of human development.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2011.12.001 10/fzsb6q 2129771:3MJ4MM34 2317526:RP7TJBIY
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:Q; CT:T; Development theory; F:learning; F:policy; Human development; Q:distance learning; Q:mobile learning; T:Educação profissionalizante; T:TVET; Vocational education and development; publicImportV1

VLIV POUŽITÍ MOBILNÍHO DOTYKOVÉHO ZAŘÍZENÍ PŘI PROCVIČOVÁNÍ UČIVA - Klubal, Libor (Klára Rybenská Experimentální ověření efektivity vỳuky anglického jazyka s využitím myenglishlab........... 128 Danuše Vymetálková, 2016)
00000 EdTechHub.ItemAlsoKnownAs: 2129771:EI2AHPC3
Keywords: _C:Australia AUS; _C:Bulgaria BGR; _C:Chile CHL; _C:China CHN; _C:Czech Republic CZE; _C:Ethiopia ETH; _C:Greece GRC; _C:Luxembourg LUX; _C:Norway NOR; _C:Poland POL; _C:Romania ROU; _C:Singapore SGP; _C:Spain ESP; _C:Sweden SWE; _C:Tunisia TUN; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Video as a tool for agricultural extension in Africa: a case study from Ghana - David, Soniia; Asamoah, Christopher (International Journal of Education and Development using ICT, 2011)
The paper explores the effectiveness of video viewing clubs (VVCs) as a training method based on a formal survey of 32 Ghanaian women farmers who were trained on cocoa integrated crop and pest management (ICPM) using this method. Results suggests that the video viewing club is effective as a relatively low cost, interactive training method for providing low literacy populations with skills, information and knowledge on complex technical topics. While there was no significant difference between VVC participants and a control group in cocoa yields and implementation of selected ICPM practices, the study demonstrated that VVC training significantly improved farmers' knowledge of most topics covered. Farmers' perception of changes in their practices provided further evidence of the positive impact of the training, as did their high rate of knowledge diffusion. The use of local facilitators in the VVCs, which created a sense of ownership and added to the credibility of the technical messages, contributed to farmers' appreciation of the method. The paper concludes by discussing the challenges of scaling up VVCs and identifying issues for further research. [PUBLICATION ABSTRACT]
KerkoCite.ItemAlsoKnownAs: 2129771:XZ5EUUA2 2317526:GWMBRM44
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:women; HDR25; P:agricultural; Q:distance learning; Q:educational technology; Q:interactive; R:case study; R:impact; R:survey; T:Training; T:trainee; Z:Agricultural education; Z:Cocoa; Z:Distance learning; Z:Educational technology; Z:Farmers; Z:Video; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Uso da tecnologia assistiva na educação inclusiva no processo de alfabetização de escolares: revisão sistemática - Biazus, Graziela Ferreira; Rieder, Carlos Roberto Mello (Revista Educação Especial, 2019)
KerkoCite.ItemAlsoKnownAs: 10.5902/1984686X33317 2129771:BFN8WIS7
Keywords: _C:Austria AUT; _C:South Africa ZAF; _C:Spain ESP; _C:United States USA; __C:filed:1; __C:scheme:1

Using the Capability Approach to improve female teacher deployment to rural schools in Nigeria - Tao, Sharon (International Journal of Educational Development, 2014)
This study focuses on the socio-cultural and institutional factors that affect female teacher deployment in rural primary schools in Nigeria. In Kwara State, there are extreme imbalances in teacher distribution between rural and urban areas due to female teachers’ active avoidance and/or attrition from rural posts. Given these problems, this article discusses an innovative use of the Capability Approach that informed a rural teacher deployment policy that addressed a number of issues that were specifically identified through female teachers’ values and lived experiences. This research not only had the positive analytical and political effects of prioritising the knowledge, participation and empowerment of female teachers; but it also provided a more fine-grained and holistic understanding of issues hindering effective deployment and retention of female Nigerian teachers, which informed the development of comprehensive and relevant strategies to address these.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2014.08.011 2129771:X48NF6KT
Keywords: Lebanon_event_2021; _C:Bangladesh BGD; _C:Canada CAN; _C:Ethiopia ETH; _C:Ghana GHA; _C:India IND; _C:Kenya KEN; _C:Lesotho LSO; _C:Liberia LBR; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nigeria NGA; _C:Norway NOR; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sudan SDN; _C:Tanzania TZA; _C:Uganda UGA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6497554 2129771:S33JRRK6 2405685:KAZQRPA7
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Using Open and Educational Resources (OERs) and Wiki’s to Support Entrepreneurship Training in Technical and Vocational Education and Training (TVET) Institutions in Zambia - Konayuma, G (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:EVAW675M 2317526:6BWLASND
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:Improvement; F:access; F:bandwidth; F:policy; Q:ICT; Q:ODEL; Q:OER; Q:digital technology; Q:educational technology; Q:open education; Q:open educational resources; Q:open learning; T:Ausbildung; T:TVET; T:Training; T:trainee; publicImportV1

Using Interactive Radio Instruction to mitigate the educational impact of COVID-19: a curated resource list - McBurnie, Chris (2020)
EdTechHub.Source: 2405685:A3T2DQ4D EdTechHub.Source: 2405685:A3T2DQ4D KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 2129771:QQWNSYJR 2129771:U4Q6CU8B 2339240:45F2G56T 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: Author:OpenDevEd; COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _C:Liberia LBR; _C:Pakistan PAK; _C:Sierra Leone SLE; _C:Sudan SDN; _C:Tanzania TZA; _C:Zambia ZMB; _EdTechHub_Output; __C:filed:1; __C:scheme:1; ___duplicate_item; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using examination and learning assessment data to uncover foundational skill gaps in Sierra Leone’s secondary schools - Waistell, Daniel; De, Sourovi; Ofori Owusu, Diana; Allen, Reg; Sanni, Kayode; Dupigny, Albert (Education technology and data science for inclusive systems, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:DDMJMXGM 2405685:J8IWHLVQ
Keywords: _C:Sierra Leone SLE; ⛔ No DOI found

Using education technology to support learners with special educational needs and disabilities in low- and middle-income countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
EdTechHub.Source: 2405685:2WY8H4WW KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3744581 2129771:QEIBUIQH 2405685:2WY8H4WW 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:GG9HHSDL
Keywords: L:Special education needs and disabilities (SEND); LP: English; _C:Brazil BRA; _C:Ghana GHA; _C:India IND; _C:Kenya KEN; _C:Lesotho LSO; _C:Pakistan PAK; _C:Portugal PRT; _C:South Africa ZAF; _C:Spain ESP; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-dode

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
EdTechHub.Source: 2405685:HLCYI98H KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 2129771:FCNVWJUI 2129771:FYPWV8NM 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H DOI:
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _C:Afghanistan AFG; _C:Algeria DZA; _C:Bangladesh BGD; _C:Burkina Faso BFA; _C:Chad TCD; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Egypt EGY; _C:France FRA; _C:Iraq IRQ; _C:Jordan JOR; _C:Kuwait KWT; _C:Lebanon LBN; _C:Liberia LBR; _C:Netherlands NLD; _C:Nigeria NGA; _C:Sierra Leone SLE; _C:South Sudan SSD; _C:Sudan SDN; _C:Syrian Arab Republic SYR; _C:Turkey TUR; _C:Uganda UGA; _C:Yemen YEM; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Using digital technology and school-based professional development to leverage interactive classroom teaching in Zambia - Hennessy, Sara; Haßler, Björn; Mwewa, G. (Millennium Goals Revisited: A Common Wealth of Learning, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:UQKD4B63 2129771:ZTJE5WPC 261495:HNV94NFU
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _r:ImportedToMyEducationEvidence

Using digital technology and school-based professional development to leverage interactive classroom teaching in Zambia - Hennessy, Sara; Haßler, Björn; Mwewa, G (2016)
This chapter describes a study which explored the feasibility of using information and communications technologies (ICTs) to support more interactive forms of subject teaching and learning in Sub-Saharan Africa. Specifically, we: • provided open educational resources (OER) to three ICT-and Internetequipped primary schools in Zambia, all serving disadvantaged communities; • worked with partners to identify the needs of school-based continuing professional development (CPD) adapted to the local context; • responded to those needs by designing an appropriate intervention – focusing on participatory, collaborative and interactive pedagogies supported by ICTs and OER, both within the classroom and for teacher development.
KerkoCite.ItemAlsoKnownAs: 2129771:QG8ESI5B 2317526:CWBQU3Q9
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:teaching; P:teacher education; P:teachers; Q:ICT; Q:OER; Q:digital technology; Q:interactive; Q:interactive pedagogy; Q:open educational resources; Q:primary education; R:evaluation; T:Classroom teaching; Z:ICT in education; Z:Intervention evaluation; Z:Primary education; Z:Teacher education; publicImportV1

Using blended learning to support marginalised adolescent girls’ education: a review of the evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952069 2129771:9Q4PMCJN 2129771:FX6TFDPQ 2339240:ENEKVCE3 2405685:7PYD5JNV 2405685:H3AI5F3C 2486141:TE93MW3V
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Brazil BRA; _C:China CHN; _C:Ghana GHA; _C:India IND; _C:Iran IRN; _C:Kenya KEN; _C:Lebanon LBN; _C:Malawi MWI; _C:Malaysia MYS; _C:Nigeria NGA; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Turkey TUR; _C:Uganda UGA; _C:United States USA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _genre:LR-literature_review; _r:ImportedToMyEducationEvidence

University education in Zambia in the face of austerity: history, trends and financing. - Masaiti, Gift; Simuyaba, Eunifridah (UNZA Press, 2018)

Universal Access Development Fund | Home - Universal Access Development Fund (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:AVUVWP3X 2405685:FNIEIP9B

UNEVOC World TVET Database: Uganda - UNESCO-UNEVOC (2014)
KerkoCite.ItemAlsoKnownAs: 2129771:UQ6LJ4WG 2317526:EMWFCMYD
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; publicImportV1

UNEVOC World TVET Database: Tanzania - UNESCO-UNEVOC (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:RD3Z2W99 2317526:MTLEG9I9
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Tanzania; publicImportV1

UNEVOC World TVET Database: Nigeria - UNESCO-UNEVOC (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:NAMI6L7Y 2317526:3M2K379W
Keywords: -FullBiblioUHMLgen; -GeneralCitations; C:Nigeria; CC:Nigeria; publicImportV1

UNEVOC World TVET Database: Kenya - UNESCO-UNEVOC (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:7P2TYCJ4 2317526:457AVM6J
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; publicImportV1

UNEVOC World TVET Database: Botswana - UNESCO-UNEVOC (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:WLP56L3H 2317526:A5LT8Q49
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; publicImportV1

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? - McBurnie, Chris; Godwin, Katie; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 2129771:DUAVS9AV 2405685:KAAC2B78
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Understanding Sub-Saharan African Learners Informal Learning Using Mobile Devices: A Case of Tanzania - Bagui, Laban; Mwapwele, Samwel Dick (The African Journal of Information Systems, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:BSNGFZWN 2129771:G9MGFU35
Keywords: HDR25; _C:Australia AUS; _C:Botswana BWA; _C:Cameroon CMR; _C:Dominican Republic DOM; _C:Eritrea ERI; _C:Gambia GMB; _C:Malaysia MYS; _C:New Zealand NZL; _C:Rwanda RWA; _C:Senegal SEN; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Togo TGO; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2129771:68VY6GT6
Keywords: _C:Sierra Leone SLE

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Publisher: Routledge _eprint: https://doi.org/10.1080/03050068.2017.1338641 KerkoCite.ItemAlsoKnownAs: 10.1080/03050068.2017.1338641 2129771:UVNJFUHG 2405685:9FVX5LB3
Keywords: Education; Liberia; Sierra Leone; _C:Sierra Leone SLE; teachers; teaching about conflict; transitional justice

Understanding elementary teachers' experiences and views using interactive whiteboards for pedagogical practices - Samsonova, Olga (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:ZWFEFQ8M
Keywords: _C:Australia AUS; _C:Canada CAN; _C:Cyprus CYP; _C:Egypt EGY; _C:Iran IRN; _C:Jordan JOR; _C:Lithuania LTU; _C:Malaysia MYS; _C:Netherlands NLD; _C:North Cyprus XNCYP; _C:Spain ESP; _C:Sweden SWE; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Understanding a competency-based curriculum and education: The Zambian perspective - Mulenga, Innocent Mutale; Kabombwe, Yvonne Malambo (Journal of Lexicography and Terminology (Online ISSN 2664-0899. Print ISSN 2517-9306)., 2019)
Keywords: ⛔ No DOI found

Uganda Vocational Qualifications Framework (UVQF) Summary of Generic Level Descriptors - Government of Uganda (Directorate of Industrial Training, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:AS2NGQU8 2317526:NCF9TRC7
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; publicImportV1

TVETA Competency Based Education and Training and Assessment Standards & Guidelines - Government of Kenya (2018)
UA-e24c707c-dc52-4d1d-98a2-551c3a4beb60 KerkoCite.ItemAlsoKnownAs: 2129771:L5K8C4SH 2317526:VAL4BH32
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; Qualification Framework; publicImportV1

TVET teacher education in Africa - Grijpstra, Douwe (2015)
This study has three broad objectives. Firstly, it seeks to compare experiences on the education and training of Technical and Vocational Education and Training (TVET) teachers in South Africa, Egypt, Ghana, Tanzania, and Cameroon. Secondly, it seeks to get input from inspiring practices from European Member States. Lastly, policy pointers should be proposed for further action. This study was commissioned as part of the South Africa - EU Strategic Partnership sectoral policy dialogue in education. Data was collected between December 2014 and September 2015. The study serves as input to that policy dialogue, in particular in relation to the education and training of upper secondary and higher TVET teachers working in institution-based TVET providers in the formal public education system. Teachers are the most important in-school factor influencing the quality of student learning and the training of teachers is the key issue in this report. However, able practitioners do not necessarily reach their potential without appropriate support nor without being sufficiently professionally challenged and rewarded. The quality of TVET teaching also depends on other factors, such as the teacher's persona; the TVET organisation (at school or college level) and the wider TVET system (national structures related to TVET of which TVET teacher education is an important element). The main research activities consisted of desk research; interviews; country studies; and comparative analysis and reporting. To validate the findings and ensure a practical link to further dissemination of the results, policy workshops were organised with policymakers in the participating countries. In this summary, key conclusions are discussed per topic. For each topic, policy pointers are presented.
KerkoCite.ItemAlsoKnownAs: 2129771:S3TWILSU 2317526:E5TP2GEZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Cameroon; C:Egypt; C:South Africa; C:Tanzania; CLL:en; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

TVET Strategic Plan 2018-2022 - Government of Kenya (2018)
A Strategic Plan that is aligned to both the dynamic operating environment and the strategic priorities of the Government as outlined in the Kenya Vision 2030, the Constitution of Kenya 2010, and other relevant regional and international policy documents serves as a guide for the organization. I am, therefore, pleased to participate in unveiling of TVETA’s 2018-2022 Strategic Plan which provides a clear road map for the achievement of competitive human capital. The development of this Strategic Plan was based on a review of the Authority’s performance and experiences since its inception, and is a culmination of an extensive consultative process among the Authority’s staff, board of directors and key stakeholders in the country. Our vision and mission are geared towards realizing our mandate by clearly identifying strategic objectives to pursue that conform to our core values. We are aware that this can only be achieved if we continuously align with the dynamism of our operating environment with a view to facilitating fair and competitive practices, while catalyzing the ever-evolving creativity and innovation of the Kenyan public
KerkoCite.ItemAlsoKnownAs: 2129771:AB3ILQTQ 2317526:L7Y2ZTG6
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; publicImportV1

TVET and community reintegration: exploring the connections in Sierra Leone's DDR process - Paulson, J. (International handbook of education for the changing world of work: bridging academic and vocational learning, 2009)
KerkoCite.ItemAlsoKnownAs: 2129771:BMIYWWKM 2405685:SI333Z4W
Keywords: _C:Sierra Leone SLE

TVET Act, nº29 of 2013 - Technical and Vocational Education and Training Act (Kenya) - L.N. 95/2013, L.N. 57/2014 - Government of Kenya (2013)
An Act of Parliament to provide for the establishment of a technical and vocational education and training system; to provide for the governance and management of institutions offering technical and vocational education and training; to provide for coordinated assessment, examination and certification; to institute a mechanism for promoting access and equity in training; to assure standards, quality and relevance; and for connected purposes
UA-fb89b6bc-0740-414a-82e2-54cf9a036c63 KerkoCite.ItemAlsoKnownAs: 2129771:LKHJI62C 2317526:PTGH7PN5
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; publicImportV1

Trialling environmental sensors in Tanzanian schools – first pilot - Toyinbo, Oluyemi; Villavicencio, Xuzel; Haßler, Björn (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257287 ZenodoArchiveConcept: 10257286 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1035 2129771:NFNWZX3A
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Travel without visas: teacher perception of a technology intervention in the Dadaab refugee camp - Mansour, Rebecca Grace Telford (University of Leicester, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:SEYEF9IQ
Keywords: _C:Afghanistan AFG; _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Cuba CUB; _C:Djibouti DJI; _C:Ethiopia ETH; _C:Germany DEU; _C:Greece GRC; _C:Guinea GIN; _C:India IND; _C:Indonesia IDN; _C:Israel ISR; _C:Kenya KEN; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Myanmar MMR; _C:Netherlands NLD; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Portugal PRT; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Senegal SEN; _C:Singapore SGP; _C:Somalia SOM; _C:Somaliland XSMLD; _C:South Sudan SSD; _C:Spain ESP; _C:State of Palestine PSE; _C:Sudan SDN; _C:Switzerland CHE; _C:Syrian Arab Republic SYR; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Yemen YEM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Transforming education service delivery in Sierra Leone: from evidence to action - Sengeh, David Moinina; May-Wilson, Hannah (Global Partnership for Education, 2020)
Sierra Leone’s education system has been plagued by events that have challenged the effective delivery of high-quality education for every child for nearly three decades. But thanks to a program launched in 2018, the government is achieving greater access, quality, and equity for children by removing financial barriers to school enrollment and improving teaching and learning outcomes.
KerkoCite.ItemAlsoKnownAs: 2129771:UJIW9JVC 2339240:BFQBRATB 2405685:PS758V8V
Keywords: _C:Sierra Leone SLE

Training Teachers at a Distance: Perceptions and Challenges of Open and Distance Learning (ODL) in Teacher Education the Zimbabwean Experience - Samkange, Wellington (Turkish Online Journal of Distance Education, 2013)
Zimbabwe like most developing countries continues to experience shortages in skills. One such area that has experienced skills shortages is education. This has resulted in governments and education institutions coming up with innovative ways to improve the training of of teachers. Such innovative models include the Open & Distance Learning (ODL) model in the development of skills. In some instances, there has been a combination of the conventional model and the ODL model. The purpose of the study was to examine the different methods used in the training of teachers and the role of ODL in addressing skills shortages. The study used the qualitative methodology and the case study design. The respondents were purposively selected. Data was collected through lesson observations, document analysis and open-ended questionnaires that were administered to senior teachers, deputy school heads and school heads. These gave a total of twenty respondents from different schools. At the same time twenty trainee teachers in different programmes with the Zimbabwe Open University (ZOU) were observed teaching and were assessed. The study also examined views, attitudes and perceptions about the training of teachers. From the data it could be concluded that the model being used by teachers' colleges (2-5-2) was more inclined to ODL than the 'conventional' model, thus demonstrating that indeed teachers can be trained through ODL. Whilst there were mixed feelings about the role of universities in the training of pre-service teachers, it could be concluded that universities had a role in the training of teachers regardless of the mode of delivery they used. The study noted that the lack of resources and lack of understanding between different stakeholders was negatively affecting the success of the ODL model of training teachers at the Zimbabwe Open University (ZOU).
KerkoCite.ItemAlsoKnownAs: 2129771:7V79AP65 2317526:56BUMTPF
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; C:Zimbabwe; CA:AandC; CL:en; CL:fr; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing country; F:attitude; F:teaching; P:measurement; P:service industry; P:teacher education; P:teacher training; P:teachers; Q:ODEL; Q:distance education; Q:distance learning; R:case study; R:observation; R:qualitative; R:questionnaire; T:Ausbildung; T:trainee; Z:Zimbabwe Open University (ZOU); Z:distance education; Z:teacher training; publicImportV1; ⛔ No DOI found

Training of School Teachers in West Africa: Remediation of Reading Difficulties through Training in Phonological Awareness and Letter Names - Briquet-Duhazé, Sophie (FIRE: Forum for International Research in Education, 2014)
The training of teachers of West Africa is carried out by the Academy of Rouen (France) and organized around an annual training plan approved by the AEFE. Each trainer only supervises twenty teachers for 5 days. Teachers from eight countries (Mauritania, Cape Verde, Senegal, Gambia, Mali, Guinea, Côte d'Ivoire and Burkina Faso), come to Dakar for a week. We have been asked four times tn Dakar (Senegal) to provide training for teachers of West Africa. It is all about being trained in order to resolve reading difficulties for students using our scientific research. This paper presents the theoretical framework of phonological awareness and letter names and the 0 phase and the beginning of Phase 1 of our research. We use these predictors as remedial reading difficulties among students aged 8 to 11 years. We present the first results.
KerkoCite.ItemAlsoKnownAs: 2129771:TC75Z8YL 2317526:ZGBCTLGU LOCAL-eric:EJ1133799
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Burkina Faso; C:Cape Verde; C:Gambia; C:Guinea; C:Ivory Coast; C:Mali; C:Mauritania; C:Senegal; CA:AandC; CL:de; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:Improvement; P:teachers; T:TVET; T:Training; T:trainee; Z:Alphabets; Z:Elementary School Students; Z:Faculty Development; Z:Foreign Countries; Z:Longitudinal Studies; Z:Phoneme Grapheme Correspondence; Z:Phonological Awareness; Z:Predictor Variables; Z:Professional Continuing Education; Z:Reading Difficulties; Z:Relevance (Education); Z:Remedial Reading; Z:Teacher Improvement; __C:filed:1; publicImportV1; ⛔ No DOI found

Training community healthcare workers on the use of information and communication technologies: a randomised controlled trial of traditional versus blended learning in Malawi, Africa - Mastellos, Nikolaos; Tran, Tammy; Dharmayat, Kanika; Cecil, Elizabeth; Lee, Hsin-Yi; PengWong, Cybele C.; Mkandawire, Winnie; Ngalande, Emmanuel; Tsung-ShuWu, Joseph; Hardy, Victoria; Chirambo, Baxter Griphin; O'Donoghue, John Martin (BMC Medical Education, 2018)
Background: Despite the increasing uptake of information and communication technologies (ICT) within healthcare services across developing countries, community healthcare workers (CHWs) have limited knowledge to fully utilise computerised clinical systems and mobile apps. The ` Introduction to Information and Communication Technology and eHealth' course was developed with the aim to provide CHWs in Malawi, Africa, with basic knowledge and computer skills to use digital solutions in healthcare delivery. The course was delivered using a traditional and a blended learning approach. Methods: Two questionnaires were developed and tested for face validity and reliability in a pilot course with 20 CHWs. Those were designed to measure CHWs' knowledge of and attitudes towards the use of ICT, before and after each course, as well as their satisfaction with each learning approach. Following validation, a randomised controlled trial was conducted to assess the effectiveness of the two learning approaches. A total of 40 CHWs were recruited, stratified by position, gender and computer experience, and allocated to the traditional or blended learning group using block randomisation. Participants completed the baseline and follow-up questionnaires before and after each course to assess the impact of each learning approach on their knowledge, attitudes, and satisfaction. Per-item, pre-post and between-group, mean differences for each approach were calculated using paired and unpaired t-tests, respectively. Per-item, between-group, satisfaction scores were compared using unpaired t-tests. Results: Scores across all scales improved after attending the traditional and blended learning courses. Self-rated ICT knowledge was significantly improved in both groups with significant differences between groups in seven domains. However, actual ICT knowledge scores were similar across groups. There were no significant differences between groups in attitudinal gains. Satisfaction with the course was generally high in both groups. However, participants in the blended learning group found it more difficult to follow the content of the course. Conclusions: This study shows that there is no difference between blended and traditional learning in the acquisition of actual ICT knowledge among community healthcare workers in developing countries. Given the human resource constraints in remote resource-poor areas, the blended learning approach may present an advantageous alternative to traditional learning.
KerkoCite.ItemAlsoKnownAs: 10.1186/s12909-018-1175-5 10/gdc33z 2129771:ZRWBTANL 2317526:Y6TI63MF
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Malawi; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing country; F:attitude; F:gender; F:learning; HDR25; P:health; P:service industry; Q:ICT; R:impact; R:questionnaire; R:trial; T:Ausbildung; Z:Blended learning; Z:Community healthcare workers; Z:Developing countries; Z:Information and communication technologies; Z:Traditional learning; Z:eHealth; Z:mLearning; publicImportV1

Traditional eye medicine practice in Benin-City, Nigeria - Ebeigbe, JA (Southern African Optometrist, 2013)
The use of traditional eye medicines as a form of eye care in Africa is very common. However, there is concern about the harmful effects of some traditional medicines on the eyes. This study was a cross-sectional survey conducted in Benin-City, Edo state, Nigeria. Sixty-eight traditional medicine practitioners (TMPs) who treated eye conditions participated in this study. Most (87%) were males and 13% were females. Their age ranged between 25 to 65 years with a mean age of 42.25 ± 2.14 years. Information was obtained through one-on-one oral interviews and a structured questionnaire consisting of open-ended questions. The most common method of training (46%) was by father-to-son tutelage. Conjunctivitis, itching and poor vision were the most common conditions treated by all practitioners. The majority of the TMPs (62%), practiced full time while 38% practiced part time. Forty six percent considered patients’ case histories as more important than physical examination of the eye while 54% felt both history and examination were equally important. Thirty-six percent of practitioners reported inverting the upper eyelids as part of their examination. Couching of cataracts was done by 38%. While 49% had referred ‘difficult’ or ‘stubborn’ cases to orthodox hospitals, 51% had never referred a case. Traditional healers are well accepted in their communities and will continue to be consulted by the people. Health education programs with emphasis on safe eye care practices need to be established for traditional healers. Working with healers and training them to recognize cases needing urgent referral and encouraging the use of non-harmful practices may provide a more sustainable health care structure in the community. Cooperation between these two aspects of medicine is extremely important for the provision of primary eye care services in rural Africa.
KerkoCite.ItemAlsoKnownAs: 2129771:9CDQAVRA 2317526:GEI8RZF9
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:learning; F:payment; P:healers; P:media; T:Formal apprenticeship; T:Lehrlingsausbildung; T:Training; publicImportV1; ⛔ No DOI found

Traditional apprenticeship in Ghana and Senegal: Skills development for youth for the informal sector - Sonnenberg, K (Journal of International Cooperation in Education, 2012)
The demographic youth bulge, representing large cohorts of youth, coupled with lack of pathways to education and employment and therefore social mobility, have become issues of great concern. As a result, youth employment and technical and vocational skills development have grown in prominence on international and national agendas in recent years. However, skills development strategies often overlook the informal sector despite the fact that in developing countries, income-generating activities in the informal sector often far exceed those of the formal sector. UNESCO’s 2012 EFA Global Monitoring Report on youth skills development states that traditional apprenticeships are an important way of acquiring transferable and job-specific skills, particularly for the informal sector. An extensive review of the literature of Ghana and Senegal reveals that these two countries have long histories of traditional apprenticeship and that these forms of skills training reach more youth than formal technical and vocational training. This paper examines the approaches these two countries’ governments have taken to increase access to and quality of non-formal skills training opportunities. Despite a lack of data on the long-term outcomes of these initiatives, programs and reforms, several important implications arise from these countries’ experiences. These implications are discussed as well as areas for future research.
KerkoCite.ItemAlsoKnownAs: 2129771:R6VJJ3WT 2317526:PNGX2ZNF
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; C:Senegal; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; HDR25; P:agriculture; P:measurement; Q:ICT; T:Ausbildung; T:Formal apprenticeship; T:Lehrlingsausbildung; T:apprentice; T:education and skills training; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Towards in-service training needs of secondary school agriculture teachers in a paradigm shift to outcome-based education in Uganda - Okiror, J.J.; Hayward, Geoff; Winterbottom, M (The Journal of Agricultural Education and Extension, 2017)
This paper examines the in-service teacher training needs of secondary school agriculture teachers in Uganda as the country moves towards an ‘outcome-based’ education by removal of subjects and instead, uses learning areas, presenting a need for new pedagogical skills among teachers. Design/methodology/approach: A cross-sectional survey was conducted in Uganda between June and September 2016 to assess the teaching methods and teacher training needs for secondary school agriculture curriculum. Data were collected from 80 agriculture teachers and 57 administrators from 60 secondary schools, randomly drawn from 25 districts in Uganda. The data were analysed with descriptive statistics. Findings: The findings show that there about 10 key competences required by the teachers to thrive in their profession. These range from traditional classroom teaching to community outreach and linkages with agribusinesses which is in tandem with outcome-based education beyond the classroom walls. Respondents highlight lack of practical agriculture skills and exposure to the modern farming practices. Theoretical implications: This paper examines role of formal in-service teacher training based on theory of change and proposes using professional learning communities for school-level improvements. Practical implication: The results were not significant enough to warrant strong recommendations. However, they suffice to highlight a growing need for in-service teacher support mechanism for a dynamic subject like agriculture using communities of practice at school and district levels. Originality/value: In the current context of growing concern for unemployment in Africa, secondary schools will require competent teachers to engage students into transferable learning, given that it is the terminal level of education for majority. © 2017 Wageningen University.
KerkoCite.ItemAlsoKnownAs: 10.1080/1389224X.2017.1338593 10.1080/1389224x.2017.1338593 10/gf62j8 2129771:5IPHE8U3 2317526:IEDH4V39 DOI-10.1080/1389224X.2017.1338593
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:Improvement; F:curriculum; F:learning; F:outcomes; F:pedagogy; F:teaching method; P:agricultural; P:agriculture; P:measurement; P:mechanic; P:services; P:teacher education; P:teacher training; P:teachers; Q:community of practice; Q:secondary education; R:interview; R:observation; R:questionnaire; R:survey; T:Classroom teaching; T:learning community; T:work-based learning; Z:Administrator Surveys; Z:Agricultural Education; Z:Agricultural education; Z:Curriculum reform; Z:Educational Needs; Z:Employment skills; Z:Foreign Countries; Z:Inservice Teacher Education; Z:Interviews; Z:Observation; Z:Outcome Based Education; Z:Questionnaires; Z:Secondary School Teachers; Z:Secondary education; Z:Teacher Competencies; Z:Teacher Surveys; Z:Teacher capacity; Z:Teacher education; Z:Teaching Methods; Z:Teaching methods; _C:Uganda UGA; publicImportV1

Towards competence-based technical-vocational education and training in Ethiopia - Solomon, GH (2016)
In the human development effort, different countries are underscoring the role of TVET in providing relevant knowledge and skills to improve productivity, increase access to employment opportunities and raise the standard of living. It is in recognition of this that, in all Ethiopian educational development endeavors, TVET has been considered to play a key role to tackle the country’s socioeconomic underdevelopment through knowledgeable and skillful manpower. Since its introduction in 1941, TVET has been guided by different policies and strategies adopted by successive governments who came to power at different times. This thesis investigates how TVET has reached the current stage of its development in Ethiopia and the challenges encountered in implementing a competence-based system aimed at improving present and future TVET practices. This introduction opens with the general state of affairs in Ethiopia as a basis for considering TVET to be a pivotal component of its socio-economic development. Describing the context in which the different studies in this thesis were conducted, this introduction closes with an introduction of the research questions that guided the different studies presented as separate chapters
KerkoCite.ItemAlsoKnownAs: 2129771:TVBKF98J 2317526:BCUWA5W6
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:T; F:outcomes; F:standards; T:TVET; T:company-based training; publicImportV1; ⛔ No DOI found

Towards a renewal of apprenticeship in West Africa - Walther, R (2008)
KerkoCite.ItemAlsoKnownAs: 2129771:N4NES3ZB 2317526:IF875PF8
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Central Africa; A:East Africa; A:Sub-Saharan Africa; A:West Africa; C:Angola; C:Benin; C:Cameroon; C:Ethiopia; C:Mali; C:Senegal; C:South Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:inclusion; F:pedagogy; P:crafts; P:economy; P:nature; Q:certificate; Q:higher education; Q:secondary education; T:Ausbildung; T:Lehrlingsausbildung; T:TVET; T:apprentice; T:trainee; publicImportV1

To vocationalise or not to vocationalise? Perspectives on current trends and issues in technical and vocational education and training (TVET) in Africa - Oketch, Moses O. (International Journal of Educational Development, 2007)
In recent years, there has been a renewed interest in the dichotomy of vocational education versus general education. This is more so as political pronouncements in many countries across the globe have taken on knowledge and skills as the key aim of the desire to improve access to education at all levels. Nowhere is this debate more tested, fiercely debated and gained controversy as in Africa. However, given recent developments in which knowledge and skills have become more acceptable terms in economically more developed nations, in which both are seen to go hand in hand, what is happening in Africa where development is highly sought but has proven to be more elusive? This has brought back to the forefront one of the dilemmas which has pre-occupied many African countries for a long time: whether to concentrate investment in general education or in vocational education. In this paper, I reflect on current trends and issues in TVET in Africa.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2006.07.004 10/bwcb97 2129771:5BA8YC3B 2317526:XHIZPKCS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; Education; F:learning; F:policy; P:administration; P:nature; Q:secondary education; R:interview; Skills; T:Educação profissionalizante; T:TVET; T:occupational education; T:vocational training scheme; Technical and vocational education; publicImportV1

‘Tich Mi Ar Tich Dem’: Designing a low-cost and scalable teacher professional development in Sierra Leone - Walker, Hannah; Tegha, Ghislaine; Lurvink, Anne-Fleur; McBurnie, Chris (Open Development & Education, 2022)
Reading Time: 4 minutes Over the past two decades, Sierra Leone has faced a series of shocks: a civil war, landslides, Ebola, and the COVID-19 pandemic. These shocks have aggravated the learning crisis that the country’s education system faces—and dramatically increased the pressure on teachers to deliver high-quality support to children. In this context, the Ministry of Basic and […]
KerkoCite.ItemAlsoKnownAs: 2129771:3UV4LJFT 2339240:75HR9DSN 2405685:FBHX876D
Keywords: _C:Sierra Leone SLE

Through the Looking Glass: Can Classroom Observation and Coaching Improve Teacher Performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (2018)
shortDOI: 10/ggft3x KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2018.03.003 10/ggft3x 2129771:PXEQ493U 2405685:7A2ZCMGH
Keywords: _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Ethiopia ETH; _C:Guatemala GTM; _C:Honduras HND; _C:India IND; _C:Japan JPN; _C:Kenya KEN; _C:Malawi MWI; _C:Nepal NPL; _C:Peru PER; _C:Philippines PHL; _C:Portugal PRT; _C:Singapore SGP; _C:United States USA; __C:filed:1; __C:scheme:1; _yl:a

Three (Post-Secondary Agricultural Education and Training) Challenges and the Concept of "Workforce Education Systems" - Rivera, William M. (Journal of agricultural education and extension, 2008)
The Comprehensive Africa Agriculture Development Program (CAADP) of the Africa Union's New Partnership for Africa's Development (AU/NEPAD), the International Food Policy Research Institute (IFPRI), in collaboration with the University of KwaZulu-Natal, held in January 2008, a conference on the subject of "Convergence between Social Service Provision and Productivity Enhancing Investments in Development Strategies" with a view to improving the complementaries between investments in social sciences and those aimed directly at raising agricultural productivity. The present paper is intended as part of a seminar series in this regard to be held at IFPRI, 9 October 2007, and serves as the basis for a paper to be presented at the CAADP/IFPRI conference in January 2008 in Durban, South Africa. (Contains 7 notes and 4 figures.)
KerkoCite.ItemAlsoKnownAs: 10.1080/13892240701820546 10/c8cf6b 2129771:6IAGKSU7 2317526:T8IRDFH8 LOCAL-PQ-61962525
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:policy; P:agricultural; P:agriculture; P:economy; P:services; P:social; T:Training; T:workplace education; Z:Agricultural Education; Z:Conference Papers; Z:Economic Development; Z:Foreign Countries; Z:Labor Force Development; Z:Productivity; Z:Social Sciences; publicImportV1

Theme 6: Leadership for Learning (Tutors) - Swaffield, Sue; MacBeath, J. (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:2J3EWDD6
Keywords: Author:Haßler; Author:OpenDevEd; _C:Chad TCD; _C:Ghana GHA; _C:Greece GRC; _C:United Kingdom GBR; _C:Uruguay URY; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence

Theme 6: Leadership for Learning (Coordinators) - Swaffield, Sue; MacBeath, J. (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:3PJ3UD5Z
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 5: Teaching and Learning Materials (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:DWV2WHF4 2129771:JEMU8JGF
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 5: Teaching and learning materials (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:ZRAHWN9Y 2129771:ZTBKVLZS
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 4: Group Work (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:MKG5RAMB
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 4: Group Work (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
This handbook is the HANDBOOK FOR PD COORDINATORS for Theme 4, focusing on group work. In many everyday situations people work alongside colleagues, speak and listen to friends, and see what others do and how they do it. This is how we all learn. As we talk to others, we discover new ideas and information. If activities in the college classrooms are centred on the tutor, then the student teachers do not get enough time to be active: they do not have the opportunity to try, to demonstrate their learning or to ask questions. In such situations, some students may only give short answers and some may say nothing at all. In large classes, the situation is even worse, with only a small proportion of students saying anything at all. One reason for doing group work in the classroom is to give students more opportunities to participate. Working in groups and pairs is about learning collaboratively. Collaborative learning means two or more student teachers working together to achieve a shared goal. This includes peer collaboration (for groups of two student teachers), and small group work (for smaller groups). It requires you to interact and talk about what you are thinking with one another in a specific learning context. Questions can be posed, ideas can be challenged and misunderstandings can be heard and investigated.
KerkoCite.ItemAlsoKnownAs: 2129771:CM625AFT 2129771:UMMTA7EM
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 3: Talk for Learning (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:JQNSU649
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 3: Talk for Learning (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:9XIQFZ7A
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 2: Questioning (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:AUZXH72U 2129771:ELQ2SUES
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 2: Questioning (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
EdTechHub.ItemAlsoKnownAs: 2129771:GSVI5ARP
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 1: Creative approaches (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:BXC77H6P 2129771:ZSIEDWMH
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Theme 1: Creative Approaches (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
EdTechHub.ItemAlsoKnownAs: 2129771:8NQR4EYA
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

The withdraw of european missionaries from St. Anthony's Catholic secondary school: what are the implications?. - Cheyeka, Austin; Masaiti, Gift; Mulenga, Innocent Mutale (2011)
Publisher: The Journal of Humanities-The University of Zambia
Keywords: ⛔ No DOI found

The use of virtual learning environments and learning management systems during the COVID-19 pandemic - McBurnie, Chris (2020)
EdTechHub.Source: 2405685:53YEZE6A KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3805843 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2405685:53YEZE6A 2405685:WBNK52L7
Keywords: Author:OpenDevEd; COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _C:Afghanistan AFG; _C:Armenia ARM; _C:Bangladesh BGD; _C:China CHN; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:France FRA; _C:Germany DEU; _C:Greece GRC; _C:Hungary HUN; _C:India IND; _C:Indonesia IDN; _C:Iraq IRQ; _C:Italy ITA; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Korea XKOR; _C:Kyrgyzstan KGZ; _C:Mexico MEX; _C:Myanmar MMR; _C:Nigeria NGA; _C:Poland POL; _C:Portugal PRT; _C:Romania ROU; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Senegal SEN; _C:Spain ESP; _C:Syrian Arab Republic SYR; _C:Tajikistan TJK; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United States USA; _EdTechHub_Output; __C:filed:1; __C:scheme:1; ___duplicate_item; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

THE UNIVERSITY OF ZAMBIA PRE-SERVICE TEACHER EDUCATION PROGRAMME: IS IT RESPONSIVE TO SCHOOLS AND COMMUNITIES’ASPIRATIONS? - Masaiti, Gift; Manchishi, Peter Chomba (European Journal of Educational Studies, 2011)
Keywords: ⛔ No DOI found

The Theoretical and Empirical Basis of Teacher Leadership: A Review of the Literature - Wenner, Julianne A.; Campbell, Todd (Review of Educational Research, 2017)
In the current review, we examined teacher leadership research completed since York-Barr and Duke published the seminal review on teacher leadership in 2004. The review was undertaken to examine how teacher leadership is defined, how teacher leaders are prepared, their impact, and those factors that facilitate or inhibit teacher leaders’ work. Beyond this, the review considered theories informing teacher leadership, teacher leadership within disciplinary contexts, and the roles of teacher leaders in social justice and equity issues. The most salient findings were (a) teacher leadership, although rarely defined, focused on roles beyond the classroom, supporting the professional learning of peers, influencing policy/decision making, and ultimately targeting student learning; (b) the research is not always theoretically grounded; (c) principals, school structures, and norms are important in empowering or marginalizing teacher leaders; and (d) very little teacher leadership research examines issues of social justice and equity.
Keywords: _C:Australia AUS; _C:Canada CAN; _C:Israel ISR; _C:Singapore SGP; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

The teacher salary system in Sierra Leone - Turrent, Victoria (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:57MI994B 2129771:EDZ7UPYF 2339240:HPKYUKLY 2405685:JYDRFRHV 4556019:2UB9U5R4
Keywords: C:Sierra Leone; _C:Sierra Leone SLE; ⛔ No DOI found

The Teacher Educators’ Knowledge of Learner Support Services in Distance Teacher Education Programmes in Selected Public Colleges of Education in Zambia - Jere, Getrude; Mulenga, Innocent Mutale; Manchishi, Peter Chomba (How Africa Has Turned Around, 2021)
Keywords: ⛔ No DOI found

THE SIERRA LEONE TEACHERS UNION: LABOR IN A POST-CONFLICT SOCIETY: AMMAN AND O'DONNELL: THE SIERRA LEONE TEACHERS UNION - Amman, John; O'Donnell, James (WorkingUSA, 2011)
KerkoCite.ItemAlsoKnownAs: 10.1111/j.1743-4580.2011.00320.x 2129771:CAMP2L5T
Keywords: _C:Sierra Leone SLE

The Sierra Leone Teachers Union: Labor in a Post-Conflict Society - Amman, John; O'Donnell, James (WorkingUSA, 2011)
The Sierra Leone Teachers Union (SLTU) has long played an important role in the country's education system and its labor movement. With more than 30,000 members, the SLTU is the largest and perhaps the most powerful union in Sierra Leone today. Nonetheless, the union struggles with challenges unheard of in developed countries. It represents teachers in an education system that was ravished by its eleven-year civil war (1991 to 2002). Not only are working conditions extremely difficult for teachers (classroom overcrowding, lack of educational materials, low pay, and often late pay), the union must negotiate union agreements with the Ministry of Education, which itself has no direct influence on the nation's coffers. Sierra Leone's Ministry of Finance and more importantly, the International Monetary Fund set policies that directly impact the quality of Sierra Leone's education system and its teachers.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1743-4580.2011.00320.x KerkoCite.ItemAlsoKnownAs: 10.1111/j.1743-4580.2011.00320.x 2129771:63MSS39D 2405685:K8W49AUJ
Keywords: _C:Sierra Leone SLE

The role that access and attitudes toward tablets have on learners’ achievement in a Johannesburg school - Hart, Samantha Anne; Laher, Sumaya (South African Journal of Education, 2019)
Publisher: Education Association of South Africa KerkoCite.ItemAlsoKnownAs: 2129771:T7BCUMAC
Keywords: _C:Australia AUS; _C:Canada CAN; _C:Korea; Republic KOR; _C:Singapore SGP; _C:South Africa ZAF; _C:Syrian Arab Republic SYR; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

The role of open educational resources (OERs) in primary education in developing nations: A case study of India - Ganapathi, Janani (Queensland University of Technology, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:DE9Z22PQ 2129771:JFPVTIE8
Keywords: _C:Afghanistan AFG; _C:Australia AUS; _C:Bangladesh BGD; _C:Brazil BRA; _C:Cambodia KHM; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Eritrea ERI; _C:Finland FIN; _C:Ghana GHA; _C:India IND; _C:Iran IRN; _C:Ireland IRL; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Lesotho LSO; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Mozambique MOZ; _C:Nepal NPL; _C:New Zealand NZL; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Poland POL; _C:Russian Federation RUS; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Sweden SWE; _C:Tanzania TZA; _C:Tibet XTIBT; _C:Togo TGO; _C:Turkey TUR; _C:Uganda UGA; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

The role and status of forced migrant teachers in education in emergencies - Penson, Jonathan (Commonwealth education partnerships, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:2AEUD2WL 2129771:AP5BHQD8 2129771:D99ESD2Q 2486141:PDRUBWDA
Keywords: _C:Afghanistan AFG; _C:Australia AUS; _C:Botswana BWA; _C:Canada CAN; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Grenada GRD; _C:Kenya KEN; _C:Malta MLT; _C:Myanmar MMR; _C:Nepal NPL; _C:Netherlands NLD; _C:Pakistan PAK; _C:Rwanda RWA; _C:Seychelles SYC; _C:Somaliland XSMLD; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Thailand THA; _C:Uganda UGA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

The ripple effects of school closures during the COVID-19 pandemic - Freeman, Sloane J.; Cohen-Silver, Justine; Baker, Jillian M.; Rozenblyum, Evelyn; Suleman, Shazeen (Canadian Family Physician, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:QIE9E6JK
Keywords: __C:filed:1; ⛔ No DOI found

The returns to vocational training and academic education: Evidence from Tanzania - Kahyarara, Godius; Teal, Francis (World Development, 2008)
In this paper we ask what can account for the continuing strong preference for academic education in Africa where the level of development is so low and there are few wage jobs and which form of educational investment, the academic or vocational, is most profitable. We argue that the answers to these questions are linked through the shape of the earnings function and the importance of firm effects. High levels of academic education have far higher returns than those available either from vocational or lower levels of academic. However at lower levels the vocational return can exceed the academic.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2007.11.011 10/dv4nwz 2129771:89TV2XR9 2317526:A9PEUINX
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Tanzania; CA:AandC; CC:Tanzania; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:manufacture; T:TVET; T:Training; Z:Benefits of education; Z:Employment skills; Z:Vocational education and training; publicImportV1

The Relevance of Teacher Autonomy-A Qualitative Case-Study of Malawi Unlocking Talent: Learning Through Technology - Kleiberg, Elisabeth Vestvik (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:WVEDPC5F
Keywords: _C:Botswana BWA; _C:Ethiopia ETH; _C:Greece GRC; _C:Malawi MWI; _C:Mozambique MOZ; _C:Norway NOR; _C:Portugal PRT; _C:Senegal SEN; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

The relationships between teachers’ emotional labor and their burnout and satisfaction: A meta-analytic review - Yin, Hongbiao; Huang, Shenghua; Chen, Gaowei (Educational Research Review, 2019)
Teaching is an emotional endeavor. Unlike mass service employees, teachers enjoy considerable autonomy in their teaching and maintain relatively stable relationships with students, parents, and colleagues. This study is a meta-analytic review of the associations between teachers' emotional labor strategies (i.e., surface acting, deep acting, and the expression of naturally felt emotions) and other relevant constructs. The meta-analysis is based on 85 empirical articles and 86 independent samples, with the experiences of 33,248 teachers represented in the articles reviewed. The meta-correlations are generally in the expected direction. Surface acting is positively related to the individual and interpersonal components of burnout and negatively related to teaching satisfaction. Deep acting is not significantly related to the individual or interpersonal components of burnout, but positively related to teaching satisfaction and the efficacy component of burnout. The expression of naturally felt emotions is negatively related to teachers’ burnout and reduced teaching satisfaction. The moderation analysis of relevant correlates also provides some insights about the research development.
Keywords: Burnout; Emotional labor; Lebanon_event_2021; Meta-analysis; Satisfaction; Teacher; _C:Australia AUS; _C:Belgium BEL; _C:Canada CAN; _C:China CHN; _C:Ethiopia ETH; _C:Finland FIN; _C:Germany DEU; _C:Greece GRC; _C:Iran IRN; _C:Italy ITA; _C:Korea; Republic KOR; _C:Malaysia MYS; _C:Netherlands NLD; _C:Oman OMN; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Turkey TUR; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

The relationship between education, economy and employment: is higher education curriculum an ingredient?. - Masaiti, Gift; Mulenga, Innocent Mutale (Keurkopie, 2014)

The RAIFFET, a network for support and development of TVET in teacher training institutions in Africa - Ginestié, J (2015)
The countries' development depends largely of the development and the effectiveness of their education systems, both to promote education for all (EFA) and technology and vocational education and training (TVET) for each of them. The situation is particularly difficult in sub-Saharan Africa (SSA) and it is very difficult for many countries to provide a school that offers all children the opportunity to attend school beyond some basics. The access to primary education is not guaranteed for all, and few of them have the opportunity to receive vocational training enabling them to obtain a recognized professional qualification. The lack of qualified and competent teachers is another manifestation of the problems. Many institutional actors, including UNESCO, help foster the development of educational policies to overcome these institutional, structural and functional weaknesses. The RAIFFET was formed to make a modest contribution to this momentum by supporting the development and structuring of teacher training and education research in SSA. This paper presents some elements of understanding of the situation and the orientations of the network's contribution to this dynamic.
KerkoCite.ItemAlsoKnownAs: 2129771:U9XKEJTC 2317526:U2UIH77L UTI-57E96D1C-2C3C-37DC-90C5-38A465CDBEF1
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Central Africa; C:Gabon; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:teacher training; P:technology; Q:ICT; T:Ausbildung; T:TVET; publicImportV1; ⛔ No DOI found

The professional development of teachers in Higher Education in Oman: a case study of English teachers in the Colleges of Applied Sciences - Al-Ghatrifi, Yaqoob (University of Reading, 2016)
EdTechHub.ItemAlsoKnownAs: 2129771:58BS4RY3
Keywords: _C:Antigua and Barbuda ATG; _C:Australia AUS; _C:Bahrain BHR; _C:Benin BEN; _C:Canada CAN; _C:China CHN; _C:Egypt EGY; _C:France FRA; _C:Germany DEU; _C:Greece GRC; _C:India IND; _C:Iran IRN; _C:Ireland IRL; _C:Israel ISR; _C:Jordan JOR; _C:Kenya KEN; _C:Kuwait KWT; _C:Malaysia MYS; _C:Malta MLT; _C:Mexico MEX; _C:Mozambique MOZ; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Oman OMN; _C:Pakistan PAK; _C:Portugal PRT; _C:Qatar QAT; _C:Saudi Arabia SAU; _C:Somalia SOM; _C:Sweden SWE; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Yemen YEM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

The Potential and Prerequisites of Effective Tablet Integration in Rural Kenya - Heinrich, Carolyn J.; Darling-Aduana, Jennifer; Martin, Caroline (2018)
EdTechHub.ItemAlsoKnownAs: 2129771:39LUB5JZ
Keywords: _C:Cambodia KHM; _C:China CHN; _C:Cuba CUB; _C:Ghana GHA; _C:Kenya KEN; _C:South Africa ZAF; _C:United States USA; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1; ⛔ No DOI found

The potential and prerequisites of effective tablet integration in rural Kenya - Heinrich, Carolyn J.; Darling-Aduana, Jennifer; Martin, Caroline (British Journal of Educational Technology, 2020)
Publisher: Wiley Online Library KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12870 2129771:ATNXRVR5
Keywords: __C:filed:1

The permanent input hypothesis : the case of textbooks and (no) student learning in Sierra Leone - Sabarwal, Shwetlena; Evans, David K.; Marshak, Anastasia (Washington, DC : World Bank, Education Global Practice Group & Africa Region, Office of the Chief Economist, 2014)
KerkoCite.ItemAlsoKnownAs: 2129771:MVW7YCWN 2405685:QFBK2Z4L
Keywords: _C:Sierra Leone SLE

The OER4Schools Professional Learning Resource: Interactive teaching with and without ICT. A practical programme for teachers in sub-Saharan Africa. - Hennessy, S.; Haßler, Björn (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:FULY4AFY
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _r:ImportedToMyEducationEvidence

The OER4Schools professional development programme: Outcomes of a sustained trial in sub-Saharan Africa - Haßler, Björn; Hennessy, S.; Hofmann, R (Frontiers in Education, 2020)
Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention showed that the programme became self-sustaining; earlier participants reported further development of their interactive teaching strategies and awareness of pupil progress; recent joiners developed similarly. Roles of teachers and pupils changed and a new classroom culture emerged. The study identifies the key mechanisms involved in sustainability, including culturally sensitive and participatory development and implementation, semi-structured multimedia materials, and supportive organisational structures for sustained professional learning. Our findings are hence framed by sociocultural influences as well as the wider policy context.
HHH3A KerkoCite.ItemAlsoKnownAs: 10.3389/feduc.2020.00146 10/ghgn5x 2129771:3LI3KD7M 2129771:6KN48Q7A 2129771:9MYSJMUJ 2129771:MKKYSSHG 2129771:YRM4QXHR 2339240:A5GQ37WB 2405685:KLUBUEJY 2405685:V7S2E5AQ 2405685:VHZVRENG 2534378:M3FT5RN4
Keywords: Active Learning; Africa; Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; C:Zambia; Culturally responsive pedagogy (CRP); Design-based implementation research; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; Inservice Teacher Education; Interactive Pedagogy; Learner-centred pedagogy; Low Income Groups; Motivation; Open Educational Resources; Peer Teaching; Resource Allocation; Rural Schools; STC-TLC; Scaffolding (Teaching Technique); Scheduling; School leadership; Shared Resources and Services; Sustainable Development; Sustainable Development Goal (SDG) 4; Sustainable Development Goal 4; Teacher Profesisonal Development; Teacher Professional Development; Technology Uses in Education; Telecommunications; Zambia; __C:filed:1; ___working_potential_duplicate; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:b; peer-facilitation; school improvement; school-based active learning; sub-Saharan Africa

The Obstacles of Geographical Information System (GIS) Development: A Study of Teachers' Distribution in Sukabumi, Indonesia - Yani, Ahmad; Rosita, Rosita (Atlantis Press, 2016)
Geographical Information System (GIS) is an application used to process data in form of thematic maps which is arranged overlapping to produce informations needed by the user. Employing descriptive method, this study indicated that basically the GIS deve
ISSN: 2352-5428
Keywords: Lebanon_event_2021; _C:Indonesia IDN; _C:Kenya KEN; __C:filed:1; __C:scheme:1

The meaning of “capacity building” for the nurse workforce in sub-Saharan Africa: An integrative review - Ridge, Laura Jean; Klar, Robin Toft; Stimpfel, Amy Witkoski; Squires, Allison (International Journal of Nursing Studies, 2018)
Background: “Capacity building” is an international development strategy which receives billions of dollars of investment annually and is utilized by major development agencies globally. However, there is a lack of consensus around what “capacity building” or even “capacity” itself, means. Nurses are the frequent target of capacity building programming in sub-Saharan Africa as they provide the majority of healthcare in that region. Objectives: This study explored how “capacity” was conceptualized and operationalized by capacity building practitioners working in sub-Saharan Africa to develop its nursing workforce, and to assess Hilderband and Grindle's (1996) “Dimensions of Capacity” model was for fit with “capacity's” definition in the field. Design: An integrative review of the literature using systematic search criteria. Data sources searched included: PubMed, the Cumulative Index for Nursing and Allied Health Literature Plus, the Excerpt Medica Database, and Web of Science. Review methods: This review utilized conventional content analysis to assess how capacity building practitioners working in sub-Saharan Africa utilize the term “capacity” in the nursing context. Content analysis was conducted separately for how capacity building practitioners described “capacity” versus how their programs operationalized it. Identified themes were then assessed for fit with Hilderband and Grindle's (1996) “Dimensions of Capacity” model. Results: Analysis showed primary themes for conceptualization of capacity building of nurses by practitioners included: human resources for health, particularly pre- and post- nursing licensure training, and human (nursing) resource retention. Other themes included: management, health expenditure, and physical resources. There are several commonly used metrics for human resources for health, and a few for health expenditures, but none for management or physical resources. Overlapping themes of operationalization include: number of healthcare workers, post-licensure training, and physical resources. The Hilderband and Grindle (1996) model was a strong fit with how capacity is defined by practitioners working on nursing workforce issues in sub-Saharan Africa. If overall significant differences between conceptualization and operationalization emerged, as the reader I want to know what these differences were. Conclusions: This review indicates there is significant informal consensus on the definition of “capacity” and that the Hilderbrand and Grindle (1996) framework is a good representation of that consensus. This framework could be utilized by capacity building practitioners and researchers as those groups plan, execute, and evaluate nursing capacity building programming.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijnurstu.2018.04.019 10/gfnhq7 2129771:C2BSPDCZ 2317526:89VSVEBZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; AAZ:Africa South of the Sahara; C:Rwanda; C:South Africa; CA:AandC; CCZ:Rwanda; CCZ:South Africa; CCZ:Uganda; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:P; CT:T; D:developing country; P:health; P:media; P:nurse; T:Training; Z:Capacity building/methods; Z:Developing countries; Z:Education; Z:Health manpower; Z:Nursing; Z:Staff; _C:Uganda UGA; publicImportV1

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (2020)
EdTechHub.Source: 2405685:HE2Q6Z8Y KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; F: Helpdesk response; LP: English; _C:Austria AUT; _C:India IND; _C:Maldives MDV; _C:Nepal NPL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Uganda UGA; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The Lifeline Program: A Case Study of Workforce Education Combating Poverty for Females in Ghana - Smith, Bettye P; Lowe, Tony; Hunt-Hurst, Patricia; Okech, David; Blalock, Emily; Dery, Alexis (International Education, 2013)
This case study research examined the contributions of the Lifeline Program in Ghana, West Africa to the preparation of young women for the workforce; this preparation is an effort to combat poverty. In this research report, a succinct overview of Ghana was provided, the economic status of the country was delineated, and the history of the Lifeline Program from its inception was given. The research provided an explanation of each of the three vocational skills training programs offered by Lifeline: catering, dressmaking, and hairdressing. The vocational skills training programs in Ghana are likened to workforce education programs in the United States. Conclusions were drawn for the Lifeline Program and the vocational skills training programs based on the Human Capital Theory, a major economic framework. Also, recommendations were suggested based on the findings and the theory that undergirded this case study. [PUBLICATION ABSTRACT]
KerkoCite.ItemAlsoKnownAs: 2129771:A4EV4G7T 2317526:EWVREBQW LOCAL-PQ-1467994353
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:women; P:economy; P:measurement; R:case study; T:Ausbildung; T:vocational skills; T:workplace education; Z:Accelerated death benefits; Z:Case studies; Z:Education; Z:Females; Z:Workforce; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

The level of Internet access and ICT training for health information professionals in sub‐Saharan Africa - Ajuwon, A A; Rhine, L (Health Information & Libraries Journal, 2008)
Background: Information and Communication Technologies (ICTs) are important tools for development. Despite its significant growth on a global scale, Internet access is limited in sub‐Saharan Africa (SSA). Few studies have explored Internet access, use of electronic resources and ICT training among health information professionals in Africa. Objective: The study assessed Internet access, use of electronic resources and ICT training among health information professionals in SSA. Methods: A 26‐item self‐administered questionnaire in English and French was used for data collection. The questionnaire was completed by health information professionals from five Listservs and delegates at the 10th biannual Congress of the Association of Health Information and Libraries in Africa (AHILA). Results: A total of 121 respondents participated in the study and, of those, 68% lived in their countries’ capital. The majority (85.1%) had Internet access at work and 40.8% used cybercafes as alternative access points. Slightly less than two‐thirds (61.2%) first learned to use ICT through self‐teaching, whilst 70.2% had not received any formal training in the previous year. Eighty‐eight per cent of respondents required further ICT training. Conclusions and recommendations: In SSA, freely available digital information resources are underutilized by health information professionals. ICT training is recommended to optimize use of digital resources. To harness these resources, intergovernmental and non‐governmental organizations must play a key role.
KerkoCite.ItemAlsoKnownAs: 10.1111/j.1471-1842.2007.00758.x 10/cqtp85 2129771:WT4HUTHS 2317526:2XSPMRJE
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Central Africa; A:East Africa; A:Sub-Saharan Africa; A:West Africa; C:Kenya; C:South Africa; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; P:electro; P:health; P:service industry; Q:ICT; Q:distance learning; T:Ausbildung; T:Training; __C:filed:1; publicImportV1

The Learnership Model of Workplace Training and Its Effective Management: Lessons Learnt from a Southern African Case Study - Davies, Theresa-Anne; Farquharson, Fiona (Journal of Vocational Education & Training, 2004)
Since 1998, the "Learnership" model of workplace training has been promoted in South Africa as a creative vehicle for addressing high unemployment rates and a serious skills shortage. This is achieved through fast-tracking the acquisition of skills and increasing a learner's chances of employment. However, because learnerships are a recent innovation, the body of applied knowledge is small. This article aims to contribute to what is known through examining a series of pilot projects, implemented between 1997 and 2001 in KwaZulu-Natal. A key finding concerns how learnerships are managed: the effective delivery of a learnership programme and of its outcomes requires the involvement of key stakeholders from the outset, role clarity and a carefully structured and monitored process of implementation. Using a case study approach, this article situates learnerships within the context of workplace training; explores four key lessons learnt and presents a proposed model of effective learnership management. (Contains 2 tables, 2 figures and 4 notes.)
KerkoCite.ItemAlsoKnownAs: 10.1080/13636820400200253 10/bcrjt6 2129771:59R9JPXA 2317526:XHHAN5YZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:outcomes; P:measurement; R:case study; T:Lehrlingsausbildung; T:TVET; T:Training; Z:Apprenticeships; Z:Case Studies; Z:Education Work Relationship; Z:Foreign Countries; Z:Job Skills; Z:Job Training; Z:Labor Market; Z:Models; Z:Pilot Projects; Z:Skill Development; Z:Vocational Education; Z:Work Experience; publicImportV1

The Informal Apprenticeship Miracle: A Case for Mbare-Magaba Informal Industry, Zimbabwe - Wonder, M; Tenson, M (Eastern Africa Social Science Research Review, 2017)
The economic turbulences faced by Zimbabwe in the first decade of the 21st century culminated in almost total demise of the formal industry. Concomitantly, this resulted in the emergence and proliferation of the informal industry as an alternative solution. This study explored the training strategies and approaches employed in the informal manufacturing industry. The study adopted the qualitative research paradigm to collect, present and analyse data. Findings from the study point to the efficacy of the informal apprenticeship in terms of human capital development and hence this skills training approach becomes the main trajectory to economic recovery for Zimbabwe.
KerkoCite.ItemAlsoKnownAs: 10.1353/eas.2017.0008 10/gf62z9 2129771:B2Z82EGH 2317526:6MAWR5BQ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Zimbabwe; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:artist; P:manufacture; P:social; T:Lehrlingsausbildung; T:apprenticeship training; publicImportV1

The influence of generational differences on the integration of educational technology in higher learning institutions - Letsie, Likeleli (University of Pretoria, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:4UJF7HR4
Keywords: _C:Australia AUS; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Egypt EGY; _C:France FRA; _C:Germany DEU; _C:Iran IRN; _C:Japan JPN; _C:Kenya KEN; _C:Kosovo XKSVO; _C:Lesotho LSO; _C:Libya LBY; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Slovenia SVN; _C:South Africa ZAF; _C:Sudan SDN; _C:Tanzania TZA; _C:Trinidad and Tobago TTO; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1

The influence of effective use of mobile devices for learning outside the classroom: case study of secondary school students in Tanzania and South Africa - Mwapwele, Samwel Dick (University of Cape Town, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:TZ8I7CPS
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:China CHN; _C:Dominican Republic DOM; _C:Eritrea ERI; _C:France FRA; _C:Ghana GHA; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Malaysia MYS; _C:Namibia NAM; _C:Nepal NPL; _C:New Zealand NZL; _C:Nigeria NGA; _C:Portugal PRT; _C:Rwanda RWA; _C:Singapore SGP; _C:South Africa ZAF; _C:Sweden SWE; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

The “Improving learning through classroom experience” study - Megogo Bokamba, Tania (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257522 ZenodoArchiveConcept: 10257521 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1038 2129771:MBPHUZIR
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

The importance of climate-friendly school buildings in Africa - Nambatya, Mauricia (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257528 ZenodoArchiveConcept: 10257527 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1039 2129771:RTMQSBV6
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

The Impact of Using Geography Open Education Resources (OER) to Capacitate Natural Science Teachers Teaching the Earth and Beyond Strand in South African Schools - Dreyer, J. M.; Dreyer, J.M. (Alternation Journal, 2018)
KerkoCite.ItemAlsoKnownAs: 10.29086/2519-5476/2018/sp21a8 2129771:57HG7SR2 2129771:VMT75YCL 2129771:YDKM3FPZ
Keywords: _C:Australia AUS; _C:China CHN; _C:India IND; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

The Impact of Teacher Effectiveness on Student Learning in Africa - Buhl-Wiggers, Julie; Kerwin, Jason; Smith, Jeffrey; Thornton, Rebecca (Research on Improving Systems of Education (RISE), 2017)
Teaching quality is known to be critical for students’ education and life prospects in developed countries. However, little is known about how teacher quality affects student learning in Africa. This paper presents the first estimates of teacher value-added from an African country, using data from a school-based RCT in northern Uganda. Exploiting the random assignment of students to classrooms within schools, we estimate a lower bound on teacher effects. A 1-SD increase in teacher quality leads to at least a 0.14 SD improvement in student performance on a reading test at the end of the year. Shifting teachers from the 10th to the 90th percentile of quality increases performance by 0.36 SDs –comparable to the most effective education interventions conducted in Africa. Our results also suggest that an increase in teacher quality can make other education interventions more efficient.
KerkoCite.ItemAlsoKnownAs: 2129771:E8NLECM5 2129771:LUER2NXX 2405685:AEMAW5PW 2405685:LSQR8MAH 2447227:8W4XYI4G 2486141:TU36ERQU
Keywords: C:Uganda; NULP; _C:Ecuador ECU; _C:India IND; _C:Kenya KEN; _C:Pakistan PAK; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:filed:1; __C:scheme:1; _genre:PR-primary_research; interesting

The impact of school mapping in the development of education in Tanzania: an assessment of the experiences of six districts - Galabawa, Justinian C. J.; Agu, Augustine Obeleagu; Miyazawa, Ichiro (Evaluation and Program Planning, 2002)
In this study the authors have looked at the impact of school mapping in the development of education in Tanzania. The study examined the experiences of six districts where school mapping exercises were carried out. The key question that guided the study is what happened after school mapping. Through a combination of instruments and/or techniques—interviews, questionnaires, focus group discussion, and document analysis, the study found that school mapping impacted in varying degrees positively on the development of education in the districts in terms of increased enrollment and attendance, decreased incidents of dropping out, improved information for decision making, and enhanced capacities of field actors to plan and take action. The authors conclusively argued that for the benefits of school mapping to be maximized and sustained, it should not be a one shot activity for data collection purposes only. Rather, it should be an on-going process of assessment, analysis, and action.
KerkoCite.ItemAlsoKnownAs: 10.1016/S0149-7189(01)00046-5 2129771:5DICP3CA
Keywords: _C:Central African Republic CAF; _C:France FRA; _C:Ghana GHA; _C:India IND; _C:Japan JPN; _C:Kenya KEN; _C:Tanzania TZA; _C:Uganda UGA; __C:filed:1; __C:scheme:1

The impact of GIS-supported teacher allocation in Sierra Leone: High-level findings on teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6504993 2129771:7AXGA8UK 2405685:SE5JPCX2
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0055 2129771:RIHMNP95 2405685:QAH4K4D6
Keywords: _C:Sierra Leone SLE

The Impact of Covid-19 on Learning - the Perspective of the Ghanaian Student - Owusu-Fordjour, C.; Koomson, C. K.; Hanson, D. (European Journal of Education Studies, 2020)
This study aimed at accessing the impact of Covid-19 on Ghana’s teaching and learning. The study employed a Descriptive survey design in which 11 items Likert-scale type of questionnaires was administered to 214 respondents mainly students in the second cycle and tertiary institutions of Ghana. The study employed simple random sampling technique in selecting the respondents for the study. The study revealed some challenges students encounter in the close down of schools due to the outbreak of the pandemic Covid-19: Students are unable to study effectively from the house thus, making the online system of learning very ineffective. Again, parents are incapable of assisting their wards on how to access online learning platform, neither can they entirely supervise the learning of their children at home without any complications. It came to light that the pandemic really has had a negative impact on their learning as many of them are not used to effectively learn by themselves. The e-learning platforms rolled out also poses challenge to majority of the students because of the limited access to internet and lack of the technical knowhow of these technological devices by most Ghanaian students. The study therefore recommends that students should be introduced to e-learning platforms to supplement classroom teaching and learning. Article visualizations:
Number: 0 KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v0i0.3000 2129771:L6VV3C9M 2129771:T9U4AGSJ 2405685:EQNYAN9P
Keywords: _COVID_DEAA-List; __C:filed:1; emotions; highlife music; lyrics; popular music; structure; ⚠️ Invalid DOI

The impact GIS-supported teacher allocation in Sierra Leone: Inception Report - McBurnie, Chris; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 2129771:SMVFRCNY 2405685:HT8ZGKAB
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

The impact and reach of MOOCs: A developing countries’ perspective - Liyanagunawardena, Tharindu; Williams, Shirley; Adams, Andrew (eLearning Papers, 2013)
Massively Open Online Courses (MOOCs) are a recent but hugely popular phenomenon in the online learning world. They are hailed by many as a solution for the developing world’s lack of access to education because MOOCs can provide learning opportunities to a massive number of learners from anywhere in the world as long as they can access the course through Internet. However, a close consideration of the ability of learn- ers from most developing countries to make use of MOOCs seems to contradict this rhetoric. This paper discusses features of MOOCs and looks at them from a developing countries’ perspective to conclude that due to a complicated set of conditions (‘access’, language, computer literacy among others) prevailing in developing countries, MOOCs may not be a viable solution for education for a large proportion of people in these ar- eas of the world. The paper further shows the need for more data on the demograph- ics of MOOC participants from developing countries to form a better understanding of MOOCs role in educating people from developing countries.
KerkoCite.ItemAlsoKnownAs: 2129771:EGN52YWE 2129771:I236WQ36 2129771:P768IDQH 2339240:KUBQWJSR 2339240:U3ZRM9IM 2405685:4RBFSPKP 2405685:WBWECXQ5 2486141:9GZATIPJ 261495:JMKKF9GF
Keywords: C:Low- and middle-income countries; MOOCs; NOTdocs.opendeved.net; _C:Afghanistan AFG; _C:Australia AUS; _C:Burundi BDI; _C:China CHN; _C:Denmark DNK; _C:Finland FIN; _C:France FRA; _C:India IND; _C:Italy ITA; _C:Jordan JOR; _C:Mexico MEX; _C:Nepal NPL; _C:Norway NOR; _C:Rwanda RWA; _C:Spain ESP; _C:Sri Lanka LKA; _C:Sweden SWE; _C:Switzerland CHE; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ⛔ No DOI found

The Effect of Technology-mediated Reading Comprehension Tasks on Autonomy and Metacognitive Strategy Use by Iranian EFL Intermediate Learners - Mehri Ghahfarokhi, Marzieh; Tavakoli, Mansoor (Journal of Modern Research in English Language Studies, 2020)
Publisher: Imam Khomeini International University KerkoCite.ItemAlsoKnownAs: 2129771:M2ANPNEQ
Keywords: _C:Canada CAN; _C:China CHN; _C:Iran IRN; _C:Turkey TUR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

The Contribution of Digital Technologies to Service Delivery: An Evidence Review - Sharmin, Shumona; Faith, Becky; Prieto Martín, P.; Ramalingam, Ben (IDS, 2017)
00001 KerkoCite.ItemAlsoKnownAs: 2129771:5QB22ESR 2129771:7M4GEMG2
Keywords: _C:Afghanistan AFG; _C:Armenia ARM; _C:Australia AUS; _C:Azerbaijan AZE; _C:Bangladesh BGD; _C:Bhutan BTN; _C:Bolivia BOL; _C:Botswana BWA; _C:Brazil BRA; _C:Burkina Faso BFA; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Catalan Republic XCATA; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Costa Rica CRI; _C:Cuba CUB; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Ethiopia ETH; _C:Gambia GMB; _C:Ghana GHA; _C:Guatemala GTM; _C:Guinea GIN; _C:Guyana GUY; _C:Honduras HND; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Kyrgyzstan KGZ; _C:Lesotho LSO; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Maldives MDV; _C:Mexico MEX; _C:Myanmar MMR; _C:Nepal NPL; _C:New Zealand NZL; _C:Niger NER; _C:Nigeria NGA; _C:Oman OMN; _C:Pakistan PAK; _C:Panama PAN; _C:Paraguay PRY; _C:Peru PER; _C:Philippines PHL; _C:Qatar QAT; _C:Romania ROU; _C:Rwanda RWA; _C:Samoa WSM; _C:Singapore SGP; _C:Solomon Islands SLB; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:State of Palestine PSE; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Venezuela VEN; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1; literature / systematic review

The Context of Training Teachers to Implement a Socially Relevant Science Education in Africa - Ogunniyi, Meshach B. (African Journal of Research in Mathematics, Science and Technology Education, 2011)
The underlying assumption to this paper is that learners' ability to appreciate the relevance of school science and its importance to socio-economic development of their communities to a large extent depends on the quality of instruction they receive from their teachers. A popular conundrum is that no country is greater than the calibre of its teachers. However, a sort of Mathew's principle of the "haves" having more and the "have-nots" losing even what they do have tends to hold. Hence, learners of well-trained teachers tend to outperform those of poorly trained teachers on most tasks. A vivid example here in South Africa is the usual wide chasm between the matriculation results of learners from the former well-resourced Model C schools and those (with few exceptions due to massive support) from the previously disadvantaged schools. In pursuit of relevance many African political leaders and policy makers have called on teacher training institutions to produce teachers who are capable of making school science relevant to learners' home environment. This paper reports an attempt that has been made to equip teachers in such a way that makes science accessible, interesting and complementary to learners' indigenous knowledge and life worlds in general.
KerkoCite.ItemAlsoKnownAs: 10.1080/10288457.2011.10740721 10/gf62k6 2129771:E4TZHI8E 2317526:ZTRC6VUX DOI-10.1080/10288457.2011.10740721
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:access; F:attitude; F:policy; F:teaching method; P:culture; P:economy; P:environment; P:measurement; P:social; P:teacher education; P:teacher training; P:teachers; R:case study; T:Training; T:trainee; Z:African Culture; Z:Case Studies; Z:Course Content; Z:Cultural Context; Z:Culturally Relevant Education; Z:Disadvantaged Schools; Z:Educational Change; Z:Educational Quality; Z:Foreign Countries; Z:Indigenous Knowledge; Z:Interdisciplinary Approach; Z:Relevance (Education); Z:Science Education; Z:Science Instruction; Z:Scientific Principles; Z:Social Problems; Z:Teacher Attitudes; Z:Teacher Education; Z:Teacher Effectiveness; Z:Teaching Methods; Z:Western Civilization; publicImportV1

The challenges and prospects of ICTs in teaching and learning in Sunyani Polytechnic, Ghana - Bonsu, KA; Duodu, A; Bonsu, K; Duodu, K (Capa Scientific Journal, 2013)
Globally, the impact of Information and Communication Technology (ICT) in the past decades has been enormous. ICT plays a crucial role in socio-economic development and in bringing the world together as a global village. Indeed, in today‟s knowledge based economy, a completely new set of skills are required. Developing countries need to respond to demand for strategies to prepare the youth for the competitive opportunities driven by information and communication technology. The role of ICT tools in education should be more emphasized despite the heavy investment on ICT infrastructure, equipment and professional development for improved education. However, the adoption of ICT and its integration in teaching and learning have met challenges. This study reports the state of ICT usage in teaching and learning at Sunyani Polytechnic, Ghana. The study highlights factors that influence effective integration of ICT in teaching and learning. The findings revealed minimal adoption of ICT in teaching and learning at Sunyani Polytechnic, Ghana. The study makes recommendations that would enhance ICT uptake and adoption when implemented.
KerkoCite.ItemAlsoKnownAs: 2129771:IBZFIJST 2317526:SDK35I7X
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:teaching; P:economy; P:teacher education; Q:ICT; Q:educational technology; R:case study; T:TVET; _C:Ghana GHA; __C:filed:1; publicImportV1; ⛔ No DOI found

The Case of Non-formal Education Provisions in Namibia - Indabawa, SA (2000)
There are established and irrefutable evidences which show the symbiotic and dialectical links between education and development. (Aklilpelu,'90, Duke,'85;Obaiiewa.'84, Omolewa.'94;Indabawa,'94; and Sagcan.'97). Education can liberate and make human beings more completely human (Freire); it can empower especially the disadvantaged groups. It is also capable of being an instrument for the eradication of literacy, preventable diseases, social apathy, social immobility and can as well enhance the human potential for greater economic productivity and reduction of human social inequality, (Anipene,'80; Adiseshiah,'80;Duke,'83; and Indabawa,'91). Given this background. all investment in educational provisions, whether formal or nonformal. will be well justified. However, this is not to suggest that education on its own will be the only precondition for human development. Education too, has its own damaging consequences on society, especially if it is used as a vehicle for promoting less than the general good of society; or it turns out to be irelevant to the popular needs ( Ayandele,'74;Akinpelu,'97; Shirley,'96). The aim of this paper is to stimulate discussion of and interest in Nonformal Educational Provisions in the Republic of Namibia. In facilitating this, ttention will be paid to seven basic issues as follows: Country background, Concept of Nonformal Education. Policy context of nonformal education provisions; Diversity of provisions; relation to formal education; Relevance of programmes to beneficiaries and Impact.
KerkoCite.ItemAlsoKnownAs: 2129771:WGLYBLCM 2317526:EAKDLNLQ UTI-315AB96B-C20B-3E81-8B60-CC3942F5FEAE
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Namibia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:ministry; P:culture; Q:higher education; Q:open learning; T:TVET; publicImportV1; ⛔ No DOI found

The Availability of Electronic Courses Using ICT Infrastructure in Teaching and Learning among Teachers in Nigeria's TVET Institutions. - Hashim, MHM; Abubakar, B (2017)
Abstract: As information and communication technology becomes a regular feature of the educational environment, it may be difficult for teaching and learning activities especially in TVET institutions to remain unchallenged. However, ICT application as a pedagogical tool in Nigerian TVET institutions is not a common practice and it also remains unclear how utilisation of ICT enhances pedagogy. This study is interested in the availability of electronic courses using ICT infrastructure in teaching and learning. Using activity theory as a guide, multiple case studies are conducted. The Qualitative Case Study Methodology is used in this research. Five TVET institutions and 20 participants are selected using maximum variation and homogeneous purposive sampling strategies, respectively. During the visits to the institutions, classroom observation is carried out, documents such as the curriculum and teacher's lecture materials are reviewed for triangulation. Semi-structured interviews are conducted with 20 selected participants as the primary data collection method. At the data analysis stage, the inductive and deductive methods are used to analyse the data and two strategies of grounded theory as open and axial coding are employed. The coding process is achieved through the use of an inherent feature of NViVOlO. The findings show that four themes: availability of infrastructure, computer specifications, educational software and connectivity.
KerkoCite.ItemAlsoKnownAs: 2129771:DLZZV2QH 2317526:W742575Q UTI-659E7698-0E52-3D96-B24B-CB8235ECD882
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:teaching; P:electro; P:teachers; Q:ICT; Q:educational technology; T:TVET; publicImportV1; ⛔ No DOI found

The Athens of West Africa: A History of International Education at Fourah Bay College, Freetown, Sierra Leone - Paracka, Daniel J. (2006)
This book is about Fourah Bay College (FBC) and its role as an institution of higher learning in both its African and international context. The study traces the College's development through periods of missionary education (1816-1876), colonial education (1876-1938), and development education (1938-2001).
KerkoCite.ItemAlsoKnownAs: 2129771:LL63YKLE 2339240:993UCWCL 2405685:3CTGQYRP
Keywords: _C:Sierra Leone SLE

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:8MVPQD5Y 2339240:FHMH4G7H 2405685:7DIVY6PP
Keywords: ⛔ No DOI found

Technology-Supported Professional Development for Teachers: Lessons from Developing Countries. - McAleavy, Tony; Hall-Chen, Alex; Horrocks, Sarah; Riggall, Anna (Education Development Trust, 2018)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2129771:3ME55RD5 2129771:AFSMJQ39 2129771:EMRI49IG 2129771:FBX8S8GL 2129771:P7FKHCWL 2339240:CNU2GKRL 2405685:FXXS4882
Keywords: C:Low- and middle-income countries; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Brazil BRA; _C:China CHN; _C:France FRA; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Kenya KEN; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Nepal NPL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Russian Federation RUS; _C:Senegal SEN; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:Viet Nam VNM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Technology for professional development: access, interest and opportunity for teachers of English in South Asia - British Council (British Council, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:7UWQ68SG 2405685:UE23QGKH
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Brazil BRA; _C:China CHN; _C:India IND; _C:Italy ITA; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Nepal NPL; _C:Pakistan PAK; _C:Sri Lanka LKA; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; __C:filed:1; __C:scheme:1

Technical Vocational Education Training (TVET) Brief - Iyengar, R; Shin, HI; Aliyu, B; Menkiti, A (2014)
As Kaura Specialist Development Foundation (KSDF) explores various pathways to support Technical Vocational Education Training (TVET) for the youth in Bauchi state, Nigeria, this brief has been written to provide information on the current status of education and youth in Bauchi state, as well as to document relevant strategies and best practices utilized around the world for TVET. Positioned within the global framework, under Sustainable Development Goals (SDGs), the aim of this brief is to highlight prevalent trends cited in the TVET literature and global examples to support a design of an effective program for Bauchi state’s youth to develop their personal and professional skills to become an integral part of the workforce and engage in lifelong learning.
KerkoCite.ItemAlsoKnownAs: 2129771:UJ2T9H5L 2317526:E57GM6XJ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Guinea; C:Mali; C:Mauritania; C:Nigeria; C:Senegal; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:gender; F:learning; P:economy; Q:distance learning; Q:mobile learning; T:Ausbildung; T:TVET; T:Training; publicImportV1; ⛔ No DOI found

Technical Vocational Education and Training (TVET) as intervention mechanism for global competitiveness: perspectives from Nigeria - Okoye, KRE; Okwelle, PC (Developing Country Studies, 2014)
At national and international platforms, it has been maintained that TVET provides the needed employable skills and attitudes necessary for effective performance in the workplace. In many nations across the globe, some reform strategies to build on the inherent strength of TVET systems has been vigorously adopted, Nigeria not left behind. This paper explores the national TVET system in response to the emergent global issues on economic productivity. The following outlines provided a guide in the discourse; TVET defined, TVET reform standard and adaptability, TVET and the state of the art in Nigeria, unemployment level and the causes in Nigeria, concept transformation as mechanism for skill acquisition and why few enrolment in TVET Programs. Based on the analysis made in this paper, some recommendations were made on ways of strengthening TVET system in Nigeria for global competitiveness.
KerkoCite.ItemAlsoKnownAs: 2129771:75FTDNBM 2317526:XM7BTMXF
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; P:mechanic; P:service industry; P:social; Q:open learning; T:Educação profissionalizante; T:TVET; publicImportV1; ⛔ No DOI found

Technical-Vocational Education and Language Policy in Ghana - Adogpa, James Nsoh (International Journal of Educational Administration and Policy Studies, 2015)
Technical and vocational graduates in Ghana are often ill-equipped to become self-reliant or well-fitted into the demands of the job market. This pattern can be examined in terms of the educational language policy implementation that disregards regional linguistic needs. This seems to arise as a result of the medium of instruction that is implemented in wholesale. This paper illustrates the need for the adoption of predominant regional Ghanaian languages to be used as medium of instruction in our various technical and vocational institutions in Ghana to enable learners grasp the desired skills and concepts that are relevant to preparing graduates of technical and vocational institutions for the job market. Such changes would better facilitate the technological and national advancement that we need.
KerkoCite.ItemAlsoKnownAs: 2129771:ECSAWI9J 2317526:3WGC7F2Y
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:policy; P:measurement; P:media; P:technology; Policy analysis; T:TVET; Z:African Languages; Z:Change Strategies; Z:Educational Change; Z:Educational Needs; Z:Educational Policy; Z:Foreign Countries; Z:Job Skills; Z:Language of Instruction; Z:Vocational Education; _C:Ghana GHA; __C:filed:1; publicImportV1; ⛔ No DOI found

Technical and Vocational Education in Cameroon and Critical Avenues for Development - Che, S. Megan (Research in Comparative and International Education, 2007)
Technical and vocational education (TVE) can influence development and economic progress for post-colonial societies. Some newly independent sub-Saharan African countries attempted curricular transformation that might produce a skilled workforce through widespread access to versions of TVE. In Cameroon, no such post-colonial curricular revolution was enacted. This article qualitatively analyzes fourteen Cameroonian secondary mathematics teachers' spontaneous discussions about the possibilities and perceived necessity for increased TVE avenues in Cameroon. Relationships between TVE, the problem of educated unemployed, the public and private sectors, and development are explored. This article views teachers' discussions from a lens of critical theory.
KerkoCite.ItemAlsoKnownAs: 10.2304/rcie.2007.2.4.333 10/fhg7ds 2129771:RTRHDLV2 2317526:4UEBKKQ7
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Cameroon; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:developing nation; F:access; F:attitude; F:curriculum; P:economy; P:teachers; R:qualitative; T:TVET; Z:Critical Theory; Z:Curriculum Development; Z:Developing Nations; Z:Economic Development; Z:Economic Progress; Z:Foreign Countries; Z:Job Skills; Z:Labor Force Development; Z:Labor Market; Z:Mathematics Teachers; Z:Secondary School Mathematics; Z:Secondary School Teachers; Z:Teacher Attitudes; Z:Technical Education; Z:Unemployment; Z:Vocational Education; publicImportV1

Technical and vocational education and training (TVET) in Nigeria and energy development, marketing and national transformation - Okoye, KRE; Chijioke, Okwelle P. (Journal of Education and Practice, 2013)
Education is considered by many as an agent of human development, social mobility and socio-economic development of any society. However, it is arguable that the type and quality of education a nation offers to its citizens is a function of the level of progression of that nation. In this context, technical and vocational education and training (TVET) has been recognized as the wide-diversified education system instrumental in making the remarkable contribution to economic growth of a country by a way of suitable manpower production relevant to the needs of industry, society and changing technological work environment. This paper explores the TVET situation for Nigeria for its transformation agenda with highlights on such factors as trends on TVET policies for human resource development, capacity building, energy development and professional marketing in the national transformation agenda.
KerkoCite.ItemAlsoKnownAs: 2129771:JVP62MTJ 2317526:PAEALDAN
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:attitude; P:electro; P:technology; T:Educação profissionalizante; T:TVET; publicImportV1; ⛔ No DOI found

Technical and vocational education and training (TVET) for young people in low- and middle-income countries: a systematic review and meta-analysis - Tripney, Janice S; Hombrados, Jorge G (Empirical Research in Vocational Education and Training, 2013)
The world is facing a worsening youth employment crisis. In response, technical and vocational education and training (TVET) is back on the development agenda after years of neglect. This systematic review examined the evidence from studies evaluating the impacts of TVET interventions for young people in low- and middleincome countries (LMICs). The 26 included studies evaluated 20 different interventions, predominantly from Latin America. Meta-analyses of the effectiveness of TVET on five outcome measure categories were conducted. The overall mean effects on overall paid employment, formal employment, and monthly earnings were small, positive, and significant; however, significant heterogeneity was observed. Moderator analysis was performed in an attempt to explain between-study differences in effects. The overall paucity of research in this area, together with specific gaps and methodological limitations, affirm the need for strengthening the evidence base. Implications for policy, practice and research are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1186/1877-6345-5-3 10/gf62zx 2129771:J9NNI3R6 2249382:8Z39TPIP 2317526:ZDA23HGH UA-ef9e8a77-a2ae-48e7-aee2-7ad36c907bed
Keywords: -AB-Review; -AB-Review-SSA; -RQAsummary; -codedOrSummarised; -review; C:Kenya; CLL:en; FF1.1/3; FF2.2; FF2.7.a; keyReview en; onLongList; retain_obsolete; revofrevSummarisedSeptember2018; summarised

Technical and vocational education and training (TVET) and skills development for poverty reduction – do rural women benefit? - Hartl, Maria (International Fund for Agricultural Development, Italy, 2009)
This paper discusses technical and vocational education and training (TVET) as well as skills development in rural areas, mainly pertaining to agriculture and related activities and explores existing gender differences. TVET has suffered from a focus on basic, and especially primary education, which led to the neglect of post-basic education and training and their non-inclusion in the UN Millennium Development Goals. Recently, there has been a renewed interest in training and skills development because of increased evidence that a minimalist approach to microfinance for poverty reduction and enterprise development did not lead to sustainable growth. The paper argues that many training interventions do not cater for the specific needs of women who are under-represented in formal training programmes and often directed towards typical female occupations. It reviews vocational and skills training in several IFAD supported programmes and explores how these target the poor and most vulnerable and to what extend gender differences in training provision, methodology, training content and transition to labour markets have been taken into account.
KerkoCite.ItemAlsoKnownAs: 2129771:7G6G9RSM 2317526:NYMGZ267
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Botswana; C:Senegal; C:Seychelles; C:Zimbabwe; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:gender; F:policy; F:women; Q:primary education; T:Ausbildung; T:TVET; T:trainee; _C:Ghana GHA; gender; publicImportV1

Technical and vocational Education and Training in Ethiopia - Krishnan, P; Shaorshadze, I (2013)
This report presents a background study of the state of Technical and Vocational Education and Training in Ethiopia. We discuss the state of TVET in Ethiopia, as well as the contextual information on education system and economic indicators in Ethiopia as they relate to the TVET implementation and policy. We argue that given the supply-driven nature of the TVET system in Ethiopia, it is important to improve its efficiency, and we propose two ways to doing this: (1) Improve efficiency and equity of the centrallydriven allocation mechanism drawing on the recent advances in matching algorithms and their application to the school choice; (2) Impact evaluation of the final labour market outcomes of the graduates has to be integral part of the TVET system, and we discuss various ways such evaluation could be conducted.
KerkoCite.ItemAlsoKnownAs: 2129771:6BTP2ZMG 2129771:VSPWZKH6 2317526:IKLU5I39 2317526:V6KZKE23
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; T:Ausbildung; T:TVET; publicImportV1; ⛔ No DOI found

Tech plus teachers: Did one-on-one phone tutorials help kids learn better during school closures in Sierra Leone? - Crawfurd, L; Evans, D; Guiterrez Bernal, M; Hares, S; Sam-Kpakra, R; Sandefur, J; Shojo, M (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:S5Z2IZTV 2339240:5Z8RBH2S 2405685:TF3CV7CH
Keywords: _C:Sierra Leone SLE

Teaching with and Learning through ICTs in Zimbabwe's Teacher Education Colleges. - Musarurwa, C (US-China Education Review, 2011)
The use of ICTs (information and communication technologies) in Zimbabwe’s teacher education colleges is of paramount importance. The teacher trainees have a dual role to play: learning through ICTs and also learning how to teach through them. Interestingly, the rate at which schools have embraced the use of ICTs is unprecedented, but this has not been matched with an equal effort by teacher education colleges and hence teacher trainees have been less exposed and trained in using such technologies. Evidently, this has created a mismatch between the need for teachers who are conversant with ICTs and e-learning and their availability. This paper stems from a pilot programme in which the author was an active participant. It reflects on efforts made to integrate ICTs into the teacher education curriculum and evaluates the impact that this programme will have on teacher education in Zimbabwe.
KerkoCite.ItemAlsoKnownAs: 2129771:SUIBMCP9 2317526:CRPHCLQS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Mozambique; C:Zimbabwe; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:curriculum; F:learning; F:teaching; P:measurement; P:teacher education; P:teacher training; Q:ICT; Q:ODEL; Q:open learning; T:TVET; meta; publicImportV1; ⛔ No DOI found

Teaching Group Counseling in Botswana: Two U.S.-Trained Counselors Discuss Experiences and Share Cultural Considerations for Practice - Coker, Angela D.; Majuta, Aaron R. (Journal for Specialists in Group Work, 2015)
There is a paucity of research in the area of teaching group counseling within an African context. In this article we describe and reflect on our experiences teaching group counseling at an institution of higher learning in the country of Botswana. We discuss cultural traditions and strengths that support an environment of group work in Botswana, describe cross-cultural challenges we experienced along the way as we implemented Western-derived didactic and experiential components of group counseling training, and discuss the ways in which we addressed the cultural differences we encountered. Implications for future cross-cultural research and training are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1080/01933922.2014.992506 10/gf62j6 2129771:77YNA8B5 2317526:9N5I6ELM
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Botswana; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:attitude; F:learning; F:pedagogy; F:teaching; P:culture; P:environment; P:social; Q:higher education; T:Training; T:trainee; Z:Acquired Immunodeficiency Syndrome (AIDS); Z:Colleges; Z:Counselor Training; Z:Cross Cultural Training; Z:Cultural Awareness; Z:Cultural Differences; Z:Foreign Countries; Z:Group Counseling; Z:Group Dynamics; Z:Higher Education; Z:Interpersonal Communication; Z:Prosocial Behavior; Z:Social Attitudes; publicImportV1

Teaching and learning of mathematics in the context of the National Numeracy Programme: Finding from a rapid in-depth qualitative study - Oliveira, Andre Correa de; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: Author:OpenDevEd; _forthcoming; _r:AddedByZotZen

Teaching and learning: achieving quality for all - UNESCO (UNESCO Publishing, 2014)
KerkoCite.ItemAlsoKnownAs: 2129771:L7BYMPGX 2129771:VSDHHN2M 2317526:84RYDD8Q 2317526:ANC99CQF 261495:N6VKK8WW
Keywords: AWP2; AWP2-actual; CitedIn:AKFC; CitedIn:OER4S-TPE-HHH2; CitedIn:OER4Schools-2012-HHH1; CitedIn:OER4Schools-HHH3; CitedIn:OER4Schools-HHH3-A; CitedIn:OER4Schools-HHH3-A-PREVIOUS; CitedIn:OER4Schools-HHH3-B; CitedIn:PhD_Thesis; EfA; GMR; RPF-May-2016; _C:Afghanistan AFG; _C:Albania ALB; _C:Algeria DZA; _C:Andorra AND; _C:Angola AGO; _C:Antigua and Barbuda ATG; _C:Argentina ARG; _C:Armenia ARM; _C:Artsakh XARTH; _C:Australia AUS; _C:Austria AUT; _C:Azerbaijan AZE; _C:Bahamas BHS; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Barbados BRB; _C:Belarus BLR; _C:Belgium BEL; _C:Belize BLZ; _C:Benin BEN; _C:Bhutan BTN; _C:Bolivia BOL; _C:Bosnia and Herzegovina BIH; _C:Botswana BWA; _C:Brazil BRA; _C:Brunei Darussalam BRN; _C:Bulgaria BGR; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Central African Republic CAF; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Congo; Republic COG; _C:Costa Rica CRI; _C:Croatia HRV; _C:Cuba CUB; _C:Cyprus CYP; _C:Czech Republic CZE; _C:Denmark DNK; _C:Djibouti DJI; _C:Dominica DMA; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Equatorial Guinea GNQ; _C:Eritrea ERI; _C:Estonia EST; _C:Ethiopia ETH; _C:Federated States of Micronesia FSM; _C:Fiji FJI; _C:Finland FIN; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Grenada GRD; _C:Guatemala GTM; _C:Guinea GIN; _C:Guinea-Bissau GNB; _C:Guyana GUY; _C:Haiti HTI; _C:Honduras HND; _C:Hungary HUN; _C:Iceland ISL; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Ivory Coast CIV

Teachers' views about technical education: implications for reforms towards a broad based technology curriculum in Malawi - Chikasanda, VK; K Otrel-Cass, K; Jones, A (International Journal of Technology and Design Education, 2011)
Internationally there has been concern about the direction of technical education and how it is positioned in schools. This has also been the case in Malawi where the curriculum has had a strong focus on skills development. However, lately there has been a call for enhancing technological literacy of students, yet little support has been provided for teachers to achieve this goal. This paper reports from a wider study that looked at teachers’ existing views and practices in technical education in Malawi. The article focuses on the findings from interviews that were conducted with six secondary school teachers to find out about their understanding of the meaning and rationale for technical education. It is also discussed how the teachers view technical education as involving skills development for making things and their thoughts on the benefits of such knowledge. It is argued that teachers’ views about technical education were strongly linked to the goals of the curriculum vacationalization policies adopted at the dawn of political independence. Besides skills training they saw the potential to impart thinking skills related to design and problem solving, and the need for essential pedagogical techniques to support learning in technical education. Examination requirements, inadequate opportunities to conduct practical activities and a lack of supportive policy were seen as limiting factors. This article claims that teachers’ views were shaped by their expectations and beliefs about the nature of technical education and what they perceived students may gain from such learning. Their views were also influenced by contextual factors which may have implications on reforms towards broader notions of technology education.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10798-010-9125-5 10/cqjzj5 2129771:JIJIU75V 2317526:W2LRL8U3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Malawi; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:curriculum; P:teachers; P:technology; Q:educational technology; T:TVET; publicImportV1

Teachers present in school but absent in class: utilization and ‘silent erosion’of learning time in the implementation of the curriculum in Mongu district of Zambia. - Mulenga, Innocent Mutale; Lubasi, Ireen Monde (2019)
Publisher: European Journal of Education Studies
Keywords: ⛔ No DOI found

Teachers' Perceptions and Students' Lived Experiences in Vocational-Technical Subjects in a Rural High School in Zimbabwe - Masinire, Alfred (Gender and Education, 2015)
This paper explores the construction of dominant models of gender among students in the Vocational-Technical. In the backdrop of dominant narratives that structure gender policies and practices in schooling in Zimbabwe, the paper elaborates upon how students' daily experiences in workrooms perpetuate the feminisation and masculinisation of fields of study such as DT and HESs in ways that inhibit the learning and achievement of boys and girls in these subjects. The argument in this paper is that in order to understand gender inequality in the Voc-Tech curriculum, educators need to understand how sociocultural perceptions of gender are constructed and embodied at the level of classroom interaction among students and teachers. Such insights provide a deeper understanding for addressing gender inequality in Voc-Tech subjects that moves beyond current structural and institutional barriers within a rural African context.
KerkoCite.ItemAlsoKnownAs: 10.1080/09540253.2015.1079357 10/gf62kx 2129771:7DPG8XQP 2317526:44W8UQC7 DOI-10.1080/09540253.2015.1079357
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Zimbabwe; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:achievement; F:attitude; F:curriculum; F:gender; F:girl; F:learning; F:policy; P:construction; P:environment; P:metal; P:teachers; R:evaluation; R:interview; R:observation; T:TVET; Z:Barriers; Z:Classroom Environment; Z:Critical Theory; Z:Curriculum Evaluation; Z:Educational Practices; Z:Feminism; Z:Foods Instruction; Z:Foreign Countries; Z:Gender Differences; Z:Gender Issues; Z:High School Students; Z:Institutional Characteristics; Z:Interviews; Z:Masculinity; Z:Metallurgy; Z:Nutrition Instruction; Z:Observation; Z:Rural Schools; Z:Sex Fairness; Z:Sex Role; Z:Student Attitudes; Z:Student Experience; Z:Teacher Attitudes; Z:Teacher Student Relationship; Z:Vocational Education; gender; publicImportV1

Teachers’ pedagogical content knowledge for teaching computer studies in rural Zambian secondary schools of North-western province. - Masumba, Collins Kasoka; Mulenga, Innocent Mutale (2019)
Publisher: Zambia Journal of Library & Information Science (ZAJLIS)
Keywords: ⛔ No DOI found

Teachers’ pedagogical content knowledge, curriculum designing, and student’s comprehension of secondary school ordinary level physics in Lusaka, Zambia. - Zulu, Jacqueline; Mulenga, Innocent Mutale (2019)
Publisher: UNESWA Journal of Education
Keywords: ⛔ No DOI found

Teachers of Refugees: A Review of the Literature - Richardson, Emily (Education Development Trust, 2018)
The United Nations High Commissioner for Refugees (UNHCR) estimates that 65.6 million people are forcibly displaced, having either crossed national borders or become internally displaced within their own countries. Of this estimate, over 22.5 million are refugees. Over half of the world's refugees are children. With an average length of displacement of approximately 20 years, the majority of these children will spend their entire childhoods away from home. Refugee children have limited access to basic social services like healthcare and education. Given the length of their displacement, generations of refugee children throughout the world could miss out on education altogether. Numerous studies show that the teacher is the most important in-school factor affecting the quality of education, particularly in refugee contexts, where the teacher is sometimes the only resource available to students. In refugee contexts where infrastructure and resources are limited, the role of the teacher is particularly important to the quality of education. However few studies to date have examined the role of teachers in refugee contexts. With more literature focusing on refugee children and youth, little is known about who the teachers of refugees are and how they are recruited, trained, retained, compensated and managed in their contexts. Importantly, there is little research on national teachers who are teaching refugee children; rather, much of the available literature focuses on refugee teachers – that is, teachers who are also refugees. In addition, this lack of literature on teachers of refugees hinders our understanding not only of their needs but also of 'how refugees can contribute to education in their host countries and (eventually) to their home countries'. The purpose of this literature review is to survey policies, practices and debates that governments and their partners must navigate to provide education for refugee populations, and the strategies they have used to select and manage teaching forces. The review analyses findings from the main literature on teachers of refugees according to the following themes: (1) recruitment, certification and selection of teachers; (2) teacher preparation and development; (3) teacher remuneration and incentives; and (4) teacher retention. In addition, for each of these themes, this review highlights the salient gaps in the research and suggests an agenda for further research. [Co-written with Leonora MacEwen and Ruth Naylor.]
Publication Title: Education Development Trust KerkoCite.ItemAlsoKnownAs: 2129771:PAW48PJ7
Keywords: Access to Education; Civil Rights; Compensation (Remuneration); Faculty Development; Financial Support; Foreign Countries; Incentives; Refugees; Research Needs; Teacher Certification; Teacher Education; Teacher Persistence; Teacher Recruitment; Teacher Role; Teacher Selection; _C:Afghanistan AFG; _C:Algeria DZA; _C:Bangladesh BGD; _C:Bhutan BTN; _C:Bosnia and Herzegovina BIH; _C:Burkina Faso BFA; _C:Cameroon CMR; _C:Chad TCD; _C:Congo XCO; _C:Croatia HRV; _C:Egypt EGY; _C:Ethiopia ETH; _C:Greece GRC; _C:Guinea GIN; _C:Iraq IRQ; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malaysia MYS; _C:Nepal NPL; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Somalia SOM; _C:South Africa ZAF; _C:South Sudan SSD; _C:State of Palestine PSE; _C:Sudan SDN; _C:Sweden SWE; _C:Syrian Arab Republic SYR; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1

Teachers Learning Together: Large-scale approaches to teacher communities of practice - Rossignoli, Serena; Amenya, Donvan; Kamana, Dieudonne; Tiganescu, Andrea; Kudenko, Irina (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:U44EAVHV 2405685:KJU6N64C 2405685:WFJZTGQZ
Keywords: C:Kenya / Rwanda; _C:Kenya KEN; _C:Rwanda RWA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

Teachers for rural schools – a challenge for South Africa - Plessis, Pierre du; Mestry, Raj (South African Journal of Education, 2019)
Poverty is rife in many African countries and this has serious implications for the provision of quality education. Rural schools face severe challenges that are unique to their environment. A lack of parental interest in children’s education, insufficient funding from the state, a lack of resources, underqualified teachers, and multi-grade teaching are some of the barriers to effective education. These challenges can be attributed to numerous sources, from within school structures and from the external environment, including local communities and education authorities. After 25 years of democracy, educational standards and learner performance in rural schooling has shown little improvement. This study illustrates the complexity and inter-connectedness of the problems faced by teachers in South African rural schools. Using qualitative research within the interpretivist paradigm, this article explores the perceptions and experiences of teachers in rural schools located in White River in the Mpumalanga province. This grounded-theory research focuses on effective teaching and learning. The findings reveal that most rural schools do not have water, sanitation, or electricity, and classrooms are in a terrible state. These issues have serious implications for effective teaching and learning.Keywords: deployment; education level; education quality; recruitment; rural schools
Keywords: _C:Australia AUS; _C:Canada CAN; _C:France FRA; _C:Ghana GHA; _C:Malaysia MYS; _C:South Africa ZAF; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1; deployment; education level; education quality; recruitment; rural schools; ⚠️ Invalid DOI

Teachers as agents of sustainable peace, social cohesion and development: theory, practice & evidence - Novelli, Mario; Sayed, Yusuf (Education as Change, 2016)
Publisher: University of Johannesburg KerkoCite.ItemAlsoKnownAs: 10.17159/1947-9417/2016/1486 2129771:88PBEAAU
Keywords: _C:Afghanistan AFG; _C:Australia AUS; _C:India IND; _C:Lebanon LBN; _C:Myanmar MMR; _C:Nepal NPL; _C:Pakistan PAK; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Teachers and the Teaching Profession in Sierra Leone: A Comprehensive Situation Analysis - Wright, Cream (TSC, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:7TAK5P96 2129771:L5SHN8BJ 2339240:BPP6QJJT 2405685:K3L9HBBP 2601447:KDYSFZB9 4556019:GI25ICPJ
Keywords: _C:Sierra Leone SLE

Teachers' Adoption of Open Educational Resources in Higher Education. - Baas, Marjon; Admiraal, Wilfried; van den Berg, Ellen (Journal of Interactive Media in Education, 2019)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 10.5334/jime.510 2129771:36F9DWH9
Keywords: _C:Netherlands NLD; _C:Tanzania TZA; _C:Turkey TUR; __C:filed:1; __C:scheme:1

Teacher transfers from primary schools in Chama district of Zambia: Causes of the massive teacher exodus and its effects on learner’s academic performance - Phiri, Donald; Mulenga, Innocent Mutale (Multidisciplinary Journal of Language and Social Sciences Education (2664-083X, Online ISSN: Print ISSN: 2616-4736), 2020)
Keywords: ⛔ No DOI found

Teacher's Voices Crying in the School Wilderness: Involvement of Secondary School Teachers in Curriculum Development in Zambia. - Mulenga, Innocent Mutale; Mwanza, Christine (Journal of Curriculum and teaching, 2019)
Publisher: ERIC

Teacher’s Voices Crying in the School Wilderness: Involvement of Secondary School Teachers in Curriculum Development in Zambia - Mulenga, Innocent Mutale; Mwanza, Christine (Journal of Curriculum and Teaching, 2019)
In Zambia, curriculum development for primary and secondary schools is done centrally. The Curriculum Development Centre (CDC), the institution placed with the responsibility of facilitating curriculum development, claims that the Zambian school curriculum is developed through a consultative and participatory approach through course and subject panels where teachers and other stakeholders are represented. However, there has been no empirical evidence to suggest the roles that teachers, who are the major implementers of the same curricular, are required to play in the development process. This study therefore, sought to establish perceptions of secondary school teachers on their role in the curriculum development process in Zambia. The concurrent embedded design of the mixed methods approach was employed with the qualitative approach dominating the study while the quantitative was used to add detail. Data from secondary school teachers was collected using questionnaires while interview guides were used for Head teachers. Raw data collected from interviews and questionnaires was analyzed using themes and descriptive statistics and then arranged into significant patterns so as to easily interpret and understand the essence of the data. The findings of the study clearly suggested that the majority of secondary school teachers in Lusaka were willing to participate in the curriculum development process, especially in situational analysis, in the formulation of educational objectives, in setting up the curriculum project, and in the writing of curriculum materials such as textbooks. From the study it was concluded that teachers were aware of some of the roles that they could play in the curriculum development but were not adequately involved in the development process.

Teacher retention in refugee and emergency settings: The state of the literature - Ring, Hannah Reeves; West, M Y (The International Education Journal: Comparative Perspectives, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:3GXIVSSW 2129771:GN4QC67U 2129771:M5HVE7L7 2486141:9QST5RRI
Keywords: _C:Afghanistan AFG; _C:Belgium BEL; _C:Bhutan BTN; _C:Cambodia KHM; _C:Chad TCD; _C:China CHN; _C:Ethiopia ETH; _C:France FRA; _C:India IND; _C:Kenya KEN; _C:Lebanon LBN; _C:Nepal NPL; _C:Nicaragua NIC; _C:Papua New Guinea PNG; _C:Sierra Leone SLE; _C:Switzerland CHE; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Teacher Retention: A Review of Policies for Motivating Rural Basic School Teachers in Ghana - Acheampong, Phinihas; Gyasi, Juliana Fosua (Asian Journal of Education and Training, 2019)
The study primarily explored the challenges of teaching in rural basic schools in Ghana. Qualitative research method through semi-structured interviews and document analyses were used as data collection instruments. The participants for the study included six educational field workers which constituted a district education officer (Circuit Supervisor), two head teachers and three classroom teachers. Priority of the findings was highlighted on the provision of accommodation with adequate installation of lighting facility, potable drinking water, and transport facilities such as a vehicle, motorbike and bicycle to ease the living constraints of teachers who serve in underprivileged learning communities. Again, professional development programs were found relevant to encourage and promote teachers working in remote areas. Results of the study shown that rural basic school teachers do not see why they should receive equivalent conditions of service as their peers who teach in urban schools. It is therefore recommended that, about one-third of teachers? salary should be apportioned as additional incentive to motivate teachers who serve in rural basic schools. Again, special student-trainees recruitment strategies should be adopted to recruit potential teachers from underprivileged communities to receive training and serve their people. This can effectively be implemented when the District Sponsorship Scheme Project is restored to enhance better deployment of teachers in underserved schools.
Publisher: Asian Online Journal Publishing Group
Keywords: Administrator Attitudes; Disadvantaged; Educational Facilities; Faculty Development; Faculty Mobility; Foreign Countries; Housing; Incentives; Rural Schools; School Districts; Student Recruitment; Teacher Education; Teacher Motivation; Teacher Persistence; Teacher Salaries; Transportation; Water Quality; _C:Botswana BWA; _C:Canada CAN; _C:China CHN; _C:Ethiopia ETH; _C:France FRA; _C:Gambia GMB; _C:Ghana GHA; _C:Lesotho LSO; _C:Malawi MWI; _C:Mozambique MOZ; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: <this> EdTechHub.Source: <this> EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3924551 2129771:2N28M8EI 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; C:sub-Saharan Africa; STC-TLC; _C:Cameroon CMR; _C:Congo XCO; _C:Ethiopia ETH; _C:Ghana GHA; _C:Jordan JOR; _C:Kenya KEN; _C:New Zealand NZL; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:t; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Teacher Professional Development at a Tsunami-Affected School in Banda Aceh - Ubit, Fadliadi; Bartholomaeus, Pam (International Education Journal: Comparative Perspectives, 2018)
The 2004 tsunami in Aceh resulted in significant post-disaster problems which extended far beyond the loss of possessions and infrastructure destruction. In addition to having to deal with their own problems as a consequence of the tsunami, teachers were faced with the additional problems arising from working with children who had been exposed to the traumatic event. Teacher professional development was regarded as an important support mechanism to help teachers in this period. Findings from a qualitative study conducted in one school affected by the tsunami in Banda Aceh provided evidence that teachers indeed needed professional development that went beyond enhancing their knowledge and skills to teach their subjects to working with young people affected by the traumatic event. This paper discusses teacher professional development, focusing on the five criteria for effective professional development proposed by Desimone.
Publisher: Australian and New Zealand Comparative and International Education Society KerkoCite.ItemAlsoKnownAs: 2129771:LN6H7GUC
Keywords: Case Studies; Evaluation Criteria; Faculty Development; Foreign Countries; Interviews; Junior High School Students; Junior High Schools; Natural Disasters; Program Effectiveness; Public School Teachers; Qualitative Research; Secondary School Teachers; Trauma; _C:Australia AUS; _C:Bangladesh BGD; _C:India IND; _C:Indonesia IDN; _C:Jordan JOR; _C:Malaysia MYS; _C:Maldives MDV; _C:Myanmar MMR; _C:Seychelles SYC; _C:Singapore SGP; _C:Somalia SOM; _C:Sri Lanka LKA; _C:Tanzania TZA; _C:Thailand THA; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
EdTechHub.Source: 2405685:VM6NXYF3 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631749 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:VM6NXYF3
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _C:Bangladesh BGD; _C:Ghana GHA; _C:India IND; _C:Jordan JOR; _C:Kenya KEN; _C:Liberia LBR; _C:Pakistan PAK; _C:South Africa ZAF; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:o

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
EdTechHub.Source: 2405685:H9W2X3KM KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631747 2129771:UEUAKMXJ 2339240:94ZP3EK4 2339240:MM2SDXUM 2339240:S4UAH7Q3 2405685:DQWJLRN5 2405685:H9W2X3KM
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; _C:Ghana GHA; _C:India IND; _C:Jordan JOR; _C:Kenya KEN; _C:Liberia LBR; _C:South Africa ZAF; _C:United Kingdom GBR; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:n

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
EdTechHub.Source: 2405685:SC5NHA65 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631745 2129771:EHFUXJQC 2129771:YHNWVMB3 2339240:94ZP3EK4 2339240:FIDI5TC2 2405685:39DIRNE9 2405685:HH3QKBIF 2405685:I3BV48CX 2405685:ITL9PIC3 2405685:K8BSWYFM 2405685:KF9F48ID 2405685:N68MMAPR 2405685:P5Y5GMFN 2405685:SC5NHA65 2486141:TAY7LNB6
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; _C:Ghana GHA; _C:India IND; _C:Jordan JOR; _C:Kenya KEN; _C:Liberia LBR; _C:South Africa ZAF; _C:United Kingdom GBR; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:m

Teacher Motivation in Sub-Saharan Africa and South Asia - Bennell, Paul; Akyeampong, Kwame (DfID London, 2007)
KerkoCite.ItemAlsoKnownAs: 2129771:242EHRP6 2129771:5XS5KY3U 2129771:N5KTN9CE 2339240:4YDHY6PL 2405685:25GLFYDL 4556019:J65GX7JX
Keywords: C:sub-Saharan Africa and South Asia; _C:Afghanistan AFG; _C:Argentina ARG; _C:Australia AUS; _C:Bangladesh BGD; _C:Benin BEN; _C:Botswana BWA; _C:Brazil BRA; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Chad TCD; _C:China CHN; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Gambia GMB; _C:Ghana GHA; _C:Guinea GIN; _C:India IND; _C:Kenya KEN; _C:Lesotho LSO; _C:Madagascar MDG; _C:Malawi MWI; _C:Mali MLI; _C:Mauritania MRT; _C:Mexico MEX; _C:Mozambique MOZ; _C:Namibia NAM; _C:Nepal NPL; _C:New Zealand NZL; _C:Nicaragua NIC; _C:Niger NER; _C:Nigeria NGA; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Sweden SWE; _C:Tanzania TZA; _C:Togo TGO; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Teacher Management Policy for Sierra Leone - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:ILC2GGZX 2129771:XQMFH5JU 2339240:5QZ2N3GQ 2405685:M6F97ARN 4556019:49UIZ3SU
Keywords: _C:Sierra Leone SLE

Teacher Management in Refugee Settings: Ethiopia. - Bengtsson, Stephanie; Fitzpatrick, Rachael; Hinz, Katja; MacEwen, Leonora; Naylor, Ruth; Riggall, Anna; West, Helen (Education Development Trust, 2020)
ISBN: 1912610035 Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2129771:KJE7FC2F
Keywords: _C:Burkina Faso BFA; _C:Burundi BDI; _C:Chad TCD; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Cuba CUB; _C:Djibouti DJI; _C:Eritrea ERI; _C:Ethiopia ETH; _C:France FRA; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Korea; Republic KOR; _C:Lebanon LBN; _C:Norway NOR; _C:Rwanda RWA; _C:Somalia SOM; _C:South Sudan SSD; _C:Sudan SDN; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Yemen YEM; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Teacher Management 2.0: Improving Teacher Deployment in Malawi - World Bank (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:F2I5PI5L
Keywords: _C:Malawi MWI; __C:filed:1; __C:scheme:1

Teacher Involvement in Curriculum Development in Zambia: A Role Analysis of Selected Secondary School Teachers in Lusaka District, Lusaka Province, Zambia - Mwanza, Christine (University of Zambia, 2017)
Keywords: ⛔ No DOI found

Teacher governance reforms and social cohesion in South Africa: from intention to reality - Salmon, Thomas; Sayed, Yusuf (Education as Change, 2016)
Publisher: University of Johannesburg
Keywords: _C:Netherlands NLD; _C:Rwanda RWA; _C:South Africa ZAF; _C:South Sudan SSD; _C:Sudan SDN; __C:filed:1; __C:scheme:1

Teacher educators as agents of change? A critical realist study of a group of teacher educators in a Kenyan university - Stutchbury, Kristina (The Open University, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:J4QKGXE7 2129771:UYJHRF48
Keywords: _C:Australia AUS; _C:Botswana BWA; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Kenya KEN; _C:Malawi MWI; _C:Mauritius MUS; _C:Mozambique MOZ; _C:Namibia NAM; _C:New Zealand NZL; _C:Nigeria NGA; _C:Rwanda RWA; _C:Senegal SEN; _C:South Africa ZAF; _C:Sudan SDN; _C:Tanzania TZA; _C:Togo TGO; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Teacher education versus teacher training: epistemic practices and appropriate application of both terminologies. - Mulenga, Innocent Mutale (2020)
Publisher: Journal of Lexicography and Terminology
Keywords: ⛔ No DOI found

Teacher education in anglophone west Africa: Does policy match practice? - Colley, Kabba E. (International Perspectives on Education and Society, 2014)
© 2014 by Emerald Group Publishing Limited All rights of reproduction in any form reserved. This chapter focuses on a study, which investigates the question: How do teacher education policies match teacher education practices in Anglophone West Africa? Teacher education policy in this chapter refers to action statements in verbal or written form made by national education authorities/agencies about teacher education, while teacher education practice refers to the work that teachers do. Using the method of research synthesis, multi-layered, purposeful sampling of various data sources, Boolean and non-Boolean search strategies, qualitative and quantitative analytical procedures, the study identified over a hundred documents. Out of these, 77 documents met the criteria for inclusion in the study. The distribution of research outcomes by Anglophone West African countries were as follows: 18.2% were on Gambia, 27.3% were on Ghana, 10.4% were on Liberia, 24.7% were on Nigeria, and 19.5% were on Sierra Leone. From this research synthesis, it is evident that there is a gap between teacher education policy and practice in Anglophone West Africa. Most teacher education policies are "add-on," meaning that they were formulated as part of a larger national policy framework on basic, secondary and tertiary education. In addition, the research synthesis found that Gambia, Ghana, Nigeria, and Sierra Leone are very similar in terms of their pre-service teacher training models, but differ in their in-service and professional development systems, while Liberia has a slightly different in-service model with varying durations. The limitations and implications of the findings for further comparative and international education research are discussed in the chapter.
KerkoCite.ItemAlsoKnownAs: 10.1108/s1479-367920140000025015 10/gf62j3 2129771:RTR537TR 2317526:3VLABS4Y
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; AAZ:West Africa; C:Gambia; C:Liberia; C:Nigeria; C:Sierra Leone; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:inclusion; F:outcomes; F:policy; P:services; P:teacher education; P:teacher training; P:teachers; Q:tertiary education; R:qualitative; R:quantitative; R:synthesis; T:Training; Z:Education; Z:Policy; Z:Supply; Z:Teacher; Z:Training; _C:Ghana GHA; _C:Sierra Leone SLE; publicImportV1

TEACHER EDUCATION CURRICULUM DESIGNING: THE IMPORTANCE OF CONNECTING UNIVERSITY CURRICULA TO SECONDARY SCHOOL KNOWLEDGE AND SKILLS CONTEXTS - Mulenga, Innocent Mutale (ZANGO: Zambian Journal of Contemporary Issues, 2019)
Keywords: ⛔ No DOI found

Teacher Education at the University of Zambia and Teacher Quality with Specific Reference to English Language - Banja, Madalitso K.; Mulenga, Innocent Mutale (Makerere Journal of Higher Education, 2019)

Teacher Education at a Distance: Impact on Development in the Community - Binns, Felicity; Wrightson, Tony (DFID, 2006)
KerkoCite.ItemAlsoKnownAs: 2129771:YC4QXI68 2405685:3IPM5K7Y
Keywords: C:Low- and middle-income countries; _C:Canada CAN; _C:Egypt EGY; _C:Ghana GHA; _C:Guyana GUY; _C:Jamaica JAM; _C:Kenya KEN; _C:Lesotho LSO; _C:Malawi MWI; _C:Mexico MEX; _C:New Zealand NZL; _C:Nigeria NGA; _C:South Africa ZAF; _C:Sudan SDN; _C:Tanzania TZA; _C:Trinidad and Tobago TTO; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Teacher Education and the Challenge of Development: a global analysis - Moon, B.; Dladla, N; Bird, A. Nordstrum, L. Hanbing, Y. McCormick, B. Banks, F. Dheram, P. Ibn Junaid, M. Wolfenden, F. Buckler, A. Gafar, A. Tao, S., L. Storey; Kirk, J.; Azlam, M.; Kingdon, G.; Dembele, M.; Miaro-II, J. Power, T., B. Anamuah-Mensah; Umar, A. (Routledge, 2013)
KerkoCite.ItemAlsoKnownAs: 2129771:9ZEGYMQF 2129771:XIRMR2Y4 2317526:JLSR2KAW 261495:GV5J6KI4
Keywords: AWP2; AWP2-actual; CitedIn:AKFC; CitedIn:OER4Schools-2012-HHH1; CitedIn:OER4Schools-HHH3; CitedIn:OER4Schools-HHH3-A; CitedIn:OER4Schools-HHH3-A-PREVIOUS; CitedIn:OER4Schools-HHH3-B; CitedIn:PhD_Thesis; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Brazil BRA; _C:Canada CAN; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Congo XCO; _C:France FRA; _C:Ghana GHA; _C:India IND; _C:Iran IRN; _C:Iraq IRQ; _C:Kenya KEN; _C:Lesotho LSO; _C:Mali MLI; _C:Nigeria NGA; _C:Pakistan PAK; _C:South Africa ZAF; _C:Sudan SDN; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

Teacher collaboration in curriculum design teams: prospects and challenges in the Zambian education system - Mwanza, Christine; Changwe, Robert (Multidisciplinary Journal of Language and Social Sciences Education (2664-083X, Online ISSN: Print ISSN: 2616-4736), 2020)
Keywords: ⛔ No DOI found

Teacher coaching in Kenya: Examining instructional support in public and nonformal schools - Piper, Benjamin; Zuilkowski, Stephanie Simmons (Teaching and Teacher Education, 2015)
Instructional coaching has improved student outcomes in the United States, and may help to solve Kenya's literacy problems. Coaching is costly, however, and evidence is lacking regarding the most cost-efficient teacher-to-coach ratio. We used student literacy outcome data from more than 8000 students participating in the Kenya Primary Math and Reading Initiative—a randomized controlled trial of instructional interventions in public and nonformal schools—to fill this gap. Coaches in larger public zones made fewer visits per teacher, and teacher-coach ratio and student performance were negatively associated. Using causal methods, we concluded that lower ratios might improve nonformal school outcomes.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2015.01.001 10/f63z7b 2129771:NYI8CY62 2129771:PI8G7IIF 2129771:ZVRS99BQ 2339240:76EQG2NV 2405685:LM7EYD5E 2405685:WU59KPEH 261495:QBFNURGR
Keywords: AWP2; C:Kenya; CitedIn:AKFC; CitedIn:OER4Schools-HHH3-B; Coaching; Instruction; Kenya; Literacy; PRIMR; _C:Canada CAN; _C:Ethiopia ETH; _C:Kenya KEN; _C:Liberia LBR; _C:Malawi MWI; _C:Mozambique MOZ; _C:Thailand THA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; professional development

Talent leadership strategies enhance teacher’s professional competencies in 21st century education for sustainable development - Xu, Ping; Yue, Xiaoyao (IOP Conference Series: Earth and Environmental Science, 2019)
Issue: 1 KerkoCite.ItemAlsoKnownAs: 10.1088/1755-1315/373/1/012003 2129771:BNSNYXS8
Keywords: _C:Canada CAN; _C:Norway NOR; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Tablet Use in Teaching: A Study on Developing an Attitude Scale for Academics. - Kayapinar, Ulas; Spathopoulou, Filomachi; Safieddine, Fadi; Nakhoul, Imad; Kadry, Seifedine (Eurasian Journal of Educational Research, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:76X8A39V
Keywords: _C:Belgium BEL; _C:Brazil BRA; _C:Canada CAN; _C:Denmark DNK; _C:France FRA; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Kuwait KWT; _C:Lebanon LBN; _C:Malawi MWI; _C:Nigeria NGA; _C:Romania ROU; _C:Saudi Arabia SAU; _C:Spain ESP; _C:Turkey TUR; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Tablet use in schools: impact, affordances and considerations - Major, Louis; Haßler, Björn; Hennessy, Sara (Handbook on Digital Learning for K-12 Schools, 2017)
00007 KerkoCite.ItemAlsoKnownAs: 2129771:485MSZJF 2129771:8BTH5YPD 2129771:FLMTLZDC 2129771:TYSXQU5W 2129771:W8LWQ8RD 2129771:YJ3TC54F
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Australia AUS; _C:New Zealand NZL; _C:Spain ESP; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
The increased popularity of tablets in general has led to uptake in education. We critically review the literature reporting use of tablets by primary and secondary school children across the curriculum, with a particular emphasis on learning outcomes. The systematic review methodology was used, and our literature search resulted in 33 relevant studies meeting the inclusion criteria. A total of 23 met the minimum quality criteria and were examined in detail (16 reporting positive learning outcomes, 5 no difference and 2 negative learning outcomes). Explanations underlying these observations were analysed, and factors contributing to successful uses of tablets are discussed. While we hypothesize how tablets can viably support children in completing a variety of learning tasks (across a range of contexts and academic subjects), the fragmented nature of the current knowledge base, and the scarcity of rigorous studies, makes it difficult to draw firm conclusions. The generalizability of evidence is limited, and detailed explanations as to how, or why, using tablets within certain activities can improve learning remain elusive. We recommend that future research moves beyond exploration towards systematic and in-depth investigations building on the existing findings documented here.
EdTechHub.Source: <this> EdTechHub.Source: 2129771:9IYKEUKJ KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:67CB8FHE 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2129771:XBQV2NGQ 2129771:XWGFIH7Y 2129771:Z688UKBU 2292090:7ASI5XLU 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2405685:7552P2EL 2405685:9I6F956M 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -missingHU; Android; Australia AUS; Author:Haßler; Author:OpenDevEd; Belgium BEL; Björn-CV-OECS; Canada CAN; Chile CHL; DL4D cited; Malawi MWI; Monday; New Zealand NZL; Spain ESP; TL:Arabic; TL:English; TL:Translated; Thailand THA; TranslationGoingAhead; Turkey TUR; _C:Brazil BRA; _C:China CHN; _C:France FRA; _C:Germany DEU; _C:India IND; _C:Kenya KEN; _C:Norway NOR; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:United Kingdom GBR; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; iPad; learning outcomes; publicImportV1; school; systematic reviews; tablets

Systems approach to tourism training and education: The Kenyan case study - Mayaka, Melphon; Akama, John S. (Tourism Management, 2007)
Abstract Kenya's tourism industry is relatively well developed (with first class hospitality establishments and tourist facilities that are juxtaposed in close proximity to pristine glistering tropical sand beaches and world renowned wildlife attractions in protected parks and reserves). Hence the country, in recent years, has become a popular destination for international visitors, especially European and North American tourists, haggling for safari tourism experience combined with relaxation in pristine glistering tropical sand beaches. Thus, Kenya provides a good case study in the examination of deficiencies in tourism training that characterises many countries in Africa and other emerging tourist destinations in different regions of the world. As this study shows Kenya, as the case is with many other Third World countries, lacks a well-coordinated tourism training strategy and educational institutions capable of providing much needed human resource training and capacity building, especially at supervisory and managerial level. This paper identifies existing deficiencies in tourism education and training in Kenya, and provides a framework that can be applied in the development of a well-coordinated national tourism training strategy and initiation of education programmes. Indeed, systems approach can be replicated elsewhere in Africa and other Third World countries where tourism is increasingly gaining momentum as a major socio-economic phenomenon.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tourman.2005.12.023 10/dq2df7 2129771:UPVEVBA3 2317526:5W9V5DR3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CCZ:Kenya; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:P; CT:R; CT:T; D:developing country; P:economy; P:measurement; P:tourism; R:case study; T:Training; Z:Developing countries; Z:Staff training; Z:Tourism education; publicImportV1

Sustaining and Scaling Pedagogic Innovation in Sub-Saharan Africa: Grounded Insights For Teacher Professional Development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this commentary we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our work of over five years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. ‘OER4Schools’ integrates interactive pedagogy, Open Educational Resources (OER) and the use of mobile devices (where available). Our focus here is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through the use of OER. Our conclusions offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for future programme design and implementation.
00000 EdTechHub.Source: <this> EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:65GDUID3 2129771:AAT7FR3H 2129771:AS7MJJEC 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2129771:NITLC7K7 2129771:ULKWW8ZY 2249382:CS9PALG8 2292090:LR6L7S7U 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:HGHAYJ5G 2339240:HR2YGWX3 2405685:NZ3GKZCR 2405685:ZFJ79LQS 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Monday; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; STC-TLC; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; TL:Arabic; TL:English; TL:Translated; Teacher Professional Development; Technology Uses in Education; Telecommunications; TranslationGoingAhead; _C:Bangladesh BGD; _C:Brazil BRA; _C:Cambodia KHM; _C:Cameroon CMR; _C:China CHN; _C:Ethiopia ETH; _C:Ghana GHA; _C:India IND; _C:Japan JPN; _C:Kenya KEN; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:a; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Sustainable tourism industry development in sub-Saharan Africa: Consequences of foreign hotels for local employment - Fortanier, Fabienne; Wijk, Jeroen van (International Business Review, 2010)
Abstract While foreign investment in the tourism industry is often considered important in stimulating sustainable development in least developed countries, empirical evidence is still scarce and ambiguous. Focusing on the social (employment) dimension of sustainable development, this paper analyses how foreign firms in the hotel industry influence the quantity of local employment (number of jobs) and its quality (skills). Using interview data with managers of 123 foreign and locally owned hotels in Mozambique, Tanzania and Ethiopia, we find that the simple scale effects of foreign hotels in least developed countries are positive. However, rather than contributing to local human capital via training, foreign firms instead prefer to hire well-trained employees from local hotels. We explore the implications of such reverse knowledge transfer for policy makers in least developed countries.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ibusrev.2009.11.007 10/fr7twp 2129771:246R5SBJ 2317526:WVC4V7D3 LOCAL-DOI:10.1016/j.ibusrev.2009.11.007
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; AA:Africa; C:Ethiopia; C:Mozambique; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:policy; F:pro-poor; P:services; P:social; P:tourism; R:interview; T:Training; T:trainee; Z:Employment; Z:Foreign direct investment; Z:International hotel industry; Z:Knowledge transfer; Z:Pro-poor tourism; Z:Services; Z:Sustainable development; publicImportV1

Sustainable green energy production from agricultural and poultry operations-A renewable energy project for community empowerment and vocational training in remote villages in South Africa - Ushimaru, Kenji (INEE Global Humanitarian Technology Conference, 2012)
The development of an innovative waste-to-energy plant in rural South Africa is now underway. A plan to construct a test unit that uses chicken droppings from a nearby chicken farm as a fuel source is presented. This waste-to-energy plant offers an opportunity to provide economic development and community empowerment. The system is based on two critical components: (1) a power generation plant which uses chicken droppings as a fuel source, and (2) a waste processing unit that is based on magnetic induction heating technology. The ultimate goal of the power plant is to utilize it as a vocational training tool to teach young people of the community to become power plant technicians, a vocational option that has never been available in rural African communities until now. © 2012 IEEE.
KerkoCite.ItemAlsoKnownAs: 10.1109/ghtc.2012.80 10/gf62nf 2129771:TX6XC4WV 2317526:THP2WYWK LOCAL-SCOPUS_ID:84873114957
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:agricultural; P:economy; P:production; P:technician; P:technology; T:TVET; Z:agricultural waste; Z:economicdevelopment; Z:induction heating; Z:job creation; Z:power plant; Z:renewableenergy; Z:steam extraction; publicImportV1

Sustainable Development Goal 4 in the Commonwealth - Status Update Report - Goldie-Scot, Matthew; Hollows, Sophie; Hennessy, Sara; Mathew, Primrose; Delbridge-Smith, Paul; Haßler, Björn (Commonwealth Secretariat, 2018)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958259 2129771:3I3WZ9D9
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Antigua and Barbuda ATG; _C:Australia AUS; _C:Bahamas BHS; _C:Bangladesh BGD; _C:Barbados BRB; _C:Belize BLZ; _C:Botswana BWA; _C:Brunei Darussalam BRN; _C:Cameroon CMR; _C:Canada CAN; _C:Cyprus CYP; _C:Dominica DMA; _C:Fiji FJI; _C:Ghana GHA; _C:Grenada GRD; _C:Guinea GIN; _C:Guyana GUY; _C:India IND; _C:Jamaica JAM; _C:Kenya KEN; _C:Kiribati KIR; _C:Lesotho LSO; _C:Malawi MWI; _C:Malaysia MYS; _C:Malta MLT; _C:Mauritius MUS; _C:Mozambique MOZ; _C:Namibia NAM; _C:Nauru NRU; _C:New Zealand NZL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Rwanda RWA; _C:Saint Kitts and Nevis KNA; _C:Saint Lucia LCA; _C:Saint Vincent and the Grenadines VCT; _C:Samoa WSM; _C:Seychelles SYC; _C:Sierra Leone SLE; _C:Singapore SGP; _C:Solomon Islands SLB; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Tanzania TZA; _C:Tonga TON; _C:Trinidad and Tobago TTO; _C:Tuvalu TUV; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Vanuatu VUT; _C:Zambia ZMB; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence

Surveillance training for ebola preparedness in Côte d’Ivoire, Guinea-Bissau, Senegal, and Mali - Cáceres, Victor M.; Sidibe, Sekou; Andre, McKenzie; Traicoff, Denise; Lambert, Stephanie; King, Melanie E.; Kazambu, Ditu; Lopez, Augusto; Pedalino, Biagio; Herrera Guibert, Dionisio J.; Wasswa, Peter; Cardoso, Placido; et al. (Emerging Infectious Diseases, 2017)
© 2017, Centers for Disease Control and Prevention (CDC). All rights reserved. The 2014–2015 epidemic of Ebola virus disease in West Africa primarily affected Guinea, Liberia, and Sierra Leone. Several countries, including Mali, Nigeria, and Senegal, experienced Ebola importations. Realizing the importance of a trained field epidemiology workforce in neighboring countries to respond to Ebola importations, the Centers for Disease Control and Prevention Field Epidemiology Training Program unit implemented the Surveillance Training for Ebola Preparedness (STEP) initiative. STEP was a mentored, competency-based initiative to rapidly build up surveillance capacity along the borders of the at-risk neighboring countries Côte d’Ivoire, Mali, Senegal, and Guinea-Bissau. The target audience was district surveillance officers. STEP was delivered to 185 participants from 72 health units (districts or regions). Timeliness of reporting and the quality of surveillance analyses improved 3 months after training. STEP demonstrated that mentored, competency-based training, where learners attain competencies while delivering essential public health services, can be successfully implemented in an emergency response setting.
KerkoCite.ItemAlsoKnownAs: 10.3201/eid2313.170299 10/gf62j5 2129771:YE4AYNIN 2317526:XZ7WLJ6I
Keywords: -FullBiblioUHMLgen; -RRQ:M:final; -missingHU; A:West Africa; C:Guinea; C:Guinea-Bissau; C:Liberia; C:Mali; C:Nigeria; C:Senegal; C:Sierra Leone; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:health; P:services; R:survey; T:Training; T:competency-based training; T:trainee; _C:Sierra Leone SLE; publicImportV1

Supporting teacher development: literature review. - Reid, Kate; Kleinhenz, Elizabeth; Australia; Department of Foreign Affairs and Trade (2015)
This literature review identifies and evaluates evidence on the effectiveness of approaches to improving teacher quality in developing countries. It examines four categories of assistance for improving teacher quality: teacher development policies; pre-service education and training; in-service professional development; and school-based support. As far as possible the review highlights practices that demonstrat effectiveness. The review describes examples from different countries, of practices in educational policy and teacher development focused on enhancing teacher quality. It identifies policies that support teacher development as well as the characteristics of effective pre-service teacher education programs and of high-quality professional learning programs for teachers. It acknowledges the need to modify and adapt intervention approaches to suit particular country contexts. [Executive summary].
OCLC: 930576865
Keywords: _C:Afghanistan AFG; _C:Australia AUS; _C:Belgium BEL; _C:Burundi BDI; _C:Cambodia KHM; _C:Canada CAN; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Egypt EGY; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:Guinea GIN; _C:Guyana GUY; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Israel ISR; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Laos LAO; _C:Lesotho LSO; _C:Malawi MWI; _C:Malaysia MYS; _C:Mali MLI; _C:Mauritius MUS; _C:Mexico MEX; _C:Mozambique MOZ; _C:Myanmar MMR; _C:Namibia NAM; _C:Nauru NRU; _C:Nepal NPL; _C:Netherlands NLD; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Peru PER; _C:Philippines PHL; _C:Senegal SEN; _C:Singapore SGP; _C:South Africa ZAF; _C:South Sudan SSD; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Sweden SWE; _C:Tanzania TZA; _C:Thailand THA; _C:Trinidad and Tobago TTO; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Vanuatu VUT; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Supporting Change in Literacy Instruction in Malawi - Sailors, Misty; Hoffman, James V.; Pearson, P. David; McClung, Nicola; Shin, Jaran; Phiri, Liveness Mwale; Saka, Tionge (Reading Research Quarterly, 2014)
In this study, we examined the effectiveness of an innovative approach to literacy instruction in Malawi on teachers' perceptions, attitudes, and instructional practices. Two groups participated in the study: Treatment teachers received complementary teaching and learning materials, workshops, and directive coaching, and control teachers received no intervention. After this five-month intervention, treatment teachers were significantly more comfortable with their languages of instruction and were more positive about their teaching ability, beliefs about the learning materials in their classroom, and beliefs about the culture of reading in their communities than control teachers were. There were no significant differences between groups when we analyzed their teaching practices or the engagement of their students. The coaching model proved to be associated with changes in teachers' beliefs and perceptions on many of our variables. These findings suggest that the program under examination was successful in promoting the conditions for success (teacher beliefs and perceptions). Further, the findings suggest that the implementation of coaching was an important source of support in implementing changes.
shortDOI: 10/ggvk3t KerkoCite.ItemAlsoKnownAs: 10.1002/rrq.70 10/ggvk3t 2129771:7UI2KR9V 2339240:FPRQN6RV 2405685:IVTVDACJ
Keywords: Adult; C:Malawi; Childhood; Coaching; Decoding; Discussion; Early childhood; English as a second language; English for speakers of other languages; English language learners; English learners; Experimental; Fairy tales; Family literacy; Home language; Home-school connections; In-service; Instructional models; Language learners; Literature; Literature-based instruction; Oral language; Parental involvement; Phonics; Program evaluation; Reading strategies; Research methodology; School based; Sight words; Sociocultural; Socioeconomic factors; Strategies; Supplementary resources; Teacher education; Textbooks; _C:Botswana BWA; _C:Fiji FJI; _C:France FRA; _C:Israel ISR; _C:Kenya KEN; _C:Malawi MWI; _C:Singapore SGP; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; and materials; folk tales; methods; phonemic awareness; phonological awareness; professional development; quasi-experimental; word recognition

Support for teachers in challenging situations as a factor of change: reflections from a continuing professional development programme in Guinea-Bissau - da Silva, Rui; Oliveira, Joana (FIRE: Forum for International Research in Education, 2020)
Issue: 2 KerkoCite.ItemAlsoKnownAs: 10.32865/fire202062181 2129771:Y7BYB9WA
Keywords: _C:Angola AGO; _C:Canada CAN; _C:Cape Verde CPV; _C:Guinea-Bissau GNB; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:Portugal PRT; _C:South Africa ZAF; _C:South Sudan SSD; _C:Sweden SWE; _C:Tanzania TZA; _C:Uganda UGA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Successes and challenges of implementing a teacher education project in rural Sierra Leone - Mcdermott, Peter; Allen, Nancy (International Journal of Educational Research, 2015)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijer.2015.02.001 2129771:BMFE5WPR 2405685:8F6MKJP5
Keywords: _C:Sierra Leone SLE

Study on the feasibility of provision of distance learning programmes in surgery to Malawi - Mains, Edward A.A.; Blackmur, James P.; Dewhurst, David; Ward, Ross M.; Garden, O. James; Wigmore, Stephen J. (The Surgeon, 2011)
Abstract Medical educational opportunities and resources are considerably limited in the developing world. The expansion of computing and Internet access means that there exists a potential to provide education to students through distance learning programmes.This study investigated the feasibility of providing distance learning course in surgery in Malawi. The study investigated the user requirements, technical requirements and Internet connections in two teaching hospitals in Malawi. In addition the appropriateness of current course material from the Edinburgh Surgical Sciences Qualification to Malawi trainees was assessed.The study found a high degree of interest from Malawian trainees in distance learning. The provision of basic science modules such as anatomy and physiology and the ability to access journals were considered highly desirable. The current ESSQ course would require extensive re-modelling to make it suitable to an African trainee’s requirements. Internet speeds remain slow and access is currently expensive.There is considerable interest in distance learning programmes in Malawi but access to them is limited partly because of slow and expensive Internet access.Understanding the needs of trainees in countries such as Malawi will allow better direction of educational aid and resources to support surgical training.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.surge.2010.11.032 10/dkdgxg 2129771:L6UR8FLG 2317526:DE9ENG9G
Keywords: -FullBiblioUHMLgen; -RRQ:M:final; A:Africa; C:Malawi; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:T; D:developing world; F:access; F:qualification; F:teaching; P:media; Q:degree; Q:distance learning; T:Training; T:distance learning program; T:trainee; Z:Education; Distance [I02.195]; Z:Education; Medical; Graduate [I02.358.399.350]; Z:Malawi [Z01.058.290.175.500]; publicImportV1

Students’ Perceptions of Financing Public Universities in Zambia: Toward a More Sustainable and Inclusive Policy Strategy - Masaiti, Gift (Funding Higher Education in Sub-Saharan Africa, 2013)

Student Teachers School Experience in Zambia: Experiences and Challenges - Mulenga, Innocent Mutale; Bwalya, Katongo (East African Journal of Education and Social Sciences, 2022)

Student Teachers School Experience in Zambia: Experiences and Challenges - Mutale Mulenga, Innocent; Bwalya, Katongo (EAST AFRICAN JOURNAL OF EDUCATION AND SOCIAL SCIENCES, 2022)
The purpose of this study was to establish challenges and experiences faced by student teachers during teaching practice in Zambia. The study employed the concurrent embedded design. Data was collected from 280 respondents including 200 student teachers, 30 host school deputy head teachers and 50 lecturers. The study employed a questionnaire, focus group discussion and an interview to collect data from the respondents. The study established some challenges which can serve as learning points for teacher educators and administrators in institutions of higher learning that are running teacher education programs. The challenges include the struggle of maintaining low costs while having a high quality school experience, lecturers hurrying through the supervision process, the tendency to involve non-lecturers to supervise students and students lack of adequate support during the school experience period. The school experience period was adequate and students had a number of benefits from it although some institutions had it at the end of the program. It was therefore recommended that school experience be continually evaluated by both the Ministry of Education and institutions that provide teacher education programs in Zambia and that the length of the school experience period be maintained so as to enhance the benefits that student teacher drew from it. It was further recommended that institutions preparing teachers should make sure that school experience is done during the teacher education period and not at the end of it so that students and their lecturers evaluate the experience before the end of the program.

Student Perceptions of the Creation and Reuse of Digital Educational Resources in a Community Development-Oriented Organisation - Paskevicius, Michael; Hodgkinson-Williams, Cheryl (http://jl4d.org/index.php/ejl4d/article/view/253/284, 2018)
This case study explores students’ perceptions of the creation and reuse of digital teaching and learning resources in their work as tutors as part of a volunteer community development organisation at a large South African University. Through a series of semi-structured interviews, student-tutors reflect on their use and reuse of digital educational resources, and identify the challenges they experience in curating, adapting, and reusing educational resources for use in their teaching activities. The data is analysed qualitatively within the framework of an activity system (Engeström, 1987) to surface the primary systemic tensions that student-tutors face in the reuse of resources found online as well as open educational resources (OER). This study found that student-tutors sourced and used educational materials from the Internet, largely irrespective of their licensing conditions, while also creating and remixing a substantial number of educational materials to make them suitable for use in their context. We conclude that greater awareness of the availability of OER and explicit open licencing for works sourced and created within community development organisations could enhance sharing, collaboration, and help sustain high impact resources.
KerkoCite.ItemAlsoKnownAs: 2129771:2P7QUS2Z 2129771:U4HBXTYW 2129771:YXSZD8F3
Keywords: _C:Canada CAN; _C:South Africa ZAF; _C:Spain ESP; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Strengthening Teacher Professional Development: Local and global communities of practice in Kakuma Refugee Camp - Mendenhall, Mary (Columbia University, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:IVDJK7KL 2339240:7WPJ543M 2405685:32Z977JS
Keywords: C:Kenya; _C:Burundi BDI; _C:Congo XCO; _C:Ethiopia ETH; _C:France FRA; _C:Kenya KEN; _C:Pakistan PAK; _C:Somalia SOM; _C:South Sudan SSD; _C:Sudan SDN; _C:Tanzania TZA; _C:Uganda UGA; __C:filed:1; __C:scheme:1

Strategy to revitalize technical and vocational education and training (TVET) in Africa - African Union (2007)
KerkoCite.ItemAlsoKnownAs: 2129771:FE4FQGSH 2317526:RMKS3KEU
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; C:Benin; C:Burkina Faso; C:Congo; Democratic Republic COD; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:curriculum; F:leadership; F:learning; F:ministry; F:policy; F:teaching; P:agricultural; P:artist; P:construction; P:crafts; P:economy; P:environment; P:health; P:technology; Q:ICT; Q:masters; R:survey; T:Ausbildung; T:Educação profissionalizante; T:Lehrlingsausbildung; T:TVET; T:apprentice; T:apprenticeship training; T:informal training; T:vocational school; _C:Ghana GHA; publicImportV1

Strategies to retain and motivate employees in Africa: Examining the case of the ministry of education in Zambia - Masaiti, Gift; Naluyele, Pamela Nachona (African Journal of Political Science and International Relations, 2011)
Publisher: Academic Journals
Keywords: ⛔ No DOI found

Strategies That Enhance Students Access to Public Technical Training Institutions in Kenya - Nganyi, JE; Odebero, SO; Onderi, H; Musera, G (International Journal of Academic Research in Business and Social Sciences, 2014)
Stakeholders in the education sector in Kenya are concerned about low students’ participation in Technical Training Institutions. Despite the Government of Kenya’s efforts to upgrade infrastructure in these institutions, students’ participation has remained low yet the realisation of Vision 2030 depends on middle level training. Therefore this study was conceptualised to establish strategies adopted by Technical Training Institutions to support students access in these institutions. This study was conducted in Western Region of Kenya. Western Region comprise of the former Western, Nyanza and rift valley Provinces. The sample constituted of 200 lecturers (principals, deputy principals, heads of departments and registrars) and 400 students from 30 Technical Training Institutions. Data was collected using questionnaires. The results show that the strategies used to attract students are bursaries, provision of competitive courses and opening more centres. However these strategies do not attract students to these Technical Training Institutions because of weak administration and implementation by the institutions. It was recommended that in an effort to promote enrolment in Technical Training Institutions, the Kenyan Government should fully fund students enrolled in Technical Training Institutions. Besides Technical Training Institutions should enhance advertisement of the courses offered; strengthen distance/e-learning; and review courses offered to meet the market demand.
KerkoCite.ItemAlsoKnownAs: 2129771:RKH467V7 2317526:MK8JHFSX UTI-716A363B-23C2-361F-B8C1-391AED460CFC
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; C:Ethiopia; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; Q:open learning; T:TVET; publicImportV1; ⛔ No DOI found

Status of TVET in the SADC region: assessment and review of technical and vocational education and training (TVET) in the Southern African Development Community Region and of the development of a regional strategy for the revitalisation of TVET - UNESCO (UNESCO, 2013)
in spite of the importance of TVET for development and a range of national reform initiatives to support TVET over the past two decades, major concerns remain regarding the state of TVET in the Southern African region. These led SADC and UNESCO to intervene through the commissioning of a pilot TVET monitoring tool and a regional review of the state of TVET, with a view to developing a new strategic programme of action for regional cooperation in TVET. As is made clear throughout this report, the evidence gathering process for these activities demonstrated the very weak current knowledge base for TVET in the region. This means that the report has to be seen as a first step towards better knowledge for better policies and practices. The limitations of the data mean that the findings are often the best currently possible rather than meeting the highest standards of rigour. Equally, the comparative analysis cannot be as sophisticated as may be possible in future years when the data are more robust. Nonetheless, the report represents an important step forward in building an evidence-driven picture of the state of TVET in Southern Africa that provides a valuable basis for future strategic interventions.
KerkoCite.ItemAlsoKnownAs: 2129771:4FTD8LQC 2317526:4QU25BEI
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; CC:Congo; CC:Lesotho; CC:Malawi; CC:Mauritius; CC:Mozambique; CC:Namibia; CC:Seychelles; CC:South Africa; CC:Tanzania; CC:Zambia; CC:Zanzibar (tz); CC:Zimbabwe; CC:eSwatini (Swaziland); CLL:en; publicImportV1

Standars and Creteria for Approval of Programmes in Vocational Enterprise Institutions (VEI) & Innovation Enterprise Institutions (IEI) Programmes (Nigeria) - Government: Nigeria (2007)
UA-ccdd094f-8691-400d-81b5-67356ec2dc3d KerkoCite.ItemAlsoKnownAs: 2129771:U5MLSFKX 2317526:WNM39HHP
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Nigeria; publicImportV1

Stakeholders' Roles in Prioritizing Technical and Vocational Education and Training in PostConflict Liberia - Forh, Edward S. (Walden University, 2014)
Postconflict governments and counterparts have collaborated to provide skills training to communities as a critical postconflict development strategy. In these undertakings, the role of community members remains largely undefined. The purpose of this qualitative descriptive case study was to understand the perceptions held by rural community members regarding the role they played in influencing government's policy priority for technical and vocational education and training (TVET) as a local human development strategy in postconflict Liberia. The conceptual framework was based on human capital theory and concepts of motivation and achievement. Fourteen participants were purposefully selected for the study. Data were collected from interviews, focus group discussion, and documents and analyzed using constant comparison. Results indicated that increasing human capital, restoring self-esteem, encouraging civic participation, and building peace were among the community members' motivations for establishing a skills training institution. Leadership, advocacy, and ownership were major roles community stakeholders played in establishing their local skill training institution; voluntarism and collaboration were found to be strategies for support to the local TVET initiatives. Findings have positive social change implications for facilitating community-initiated TVET programs for youth employment as well as informing TVET policies in countries transitioning from conflict to development.
KerkoCite.ItemAlsoKnownAs: 2129771:I45EDFZ6 2317526:V4Y69WGI
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Liberia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:achievement; F:leadership; F:motivation; F:policy; P:administration; P:social; Q:higher education; R:case study; R:focus groups; R:interview; R:qualitative; T:TVET; T:Training; Z:Education Policy; Z:Higher Education Administration; Z:Higher education; Z:Sub Saharan Africa Studies; Z:Vocational education; publicImportV1; ⛔ No DOI found

Social Work in Ghana: A Participatory Action Research Project Looking at Culturally Appropriate Training and Practice - Kreitzer, Linda; Abukari, Ziblim; Antonio, Patience; Mensah, Johanna; Kwaku, Afram (Social Work Education, 2009)
Social work emerged in the western world, particularly in the USA and the United Kingdom, at the turn of the twentieth century. Western social welfare systems were introduced to other countries through the colonial empires of the nineteenth and twentieth centuries and social work training reflected these systems. However, many of these countries have revised their curricula to make them more culturally appropriate while others are still in this process. This article highlights issues concerning social work education and training in Ghana, West Africa through a Participatory Action Research project. Themes emerging concerning the present curriculum, the professional association and social work in Ghana are presented. Action plans instigated from this project are described, ending with a future challenge for social work in Africa.
KerkoCite.ItemAlsoKnownAs: 10.1080/02615470802109973 10/cr52q8 2129771:TFSF8YSL 2317526:TCEBIBJZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:West Africa; CA:AandC; CCZ:Ghana; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:curriculum; P:culture; P:social; T:Ausbildung; Z:Localization; Z:Participatory Action Research; Z:Social Work; Z:Social Work Curriculum; _C:Ghana GHA; publicImportV1

Social Studies Curriculum at the Crossroads: Implementation of the Secondary School Social Studies Curriculum in Chingola District of Zambia - Moobola, Larry; Mulenga, Innocent Mutale (European Journal of Education Studies, 2020)
Keywords: ⛔ No DOI found

Social protection responses to the COVID-19 lockdown in South Africa - Devereux, Stephen (The Conversation, 2020)
Several groups of people are at high risk of hardship, especially those who have effectively become unemployed because of the lockdown.
Library Catalog: theconversation.com KerkoCite.ItemAlsoKnownAs: 2129771:T2BWADVF

Social Justice and Diversity in Zambia: The Role of Civic Education and Teachers - Chivunda, Kaumba; Kabombwe, Yvonne; Mwanza, Christine; Mupeta, Sydney (Asian Journal of Education and Social Studies, 2023)
This article explores the role civic education plays in social justice and diversity in Zambia from the civic education teacher’s perspective as well as establish the extent to which teacher’s themselves are actively engaged in social justice and diversity. Predicated on the fundamental role civic education plays in teaching and promoting diversity and social justice, it is highly expected that civic education teachers should be the lodestars in undertaking this activity. It is noted that teachers of civic education can bring about social justice in society; this can be achieved through active participation in local communities and consolidating the teaching of democracy, human rights and promotion of participation within people’s local communities and global level for social justice. Therefore, the teaching for diversification is of great significance in the delivery of Civic Education in Zambia both at teacher training and secondary school level. Anchored on the explanatory design as a methodological bedrock, this study found that teachers where not actively engaged with issues of diversity. The study concludes that there is little to no engagement among teachers in diversity and in bringing about social change especially on matters that affect the wider community. This is partly attributed to the impractical nature in which Civic Education is delivered at secondary school or tertiary level. The study recommends that different approaches to the teaching of civic education must be introduced in the civic education curriculum.
Num Pages: 9 Number: 4 KerkoCite.ItemAlsoKnownAs: 2129771:MU56QNIZ 2129771:N73KHN5I 2129771:SRRXRV2D

Social isolation and aging in Zambia: examining the possible predictors - Mapoma, Christopher Chabila; Masaiti, Gift (Journal of Aging Research, 2012)
Publisher: Hindawi

Skilled labour shortage: a qualitative study of Ghana’s training and apprenticeship system - Ayentimi, Desmond Tutu; Burgess, John; Dayaram, Kantha (Human Resource Development International, 2018)
The impacts of training and apprenticeship education towards building high-level technical and vocational skills that support human capital development and attracting foreign direct investment are being reshaped by global competition. This article draws on human capital theory to report on a qualitative study that explores skilled labour challenges within Ghana’s training and apprenticeship system through the lens of the demand side of employment perspective. The ﬁndings point to a training mismatch, lack of regulations and ineﬀective apprenticeship programmes, underinvestment in education and training, and outdated training programmes. The bottlenecks in the supply of skilled labour in Ghana are hampering the ﬁrms’ ability to ﬁnd skilled labour across industries. We suggest improved social partnership between industries and training institutions, with increased government investment in training and apprenticeship programmes, as a way forward to address the technical and vocational skilled labour supply bottlenecks. Wider implications for the African region which shares similar developing contexts are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1080/13678868.2018.1447881 10/gf62j4 2129771:7CCEGI9P 2129771:VR5IUN53 2317526:77W3HCTM LOCAL-SCOPUS_ID:85044955362
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CCZ:Ghana; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:developing context; F:regulation; P:social; R:impact; R:qualitative; T:Lehrlingsausbildung; T:Training; T:vocational skills; Z:Skilled labour shortages; Z:social partnership; Z:training and apprenticeship systems; _C:Ghana GHA; __C:filed:1; publicImportV1

Sistemas internacionais de aprendizagem profissional: uma análise comparativa em alguns países desenvolvidos e emergentes - Veloso, José Rodrigo Paprotzki; Rodrigues, Marta M Assumpção (Universidade de Aveiro, 2016)
Este trabalho examina as políticas públicas que articulam educa- ção e trabalho para a juventude, de uma perspectiva comparada, contrapondo as trajetórias de países desenvolvidos e em desenvolvimento. Mais especificamente, focaliza a política de formação de aprendizes (Aprendizagem) nos casos de Alemanha, Inglaterra, França, Estados Unidos, Brasil, África do Sul e Índia. O objetivo é revelar que há algo que antecede os formatos atuais que, ao formar imagens políticas específicas, ilumina os cenários dos sistemas de Aprendizagem dos países analisados. Lança mão do enfoque da trajetória histórica (path dependence) para analisar as particularidades de cada caso.
KerkoCite.ItemAlsoKnownAs: 2129771:7AR9W9PH 2317526:U7GDHZN3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Angola; CLL:pt; publicImportV1; skills

Sierra Leone turns to technology and analytics to put quality back into education - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
Today, an estimated 2 million students return to school for the second year of the Free Quality School Education (FQSE) Program. The Government of Sierra Leone commits 21% of theRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:CBS45LK8 2405685:Z3DPRDU6
Keywords: _C:Sierra Leone SLE

Sierra Leone: Transforming the Country through Innovation - O'Connor, Shane; Zurutuza, Naroa (UNICEF, 2019)
Library Catalog: www.unicef.org KerkoCite.ItemAlsoKnownAs: 2129771:X8QL3JAV 2405685:XYSCRRC4
Keywords: _C:Sierra Leone SLE

Sierra Leone teacher & school MIS developments: Sierra Leone Education Attendance Monitoring System (SLEAMS) and Teacher Records Management (TRM) system - Graham, Hannah (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:CZCVZEPG 2339240:KB3DUZXF 2405685:5NEC3AR4
Keywords: _C:Sierra Leone SLE

Sierra Leone TCPD Sandbox Report (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7217149 ZenodoArchiveConcept: 7217148 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7217149 2129771:3KQCZEP4 2405685:9NR4RZ98
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
ZenodoArchiveID: 5652005 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652005 2129771:DGE5S596 2405685:RT5H8XNG
Keywords: _C:Sierra Leone SLE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707926 2129771:R5KV473Q 2405685:FB4FWFP9
Keywords: _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _zenodoETH

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
ZenodoArchiveID: 5652007 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652007 2129771:TF3VJYTG 2405685:KZ6FTNMC
Keywords: _C:Sierra Leone SLE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707910 2129771:R8LRYX3A 2405685:7HCBSU4P
Keywords: _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector. In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4584801 2129771:AUZKK7ID 2339240:F47KL5P7 2339240:VJ2SHXTR 2405685:DJHAECID 2405685:JV4FPSJW
Keywords: Author:OpenDevEd; _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Sierra Leone research and knowledge systems: a rapid literature review - Tarawallie, Mamoud Idriss (INASP, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:YBNPSUAZ 2339240:83QNDI62 2405685:8PAQ6CIE
Keywords: _C:Sierra Leone SLE

Sierra Leone : Poverty Reduction Strategy Paper-Progress Report (2005-2007) - International Monetary Fund (2008)
This report describes the progress made in implementing the Poverty Reduction Strategy Paper for Sierra Leone covering the period 2005–07. Efforts to reform the public sector were not successful. Management and Functional Reviews were conducted for several ministries, departments, and agencies but the recommendations were not implemented. A Senior Executive Service program was also developed but government and development partners could not agree on an implementation strategy and therefore the funds required for implementation were not provided.
KerkoCite.ItemAlsoKnownAs: 2129771:AQK3JHM4 2405685:WDN7YDZH
Keywords: _C:Sierra Leone SLE

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
KerkoCite.ItemAlsoKnownAs: 10.5258/SOTON/WP00645 2129771:7A8E4V54 2339240:2AJ3LMLD 2405685:92787LQS
Keywords: Population distribution; Population; Dasymetric disaggregation; _C:Sierra Leone SLE

Sierra Leone National Innovation and Digital Strategy (2019-2029): Digitization for all: Identity, Economy, and Governance - Directorate of Science, Technology & Innovation (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:QDFIFWI3 2339240:ZAK6UTWJ 2405685:65CSGZUZ
Keywords: _C:Sierra Leone SLE

Sierra Leone National Innovation and Digital Strategy - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:4PWLI67K 2405685:ALD9DQ6P
Keywords: _C:Sierra Leone SLE

Sierra Leone Multiple Indicator Cluster Survey 2017, survey findings report - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:P8593M2K 2339240:SMX372XG 2405685:EP6QPCSW
Keywords: _C:Sierra Leone SLE

Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:2TC7LDGS 2339240:7794TCGJ 2405685:N9SALPUS
Keywords: _C:Sierra Leone SLE

Sierra Leone - Multiple Indicator Cluster Survey 2017 - World Bank (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:C6I7P6ZI 2339240:693W742X 2405685:4ULW3LMX
Keywords: _C:Sierra Leone SLE

Sierra Leone Multiple Indicator Cluster Survey - UNICEF (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:2P9NEZ9I 2405685:6T7FE548
Keywords: _C:Sierra Leone SLE

Sierra Leone Medium Term National Development Plan (Volume 1) - Ministry of Planning and Economic Development (Sierra Leone) (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:J94ULW4C 2405685:CZE9NFVC
Keywords: _C:Sierra Leone SLE

Sierra Leone Media Landscape Report - BBC Media Action (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:KM54UTV8 2339240:7N6UW9TG 2405685:644SZI8D
Keywords: _C:Sierra Leone SLE

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - DSTI Media (Directorate of Science, Technology and Innovation, 2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
KerkoCite.ItemAlsoKnownAs: 2129771:A2M8VZC9 2405685:B6TMDRUY
Keywords: _C:Sierra Leone SLE

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - Sierra Leone Education Innovation Challenge (2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:UPP2U9U3 2405685:XUALMEQ5
Keywords: _C:Sierra Leone SLE

Sierra Leone: education country status report; an analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone; 2013 (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:FV47UIZ5 2405685:JAEVJQUR
Keywords: _C:Sierra Leone SLE

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)
KerkoCite.ItemAlsoKnownAs: 2129771:BQXDV8SC 2405685:FWX5GT4H
Keywords: _C:Sierra Leone SLE

Sierra Leone Education Attendance Monitoring System (SLEAMS) Pilot Phase: Inception Report - Kawa, Muniru; Graham, Hannah; Lee, Philip; Murray, Tobias; Malyon, Stephanie (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:YER5RF7X 2339240:EPHMUJLL 2405685:F8XG7GDF
Keywords: _C:Sierra Leone SLE

Sierra Leone Education Attendance Monitoring System (SLEAMS) Final Technical Report - Graham, Hannah; Kawa, Muniru; Lee, Philip; Malyon, Stephanie; Hayward, Harry; Conteh, Sheriff; Chandia, Gloria (Charlie Goldsmiths Associates, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:ZPDPUFYQ 2339240:M68LGCE7 2405685:FTT9TD2Y
Keywords: _C:Sierra Leone SLE

Sierra Leone Education Attendance Monitoring System - Teaching Service Commission (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:XSW486H9 2339240:CLIEEVEU 2405685:XV88ZYD7
Keywords: _C:Sierra Leone SLE

Sierra Leone | Education and Literacy Statistics - UNESCO (2020)
...
Last Modified: 2017-04-12 Library Catalog: uis.unesco.org KerkoCite.ItemAlsoKnownAs: 2129771:FQZ2XEPH 2405685:Y6JYY6Q6
Keywords: _C:Sierra Leone SLE

Sierra Leone: Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund (IMF, African Department, 2019)
ISBN: 9781498324960 ISSN: 1934-7685 Issue: 218 Publisher: INTERNATIONAL MONETARY FUND Volume: 2019 KerkoCite.ItemAlsoKnownAs: 10.5089/9781498324960.002.A001 2129771:2MR58KI3 2339240:6RP4BCNR 2405685:LICLRGV3
Keywords: _C:Sierra Leone SLE

Sierra Leone : Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund. African Dept. (2019)
The Government of Sierra Leone’s new Medium-term National Development Plan (MTNDP) 2019–2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone’s citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government’s flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.
9781498324960/1934-7685 KerkoCite.ItemAlsoKnownAs: 2129771:7SQ8YQ8J 2405685:DJ4XD4HB
Keywords: _C:Sierra Leone SLE

Sierra Leone designs online portal to take long wait out of teacher recruitment - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
A new teacher recruitment portal developed at the Directorate of Science, Technology, and Innovation (DSTI) will make it easier and faster for education administrators to hire teachers, and allocate teachersRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:CJS795T9 2405685:UWP4N7FT
Keywords: _C:Sierra Leone SLE

Sierra Leone Demographic and Health Survey 2019 - Statistics Sierra Leone (The DHS Program, 2020)
ICF
KerkoCite.ItemAlsoKnownAs: 2129771:H94TRS8B 2339240:J5MWI9UW 2405685:MEUW6R9C 2405685:MZXSNEV5
Keywords: _C:Sierra Leone SLE

Sierra Leone Demographic and Health Survey 2008 - Statistics Sierra Leone (Ministry of Health and Sanitation, 2009)
KerkoCite.ItemAlsoKnownAs: 2129771:VN9SZBLW 2405685:XJLGGACD
Keywords: _C:Sierra Leone SLE

Sierra Leone CPD Sandbox - Draft Theory of Change - Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4959786 2129771:47RUCMAS 2405685:T7AUREA5
Keywords: _C:Sierra Leone SLE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (World Bank; OECD; Harvard Global Education Innovation Initiative; HundrED, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:SG89XZMW 2339240:BRFU9F86 2405685:93KUAPNF 2405685:9APBFG2P 2405685:CXIWGJLQ 2405685:STZ89LHX 2534378:UQINHJH2
Keywords: _C:Sierra Leone SLE

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:AP88Z6FH 2339240:XVKVLR6R 2405685:QV99MR4Q
Keywords: _C:Sierra Leone SLE

Sierra Leone 2015 population and housing census: Thematic report on poverty and durables - Statistics Sierra Leone (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:VBCDYP57 2339240:YKBEPH82 2405685:MPV2GIIW
Keywords: _C:Sierra Leone SLE

Sierra Leone 2015 Population and Housing Census: Thematic Report on Disability - Kabia, Francis; Tarawally, Umaru (Statistics Sierra Leone, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:BELVCZKC 2405685:BI8HMKXI
Keywords: _C:Sierra Leone SLE

Shifting from government bursaries to a loan scheme in higher education: Exploring the Zambian experience in student financial Aid - Masaiti, Gift; Mwelwa, Kapambwe; Mwale, Nelly (International Journal of African Higher Education, 2015)
Keywords: ⛔ No DOI found

Senior Secondary School, Scope and Sequence , Maths - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745386 2129771:XY9BECIT
Keywords: SSEIP; _C:Sierra Leone SLE

Senior Secondary School, Scope and Sequence , English (Revised) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745384 2129771:EJUWX6JV
Keywords: SSEIP; _C:Sierra Leone SLE

Senior Secondary I, II, III, IV Mathematics (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745392 2129771:NX7CKDU3
Keywords: SSEIP; _C:Sierra Leone SLE

Senior Secondary I, II, III, IV Literature in English (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745388 2129771:795GGLGX
Keywords: SSEIP; _C:Sierra Leone SLE

Senior Secondary I, II, III, IV English (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745390 2129771:VCMP3KNW
Keywords: SSEIP; _C:Sierra Leone SLE

Seeing, thinking and acting against malaria - A new aprroach to health worker training in rural Gambia - Dawson, Angela; Joof, Balla Musa (Education for Health: Change in Learning and Practice, 2005)
Context: In the Gambia, West Africa, Malaria is a major cause of death among children in rural areas. It has been estimated that in one division in the country malaria accounts for 40% of all deaths in children aged between one and 4 years. Most malaria cases are managed at home assisted by primary healthcare workers. The strategic plan of Gambia's National Malaria Control Programme includes improved training and supervision of all health care providers, at all levels, and increased community awareness in order to reduce the malaria burden by 50% before 2007. Issue: A malaria in-service training program for Community Health Nurses (CHNs) working at village level was piloted in 2004. The program includes a computer-based training (CBT) package, the first of its kind for health professionals in Gambia. The education program is part of a larger initiative, funded by the Gates Malaria Partnership, that aims to increase community involvement in malaria control. The objective of the course is to enable CHNs to facilitate the change process. The curriculum was informed by a reference group and stakeholder input. Interviews and evaluation forms were used to gather information about learner experience and learning preferences. Analysis: The CBT package was well received. Learners reported wanting more computer instruction, but felt they had gained confidence. There was resistance from other health professionals regarding the development of information technology skills in CHNs. This related to the perceived role and status of CHNs, as well as confidence in their ability. Some modifications of the CBT package were necessary, including the reworking of some activities and language. Lessons learned: There are issues related to sustainability and resource implications that need to be addressed. Opportunities exist to expand e-learning in the Gambia for preservice CHNs and other professionals. An investigation into the viability of reproducing this module as a generic planning tool for allied health workers and other extension workers at community level will be undertaken. © 2005 Taylor & Francis.
KerkoCite.ItemAlsoKnownAs: 10.1080/13576280500307264 10/bfh3zx 2129771:KLEWJXLA 2317526:E2YJ43S8
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Gambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing context; F:curriculum; F:learning; P:health; P:health professionals; P:nurse; Q:ICT; Q:e-learning; R:evaluation; R:interview; T:Ausbildung; T:Training; T:work-based learning; Z:Community health nurses; Z:Computer based training developing contexts; Z:Health worker education and training; Z:computer based training developing contexts; Z:health worker education and training; publicImportV1

Secondary education expansion in Tanzania: Policy and practice implications for teachers’ sense of efficacy - Lawrent, Godlove (The University of Waikato, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:H62WXHNT
Keywords: _C:Australia AUS; _C:Austria AUT; _C:Belgium BEL; _C:Belize BLZ; _C:Benin BEN; _C:Burundi BDI; _C:Canada CAN; _C:China CHN; _C:Congo XCO; _C:Czech Republic CZE; _C:Dominican Republic DOM; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Lebanon LBN; _C:Lesotho LSO; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nepal NPL; _C:Netherlands NLD; _C:New Zealand NZL; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Oman OMN; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Portugal PRT; _C:Rwanda RWA; _C:Senegal SEN; _C:Singapore SGP; _C:Slovakia SVK; _C:Slovenia SVN; _C:South Africa ZAF; _C:Spain ESP; _C:Sudan SDN; _C:Sweden SWE; _C:Switzerland CHE; _C:Tanzania TZA; _C:Trinidad and Tobago TTO; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Second handbook of information technology in primary and secondary education - Voogt, Joke (Springer Berlin Heidelberg, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:KI9MCHVT
Keywords: _C:Afghanistan AFG; _C:Albania ALB; _C:Algeria DZA; _C:Andorra AND; _C:Angola AGO; _C:Argentina ARG; _C:Australia AUS; _C:Austria AUT; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Belarus BLR; _C:Belgium BEL; _C:Benin BEN; _C:Bhutan BTN; _C:Bolivia BOL; _C:Bosnia and Herzegovina BIH; _C:Botswana BWA; _C:Brazil BRA; _C:Brunei Darussalam BRN; _C:Bulgaria BGR; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Costa Rica CRI; _C:Croatia HRV; _C:Cuba CUB; _C:Cyprus CYP; _C:Czech Republic CZE; _C:Denmark DNK; _C:Djibouti DJI; _C:Dominica DMA; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Equatorial Guinea GNQ; _C:Eritrea ERI; _C:Estonia EST; _C:Ethiopia ETH; _C:Fiji FJI; _C:Finland FIN; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Guatemala GTM; _C:Guinea GIN; _C:Holy See VAT; _C:Honduras HND; _C:Hungary HUN; _C:Iceland ISL; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Jamaica JAM; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Kiribati KIR; _C:Korea XKOR; _C:Korea; Democratic People's Republic PRK; _C:Korea; Republic KOR; _C:Kosovo XKSVO; _C:Kuwait KWT; _C:Laos LAO; _C:Latvia LVA; _C:Lebanon LBN; _C:Lesotho LSO; _C:Liberia LBR; _C:Libya LBY; _C:Lithuania LTU; _C:Luxembourg LUX; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Maldives MDV; _C:Mali MLI; _C:Malta MLT; _C:Mauritania MRT; _C:Mauritius MUS; _C:Mexico MEX

Scope and Sequence Maths Class 09 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745242 2129771:4568QN8T
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 08 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745240 2129771:ZABB2M4A
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 07 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745238 2129771:FXLVJGG3
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 06 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745147 2129771:AXWFTR3A
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 05 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745145 2129771:MYFEENMD
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 04 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745143 2129771:RTJGJTNK
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 03 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745141 2129771:H96CHCTP
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 02 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745139 2129771:LUNZZXIZ
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence Maths Class 01 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745137 2129771:PDMDY6DQ
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 09 UNAPPROVED - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745236 2129771:2ZLMCEMV
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 09 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745234 2129771:3DXSVQ9Q
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 08 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745232 2129771:ZDFYEXZ3
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 07 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745230 2129771:4IDNNLDR
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 06 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745135 2129771:M4F7UWVY
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 05 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745133 2129771:XDWVBFBQ
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 04 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745131 2129771:JCHZKX47
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 03 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745129 2129771:V5HEISJ4
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 02 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745127 2129771:MJUDZSN9
Keywords: SSEIP; _C:Sierra Leone SLE

Scope and Sequence English Class 01 - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745125 2129771:RIUVVQ3C
Keywords: SSEIP; _C:Sierra Leone SLE

Scientists at DSTI go the extra mile to make it easier for children to get to school - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
Mike Fabrikant, a software developer from Washington D.C., is embedded within the data science team at the Directorate of Science, Technology, and Innovation (DSTI) to support systems delivery. His workRead More
Library Catalog: www.dsti.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:AHVZTQF6 2405685:9K5VWY7C

Schools ICT project - Universal Access Development Fund (Sierra Leone) (2020)
Library Catalog: uadf.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:PMQHZDC7 2405685:UXGCRKTI

School-to-school mobility patterns and retention rates of payroll teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7421516 ZenodoArchiveConcept: 7421515 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7421516 10.53832/edtechhub.0143 2129771:4HUI65EI 2405685:DE7XUSMJ
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

School Program of In-service Training for the Term (SPRINT) Programme in Zambia -A Case of Collaboration Towards Self-Reliant Education Development - Mubanga, Ruth (Collaboration toward Greater Autonomy in Educational Development, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:BN7RXG6G 261495:Q5AN7HX8

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6958056 10.53832/edtechhub.0106 2129771:BNM5JIWY 2405685:MFH269TU
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (The World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2129771:MLQ2ECBX 2339240:TQTHH2MX 2405685:55GPK4S9
Keywords: _C:Sierra Leone SLE

School Facet Through Surrounding Factors: A Geospatial Analysis of Community Social Capital Impacting Elementary Schools - Budhwani, Sajjid (University of Denver, 2020)
School performance rating is an important factor which not only provides a quick snapshot of how the students are performing on various measurement indicators but also decides a school’s future course of actions, strategies, resources, and its existence. Despite its significant importance, the school performance framework does not consider where the schools are geographically located and the surrounding factors within which they operate. The researcher of this study presented a landscape of the surrounding factors and its impact on the elementary schools within Denver Public Schools district. In this study, the surrounding factors are geospatially analyzed to determine the extent of spatial variation in the availability and accessibility of community social capital resources to the elementary schools. Using geospatial research methods, the researcher created three service area models for each elementary school to access community social capital resources that are available within its surrounding environment. Spatial concepts, tools, and inferential statistics were used to analyze spatial pattern and the relationship between the forms of community social capital resources and the elementary schools. As a result of this relationship analysis, a new term was conceptualized: School Facet through Surrounding Factors [SF]2.
ISBN: 9798678177995
Keywords: Community resources; Community social captial; Education and GIS; School surrounding; Social capital; Spatial equity; _C:Canada CAN; _C:China CHN; _C:Finland FIN; _C:France FRA; _C:India IND; _C:Israel ISR; _C:Jordan JOR; _C:Mexico MEX; _C:Netherlands NLD; _C:Philippines PHL; _C:Sweden SWE; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

School-Based Teacher Professional Development in East Africa: Emerging Lessons from Kenya and Tanzania - Hardman, Jan (International Handbook of Teacher Quality and Policy, 2017)
This chapter discusses the main challenges facing both governments and the international donor community in the East African region as they implement effective teacher professional development. It reviews the emerging evidence suggesting educational quality is largely obtained by engaging teachers in reviewing their pedagogical processes at the school and classroom levels. It concludes with a discussion of the key priorities for policymakers in Kenya, Tanzania and East Africa more generally as they work towards improving pedagogical practices of both teachers and teacher educators and raising learning outcomes for all children as part of the new post-2015 education agenda.
KerkoCite.ItemAlsoKnownAs: 10.4324/9781315710068-34 2129771:7SKAMBEG 2129771:N74HV2IR
Keywords: _C:Canada CAN; _C:Cuba CUB; _C:Finland FIN; _C:Japan JPN; _C:Kenya KEN; _C:Korea; Republic KOR; _C:Malawi MWI; _C:Senegal SEN; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

School-based professional development in a developing context: Lessons learnt from a case study in Zambia - Haßler, Björn; Hennessy, S.; Cross,, A. (Professional Development in Education, 2014)
This paper reports on the development and outcomes of the second phase of OER4Schools, a school-based professional development programme supporting interactive forms of subject teaching in conjunction with Open Educational Resources (OER) and technology in Zambian primary schools. We worked with partners to identify the needs of school-based continuing professional development adapted to the local context; the programme was based on participatory, collaborative and inquiry-based pedagogies for both classroom learning and teacher development. We worked over a one-year period with four experienced teachers in two basic (primary) schools serving disadvantaged communities. Data were collected from observations, interviews, surveys, lesson planning/review meetings and team workshops. All participants integrated OER and technology into mathematics and science lessons and developed more interactive practices, including collaborative learning. Professional dialogue, quality conversations, reflective practice, cultural sensitivity, peer learning and cooperation were pivotal mechanisms through which teachers shifted their focus from teaching (and teacher exposition) to student learning. Seeing students as capable individuals, teachers raised their expectations and developed insight into interactive practices such as group work, providing meaningful opportunities for student collaboration and active learning by all.
00015 EdTechHub.Copy: 2405685:RUTXQFGV KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2014.938355 10/gfv5xw 2129771:7RVZCL3K 2129771:GA2J43XP 2129771:NAPYJ8MD 2129771:TU868QEN 2129771:Y2CH4MCW 2405685:RUTXQFGV 257089:F5UDH5X5 261495:VMEXDVG4
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Iran IRN; _C:Italy ITA; _C:Malawi MWI; _C:Namibia NAM; _C:Nigeria NGA; _C:South Africa ZAF; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:a

School: a second home for the children - Warwocki, Pawel (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257503 ZenodoArchiveConcept: 10257502 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1037 2129771:NW5NJAGB
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Revitalizing Technical and Vocational Education in Nigeria for Youths and National Development - Ogbondah, Livinus; Wobi, KK (Journal of Education and Practice, 2014)
Nigeria as a developing nation cannot but strive to meet with the fast speed of technological advancement and the challenges in a globalize world nowadays. If she must address the numerous technological and job challenges, the issue of technology, skills and vocation acquisition must be tackled with all sincerity in the country’s education system. Highly industrialized nations have at one time or the other identified technical and vocational education as a transformational and development key index policy trust for technological growth, economic performance and development in general. Technical and vocational education lays emphasis on learning, skills acquisition; job creation and development that would enable individual engaged in it adjust to the changes in the ever dynamic society of today. This paper therefore, tends to examine this aspect of education in the country’s education system and the need to revitalize it to promote the technological growth in particular and development in general. It suggests among others; adequate funding, improvement of the status of technical and vocational education and training of needed manpower to impart the requisite skills and competencies the youths required in the technology world of today.
KerkoCite.ItemAlsoKnownAs: 2129771:Y2CX5IBY 2317526:XXZHYLIM UTI-8AB811C3-40A0-3034-BA8C-72A1082F4B5A
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Central Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; Q:educational technology; T:Educação profissionalizante; T:TVET; publicImportV1; ⛔ No DOI found

Revitalizing Education Development in Sierra Leone (REDISL) Project - World Bank (2014)
KerkoCite.ItemAlsoKnownAs: 2129771:GFXZQ5YD 2405685:8ISYUKP9
Keywords: _C:Sierra Leone SLE

Revised National Youth Policy - Government of Botswana (2010)
UA-10998dbb-5050-4624-951a-223039ab87a1 KerkoCite.ItemAlsoKnownAs: 2129771:HEMKTILZ 2317526:BKRPWCAB
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; publicImportV1

Review of national education policies: Teacher quality and learning outcomes - Hunt, Frances (PROSPECTS, 2015)
This article provides an overview of how teacher quality and learning outcomes are included in national education policies. It responds to a set of speciﬁc questions focused on strategies to improve learning, links between teacher quality and learning outcomes, and how policy seeks to overcome learning obstacles for the most disadvantaged. The article uses data collated from the national education plans of forty developing countries. It includes a summary of key lessons and observations related to the inclusion of teaching and learning in education policy and a range of strategies that can support teaching and learning, both directly and indirectly.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-015-9356-z 2129771:VCQK6BQP
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Belize BLZ; _C:Bhutan BTN; _C:Cambodia KHM; _C:Colombia COL; _C:Ecuador ECU; _C:Egypt EGY; _C:Ethiopia ETH; _C:Gambia GMB; _C:Ghana GHA; _C:Guinea GIN; _C:Guinea-Bissau GNB; _C:Guyana GUY; _C:India IND; _C:Indonesia IDN; _C:Jamaica JAM; _C:Kenya KEN; _C:Laos LAO; _C:Lebanon LBN; _C:Lesotho LSO; _C:Liberia LBR; _C:Malawi MWI; _C:Mauritius MUS; _C:Mozambique MOZ; _C:Namibia NAM; _C:Nepal NPL; _C:Nigeria NGA; _C:Papua New Guinea PNG; _C:Paraguay PRY; _C:Peru PER; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:State of Palestine PSE; _C:Sudan SDN; _C:Tanzania TZA; _C:Uganda UGA; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

Review of agricultural technical vocational education and training (ATVET) in Africa : best practices from Benin, Ethiopia, Namibia and Sierra Leone - NEPAD (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:MRLFQA2A 2317526:UXBUFKAU
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Benin; C:Ethiopia; C:Namibia; C:Sierra Leone; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:agricultural; T:TVET; _C:Sierra Leone SLE; publicImportV1

Rethinking the role of teacher education in Zambia: quality curriculum designing as a missing link in explaining teacher's pedagogical content knowledge. - Mulenga, Innocent Mutale (2016)
Publisher: THE AFRICAN FEDERATION OF TEACHING REGULATORY AUTHORITIES (AFTRA …
Keywords: ⛔ No DOI found

Rethinking quality assurance in curriculum development and implementation for higher education in Africa. - Mulenga, Innocent Mutale (2020)

Rethinking mobile learning for development: Using the Capability Approach and a mixed-methods systematic review to conceptualise the application of mobile technologies as an educational tool in Low-and Middle-Income Countries - Langer, Laurenz (UCL (University College London), 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:BG4ZYAUR 2129771:CJXZIALC 2129771:RS4CDYDC 2129771:SATN7D48 2129771:XTA3NAN5
Keywords: _C:Afghanistan AFG; _C:Albania ALB; _C:Algeria DZA; _C:Angola AGO; _C:Antigua and Barbuda ATG; _C:Argentina ARG; _C:Armenia ARM; _C:Australia AUS; _C:Azerbaijan AZE; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Barbados BRB; _C:Belarus BLR; _C:Belize BLZ; _C:Benin BEN; _C:Bhutan BTN; _C:Bolivia BOL; _C:Bosnia and Herzegovina BIH; _C:Botswana BWA; _C:Brazil BRA; _C:Bulgaria BGR; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Central African Republic CAF; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Costa Rica CRI; _C:Croatia HRV; _C:Cuba CUB; _C:Cyprus CYP; _C:Czech Republic CZE; _C:Djibouti DJI; _C:Dominica DMA; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Eritrea ERI; _C:Estonia EST; _C:Ethiopia ETH; _C:Federated States of Micronesia FSM; _C:Fiji FJI; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Grenada GRD; _C:Guatemala GTM; _C:Guinea GIN; _C:Guyana GUY; _C:Haiti HTI; _C:Honduras HND; _C:Hungary HUN; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Italy ITA; _C:Ivory Coast CIV; _C:Jamaica JAM; _C:Japan JPN; _C:Jordan JOR; _C:Kazakhstan KAZ; _C:Kenya KEN; _C:Kiribati KIR; _C:Korea XKOR; _C:Kosovo XKSVO; _C:Kyrgyzstan KGZ; _C:Laos LAO; _C:Latvia LVA; _C:Lebanon LBN; _C:Lesotho LSO; _C:Liberia LBR; _C:Libya LBY; _C:Lithuania LTU; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Maldives MDV; _C:Mali MLI; _C:Malta MLT; _C:Marshall Islands MHL; _C:Mauritania MRT; _C:Mauritius MUS; _C:Mexico MEX; _C:Mongolia MNG; _C:Montenegro MNE

Restructuring vocational and technical education in Ghana: The role of leadership development - Boateng, C (International Journal of Humanities and Social Science, 2012)
Vocational technical education and training in Ghana is currently undergoing restructuring. Many reforms are in place to improve the quality of provision and learning outcomes to make it more accessible and attractive to all, and to ensure it is relevant and connected to the world of work. The potential success of these reforms will depend largely on the administrators and managers who are responsible for generating ideas and formulating policies ,as well as those responsible for transforming policies into practice. In this regard, effective leadership becomes an important variable that must be considered in the new vocational education environment. There is the need for Ghana to pay attention to providing leadership programs and guidance to current leaders and new and aspiring administrators and managers of vocational technical education. Such leadership development programs should attempt to cultivate in individuals key attributes and characteristics that can predispose successful leadership performance. The availability of leadership development programs and the possibility of being able to acquire certain leadership behaviours and enhance and use certain leadership attributes holds great promise for those participating in and leading vocational educational programs, reform efforts, and the change process in the country.
KerkoCite.ItemAlsoKnownAs: 2129771:M5PF2WFZ 2317526:5ZL9IKEU
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:leadership; F:policy; T:TVET; _C:Ghana GHA; __C:filed:1; publicImportV1; ⛔ No DOI found

Research on open educational resources for development in the Global South: Project landscape - Arinto, Patricia; Hodgkinson-Williams, Cheryl; King, Thomas; Cartmill, Tess; Willmers, Michelle (African Minds, International Development Research Centre & Research on Open …, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:MF6CC6DN
Keywords: _C:Afghanistan AFG; _C:Argentina ARG; _C:Australia AUS; _C:Austria AUT; _C:Bangladesh BGD; _C:Belgium BEL; _C:Bolivia BOL; _C:Brazil BRA; _C:Cambodia KHM; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Costa Rica CRI; _C:Cuba CUB; _C:Ecuador ECU; _C:El Salvador SLV; _C:Estonia EST; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Ireland IRL; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Laos LAO; _C:Malawi MWI; _C:Malaysia MYS; _C:Mauritius MUS; _C:Mexico MEX; _C:Mongolia MNG; _C:Morocco MAR; _C:Mozambique MOZ; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:North Cyprus XNCYP; _C:Oman OMN; _C:Pakistan PAK; _C:Paraguay PRY; _C:Peru PER; _C:Philippines PHL; _C:Poland POL; _C:Portugal PRT; _C:Russian Federation RUS; _C:Slovenia SVN; _C:Somalia SOM; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Sweden SWE; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Tunisia TUN; _C:Turkey TUR; _C:Uganda UGA; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Venezuela VEN; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:95P2UK7M 2339240:ANFH2ALH 2405685:QAFBTUE9
Keywords: _C:Sierra Leone SLE

Republic of Sierra Leone: Education sector analysis: assessing the enabling environment for gender equality - UNICEF (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:TQXPLCCH 2339240:A6RXK3ZC 2405685:UG524M3N
Keywords: _C:Sierra Leone SLE

Report of the Southern Africa Regional Workshop on Work-based Learning - UNESCO (UNESCO, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:ZPAQFU4K 2317526:3NBNID95 UA-F2995AA5-6107-4844-947D-1B83B3717878
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; CC:Botswana; CC:Lesotho; CC:Malawi; CC:Mozambique; CC:Namibia; CC:South Africa; CC:Zambia; CC:Zimbabwe; CC:eSwatini (Swaziland); CLL:en; publicImportV1

Relationship of Job Satisfaction and Turnover Intention of Private Secondary School Teachers - Shah, Nazir Haider; Jumani, Nabi Bux (Mediterranean Journal of Social Sciences, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:2IQWSF4E 2129771:XV4URHIR
Keywords: Lebanon_event_2021; _C:Australia AUS; _C:Cameroon CMR; _C:Canada CAN; _C:China CHN; _C:Cyprus CYP; _C:Greece GRC; _C:India IND; _C:Italy ITA; _C:Korea XKOR; _C:Malaysia MYS; _C:New Zealand NZL; _C:Nigeria NGA; _C:Pakistan PAK; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Rehabilitation in Seven Sub-Saharan African Countries: Personnel Education and Training - Mpofu, Elias; Jelsma, Jennifer; Maart, Soraya; Levers, Lisa Lopez; Montsi, Mercy M R; Tlabiwe, Pinkie; Mupawose, Anniah; Mwamwenda, Tuntufye; Ngoma, Mary Shilalukey; Tchombe, Therese Mungah S (Rehabilitation Education, 2007)
KerkoCite.ItemAlsoKnownAs: 10.1891/088970107805059562 10/gf623d 2129771:XNNGBTDH 2317526:DRQNSP23 LOCAL-PQ-224986316
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Botswana; C:Cameroon; C:Rwanda; C:South Africa; C:Tanzania; C:Zambia; C:Zimbabwe; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:curriculum; F:disability; P:culture; P:health; P:services; P:technician; T:TVET; T:Training; publicImportV1

Regulation on the Assessment Process and Procedures for Adult Education and Training (AET) - NQF Level 1 - Government of South Africa (2013)
UA-7a419a3c-dc3e-4636-855a-a3892e5a20b8 KerkoCite.ItemAlsoKnownAs: 2129771:IFI3Y6WR 2317526:9H4IERYD
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; Qualification Framework; publicImportV1

Reforming teacher education in Tanzania - Hardman, F; Abd-Kadir, J; Tibuhinda, A (International Journal of Educational Development, 2012)
It is widely acknowledged that in order to improve the quality of education in primary schools in developing countries there is a need to place pedagogy and its training implications at the centre of teacher education reform. Like many countries in Eastern and Southern Africa, Tanzania has introduced various initiatives and reforms to improve the quality of teacher education at the pre- and in-service stages. Drawing on evidence from a baseline study of primary teacher interactional and discourse practices, and a review of teacher training colleges, this paper explores the training needs of teacher educators in Tanzania who, in the light of recent reforms to teacher education, will be responsible for education and training at the pre and in-service levels.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2012.01.002 10/f37fn5 2129771:GK5LZYEH 2317526:AD2UXXH5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:T; D:developing country; F:pedagogy; F:teaching method; P:services; P:teacher education; P:teacher training; P:teachers; Q:college education; Q:primary education; T:Training; T:training needs; Z:African languages; Z:College education; Z:English language; Z:Mathematics education; Z:Primary education; Z:Teacher education; Z:Teaching methods; publicImportV1

Reflecting on Five Decades of Teacher Professional Development in Tanzania: The Missing Dimensions - Dachi, Hillary (Papers in Education and Development, 2016)
The importance of teacher development need not be over stated. This is adducible by the fact that transformations, innovations and diffusions in education make it imperative that teachers have to continually change and adopt. This paper takes stock of the trajectory of teacher professional development in Tanzania by locating related initiatives in the macro-policies and education transformations spanning a period of nearly five decades. It identifies the missing dimensions for robust in-service continuous professional development programmes (CPD) for primary and secondary school teachers. The paper proposes the need to support a cost effective in-service CPD model, which is school based designed around a reflective practitioner approach, for which teaching is an interactive problem solving professional undertaking requiring continuous updating of key competences that teachers require for classroom practices. Key words: teachers’ professionalism; teachers’ continuous professional development; macro-policies; education transformations
KerkoCite.ItemAlsoKnownAs: 2129771:3DAXHV2W 2129771:FA2SH9AA
Keywords: _C:Canada CAN; _C:Finland FIN; _C:Germany DEU; _C:Ghana GHA; _C:Kenya KEN; _C:Korea; Republic KOR; _C:Malaysia MYS; _C:Namibia NAM; _C:Sweden SWE; _C:Tanzania TZA; _C:Uganda UGA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Reflecting on epistemic injustices in open and online education - Adam, Taskeen (Open Development & Education, 2020)
In memory of Hector Pieterson and the hundreds of student protesters that were brutally murdered by police on the 16 June 1976 in the Soweto Uprising in South Africa. The Soweto Uprising refers to the protests by black South African high school students during apartheid against the use of Afrikaans as a medium of instruction. […]
Library Catalog: opendeved.net KerkoCite.ItemAlsoKnownAs: 2129771:E4ZPDX8Z
Keywords: Author:OpenDevEd

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone
shortDOI: 10/ggqvr7 KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 10/ggqvr7 2129771:NVZ6YY8M 2339240:6IXLT92N 2405685:6Z36JH5J 2405685:S35X3HD9
Keywords: _C:Sierra Leone SLE

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 2129771:TJLHF968
Keywords: _C:Sierra Leone SLE

Recruiting, Retaining, and Retraining Secondary School Teachers and Principals in Sub-Saharan Africa - Mulkeen, Aidan; Chapman, David; DeJaeghere, Joan; Leu, Elizabeth (The World Bank, 2007)
KerkoCite.ItemAlsoKnownAs: 10.1596/978-0-8213-7066-7 2129771:5HWPXNVN
Keywords: _C:Angola AGO; _C:Benin BEN; _C:Botswana BWA; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Central African Republic CAF; _C:Chad TCD; _C:China CHN; _C:Comoros COM; _C:Congo XCO; _C:Djibouti DJI; _C:Dominican Republic DOM; _C:Equatorial Guinea GNQ; _C:Eritrea ERI; _C:Ethiopia ETH; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Ghana GHA; _C:Guinea GIN; _C:Guinea-Bissau GNB; _C:India IND; _C:Ireland IRL; _C:Kenya KEN; _C:Lebanon LBN; _C:Lesotho LSO; _C:Liberia LBR; _C:Madagascar MDG; _C:Malawi MWI; _C:Mali MLI; _C:Mauritania MRT; _C:Mauritius MUS; _C:Mozambique MOZ; _C:Namibia NAM; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Rwanda RWA; _C:Senegal SEN; _C:Seychelles SYC; _C:Sierra Leone SLE; _C:Somalia SOM; _C:South Africa ZAF; _C:Sudan SDN; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Togo TGO; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

RECOVR Sierra Leone: Tracking the Effects of the COVID-19 Pandemic - Warren, Shana; Parkerson, Doug; Collins, Elliott (Innovations for Poverty Action, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:AICBGTTB 2405685:BU58QF73
Keywords: _C:Sierra Leone SLE

Recovering from school closures in Sierra Leone: Status of pupil learning outcomes in junior and senior secondary schools - Leh Wi Lan (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:JJCI62EG 2339240:TVYLJS4I 2405685:IUJU327A
Keywords: _C:Sierra Leone SLE

Reconstructing education in post-conflict Sierra Leone - Pai, Grace (Security, Education and Development in Contemporary Africa, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:WJPJDQJK 2405685:83TRVQZR
Keywords: _C:Sierra Leone SLE

Reconhecimento do trabalho de cuidado: o caso do Programa Expandido de Trabalhos Públicos na África do Sul - Bilo, Charlotte; others (International Policy Centre for Inclusive Growth, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:HJZ3AZIP 2317526:JDH9DFC9
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:South Africa; CLL:pt; publicImportV1

Recognition of Prior Learning Implementation in Library and Information Science Schools in South Africa: A Literature Review - Hlongwane, I (Africa Education Review, 2018)
This article reviews the literature on trends and practices of recognition of prior learning (RPL) in Africa and internationally with specific reference to some of the key elements of the RPL system, including; purpose; assessment methods; quality assurance; and legislative and regulatory frameworks. In addition, a theoretical foundation of RPL is discussed underpinned by the experiential learning theory principles with a brief description of other learning theories related to RPL. The article also discusses the trends and practices of RPL in African countries with an established RPL system. The key finding of the literature review was that there are different conceptions of RPL globally but which all have a similar purpose, that is, economic benefit. Africa has a different take on RPL. A portfolio of evidence is the most commonly used method of assessment both internationally and in Africa with an increased use of e-portfolios internationally. A variety of quality assurance methods are used which differ from country to country but are similar to the Council for Adult and Experiential Learning (CAEL) quality standards which have been in use for many decades in the United States (US) since the inception of RPL. There are discrepancies in terms of legislative and regulatory frameworks. Some countries in Africa and internationally have no formal legislative and regulatory frameworks for RPL despite providing RPL services for years or decades. South Africa and Mauritius boast standardised and regulated RPL systems as do other developed countries such as New Zealand.
KerkoCite.ItemAlsoKnownAs: 10.1080/18146627.2017.1353396 10/gf622j 2129771:MQLD49S4 2317526:4T39VFR5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Mauritius; C:Namibia; C:Seychelles; C:South Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:Q; CT:R; CT:T; F:learning; Q:open learning; R:literature review; SpecialTopic:Library; T:TVET; publicImportV1

Recent research on geometry education: an ICME-13 survey team report - Sinclair, Nathalie; Bussi, Maria G. Bartolini; de Villiers, Michael; Jones, Keith; Kortenkamp, Ulrich; Leung, Allen; Owens, Kay (ZDM, 2016)
KerkoCite.ItemAlsoKnownAs: 10.1007/s11858-016-0796-6 10/gf49zc 2129771:KBL2L4KL 2129771:VUAH22CM
Keywords: _C:Argentina ARG; _C:Australia AUS; _C:Austria AUT; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Ethiopia ETH; _C:France FRA; _C:Georgia GEO; _C:Germany DEU; _C:Greece GRC; _C:Guinea GIN; _C:India IND; _C:Israel ISR; _C:Italy ITA; _C:Japan JPN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Mauritius MUS; _C:Mexico MEX; _C:Nepal NPL; _C:Netherlands NLD; _C:Nigeria NGA; _C:Peru PER; _C:Poland POL; _C:Portugal PRT; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Re-Integrating Vocational Technical Skill Acquisition into the Educational Curriculum: Capacity Building for Future Professionals - Olukanni, David O.; Aderonmu, Peter A.; Ogbiye, Adebanji S.; Akinwumi, Isaac I.; Chova, LG; Martinez, AL; Torres, IC (ICERI 2014, 2014)
One of the observable problems facing most developing nations today is the non-availability of adequately trained and well-motivated professionals with the capacity to solving problems of national development. Many University graduate professionals complain of unemployment. However, there exist substantial employment opportunities in Africa and other developing nations but the major challenge being that, the skills to match up with imminent challenges are missing. There is, therefore a need to re-integrate vocational technical skill acquisition into the Educational Curriculum for young professionals with proper mental orientation and practical skills for solving societal problems. This paper underlined the necessity of re-integrating vocational technical education (VTE) courses with special targets on sustainability and capacity building aspect of citizenry lives with a view to ascertain the empowerment of students for self employment after graduation. In a bid to achieve this, the current pedagogical approach and curriculum dynamics employed at the Architecture and Civil Engineering Department of Covenant University Ota, Nigeria was evaluated. Specific reference was made in terms of knowledge application from fabrication, construction in timber, reinforced concrete and steel to the main architectural design project. As regards the capacity building development aspect within the architectural and civil engineering education, the application of the respective vocational technical knowledge, obtained through lectures, site works and work shop practices were of major essence in collaborative design projects. It is expected that the indispensability of VTE courses for a successfully-integrated design would bind every element of the design together in different scales. In this way, the sustainability component of the designs in the studio, engineering workshop practice and energy-efficient design would be put to use. The study recommended the investigation and application of all critical elements of VTE-based curriculum development for a sustainable capacity development of emerging future professionals.
KerkoCite.ItemAlsoKnownAs: 2129771:KJHLPP9Q 2317526:GQUWIYUQ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:T; D:developing nation; F:curriculum; F:pedagogy; P:architecture; P:construction; T:TVET; T:trainee; Z:Capacity Building; Z:Educational Curriculum; Z:Future Professionals; Z:Sustainability; Z:Vocational Technical Skill; publicImportV1; ⛔ No DOI found

Pushing the child centred approach in Myanmar: the role of cross national policy networks and the effects in the classroom - Lall, Marie (Critical Studies in Education, 2011)
shortDOI: 10/ffvjm9 KerkoCite.ItemAlsoKnownAs: 10.1080/17508487.2011.604072 10/ffvjm9 2129771:HTJAIJ8S 2405685:R89YSEAB
Keywords: C:Myanmar; _C:Australia AUS; _C:Canada CAN; _C:Germany DEU; _C:India IND; _C:Japan JPN; _C:Mongolia MNG; _C:Myanmar MMR; _C:Pakistan PAK; _C:South Africa ZAF; _C:Thailand THA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

Public-private partnership for skill acquisition and vocational technical education development in Nigeria - Okpor, I; Najimu, H (Mediterranean Journal of Social Sciences, 2012)
This paper discusses the Private Sector Partnership with Education for Skill Acquisition and Vocational Technical Education Development. The relevance of the partnership on bringing skilled and trained manpower in their area of specialization is for the purpose of national development and self actualization. Strategies were identified for the effectiveness of the programme.
KerkoCite.ItemAlsoKnownAs: 2129771:CI83ZTKH 2317526:CKZC5QTG
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; T:Ausbildung; T:TVET; T:occupational education; publicImportV1; ⛔ No DOI found

Public Administration Training and Development in Africa: The Case of the Republic of South Africa - Subban, Mogie; Vyas-Doorgapersad, Shikha (Journal of Public Affairs Education, 2014)
South Africa is a developmental state that suffers from a lack of management capacity in the public service. Hence, a national imperative focuses on addressing talent management and building a cohort of qualified and competent public servants. The synergistic link between public sector management and the content of public administration can be associated with and contribute to addressing critical skills shortages in the public service. Training in this regard with the demand for and supply of competent managers raises some serious consideration. Given that academicians and scholars often criticize the history and evolution of education and training in public administration as being overly administrative and outdated, how has the need for a transformative management-governance context advanced in South Africa? In this regard, a range of "soft skills" deemed necessary for the developmental agenda in South Africa is a focal point of contemporary public administration. From a training perspective, methodologies include problem-based learning, performance-oriented and situation-emergent training, project management approach to managerial problems, and emphasis placed on indigenous management knowledge in a developmental context. We hope that these innovative approaches would address the wide managerial gap in the public administration environment.
KerkoCite.ItemAlsoKnownAs: 10.1080/15236803.2014.12001804 10/gf622g 2129771:U9QT565G 2317526:JN7MMLM7 LOCAL-WOS:000410029600006
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:learning; P:administration; P:environment; P:service industry; T:Ausbildung; Z:action learning; Z:capacity; Z:developmental state; Z:new public governance; publicImportV1

Psychological Framework for Quality Technical and Vocational Education and Training in the Twenty-First Century - Sarfo, FK (Learning, Design, and Technology, 2016)
To cope with the rapid changes in the real world of work and to prepare the workforce to enter the twenty-first century, there is a paradigm shift in the modern Technical and Vocational Education and Training (TVET) toward competency-based training (CBT) or vocational pedagogy. However, there is the lack of literature/research in TVET education that reveals the fundamental understanding and roles of contemporary learning theories in instructional psychology for creating successful competency-based learning environments for quality TVET teaching and learning. To contribute to the solution, this paper argues that there are significant relationships between (1) knowledge and skills and their associated learning processes required of modern TVET and (2) learning outcomes and their associated learning processes of the contemporary learning theories. In accordance with this assertion, an integrated learning theories for quality TVET education is proposed. The logic is that, supported by consistent empirical evidence as discussed in this paper, the conditions and instructional methods of the learning theories could be successfully used to design powerful competency-based learning environments to promote the development of technical and vocational expertise in TVET teaching and learning for the twenty-first century.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-319-17727-4_65-1 10/gf622m 2129771:PFKXJ28J 2317526:2X7AQQ3N UTI-61077B51-DB52-3D8E-A2D1-A8D7C4EFFC99
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; T:TVET; T:Training; _C:Ghana GHA; publicImportV1

Prospects, Issues and Challenges of Technical and Vocational Education and Training (TVET) in Revamping Nigeria's Depressed Economy - Bolarina, Fehintola Fatimoh Bintu; Akinyele, Temitayo Abosede (International Journal of Vocational and Technical Education Research, 2018)
Nigeria aspires to become a major player in the world economy in line with her Vision 20-2020. To achieve this ambitious goal, the most crucial vehicle apart from power and infrastructure, is a skilled and competent workforce. This is necessary for the effective implementation of national development projects and for attracting necessary international investment by hi-tech industries. (NBTE, 2011). Technical and Vocational Education and Training (TVET) is used as a comprehensive term referring to those aspects of the educational process involving, in addition to general education, the study of technologies and related sciences, the acquisition of practical skills, attitudes, understanding and knowledge relating to occupations in various sectors of economic and social life (UNESCO and ILO 2001) In addition to technical knowledge and aptitude, TVET is also concerned with softer skills like communication, negotiation and teamwork. It is dispensed in public and private educational establishments or other forms of formal or informal instructor aimed at granting all segments of the society access to lifelong resources.
KerkoCite.ItemAlsoKnownAs: 2129771:RCZXNRUT 2317526:V85JMU8R UTI-8A876AB1-4639-3E89-A9AA-2B55532EA115
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:West Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; Q:higher education; T:CTE; T:OE; T:PVE; T:TVET; T:career; T:occupational education; T:professional and vocational education; publicImportV1; ⛔ No DOI found

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:CKJRFWUQ 2405685:GVAZB6TM

Promotion of PV Uptake and Sector Growth in Kenya through Value Added Training in PV Sizing, Installation and Maintenance - Simiyu, Justus; Waita, Sebastian; Musembi, Robinson; Ogacho, Alex; Aduda, Bernard (Energy Procedia, 2014)
Abstract Sub-Saharan Africa, and more specifically the East African region, has the lowest rates of access to electricity in the world. On average, at most 15% of the rural population has access to electricity. Rural households and remote institutions use traditional energy sources such as charcoal, firewood, kerosene and diesel for generator sets, batteries and dry cell batteries. On the other hand, the region is one of the most promising in the world in economic development with growth levels being high and market saturation is a far away future problem. This growth has however been hampered by several factors with lack of energy being one of them. Kenya being one of the countries in the region faces a similar problem with the traditional sources of hydro facing weather related challenges. The situation is more wanting in the rural setting having only achieved electrification rates of between 5 and 10%. The rural being where the majority of low-income earning groups reside is further compounded with large geographical imbalance in electricity demand and supply. The main challenge to adopting pv utilization however, is lack of local capacity to handle the uptake all the way from solar home systems to grid connected and hybrid systems. According to Kenya Renewable Energy Association (KEREA), it is estimated that between 800 and 1000 pv technicians have been in practice since this sector started in Kenya in the late eighties, majority of them having the basic skills but no formal training to provide the service. They however have been offering necessary service to end-users and are hence an important aspect in the pv sector as a whole. Currently the pv (mainly SHS) comprise an over the counter trade system which provides loopholes when it comes to quality of products and installation. To safeguard the quality and safety of installations, formal training has to be incorporated in the system.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.egypro.2014.10.290 10/gf62p8 2129771:VFFH9ZCF 2317526:W57PZ89F
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; A:Sub-Saharan Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:access; P:culture; P:economy; P:electro; P:services; P:technician; T:Training; Z:Pv training; Z:cultural acceptance; Z:value addition; publicImportV1

Project updates for Climate, Environment and Education Adaptation Research (CLEEAR) Tanzania Steering Committee - Villavicencio, Xuzel; Haßler, Björn; Jengo, Eunice (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10944958 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1130 ZenodoArchiveConcept: 10944957
Keywords: _r:AddedByMyEducationEvidence

Project updates for Climate, Environment and Education Adaptation Research (CLEEAR) Tanzania Steering Committee - Villavicencio, Xuzel; Hassler, Bjoern (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10203975 ZenodoArchiveConcept: 10203974 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1032 2129771:6V9PMAJB
Keywords: _r:AddedByMyEducationEvidence

Project Information Document: Sierra Leone Free Education Project - World Bank (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:KKB6BM39 2405685:GIC5MV46
Keywords: _C:Sierra Leone SLE

Project Information Document (PID): Sierra Leone Free Education Project (P167897) - World Bank (World Bank Group, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:MB6GPUQR 2339240:6FWAUCW5 2405685:XAKZSJBD
Keywords: _C:Sierra Leone SLE

Professionalisierung von Bildungs- und Berufsberatung in Nigeria – Analyse der nationalen und internationalen theoriebegründeten Konzeptentwicklung und der Vernetzung der Akteure - Raji, Moromoke Nimota (Technische Universität Dresden, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:VMRLDQP2 2317526:WZQQAWNR
Keywords: C:Nigeria

Private Technical and Vocational Education in Sub-Saharan Africa: Provision Patterns and Policy Issues. New Trends in Technical and Vocational Education - Atchoarena, David; Esquieu, Paul (International Institute for Educational Planning, 2002)
The private provision trend in technical and vocational education (TVE) in sub-Saharan Africa occurred as the deterioration of state-run TVE systems in the region created a market niche for private providers. While advocates of deregulation believe the adoption of market principles in TVE will lead to greater efficiency and effectiveness, private providers have emerged in an uncoordinated and unmonitored fashion. A literature review and case studies of two countries Senegal and Mali led to some of the following key findings: (1) in some countries the majority of TVE students are enrolled in private institutions; (2) a large number of private TVE institutions operate illegally; (3) private provision concentrates on the service and commercial trades; and (4) the private sector may operate with lower costs and be more responsive to the labor market, but they do not provide much job-related training or include work-experience programs. Some of the policy issues are as follows: (1) simplifying procedures for establishing private TVE institutions facilitates their growth but is not sufficient to prevent the growth of an illegal sector; (2) the lack of regulation for private TVE institutions raises complex issues regarding the mechanisms required to ensure quality and protect consumers against abuses; and (3) for private TVE to succeed, students and the programs themselves must receive some public funding and develop relationships with industry. (Includes 84 references.) (MO)
KerkoCite.ItemAlsoKnownAs: 2129771:GYDI5ALR 2317526:87DIRPTS LOCAL-eric:ED480333
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; A:Sub-Saharan Africa; C:Mali; C:Senegal; CA:AandC; CC:Mali; CC:Senegal; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; Case Study; F:policy; F:regulation; P:mechanic; P:services; Q:Postsecondary Education; R:case study; R:literature review; T:TVET; T:Training; T:vocational school; Z:Case Studies; Z:Compliance (Legal); Z:Education Work Relationship; Z:Educational Development; Z:Educational Finance; Z:Educational Policy; Z:Educational Quality; Z:Federal Regulation; Z:Foreign Countries; Z:Free Enterprise System; Z:Government Role; Z:Government School Relationship; Z:Postsecondary Education; Z:Private Education; Z:Proprietary Schools; Z:Public Education; Z:Quality Control; Z:School Business Relationship; Z:Vocational Education; Z:Vocational Schools; publicImportV1; ⛔ No DOI found

Private-Public Partnership and Technical Vocational Education and Training (TVET) in a Developing Economy - Okoye, KRE; Chijioke, Okwelle P. (Arabian Journal of Business and Management Review (Oman Chapter); Sohar, 2013)
Technical Vocational Education and Training (TVET) system is widely recognised as education system expected to produce a competent workforce who can compete and excel in a rapidly changing environment and improves a country's economy. That TVET system in Nigeria and many other countries are in crisis or in immediate need for intervention, are often heard. Private Public Partnership (PPP) is viewed as an alternative strategy put forward to address the challenges confronting this all-important education system. Therefore, this paper attempts to add to the available literature on PPP in TVET by examining; conceptualizing PPP and its relative importance in economic growth, revamping TVET for technological advancement and economic growth in Nigeria through PPP collaboration. Constraints on TVET as a measure for economic development in Nigeria were also highlighted. The paper concludes by recommending for a proper PPP involvement in TVET system in Nigeria to enhance its economic potentiality. [PUBLICATION ABSTRACT]
KerkoCite.ItemAlsoKnownAs: 10.12816/0002333 10/gf623m 2129771:7DMPRDQN 2317526:DLRDBJDN
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; Business And Economics–Management; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; Economic growth; P:economy; Public private partnerships; Q:Private Public Partnership; Studies; T:TVET; Vocational education; publicImportV1

Primary Teacher Education in Rural Cameroon: Can Informal Learning Compensate for the Deficiencies in Formal Training? - Wohlfahrt, Melanie U (Africa Education Review, 2018)
The objective of the research on which this article reports was to evaluate the training conditions of primary school teachers in rural Cameroon, so as to identify alternative paths towards their qualification through informal learning in the workplace and outside. Following Denzin's (2009) between-methods triangulation approach, quantitative techniques, including statistical analyses and standardised questionnaires, were applied in addition to qualitative techniques, such as face-to-face interviews and observations of practising teachers and experts. The article presents the most common learning strategies of teachers in rural areas of Cameroon and recommends seminal solutions for teacher education. It can be concluded that informal learning in the workplace corresponds to traditional ways of learning in collectivist-oriented, oral societies in rural areas. Therefore, the combination of informal methods with formal structures of teacher education could improve the current educational system of many African countries, and provide a solution to meet the high demand for qualified staff within restricted budgets.
KerkoCite.ItemAlsoKnownAs: 10.1080/18146627.2016.1224586 10/gfv9vv 2129771:EYKMC27A 2317526:NXXB9H78
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Cameroon; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:attitude; F:learning; F:qualification; F:standards; F:teaching; F:teaching method; P:media; P:school teacher; P:teacher education; P:teachers; Q:informal learning; R:interview; R:observation; R:qualitative; R:quantitative; R:questionnaire; R:trial; T:Ausbildung; T:Training; T:workplace education; Z:Elementary school teachers; Z:Learning; Z:Rural areas; Z:Rural schools; Z:Teacher education; publicImportV1

Preverovaní vedomostí žiakov vo vybranom učive predmetu technika pomocou PC - Stadtrucker, Roman (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:83CL4F23 2129771:DBDCZNQ8 2129771:E47TI5DL
Keywords: _C:Australia AUS; _C:Luxembourg LUX; _C:Mali MLI; _C:Singapore SGP; _C:Slovenia SVN; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Post-primary agricultural education and training in sub-Saharan Africa: Adapting supply to changing demand - Vandenbosch, T (2006)
KerkoCite.ItemAlsoKnownAs: 2129771:PT4WBLLL 2317526:KYFPAVSC
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Benin; C:Burkina Faso; C:Ethiopia; CA:AandC; CL:de; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:ministry; P:agricultural; P:agriculture; P:economy; P:environment; Q:ICT; Q:certificate; Q:secondary education; R:impact; T:Ausbildung; T:Educação profissionalizante; T:TVET; T:Training; T:apprenticeship training; T:trainee; _C:Ghana GHA; _C:Uganda UGA; publicImportV1; ⛔ No DOI found

Portability, Feasibility, Collaborativeness: Teachers’ Perception Of Tablet Use For Inclusive Education - Benigno, Vincenza; Caruso, Giovanni; Epifania, Marina Ottavia; Fante, Chiara; Ravicchio, Fabrizio; Trentin, Guglielmo (ICERI2017 Proceedings, 2017)
Tablet are characterized by features such as their ease of use, portability, feasibility and they are easily employable in collaborative learning (Schuck et al., 2013). Students themselves consider them as an effective tool for reflection, since it allows them to deepen their knowledge thanks to the possibility of on-line searching (Parmigiani et al., 2015). On the other side, teachers are aware of the fact that tablets can help in making lesson more interesting and varied (Heinrich, 2012), but their use also needs a rethinking of the pedagogical approach (Culé & Gasparini, 2012) since tablets allow a more students-centred learning (Ludwig et al., 2011). Further, Information and Communication Technologies in general are also used for the inclusion of the disabled children into class activities (Ifenthaler & Schweinbenz, 2013). We argue that tablets, thanks to their abovementioned features, may be particularly helpful in fostering the inclusion of children who are not disabled, but who cannot attend school for medical reasons. The socio-educational inclusion of these children was the main aim of the TRIS project (Tecnologie per l’Inclusione Socio-educativa [Technologies for socio-educational inclusion]), and Information and Communication Technologies, combined with new pedagogical methodologies, played a key role for the pursuing of this aim. During this project, we equipped a middle school classroom with one tablet for each teacher and student. In addition, after one year several activities were planned in collaboration with teachers to evaluate the use of tablets and some specific apps in different teaching area. The activity developed for chemistry involved the use of augmented reality software, and we were investigating its effect on students’ attitudes towards the subject. The one developed for Italian language was aimed to the investigation of whether the affordance of a specific app for the creation of mental app have helped the students in their creation in respect to paper and pencil. In this paper, we report the results regarding teachers’ perception of tablet use in everyday class activities, involving both their competencies and the frequency of use. We considered the impact of the tablet after six months and after one year and a half from their introduction. Furthermore, at the end of the specific activity, the teachers were interviewed in order to understand the potentiality of the tablet for the abovementioned subjects, for the inclusion of the homebound student, and the difficulty found in the planning and managing of the activities. All the teachers involved (n= 7) sustained the utility of the tablet for classes, mentioning its capacity to foster communication in collaborative working and to gain students’ attention. They mostly used the tablet for students’ individual work, on-line research, and for collaborative activities with the homebound student. Regarding the activities carried out with the teachers, they kept sustaining the tablet capacity to motivate students and to foster their active participation, but they also expressed several concerns regarding the high amount of time needed to plan and to implement the activities using the tablet.
00000 KerkoCite.ItemAlsoKnownAs: 10.21125/iceri.2017.1312 10/gdm2ts 2129771:HE7QTZR8 2129771:KWSQ5QZS 2129771:LKSPGFSP 2129771:QPWDTFS8 2129771:T2MY6M9C 2129771:W9JUIT8E
Keywords: _C:Italy ITA; _C:Trinidad and Tobago TTO; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Polytechnic Law - Government of Ghana (2007)
KerkoCite.ItemAlsoKnownAs: 2129771:U7I7API9 2317526:UBUZL5GW
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Ghana; publicImportV1

Políticas públicas em educação: um apanhado histórico - Cá, Lourenço Ocuni; Ocuni Cá, Cristina Mandu (2015)
Este trabalho pretende documentar e analisar as estruturas educacionais da Guiné-Bissau, a falta de infraestrutura deixada pelo colonialismo português e a implementação do novo sistema educacional pelo Partido Africano para Independência da Guiné e Cabo Verde (PAIGC). A análise é feita por meio de avaliação do desempenho de sucessivos períodos que fizeram parte da história educacional do país. Nesta análise, destaca-se, em primeiro momento, a ausência de instituições escolares na sociedade linhageira africana, não que isto significasse a inexistência de ensino-aprendizagem, pois se tratava de uma cultura oral que veio a ser sobreposta pela cultura escrita europeia. Nesse sentido, no ensino colonial, a Igreja Católica desempenhou o papel fundamental na docilização dos guineenses. A igreja não só ajudou na implantação da política educacional, como também participou na legitimação do colonialismo português, sancionando e santificando a missão civilizadora e função histórica de Portugal. Paralelamente a essa educação, o movimento de libertação nacional da Guiné e Cabo Verde (PAIGC) idealizou e instaurou a educação nas Zonas Libertadas (1963-1973) esta educação era mais aberta e mais dinâmica em relação ao mundo exterior. Ela não tinha mais como objetivo principal produzir uma situação de equilíbrio e de estagnação e sim procurava apoiar-se e favorecer o processo geral da luta de libertação nacional em que se inseria.
KerkoCite.ItemAlsoKnownAs: 10.20396/etd.v17i1.8634820 10/gf6224 2129771:8BQFNJDG 2317526:Z2ASVCI4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Cape Verde; C:Guinea; C:Guinea-Bissau; CA:AandC; CL:en; CL:fr; CL:pt; CLL:pt; CLS:en; CT:A; CT:C; CT:P; CT:T; P:culture; P:health; T:apprenticeship; publicImportV1

Policy Review on Adult Learning: The Adult Non-formal Education Policy of Mali, West Africa - Gadio, Moussa (Adult Learning, 2011)
The shift to democracy was manifested in a constitution voted in 1992 that declared education a fundamental civil right and granted citizens the freedom of organizing themselves around their own needs. [...]new actors emerged in the education sector like the civil society and the private sector. Rapid changes in all societies today are creating new needs in relation with lifelong learning that the policy document doesn't cover sufficiently. [...]the policy document should be amended and completed with enforcement laws to provide adult education professionals and practitioners with instruments that would help to effectively recognize and reorganize the field to adapt it to the changing needs of modern Mali.
KerkoCite.ItemAlsoKnownAs: 10.1177/104515951102200303 10/gf623j 2129771:3ETCYCY8 2317526:9NUH92WE LOCAL-PQ-1430243183
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Mali; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:policy; Q:adult education; Q:lifelong learning; T:continuing education; Z:Adult education; Z:Adult learning; Z:Continuing education; Z:Decentralization; Z:Democracy; Z:Education policy; Z:Lifelong learning; publicImportV1

Policy Response, Social Media and Science Journalism for the Sustainability of the Public Health System Amid the COVID-19 Outbreak: The Vietnam Lessons - La, Viet-Phuong; Pham, Thanh-Hang; Ho, Manh-Toan; Nguyen, Minh-Hoang; P. Nguyen, Khanh-Linh; Vuong, Thu-Trang; Nguyen, Hong-Kong T.; Tran, Trung; Khuc, Quy; Ho, Manh-Tung; Vuong, Quan-Hoang (Sustainability, 2020)
Having geographical proximity and a high volume of trade with China, the first country to record an outbreak of the new Coronavirus disease (COVID-19), Vietnam was expected to have a high risk of transmission. However, as of 4 April 2020, in comparison to attempts to containing the disease around the world, responses from Vietnam are seen as prompt and effective in protecting the interests of its citizens, with 239 confirmed cases and no fatalities. This study analyzes the situation in terms of Vietnam’s policy response, social media and science journalism. A self-made web crawl engine was used to scan and collect official media news related to COVID-19 between the beginning of January and April 4, yielding a comprehensive dataset of 14,952 news items. The findings shed light on how Vietnam—despite being under-resourced—has demonstrated political readiness to combat the emerging pandemic since the earliest days. Timely communication on any developments of the outbreak from the government and the media, combined with up-to-date research on the new virus by the Vietnamese science community, have altogether provided reliable sources of information. By emphasizing the need for immediate and genuine cooperation between government, civil society and private individuals, the case study offers valuable lessons for other nations concerning not only the concurrent fight against the COVID-19 pandemic but also the overall responses to a public health crisis.
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/su12072931 2129771:QKI33LFP
Keywords: COVID-19; SARS-CoV-2; Vietnam; _C:Australia AUS; _C:Belgium BEL; _C:Brazil BRA; _C:China CHN; _C:France FRA; _C:Germany DEU; _C:India IND; _C:Iran IRN; _C:Italy ITA; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Nigeria NGA; _C:Switzerland CHE; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1; coronavirus; pandemic; policy response; public health system; science journalism; social media

Policy and practice: roles of the guidance and counseling teachers in the implementation of the girls’ reentry policy in selected schools in Lusaka, Zambia. - Mulenga, Innocent Mutale; Mukaba, Brenda (2018)
Publisher: Journal of Education and Practice KerkoCite.ItemAlsoKnownAs: 2129771:PBND6QHC 2129771:XH36HK83
Keywords: ⛔ No DOI found

Planning and governance for blended pedagogies and engagement of knowledge economy for South Africa's national development agenda - Ramoroka, Tlou Millicent (University of Limpopo, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:74WPDFSZ 2129771:PYLG6CVU
Keywords: _C:Algeria DZA; _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Congo XCO; _C:Dominican Republic DOM; _C:Egypt EGY; _C:Estonia EST; _C:Finland FIN; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Ireland IRL; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Latvia LVA; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Netherlands NLD; _C:Nigeria NGA; _C:North Macedonia MKD; _C:Norway NOR; _C:Poland POL; _C:Romania ROU; _C:Serbia SRB; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Sweden SWE; _C:Thailand THA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

Pharmacists, Pharmacy Training and Mental Health Care Provision in Ghana - Owusu-Daaku, Frances (Pharmacy Education, 2014)
Background: Generally, mental health care seeking in Ghana, a small, very religious West African nation of about 25 million people, is a pluralistic phenomenon, fraught with stigma. The advent of biomedical medicines, with pharmacists involved in providing medicines for mental health care, has somewhat lessened this stigma. Context: Has the pharmacy curriculum in Ghana adequately prepared students to be part of a mental health team? What is the attitude of pharmacy students and pharmacists towards mental health provision? Will the passage of the Mental Health Bill make any impact on pharmacists' role in mental health? Answers to these questions are explored by examining literature and relevant institutional documents Evaluation: Minimal attention has been paid to the training of pharmacists in the provision of mental health care, especially in Ghana. It is recommended that pharmacists themselves and related bodies collaborate to make effective use of this neglected potential.
KerkoCite.ItemAlsoKnownAs: 2129771:QHNMBMY8 2317526:F7FDC49G
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; CA:AandC; CCZ:Ghana; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:attitude; F:curriculum; P:health; P:measurement; P:media; R:impact; T:Ausbildung; Z:Pharmacists; Z:mental health; Z:pharmacy training; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Pharmaceutical education in the South African multicultural society - Summers, R; Haavik, C; Summers, B; Moola, F; Lowes, M; Enslin, G (American Journal of Pharmaceutical Education, 2001)
In 1995, South Africa commenced the implementation of a new quality assurance program at all educational levels, which promotes outcomes-based education. Degree programs and academic institutions have to be accredited by the South African Qualifications Authority through discipline-specific Education Training and Quality Assurance bodies. In response to these changes in education structure, the South African Pharmacy Council has developed outcomes-based competency standards for entry-level pharmacists. On the basis of these standards, the School of Pharmacy of the Medical University of Southern Africa, which served a non-white population during the apartheid era, and the Technikon Pretoria, which served a predominantly white student population, have jointly established an integrated, problem-based BPharm curriculum. The student intake on the program reflects the South African demographic composition. The course is designed to meet both the competency requirements and the needs of historically disadvantaged sections of the community. It is now in its third year, with encouraging pass rates.
KerkoCite.ItemAlsoKnownAs: 2129771:D6AT4C4Y 2317526:654WSUFT
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:curriculum; F:outcomes; F:qualification; F:standards; P:media; P:technology; Q:degree; T:Ausbildung; publicImportV1; ⛔ No DOI found

Pedagogical renewal in sub‐Saharan Africa: the case of Uganda - Altinyelken, Hülya K. (Comparative Education, 2010)
shortDOI: 10/cns9bx KerkoCite.ItemAlsoKnownAs: 10.1080/03050061003775454 10/cns9bx 2129771:SK5ZYYKU 2405685:LE8JDQQF
Keywords: C:sub-Saharan Africa; _C:Australia AUS; _C:Botswana BWA; _C:Cuba CUB; _C:Egypt EGY; _C:Ethiopia ETH; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Ghana GHA; _C:Kenya KEN; _C:Mali MLI; _C:Mauritius MUS; _C:Namibia NAM; _C:Netherlands NLD; _C:South Africa ZAF; _C:Tanzania TZA; _C:Tibet XTIBT; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Pedagogic change by Zambian primary school teachers participating in the OER4Schools professional development programme for one year - Hennessy, Sara; Haßler, Björn; Hofmann, Riikka (Research Papers in Education, 2015)
Supporting and upskilling teachers are essential to enhancing the quality of learning in developing contexts – the focus of Education For All – yet little evidence exists concerning what kinds of teacher education are actually most effective and what changes in ‘quality’ are desired and feasible. This paper illustrates how a concrete, research-informed school-based, model of professional development in sub-Saharan Africa can address the quality agenda. It reports on a trial of a pioneering, multimedia programme supporting interactive mathematics and science teaching using open educational resources and classroom digital technology, where available. The programme was carefully adapted to the Zambian context and ran weekly for one school year with 12 teachers in a low-resourced primary school. The study examined the impact on teachers' thinking and classroom practices. Data were derived from observations, lesson and workshop recordings, teacher interviews, portfolios and audio diaries. Through a teacher-led workshop approach and trialling new pedagogical strategies, teachers raised their expectations of pupils, adapted to learners’ knowledge levels, used more practical and group work, and integrated technology use. Pupils built deeper understanding of subject matter, were actively engaged, worked collaboratively and used digital technologies for problem-solving.
EdTechHub.Source: <this> EdTechHub.Source: <this> EdTechHub.Source: 2129771:QGHFB3QL KerkoCite.ItemAlsoKnownAs: 10.1080/02671522.2015.1073343 10/gftr46 2129771:2RSUFZXK 2129771:4DDI7MD4 2129771:5P2TUQQC 2129771:CPWUEHPK 2129771:DLXY6Q8J 2129771:QGHFB3QL 2129771:TG8DGQ3P 2129771:WHB6UUT9 2339240:UTDG7DWR 2405685:CSCFPKV2 2405685:NAJLZ3FE 2405685:R5KQR27A 2405685:S9FRC57W 2534378:4NJUGCID 2534378:E2PEHWQT 2534378:GGBWWEIN 2534378:HQ26LIRW 2534378:QVE8VZAZ 2534378:Z7EEHWT2 257089:AGK9WB3X 257089:FXEJEAA9 261451:ENUVRNA2 261495:4NPFWURU 261495:YIZHH9Z5
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:sub-Saharan Africa; CAREER development; EDUCATION – Study & teaching; GRADUATE education; PROFESSIONAL education; TEACHER training; ZAMBIA; Zambia; _C:Australia AUS; _C:India IND; _C:Iran IRN; _C:Japan JPN; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:Rwanda RWA; _C:South Africa ZAF; _C:Tonga TON; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __:import:01; __:match:final; __:matched; __:study_id:2099887; __C:filed:1; __C:scheme:1; ___working_potential_duplicate; __finaldtb; _r:ImportedToMyEducationEvidence; _yl:a; digital technology; docs.opendeved.net; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Partnerships with industry for efficient and effective implementation of TVET - Lee, J (International Journal of Vocational Education and Training, 2010)
This article focuses on partnership with industry as a means to efficiently and effectively implement technical and vocational education and training (TVET). Specifically, this article examines the situation in Africa, which is suffering from a chronic lack of skilled workforces both quantitatively and qualitatively. It outlines applicable six strategies to strengthen partnerships in TVET: (1) the industry’s involvement in the development and expansion of TVET, (2) a 60+40 training system to increase efficiency and productivity, (3) introducing national technology qualification (NTQ) system, (4) systemizing lifelong TVET, (5) TVET’s strategic transition, and (6) establishing regulatory and systemic framework. In addition, it displays an overview of partnership-based TVET system, which is a combination of the six strategies.
KerkoCite.ItemAlsoKnownAs: 2129771:GRLB4Y43 2317526:AVZ9A8SE UTI-6ADD4FC1-2383-305A-A941-0CBC2A5A6CC8
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:policy; Q:distance learning; R:evaluation; T:Ausbildung; T:Educação profissionalizante; T:TVET; T:firm-based training; publicImportV1; ⛔ No DOI found

Pandemic underscores gross inequalities in South Africa, and the need to fix them - Graham, Lauren (The Conversation, 2020)
While small businesses will be partially cushioned by government support measures, there's no support for the most vulnerable workers.
Library Catalog: theconversation.com KerkoCite.ItemAlsoKnownAs: 2129771:HT28YU32

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
EdTechHub.Source: 2405685:9TKV7H6E KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:Z2VNN7ER
Keywords: Author:OpenDevEd; F: Helpdesk response; L:Out-of-school populations; LP: English; _C:Bangladesh BGD; _C:China CHN; _C:India IND; _C:Kenya KEN; _C:Liberia LBR; _C:Malaysia MYS; _C:Maldives MDV; _C:Mexico MEX; _C:Mongolia MNG; _C:Nepal NPL; _C:Pakistan PAK; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Sri Lanka LKA; _C:Tanzania TZA; _EdTechHub_Output; _GS:indexed; __C:filed:1; __C:scheme:1; _cover:v1; _r:CopiedFromEvLib; _r:ImportedToMyEducationEvidence; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The COVID-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable now that schools are closed. They are isolated at home and unable to access information as easily as when they were attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
EdTechHub.Source: 2405685:LP4PGMNA KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3891379 2129771:3YH4WC8N 2129771:7J2S7YUK 2129771:J35ZR45N 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2405685:4PAZ4ZQH 2405685:LP4PGMNA 2405685:XIQ5CL9B 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _C:Bangladesh BGD; _C:Ethiopia ETH; _C:India IND; _C:Ireland IRL; _C:Kenya KEN; _C:Pakistan PAK; _C:Rwanda RWA; _C:United Kingdom GBR; _C:United States USA; _DOILIVE; _EdTechHub_Output; _GS:indexed; __C:filed:1; __C:scheme:1; _cover:v1; _r:CopiedFromEvLib; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Overview of funding for construction craft skills training in Sub-Saharan Africa: A case study of Zambia - Muya, Mundia; Price, A. D F; Edum-Fotwe, F. T. (Construction Management and Economics, 2006)
The wealth of any nation is ultimately based on its human resource or social capital. Education and training are the primary vehicles of developing this resource. Funding of formal construction craft skills training at trade institutions in Sub-Saharan Africa (SSA) is examined, using Zambia as a country case study. The data in the research were collected via semi-structured questionnaire interviews directed at government financed trades training schools offering construction programmes in Zambia. Results of the research show that formal construction craft skills training in Zambia has not been adequately funded over the years resulting in: ill-qualified low numbers of poorly remunerated teaching staff; poorly maintained infrastructure and workshop facilities not well equipped for teaching purposes; and out-dated curricula of construction craft programmes. A wide range of measures is required to improve funding for construction craft skills training. These include: increased training regulation and co-ordination by government, development of efficient and effective funding mechanisms that involve employers of crafts-persons, and training provision frameworks that encourage increased involvement of private training providers. © 2006 Taylor & Francis.
KerkoCite.ItemAlsoKnownAs: 10.1080/01446190500310585 10/cpx4fh 2129771:RVA4VZ6S 2317526:BDGHSBTQ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Zambia; CA:AandC; CCZ:Zambia; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:regulation; F:teaching; P:construction; P:crafts; P:measurement; P:mechanic; P:social; R:case study; R:interview; R:questionnaire; T:Training; Z:Construction craft skills; Z:Sub-Saharan Africa; Z:Training; publicImportV1

Outputs Register: The impact of GIS-supported teacher allocation in Sierra Leone - McBurnie, Chris (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396199 2129771:KC58MGKU 2405685:WXBISTFE
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Outputs register for HLR3 - Teacher Allocation Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6472492 10.53832/edtechhub.0089 2129771:3J4TNGDZ 2405685:9XJGEX5Z
Keywords: Author:OpenDevEd; _C:Sierra Leone SLE; _r:AddedByZotZen

Organizational culture and creativity in entrepreneurship education: A study of secondary education in Nigeria - Moses, Chinonye Love; Ayodele, Olokundun Maxwell; Mosunmola, Akinbode; Gbenga, Agboola Mayowa (Research Journal of Applied Sciences, 2016)
© Medwell Journals, 2016. This study was based on an ethnographic research of the culture of entrepreneurship teaching in 2nd Evangelical Church in West Africa (ECWA) Secondary School. Data was collated through the instrument of in depth interview and was analyzed through content analysis. The findings showed that there is positive relationship between organizational culture and creativity in entrepreneurship education. This is an indication that organizational culture impacts heavily on creativity in entrepreneurship teaching. The study concluded with the sections of recommendations for policy implications.
KerkoCite.ItemAlsoKnownAs: 2129771:L7T9E59E 2317526:YCJMLZEP
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Nigeria; CA:AandC; CCZ:Nigeria; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:policy; F:teaching; P:culture; Q:secondary education; R:impact; R:interview; T:entrepreneurship education; Z:Creativity; Z:Entrepreneurship education; Z:Organizational culture; Z:Secondary education; publicImportV1; ⛔ No DOI found

ORBIT and OER4Schools: supporting effective primary and secondary school practice through OER - Haßler, Björn; Hennessy, Sara; Jestaz, Caroline (Proceedings of Cambridge 2012: Innovation and Impact - Openly Collaborating to Enhance Education, 2012)
KerkoCite.ItemAlsoKnownAs: 2129771:6JDPUE7P 2129771:QFW8NS5E
Keywords: Author:Haßler; Author:OpenDevEd; _C:Australia AUS; _C:Belgium BEL; _C:Bolivia BOL; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Costa Rica CRI; _C:Cuba CUB; _C:Czech Republic CZE; _C:Denmark DNK; _C:Ecuador ECU; _C:Estonia EST; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Hungary HUN; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Ivory Coast CIV; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Malawi MWI; _C:Malaysia MYS; _C:Mauritius MUS; _C:Mexico MEX; _C:Nepal NPL; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Norway NOR; _C:Peru PER; _C:Poland POL; _C:Portugal PRT; _C:Romania ROU; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:Slovenia SVN; _C:South Africa ZAF; _C:Spain ESP; _C:Sudan SDN; _C:Sweden SWE; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Viet Nam VNM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; ⛔ No DOI found

Orange Education Portal - Orange Sierra Leone (2020)
Library Catalog: www.orange.sl KerkoCite.ItemAlsoKnownAs: 2129771:STMA8EXT 2405685:YV3WDQAQ

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:6XTCFJU4 2339240:ZNYWJ9PF 2405685:7HSIXMSV
Keywords: _C:Sierra Leone SLE; ___working_potential_duplicate

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:XHLB9RHT 2405685:AN5GA9QR
Keywords: _C:Sierra Leone SLE; ___working_potential_duplicate

Open Educational Resources Guide for Colleges of Education - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:3B42MMRX
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Open Educational Resources: Challenges and Opportunities in Indian Primary Education - Ganapathi, Janani (International Review of Research in Open and Distributed Learning, 2018)
Publisher: Athabasca University KerkoCite.ItemAlsoKnownAs: 10.19173/irrodl.v19i3.3662 2129771:R5XYHP56 2129771:SF383X85
Keywords: _C:Australia AUS; _C:India IND; _C:Kenya KEN; _C:New Zealand NZL; _C:Poland POL; _C:South Africa ZAF; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Open Data Readiness Assessment: Sierra Leone - World Bank (2015)
KerkoCite.ItemAlsoKnownAs: 2129771:RZH9ACII 2339240:GHD8WBJM 2405685:5GLY6KEA
Keywords: _C:Sierra Leone SLE

Open Data Readiness Assessment: Prepared for the Government of Sierra Leone - Chrzanowski, Pierre; Holm, Jeanne; Manley, Laura; Dodds, Elizabeth; Baker, Rob (World Bank Group; Open Aid Partnership, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:ZWH5D8DC 2405685:83I8VUFY
Keywords: _C:Sierra Leone SLE

Open Content - Haßler, Björn; Mays, Tony (International Encyclopedia of Digital Communication and Society, 2015)
HMOC EdTechHub.Copy: 2405685:UP7P7L2D KerkoCite.ItemAlsoKnownAs: 2129771:DWC5YGAD 2129771:FY5V62YE 2129771:W9Q5K32L 2405685:UP7P7L2D 2486141:C7AQI94R 261495:NHM4H2R9
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Canada CAN; _C:France FRA; _C:South Africa ZAF; _C:Spain ESP; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence

Open at the Margins - Adam, Taskeen; Allen, Nicole; Amiel, Tel; Asino, Tutaleni; Atenas, Javiera; Bali, Maha; Barnes, Naomi; Bourg, Chris; Bouterse, Siko; Caines, Autumm; Campbell, Lorna M.; Cangialosi, Karen; et al. (Rebus Community, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:8Q7MBRTS
Keywords: Author:OpenDevEd; _C:Austria AUT; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Cuba CUB; _C:Egypt EGY; _C:Finland FIN; _C:France FRA; _C:Georgia GEO; _C:Germany DEU; _C:Greece GRC; _C:India IND; _C:Iran IRN; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Jordan JOR; _C:Malaysia MYS; _C:Mexico MEX; _C:Netherlands NLD; _C:Nigeria NGA; _C:Portugal PRT; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:Somalia SOM; _C:South Africa ZAF; _C:Spain ESP; _C:State of Palestine PSE; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Venezuela VEN; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence

Open and distance learning for health: supporting health workers through education and training - Dodds, T (Open Learning: The Journal of Open, Distance and e-Learning, 2011)
This case study surveys the growing use of open and distance learning approaches to the provision of support, education and training to health workers over the past few decades. It classifies such uses under four headings, providing brief descriptions from the literature of a few examples of each group. In conclusion, it identifies key lessons from the experience of open and distance learning generally that could be of benefit in health education and training at a distance.
KerkoCite.ItemAlsoKnownAs: 10.1080/02680513.2011.567757 10/gf6225 2129771:JPSIX5HQ 2317526:J9WSZLRZ UTI-5ACC3104-9BB4-3C7F-8B7B-FFDE5E23EA04
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Gambia; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:health; P:measurement; Q:ODEL; Q:distance learning; Q:e-learning; Q:open educational resources; Q:open learning; T:Ausbildung; T:Training; T:continuing education; publicImportV1

One Laptop per Child Rwanda: Enabling Factors and Barriers - Adam, Taskeen; Haßler, Björn; Cruickshank, Heather (Empowering the 21st Century Learner, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:PZE5L9QW 2129771:WDGI2A2F 2486141:PZQAFS2P
Keywords: Author:Haßler; Author:OpenDevEd; _C:Australia AUS; _C:Austria AUT; _C:Bangladesh BGD; _C:Belgium BEL; _C:Botswana BWA; _C:Burkina Faso BFA; _C:Canada CAN; _C:China CHN; _C:Croatia HRV; _C:Cuba CUB; _C:Cyprus CYP; _C:Denmark DNK; _C:Egypt EGY; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Iran IRN; _C:Israel ISR; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Malaysia MYS; _C:Mexico MEX; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Norway NOR; _C:Peru PER; _C:Poland POL; _C:Portugal PRT; _C:Romania ROU; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Serbia SRB; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

On Technology Integration: Perspective from Nigeria - Ifinedo, Eloho (JYU dissertations, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:2V2PSB3B
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Egypt EGY; _C:Estonia EST; _C:Finland FIN; _C:France FRA; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Israel ISR; _C:Italy ITA; _C:Kenya KEN; _C:Korea; Republic KOR; _C:Luxembourg LUX; _C:Malawi MWI; _C:Malaysia MYS; _C:Mali MLI; _C:Mauritius MUS; _C:Mexico MEX; _C:Morocco MAR; _C:Mozambique MOZ; _C:Netherlands NLD; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1; ⛔ No DOI found

OECD Reviews of Vocational Education and Training - Key Messages and Country Summaries - OECD (2015)
Full country policy reviews have been conducted, as part of the two OECD studies on VET, in Australia, Austria, Chile, China, Costa Rica, Czech Republic, Denmark, Egypt, Germany, Hungary, Ireland, Israel, Kazakhstan, Korea, Mexico, the Netherlands, Norway, South Africa, Sweden, Switzerland, the United Kingdom (England and Wales), and the United States (with case studies of Florida, Maryland and Washington State) and also the U.S states of South Carolina and Texas.
KerkoCite.ItemAlsoKnownAs: 2129771:STK8I4G3 2317526:9NUHFVZM UA-0E8E2366-8886-43BB-850D-1BFBA9676A04
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; CC:Australia; CC:Austria; CC:Chile; CC:China; CC:Costa Rica; CC:Czech Republic; CC:Denmark; CC:Egypt; CC:Germany; CC:Kazakhstan; CC:Korea; CC:Mexico; CC:Netherlands; CC:Norway; CC:South Africa; CC:Sweden; CC:Switzerland; CC:UK; CC:United States; CLL:en; Hungary; publicImportV1

NQF Act nº67, 2008 - National Qualifications Framework - Government of South Africa (2009)
To provide for the National Qualifications Framework; to provide for the responsibilities of the Minister of Education and the Minister of Labour; to provide for the South African Qualifications Authority; to provide for Quality Councils; to provide for transitional arrangements; to repeal the South African Qualifications Authority Act, 1995; and to provide for matters connected therewith.
UA-d4ff8ae5-bccd-42b5-9b9d-185af4304c87 KerkoCite.ItemAlsoKnownAs: 2129771:4H3DWEXY 2317526:RJ6IDATN
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; Qualification Framework; publicImportV1

Nouvelles formes d’apprentissage en Afrique de l’Ouest: Vers une meilleure insertion professionnelle des jeunes - Walther, Richard (2008)
KerkoCite.ItemAlsoKnownAs: 2129771:59I3LR3U 2317526:USLKC67W
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; C:Benin; C:Mali; C:Senegal; C:Togo; CLL:fr; publicImportV1; ⛔ No DOI found

Non-formal vocational education in Uganda: Practical empowerment through a workable alternative - Blaak, M.; Zeelen, J.; Openjuru, , G.L. (International Journal of Educational Development, 2013)
This article reflects on the potential of non-formal vocational education in Uganda to improve the quality of life of those excluded from formal education. Based on an exploration of humanizing development theorists Sen, Freire and Nyerere, together with two case studies, practical empowerment is described as a desirable outcome of education for development. Practical empowerment includes acquiring marketable skills as well as capabilities to critically give direction to one's life. Although education leading to this outcome is desirable for all, non-formal vocational education can reach those currently excluded from formal education, thus enhancing their empowerment by equipping them with useful skills and knowledge. © 2012 Elsevier Ltd.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2012.02.002 10/gf62mt 2129771:8TXYAWXU 2317526:QFZ3G83W DOI-10.1016/j.ijedudev.2012.02.002
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:outcomes; HDR25; R:case study; T:TVET; Z:Alternative provision; Z:Drop-out; Z:Employment skills; Z:Poverty; Z:Vocational education and training; _C:Uganda UGA; __C:filed:1; publicImportV1

New product development process: The case of selected technical and vocational colleges in Nigeria - Oyebola, Abiodun Isaac; Olaposi, Titilayo Olubunmi; Adejuwon, Olawale Oladapo; Akarakiri, Joshua Babatunde (African Journal of Science, Technology, Innovation and Development, 2018)
© 2017 African Journal of Science, Technology, Innovation and Development. An examination of the literature reveals that studies on new product development processes have been carried out mostly in western contexts using sequential models. This study was conducted using the innovation systems approach and a sequential model to analyze new product development processes in selected technical and vocational colleges in Nigeria. Using a questionnaire survey method, the sequential model revealed that most of the respondents (91%) conceived of their products through job experience and only 4.9% conceived of product ideas through R&D, showing a weakness in science-based enquiries in the invention stages. In addition, 73.9% developed prototypes while 82.2%, 80.4%, and 69.2% conducted feasibly studies, business analyses and market surveys, respectively. These results imply capability in the commercialization stages of the sequential model. The systems of innovation approach however revealed very weak linkages with universities and R&D institutes which could have complemented lack of R&D activities in the technical and vocational colleges. While some useful and beneficial technological products have been developed in the colleges, we conclude that the use of sequential models and systems of innovation approach may bring a fresh perspective to the product development process.
KerkoCite.ItemAlsoKnownAs: 10.1080/20421338.2017.1381458 10/gf62p5 2129771:SQHSDCCC 2317526:T7FIYYQ5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:measurement; P:technology; R:questionnaire; R:survey; T:TVET; T:vocational college; Z:innovation; Z:process; Z:product development; Z:technical and vocational education; Z:technological products; publicImportV1

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, the EdTech Hub participated in an “Ask me anything” session for policy-makers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the COVID-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the COVID-19 pandemic, presented by the World Bank EduTech team and the EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
EdTechHub.Source: 2405685:UXQG7GRG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 2129771:X82WTVD8 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:UXQG7GRG
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:Nepal; F: Helpdesk response; LP: English; _C:Austria AUT; _C:Bangladesh BGD; _C:Kenya KEN; _C:Korea XKOR; _C:Liberia LBR; _C:Nepal NPL; _C:Pakistan PAK; _C:Singapore SGP; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 2129771:4LIQQUDW 2129771:5UVWHG6S 2129771:VFG8KQPH 2339240:94IZR4ET 2339240:TST2YB8H 2405685:FEXGB4IJ 2405685:ZGYUEEZQ 4426965:S8FRGESP
Keywords: Author:OpenDevEd; _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _cover:v3; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

National Policy on Community Education and Training Colleges - Government of South Africa (2015)
UA-c934d266-f205-45a0-a9e3-e144ec21abcf KerkoCite.ItemAlsoKnownAs: 2129771:S5XPV9GQ 2317526:SLS2TTI3
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; publicImportV1

National Industrial Training Standards - Government of Kenya (2015)
UA-7a3601b7-cd04-42c0-8a72-3405e7a31140 KerkoCite.ItemAlsoKnownAs: 2129771:KVKDBW9A 2317526:HYXNDWY2
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; Qualification Framework; publicImportV1

National ICT Policy of Sierra Leone - Ministry of Information and Communications (Government of Sierra Leone, 2009)
KerkoCite.ItemAlsoKnownAs: 2129771:ZGPWB7P4 2339240:GI5IQFVY 2405685:BVA56A3C
Keywords: _C:Sierra Leone SLE; ⛔ No DOI found

National Education Standards - primary and secondary education - Government of Malawi (2015)
UA-a102ca97-c919-4c5e-8762-6d9522ed1b77 KerkoCite.ItemAlsoKnownAs: 2129771:8E5PPF7X 2317526:PRMLTNFC
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Malawi; Qualification Framework; publicImportV1

National Education Policy - Ministry of Education, Youth and Sports (Sierra Leone) (2010)
KerkoCite.ItemAlsoKnownAs: 2129771:VDJZCK59 2405685:YLXI3EW2

National Credit and Qualifications Framework - Government of Botswana (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:7RZIN9I4 2317526:SXN7LTXV
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; Qualification Framework; publicImportV1

Narrowing the Digital Divide a case study of “learning by doing” approach to narrowing the Digital Divide in East Africa (Kenya) by Dubai Women's College students - Butt, Z; Chaudhri, AA; Nassiri, N (2013)
It is globally assumed that improvements in Information Communication Technology (ICT) will enforce a better global communication; improve business processes and commercial activities, thereby leading to superior standards of living for individuals while benefitting society. This paper narrates the experiences of fifteen HCT students who visited Kenya in an attempt to narrow the existing “Digital Divide” by building computer networking labs in some of the vocational institutes in remote East Africa. This paper encapsulates key reflections of the study tour participants who embraced a “learning by doing” model in order to gain valuable international work experience and narrow the digital divide in four educational institutes in Kenya. The success of this initiative mandates that we document the learning from this experience in order to ensure success and sustainability of future projects of similar calibre. We believe the process of conducting “international field-trips” followed by reflections formulating lessons learnt from these trips will be useful for future volunteers.
KerkoCite.ItemAlsoKnownAs: 2129771:UA9KC9S9 2317526:ALC3S6WJ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; F:learning; F:women; P:economy; Q:digital divide; Q:digital technology; R:case study; T:TVET; publicImportV1; ⛔ No DOI found

Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (2017)
There are severe geographical disparities in pupil-teacher ratios (PTR) across Malawi, with most teachers concentrated near commercial centers and in rural schools with better amenities. Most of the variation in PTR is concentrated in small sub-district areas, suggesting a central role for micro-geographic factors in teacher distribution. Employing administrative data from several government sources, regression analysis reveals that school-level factors identified by teachers as desirable are closely associated with PTR, including access to roads, electricity, and water, and distance to the nearest trading center, suggesting a central role for teachers’ interests in PTR variation. Political economy network mapping reveals that teachers leverage informal networks and political patronage to resist placement in remote schools, while administrative officials are unable to stand up to these formal and informal pressures, in part because of a lack of reliable databases and objective criteria for the allocation of teachers. This study curates a systematic database of the physical placement of all teachers in Malawi and links it with data on school facilities and geo-spatial coordinates of commercial centers. The study develops a consistent and objective measure of school remoteness, which can be applied to develop policies to create rules for equitable deployments and targeting of incentives. Growing awareness of disparities in PTRs among district education officials is already showing promising improvements in targeting of new teachers. Simulation results of planned policy applications show significant potential impacts of fiscally-neutral approaches to targeted deployments of new cohorts, as well as retention of teachers through data-calibrated incentives.
Keywords: Data-driven model; Deployments; Lebanon_event_2021; Malawi; Political economy; Schools; Teachers; _C:Brazil BRA; _C:Gambia GMB; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Italy ITA; _C:Malawi MWI; _C:Mozambique MOZ; _C:Philippines PHL; _C:Singapore SGP; __C:filed:1; __C:scheme:1

Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (International Journal of Educational Development, 2019)
There are severe geographical disparities in pupil-teacher ratios (PTR) across Malawi, with most teachers concentrated near commercial centers and in rural schools with better amenities. Most of the variation in PTR is concentrated in small sub-district areas, suggesting a central role for micro-geographic factors in teacher distribution. Employing administrative data from several government sources, regression analysis reveals that school-level factors identified by teachers as desirable are closely associated with PTR, including access to roads, electricity, and water, and distance to the nearest trading center, suggesting a central role for teachers’ interests in PTR variation. Political economy network mapping reveals that teachers leverage informal networks and political patronage to resist placement in remote schools, while administrative officials are unable to stand up to these formal and informal pressures, in part because of a lack of reliable databases and objective criteria for the allocation of teachers. This study curates a systematic database of the physical placement of all teachers in Malawi and links it with data on school facilities and geo-spatial coordinates of commercial centers. The study develops a consistent and objective measure of school remoteness, which can be applied to develop policies to create rules for equitable deployments and targeting of incentives. Growing awareness of disparities in PTRs among district education officials is already showing promising improvements in targeting of new teachers. Simulation results of planned policy applications show significant potential impacts of fiscally-neutral approaches to targeted deployments of new cohorts, as well as retention of teachers through data-calibrated incentives.
Keywords: Data-driven model; Deployments; Lebanon_event_2021; Malawi; Political economy; Schools; Teachers; _C:Brazil BRA; _C:Gambia GMB; _C:India IND; _C:Indonesia IDN; _C:Italy ITA; _C:Malawi MWI; _C:Mozambique MOZ; _C:Norway NOR; _C:Philippines PHL; _C:Singapore SGP; __C:filed:1; __C:scheme:1

MOOCs for Professional Development of Teachers through E-Learning System: The Indian Scenario - Kayal, Soumen; Kayal, Baisakhi Das (SRELS Journal of Information Management, 2020)
KerkoCite.ItemAlsoKnownAs: 10.17821/srels/2020/v57i2/151966 2129771:3DTBRMRT
Keywords: _C:France FRA; _C:India IND; _C:Kenya KEN; _C:South Africa ZAF; _C:Spain ESP; _C:United States USA; __C:filed:1; __C:scheme:1

Mobile learning in schools: Key issues, opportunities and ideas for practice - Wishart, Jocelyn (Routledge, 2017)
EdTechHub.ItemAlsoKnownAs: 2129771:LXIQ529R
Keywords: _C:Australia AUS; _C:Austria AUT; _C:Bangladesh BGD; _C:Brunei Darussalam BRN; _C:Canada CAN; _C:China CHN; _C:Denmark DNK; _C:Finland FIN; _C:France FRA; _C:India IND; _C:Italy ITA; _C:Jamaica JAM; _C:Japan JPN; _C:Korea XKOR; _C:Lebanon LBN; _C:Malaysia MYS; _C:Nepal NPL; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Portugal PRT; _C:Qatar QAT; _C:Singapore SGP; _C:Slovenia SVN; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Sweden SWE; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Mobile learning bridging the gap in agricultural extension service delivery: Experiences from Sokoine University of Agriculture, Tanzania - Sanga, C; Mlozi, M; Haug, R; Tumbo, S (International Journal of Education and Development using Information and Communication Technology, 2016)
The ubiquitous nature of mobile phones offers a noble environment where farmers can learn informally anywhere, anytime and at any location. This is an innovative way to address some of the weakness of conventional agricultural extension service. Few empirical studies have reported on the development of mobile phone application to support blended learning for smallholder farming communities in developing countries. This study adopted a participatory action research method to develop innovative communication pathways in dissemination of agricultural information, agricultural knowledge and proven agricultural technologies from either extension agents or agricultural research centres or universities to farmers. The respondents who tested the system were selected random from 19 villages in Kilosa District, Tanzania. The developed systems support blended learning using mobile learning (m-learning) and electronic learning (e-learning). The findings from this study show that the systems can provide innovative mobile agricultural extension service to more than 380 smallholder farmers via web- and mobile-phone-based farmers’ advisory information systems.
KerkoCite.ItemAlsoKnownAs: 2129771:8ITNR724 2317526:QJP4S2HT UTI-58288E2E-A7C1-3BBC-8FF2-B93729779CF7
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:agricultural; P:agriculture; P:economy; P:services; Q:ICT; Q:mobile learning; T:Training; T:continuing education; publicImportV1; ⛔ No DOI found

Mitigating COVID-19 impacts and getting education systems up and running again: Lessons from Sierra Leone - Davis, Edward; Berry, Chris (Global Partnership for Education, 2020)
Reflexions on some of the lessons from the Sierra Leone Ebola education response that could be relevant for countries facing shutdowns of their education systems due to the COVID-19 pandemic.
KerkoCite.ItemAlsoKnownAs: 2129771:3FB8TGLH 2339240:NIUY9YWK 2405685:CVJKIQ8D
Keywords: _C:Sierra Leone SLE

Ministry of Information and Communications | Home - Ministry of Information and Communications (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:KJ4CSE7U 2405685:MV5RWXEF

Midline survey: Transforming teacher education and learning - T-TEL (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:STGNQILB 2339240:MJM6PHCK 2405685:UMGJ8LUJ
Keywords: _C:Ghana GHA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Methods of financing technical and vocational education and training, and entrepreneurship education to support skills development in Lusaka Province, Zambia - Mubanga, Philip; Hock, Oo Yu; Asif, Mahbub Karim; Mulenga, Innocent Mutale (International Journal of Research and Scintific Innovation (IJRSI), 2019)
Publisher: Research Gate
Keywords: ⛔ No DOI found

Meeting the Academic and Social-Emotional Needs of Nigeria’s Out-of-School Children | INEE - Miheretu, Adane (International Rescue Committee, 2019)
As part of their response to number of out-of-school children in Nigeria, with the support from UK Aid, the International Rescue Committee (IRC) and Creative Associates International developed the Accelerated Learning Program (ALP) model in Nigeria. ALPs are flexible, age-appropriate educational programs which aim to address the needs of OOS children and youth by preparing them for entry or re-entry into the mainstream educational system. By enrolling these students, ALPs strive to make up for lost time and shore up the essential skills these students may have never developed or lost after their educations were derailed.
KerkoCite.ItemAlsoKnownAs: 2129771:XPGY55IA
Keywords: _C:Nigeria NGA; __C:filed:1; __C:scheme:1

Meeting agenda matters: promoting reflective dialogue in teacher communities - Dogan, Selcuk; Yurtseven, Nihal; Tatık, Ramazan Şamil (Professional Development in Education, 2018)
(2018). Meeting agenda matters: promoting reflective dialogue in teacher communities. Professional Development in Education. Ahead of Print.
00000 EdTechHub.ItemAlsoKnownAs: 2129771:ZJJHS979
Keywords: _C:Australia AUS; _C:Lebanon LBN; _C:Pakistan PAK; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Measuring and predicting process quality in Ghanaian pre-primary classrooms using the Teacher Instructional Practices and Processes System (TIPPS) - Wolf, Sharon; Raza, Mahjabeen; Kim, Sharon; Aber, J. Lawrence; Behrman, Jere; Seidman, Edward (Early Childhood Research Quarterly, 2018)
© 2018 Elsevier Inc. In recent years, there has been an increase in the demand for and supply of early childhood education (ECE) in low- and middle-income countries. There is also growing awareness that unless ECE is of high quality, children may attend school but not learn. There is a large literature on the conceptualization and measurement of ECE quality in the United States that focuses on the nature of teacher-child interactions. Efforts to expand access to high quality ECE in low- and middle-income countries will require similar measurement efforts that are theoretically-grounded and culturally-adapted. This paper assesses the factor structure and concurrent validity of an observational classroom quality tool to assess teacher-child interactions—the Teacher Instructional Practices and Processes System©(TIPPS; Seidman et al., 2013)—in Ghanaian pre-primary classrooms. We find evidence of three conceptually distinct but empirically correlated domains of quality: Facilitating Deeper Learning (FDL), Supporting Student Expression (SSE), and Emotional Support and Behavior Management (ESBM). Teachers’ schooling level, training in early childhood development, and professional well-being positively predict the three quality domains in different ways. SSE and ESBM predict classroom end-of-the-school-year academic outcomes, and SSE predicts classroom end-of-the-school-year social-emotional outcomes. Implications for the field of international education and global ECE policy and research are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ecresq.2018.05.003 10/gfjkng 2129771:RR2UQS7G 2317526:AH9T7QFQ
Keywords: -FullBiblioUHMLgen; -RRQ:LOW; A:Sub-Saharan Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:middle-income country; F:access; F:learning; F:outcomes; F:policy; P:culture; P:measurement; P:nature; P:social; P:teacher education; P:teachers; R:observation; T:Training; Z:Pre-primary school; Z:Process quality; Z:School readiness; Z:Sub-Saharan Africa; Z:Teacher education; Z:Teacher-child interactions; _C:Ghana GHA; publicImportV1

Maverick Citizen: Access to water and sanitation in South Africa: A renewed call for more action - Mudombi, Shakespear (Daily Maverick, 2020)
While the main discourse in accessing basic services such as water and sanitation focuses on universal access, in reality such access – as highlighted so starkly as the country attempts to halt the spread of the coronavirus – is not equitable.
Library Catalog: www.dailymaverick.co.za KerkoCite.ItemAlsoKnownAs: 2129771:RD4465HR

Maths WAEC BECE Exam Syllabus - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745442 2129771:ZA8MC4HR
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745292 2129771:YGCURLAQ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745360 2129771:D4QXSLUF
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 2 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745438 2129771:9RLSMP7W
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745290 2129771:AXCH2GJ9
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745358 2129771:KFP83EGL
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4, Term 1 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745436 2129771:WGVMCVUW
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4 Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745382 2129771:74F5KF4B
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 4 Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745380 2129771:U7UWWNCG
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745288 2129771:JYUSBXYW
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745356 2129771:R7943AHM
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 3 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745434 2129771:YY2479ZJ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745286 2129771:HQ36BT6H
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745354 2129771:FJRZW732
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 2 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745432 2129771:X87XXHJ2
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745284 2129771:PWMZMSUZ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745352 2129771:CUYDXHT7
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3, Term 1 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745430 2129771:PTKDHRND
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3 Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745378 2129771:IPI9KPYE
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3 Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745376 2129771:N94SIPVA
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 3 Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745374 2129771:3FM3R6ZU
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745282 2129771:N64A75FH
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745350 2129771:9RKJANKS
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 3 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745428 2129771:TDJMU526
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745280 2129771:X4YAG6ZJ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745348 2129771:XAZLCQSH
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 2 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745426 2129771:BPD5XYDP
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745278 2129771:GJCKRRL7
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745346 2129771:YQC4EXRF
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2, Term 1 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745424 2129771:K2C3IBML
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2 Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745372 2129771:6C6BFNXE
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2 Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745370 2129771:F546CMHJ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 2 Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745368 2129771:Y6M7QW57
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745276 2129771:KPTVH8T4
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745344 2129771:6GZXD6BP
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 3 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745422 2129771:9NCCYFCY
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745274 2129771:H4DV3K77
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745342 2129771:6M5HQFEF
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 2 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745420 2129771:6SBH7F6Y
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745272 2129771:IIUCXCRJ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745340 2129771:JHMGTTWK
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1, Term 1 DS, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745418 2129771:AYRWTY3Y
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1 Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745366 2129771:K7AHZVRR
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1 Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745364 2129771:TBEAR3UM
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Senior Secondary School, Year 1 Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745362 2129771:JKQFJHJL
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 09, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745192 2129771:KRTR8EZC
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 09, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745189 2129771:A5Z9TQAN
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 09, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745187 2129771:IWQPQMF6
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 08, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745185 2129771:2HQ95ZYD
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 08, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745183 2129771:NNV36U6G
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 08, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745181 2129771:AB82525H
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 07, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745179 2129771:6QX3D8FX
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 07, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745177 2129771:X3L6JBTH
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 07, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745175 2129771:D3TWSMDM
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 06, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745122 2129771:D3NAJK5X
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 06, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745120 2129771:7ABYBSEQ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 06, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745118 2129771:BDP4QIMJ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 05, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745116 2129771:88V39KSR
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 05, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745114 2129771:259DLBTQ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 05, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745112 2129771:VS2ABGSD
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 04, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745110 2129771:44VSRPZ5
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 04, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745108 2129771:JEDW9G2Q
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 04, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745106 2129771:8KH4DW3S
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 03, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745104 2129771:Y4KNQZ2K
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 03, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745102 2129771:VLFW8IC4
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 03, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745100 2129771:XWZGW9EE
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 02, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745098 2129771:6XBDQ2CQ
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 02, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745096 2129771:ZX8V6RID
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 02, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745094 2129771:XYEAJT6R
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 01, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745092 2129771:MS8BEQA6
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 01, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745090 2129771:47RB7ZL9
Keywords: SSEIP; _C:Sierra Leone SLE

Maths, Class 01, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745088 2129771:9A7DY7VM
Keywords: SSEIP; _C:Sierra Leone SLE

Mathematics teacher education curriculum at a university in Zambia: student teachers’ acquisition of appropriate competencies for teaching mathematics in secondary school. - Changwe, Robert; Mulenga, Innocent Mutale (2018)
Publisher: Multidisciplinary Journal of Language and Social Sciences Education
Keywords: ⛔ No DOI found

Math, Class 09, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745228 2129771:P5KCADN5
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 09, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745226 2129771:7NNZKGN3
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 09, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745224 2129771:7YYTIDRE
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 08, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745222 2129771:5DNFGHPN
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 08, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745220 2129771:8U5QALAY
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 08, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745218 2129771:NMPPR9R2
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 07, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745216 2129771:CNASGSXP
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 07, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745214 2129771:8BRJAL4Y
Keywords: SSEIP; _C:Sierra Leone SLE

Math, Class 07, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745212 2129771:BWG6JGD2
Keywords: SSEIP; _C:Sierra Leone SLE

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya. - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 10.13189/ujer.2018.060604 2129771:WTA327GX
Keywords: _C:China CHN; _C:Kenya KEN; __C:filed:1; __C:scheme:1

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652942 10.53832/edtechhub.0068 2129771:SYUMIUV3 2339240:HHY6M835 2405685:EE9QCGHI 2405685:RN79UTQY
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Mapping Non-formal Education at Post-primary Educational Level in Uganda - Bananuka, T; Katahoire, AR (2008)
1. This paper explores various cases of non-formal education at post-primary education level in Uganda with special focus on the analysis of the context of NFE provision and the curriculum. Other issues explored included educator training, materials development, teaching and learning methods, policy development and implementation, the relationship with formal education, linkages with work and employment and issues of sustainability and continuity. 2. The study findings suggest that Non-formal Education at post-primary education level is run on a rather ad hoc basis without clearly defined structures save for the recent initiatives in Community Polytechnics. Much as various policy documents and statements advocate for the integration of Non-Formal Education into the PPE level and the education system as a whole, the policy statements lack proper follow up and coherence. This is a contrast to government’s commitment to international protocols and proclamations on EFA – a position that would have seen NFE clearly streamlined in the entire education system. 3. Despite the lack of a policy framework to direct Non-Formal Education at PPE level, a number of advancements in terms of policies have been made. These include the draft Education Bill for educationally disadvantaged children at primary level and the adoption of a modularized curriculum for Community Polytechnics. These advancements however have not come easy as government has over time backtracked on the issue of Non-Formal Education particularly at PPE level. 4. Notable challenges still facing Non-Formal Education in Uganda include lack of specialized training for trainers, limited funding for the education sector which renders NFE a none priority and lack of policy framework to regulate and inform NFE as an alternative route to PPE in the country among others.
KerkoCite.ItemAlsoKnownAs: 2129771:EA9BUVQ7 2317526:UGSJKI92
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; Q:PhD; Q:community education; Q:primary education; T:TVET; T:company-based training; _C:Uganda UGA; publicImportV1; ⛔ No DOI found

Mapping education data in sub-Saharan Africa: Our experience from the Unlocking Data campaign and Sierra Leone - Unlocking Data (2021)
KerkoCite.ItemAlsoKnownAs: 2129771:IVNL5DT5 2339240:HAKTFJKU 2405685:YPE9D2W3
Keywords: _C:Sierra Leone SLE

Mainstreaming an Effective Intervention: Evidence from Randomized Evaluations of “Teaching at the Right Level” in India - Banerjee, Abhijit; Banerji, Rukmini; Berry, James; Duflo, Esther; Kannan, Harini; Mukherji, Shobhini; Shotland, Marc; Walton, Michael (National Bureau of Economic Research, 2016)
Previous randomized studies have shown that addressing children’s current learning gaps, rather than following an over-ambitious uniform curriculum, can lead to significant learning gains. In this study, we evaluate a series of efforts to scale up the NGO Pratham’s approach to teaching children according to their actual learning level, in four Indian States. While this approach was previously shown to be extremely effective when implemented with community volunteers outside of school, the objective of these new scale-up evaluations was to develop a model that could be implemented within the government school system. In the first two instances (Bihar and Uttarakhand), the methodology was not adopted by government schoolteachers, despite well-received training sessions and Pratham support. Motivated by the quantitative and qualitative analysis of these early attempts, we adapted the approach and designed large-scale experiments in the states of Haryana and Uttar Pradesh to test two new scale-up models. In Haryana, teachers received support from government resource persons trained by Pratham, and implemented the approach during a dedicated hour. In Uttar Pradesh, Pratham volunteers implemented high-intensity, short-burst “learning camps” for 40 days, in school and during school hours, with additional 10-day summer camps. Both models proved effective, with gains in language of 0.15 standard deviation in Haryana, and 0.70 standard deviations in Uttar Pradesh, on all students enrolled in these schools at baseline. These two models provide blueprints that can be replicated inside other government systems.
Series: Working Paper Series KerkoCite.ItemAlsoKnownAs: 10.3386/w22746 2129771:4SI8CL4K 2129771:IJ484UVX 2129771:JP65D9ZN 2129771:QHBP9EXP 2129771:WAVMVLKN 2405685:LEGZTSPV 2486141:KZKGLZ26
Keywords: C:India; _C:Ghana GHA; _C:India IND; _C:Kenya KEN; _C:Nepal NPL; _C:Pakistan PAK; _C:Tanzania TZA; _C:Uganda UGA; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Local community training and education in southern Tanzania—a case study - Howe, Vicki (Marine Policy, 2001)
Abstract Local coastal communities are highly dependent upon the marine environment not only for protein but also as a primary source of income. In addition, there are growing economic opportunities offered within the coastal zone. As populations increase in these areas there is an increasing demand on coastal resources. This in turn requires effective management initiatives at regional, national and local levels.The Marine Education and Training Programme in Mtwara, southern Tanzania was a small scale capacity building project that incorporated two elements; a primary schools field day education programme and a marine coastal resources course for fishermen and women from the Mtwara District. The programme ran for a period of 1year and during that time 14 schools, 198 children, 34 fishermen, 2 women and 14 villages participated. Results from preliminary evaluation indicated that such education is not only welcome by the local government offices, teachers, village chairmen and fishermen as an expansion of the knowledge base, but is also an important and valuable stepping stone for the local communities to become active in issues regarding the management of coastal resources.
KerkoCite.ItemAlsoKnownAs: 10.1016/s0308-597x(01)00029-x 10/bkddg8 2129771:8F3ZUDIB 2317526:I83Z95UT
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Tanzania; CA:AandC; CCZ:Tanzania; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:women; P:economy; P:environment; P:teachers; R:case study; R:evaluation; T:Training; Z:Capacity building; Z:East Africa; Z:Local community; Z:Marine environmental education; publicImportV1

Loans and Scholarships in Africa’s Higher Education Finance: A Comparative Analysis of Capitation, Policy and Recoveries in Eleven Countries - Chirwa, Ireen Nayame; Masaiti, Gift; Mwale, Nelly; Mkandawire, Sitwe Benson; Mulenga, Innocent Mutale; Sichula, Noah Kenny (British Journal of Education, 2022)
Publisher: European-American Journals

Loans and scholarships in Africa’s higher education finance: a comparative analysis of capitation, policy and recoveries in eleven countries. - Nayame-Chirwa, Ireen; Masaiti, Gift; Mwale, Nelly; Mkandawire, Sitwe Benson; Mulenga, Innocent Mutale; Sichula, Noah Kenny (2022)
Publisher: British Journal of Education, 10 (16), 67-88
Keywords: ⛔ No DOI found

LIS curriculum in French-speaking West Africa in the age of ICTs: The case of Benin and Senegal - Mêgnigbêto, Eustache (The International Information & Library Review, 2007)
Summary LIS training programme in Africa date from early independence period. In French-speaking West African area, few countries have an LIS school. The existing schools have been created in partnership with either an international organization or a northern country. The curriculum delivered is not always updated as in developed countries. The main objective of this article is to measure the gap between LIS curriculum as actually delivered in developed and developing countries in the age of the information and communication technologies (ICTs). A couple of schools were chosen—English and French-speaking area—from Northern America and Western Europe; their curriculum served as basis for evaluating those in West African French-speaking countries. The conclusion that can be drawn from the study is that LIS curriculum in Africa has changed less since the schools’ first creation and ICTs are not present as in Western countries. This trend brings out the problem of the curriculum pertinence and the competitiveness of the graduate students in the international employment market.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.iilr.2007.02.007 10/d26vb2 2129771:E4284BH5 2317526:8MLC73K9
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:West Africa; C:Benin; C:Senegal; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:Q; CT:T; D:developing country; F:curriculum; Q:ICT; SpecialTopic:Library; T:Training; publicImportV1

Linking vocational education and training (VET) progression pathways into the academic route in Tanzania: Case study in electrical and mechanical engineering programmes at Arusha technical college (ATC) - Augustine, S. Mbitila; Richard, J. Masika; Donatha, E. Mwase (International Journal of Vocational and Technical Education, 2017)
The bridging course was designed by the Vocational and Education Training Authority (VETA) in collaboration with three technical Colleges/Institutions: Arusha Technical College, Dar es Salaam Institute of Technology and Mbeya University of Science and Technology under the auspices of National Council for Technical Education (NACTE). The course was an immediate solution to the missing link between the Vocational Education and Training (VET) pathway for graduates and the Tanzanian national education model. Data were collected from a random sample of 350 students, from various parts of the country, to analyze the problem. Comparison tests of performance between students from the bridging course and from other educational routes were conducted. Results demonstrate that, the bridging course is a substantive solution to enabling VET students to progress toward further studies. Bridging courses in Technical Colleges and Institutes of Technology offer a valuable contribution to the vocational training sector if sponsored by both Government and Private sector in terms of fiscal and non-fiscal resources.
KerkoCite.ItemAlsoKnownAs: 2129771:EY27CPFF 2317526:Y8BZ57SA UTI-6E2C391A-E3E5-330F-AE6F-A8A33CEC6B33
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:electro; P:mechanic; R:case study; T:TVET; T:Training; T:vocational training centre; __C:filed:1; publicImportV1; ⛔ No DOI found

Linking informal apprenticeship and formal education in South-Eastern Nigeria through market/mechanic village schools - Ogwo, Benjamin (2013)
The Nigerian government as well as international agencies have implemented several informal apprenticeship intervention programmes aimed at improving productivity, trade union leadership and literacy/numeracy of practitioners. One of such interventions is the Education Trust Fund (ETF) intervention in boy-child education within south-eastern Nigeria established by UNICEF. This paper highlights the process, nature, and scope of the ETF intervention in relation to informal apprenticeships. As research meth9odology, the research & development (R&D) design was used for the study. Among other outcomes, the UNICEF market/mechanic village school curriculum was modified using open-learning principles by informal apprenticeship. School is taken to the apprentices rather than the apprentices to school by incorporating formal education into informal apprenticeship thus ensuring certification and enhanced social status for informal apprenticeship graduates.
KerkoCite.ItemAlsoKnownAs: 2129771:UTQZWLF3 2317526:P4HA5X54
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:curriculum; P:mechanic; P:social; Q:certificate; Q:e-learning; R:survey; T:Formal apprenticeship; T:Lehrlingsausbildung; publicImportV1

Lifelong learning, lifelong education and adult education in higher institutions of learning in Eastern Africa: The case of Makerere University Institute of Adult and Continuing Education - Openjuru, , G.L. (International Journal of Lifelong Education, 2011)
This paper advocates for policy recognition of lifelong learning by institutions of higher learning and governments in Eastern Africa. Lifelong learning and lifelong education are two concepts that aim at widening access to and the participation of adult learners in the acquisition of new knowledge, skills, values and attitudes. There are many reasons for advocating for lifelong learning and education in higher institutions of learning in Eastern Africa. Firstly, the demand for higher education in Eastern Africa has increased phenomenally. Secondly, the need to cope with this fast-changing world calls for a continuous acquisition of new knowledge, skills and attitude. This paper looks at the concepts of lifelong learning (LLL) and lifelong education (LLE) in relation to the changes that are affecting the provision of universitybased learning opportunities for non-traditional students in Eastern Africa, with examples from Makerere University Institute of Adult and Continuing Education in Uganda. In looking at the concepts of LLL and LLE, other concepts of lifewide learning and the learning society are also discussed. Adult learning and adult education are discussed as concepts that are used by adult educators in Eastern Africa with very limited understanding of what they really mean. The confusion in the use of these emerging and popular concepts in Eastern Africa is discussed. The paper presents some recommendations for higher institutions of learning in Eastern Africa to develop a clear understanding of and embrace lifelong learning. © 2011 Taylor & Francis.
KerkoCite.ItemAlsoKnownAs: 10.1080/02601370.2011.538182 10/cfzbzf 2129771:KVUATX45 2317526:GKNW4U5H
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:eastern Africa; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; F:attitude; F:learning; F:policy; F:teaching; P:measurement; P:teachers; Q:adult education; Q:distance education; Q:higher education; Q:lifelong learning; R:case study; T:continuing education; Z:Adult Education; Z:Adult Educators; Z:Adult Learning; Z:Adult Students; Z:Adult education; Z:African Studies; Z:Case Studies; Z:Concept Teaching; Z:Continuing Education; Z:Continuing education; Z:Definitions; Z:Distance Education; Z:Distance education; Z:Educational Opportunities; Z:Expansion of provision; Z:Foreign Countries; Z:Higher education; Z:Institutional Characteristics; Z:Knowledge; Z:Lifelong Learning; Z:Lifelong learning; Z:Nontraditional Students; Z:Teachers; _C:Uganda UGA; publicImportV1

Lessons learnt from informal apprenticeship initiatives in Southern and Eastern Africa - Aggarwal, A (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:2NAGN4HC 2317526:AEINLRYL
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:eastern Africa; C:Malawi; C:Tanzania; C:Zambia; C:Zimbabwe; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; HDR25; T:Lehrlingsausbildung; publicImportV1; ⛔ No DOI found

Lessons from the Covid-19 Pandemic: Can Public Primary and Secondary Schools in Lusaka District of Zambia use Blended and Distance Teaching and Learning? - Mulenga, Innocent Mutale; Siluma, V. (Zambia Journal of Distance Education, 2021)
Keywords: ⛔ No DOI found

Lessons for developing countries from experience with technical and vocational education and training - Kingombe, Christian (Economic Challenges and Policy Issues in Early Twenty-First-Century Sierra Leone, 2011)
The literacy requirements of both globalization and technological change necessitate enhancement of literacy education and training to keep pace with these phenomena. Sierra Leone‘s An Agenda for Change – Second Poverty Reduction Strategy (PRSPII) 2008-2012 has mainstreamed youth employment and the government has developed a National Action Plan on Youth Employment. Moreover, TVET in Sierra Leone needs a new focus and new direction to strongly respond to the PRSP. In fact a national harmonized policy for TVET is required for a national curriculum. Hitherto, the development and implementation of TVET reform programmes has been severely hampered by budgetary constraints in all 16 countries in the ECOWAS. Based on frontier research on the lessons learned from recent TVET reforms in other developing countries, this paper aims to inform the future comprehensive design and implementation of strategies for TVET in Sierra Leone . The paper makes suggestions for how to address future challenges and opportunities to ensure that the good performance of TVET reforms contribute to the promotion of sustainable growth through private sector development. The paper is structured as follows. Section 2 provides a stock taking of the available quantitative evidence on the impact of TVET. Section 3 presents and discusses different institutional and strategic TVET frameworks. Section 4 discusses the importance of a demand-oriented TVET system. Section 5 discusses the various existing and potential sources for the financing of the TVET system. Section 6 pres ents various examples of successful external cooperation on TVET projects in Africa and Asia. Finally, section 7 concludes and presents policy options.
KerkoCite.ItemAlsoKnownAs: 2129771:P729X3LJ 2317526:ZGB6R7BP
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Sierra Leone; CA:AandC; CC:Sierra Leone; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:T; D:developing country; Education / Educational Policy & Reform / General; F:learning; F:policy; P:economy; P:measurement; P:teachers; Q:certificate; Q:community education; Q:distance learning; Q:primary education; Q:secondary education; T:Lehrlingsausbildung; T:TVET; _C:Sierra Leone SLE; publicImportV1; ⛔ No DOI found

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:V7V2FSG3 2405685:9PJP3ZYU
Keywords: _C:Sierra Leone SLE

Leh Wi Lan: Improving The Quality Of Secondary Education In Sierra Leone - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:M45ESUCB 2405685:Y7RFFB9I
Keywords: _C:Sierra Leone SLE

Learning the master's trade: Apprenticeship and human capital in Ghana - Frazer, Garth; Frazer, Garth (Journal of Development Economics, 2006)
This paper explores the institution of apprenticeship in Ghana. A model is presented where apprenticeship training is idiosyncratic, increasing an individual's productivity in the current firm, but not in any other firm. Still, individuals are willing to fund apprenticeships as they can reap the returns to the specific training of apprenticeship if they manage to acquire the capital required to start their own firms, and replicate the technology and business practice of the apprenticeship firm. Predictions of the model for the productivity and remuneration of different workers are developed and tested using both a linked employer-employee survey of manufacturing firms and a national household survey. © 2006 Elsevier B.V. All rights reserved.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2005.06.006 10/dmcqmr 2129771:3SI4ZNWZ 2317526:FE8I5WXW
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:remuneration; P:manufacture; P:technology; Q:masters; R:survey; T:Lehrlingsausbildung; T:Training; T:apprenticeship training; Z:Apprenticeship; Z:Human capital; _C:Ghana GHA; publicImportV1

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2129771:RHCG2CAA 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7
Keywords: _C:Sierra Leone SLE; _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Learner orientation through professional development of teachers? Empirical results from cascade training in Anglophone Cameroon - Lange, Sarah (Compare: A Journal of Comparative and International Education, 2014)
KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2013.841027 10/gfvv7x 2129771:95VP3EV5 2129771:E4373A25 2317526:8DZUAC7R
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Cameroon; CA:AandC; CCZ:Cameroon; CL:en; CL:fr; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:low-income country; F:attitude; F:learning; F:teaching; P:measurement; P:service industry; P:teacher training; P:teachers; R:quantitative; T:Ausbildung; T:trainee; T:work-based learning; Z:cascade training; Z:learner orientation; Z:professional development; Z:sub-Saharan Africa; Z:teachers; publicImportV1

Learner-centred education in developing country contexts: From solution to problem? - Schweisfurth, Michele (International Journal of Educational Development, 2011)
Learner-centred education (LCE) has been a recurrent theme in many national education policies in the global South, and has had wide donor support through aid programmes and smaller projects and localised innovations. However, the history of the implementation of LCE in different contexts is riddled with stories of failures grand and small. In coming to understand how LCE has been conceived, researched, and reported in relation to developing country contexts, a good starting point is the International Journal of Educational Development (IJED), where a wide range of articles on this theme has been published over the years. In all, 72 relevant articles were identified among the issues available on-line, comprising a weighty body of evidence concerning the nature and implementation of LCE. The vast majority are studies exploring the issues – and problems – of implementation of LCE-based programmes in particular settings. Emerging from these investigations is a variety of explanations for this perennial challenge: problems with the nature of reform and its implementation; barriers of material and human resources; interactions of divergent cultures; and the all-important questions of power and agency in the process. After a descriptive breakdown of the 72 articles, each of these implementation issues is explored in turn. The article considers the implications of this for future initiatives, research and scholarship in this area. The begged questions are: why do the same problems recur repeatedly, and how do we move beyond the normative ‘shoulds’ and the practical ‘can’ts’?
EdTechHub.Source: 261495:XXWTECRZ KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2011.03.005 10/cnfz43 2129771:EC9IQLP9 2129771:MRVKFR4A 2405685:LDEHPJCR 261495:MFFSFUSR 261495:XXWTECRZ
Keywords: _C:Barbados BRB; _C:Botswana BWA; _C:Brunei Darussalam BRN; _C:Canada CAN; _C:China CHN; _C:Eritrea ERI; _C:Gambia GMB; _C:Ghana GHA; _C:Guinea-Bissau GNB; _C:India IND; _C:Indonesia IDN; _C:Jordan JOR; _C:Kenya KEN; _C:Lesotho LSO; _C:Malawi MWI; _C:Mexico MEX; _C:Namibia NAM; _C:Nigeria NGA; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Peru PER; _C:Poland POL; _C:Russian Federation RUS; _C:Saudi Arabia SAU; _C:Sierra Leone SLE; _C:Solomon Islands SLB; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Syrian Arab Republic SYR; _C:Tanzania TZA; _C:Trinidad and Tobago TTO; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

Leadership development for technical and vocational education and training college leaders in South Africa: A post-graduate curriculum framework - Robertson, Catherine A; Du Plessis, CA (2015)
ENGLISH ABSTRACT: The South African public technical and vocational education and training (TVET) colleges have experienced considerable change in the past 20 years. Recently, these colleges have become the focal point of education and training, ever since the publication of the Green Paper on Post-School Education and Training in 2012, transferring the colleges to the higher education and training system. These colleges are expected to increase their enrolments from 650 000 to 2.5 million by 2030. Leaders in these institutions have been faced with constant challenges in a rapidly changing environment. It has been internationally acknowledged that in order for leaders at all levels of vocational education and training institutions to be capable of and effective in transforming their institutions, leadership development is essential. Even though a leadership development programme was advocated in the Green Paper on Further Education and Training in South Africa (RSA, 2012), this training was not mentioned specifically in the subsequent White Paper (RSA, 2014). This lack of leadership development prioritisation of leaders in this sector differs from governments in other countries where customised leadership development in this complex sector has not only been prioritised but has become a matter of urgency. The purpose of this study was thus to develop a leadership development curriculum framework specifically for leaders, present and future, of public TVET colleges in South Africa. These colleges have also been examined as activity systems with their cultural and historical influences, according to Engeström’s (1987) version of activity theory. Through interactive qualitative analysis (IQA), an interpretive methodology grounded in systems theory (Northcutt & McCoy, 2004) which uses an interpretive approach by means of focus group and individual interviews with different constituency populations, an attempt was made to gain an understanding of what challenges these college leaders face and what knowledge, skills, attributes and attitudes they may need to achieve the mandate of the White Paper (RSA, 2014). AFRIKAANSE OPSOMMING: Die openbare tegniese en beroepsgerigte onderwys-en-opleidingskolleges in Suid-Afrika het die afgelope 20 jaar groot veranderings ervaar. Hierdie kolleges het onlangs die hoof-fokuspunt van onderwys en opleiding geword vandat die Groenskrif vir Na-skoolse Onderwys en Opleiding in 2012 gepubliseer is, wat die kolleges verskuif het na die hoër onderwys-en-opleidingstelsel met die verwagting om teen 2030 inskrywings van 650 000 tot 2.5 miljoen te vermeerder. Leiers in hierdie instellings ondervind voortdurende uitdagings in ’n vinnig-veranderende omgewing. Daar word internasionaal erken dat om leiers op alle vlakke by beroepsgerigte onderwys-en-opleidingsinstellings in staat te stel om hierdie instellings effektief te transformeer, leierskapontwikkeling essensieel is. Al word leierskapontwikkeling in die Groenskrif vir Na-skoolse Onderwys en Opleiding voorgestel, word daar nie vir hierdie opleiding in die daaropvolgende Witskrif (2014) voorsiening gemaak nie, wat verskil van die optrede van regerings in ander lande wat leierskapsontwikkeling in hierdie komplekse sektor prioritiseer. Gepaste leierskapskwalifikasies en -programme is oral ter wêreld vir leiers in dié sektor beskikbaar, maar nie in Suid-Afrika nie. Hierdie kolleges is ook as aktiwiteitstelsels ondersoek en daardeur is ’n analise van die kulturele en historiese invloede gemaak volgens Engeström (1987) se weergawe van Aktiwiteitsteorie. Die doel van hierdie studie was dus om ’n leierskapkurrikulumraamwerk vir huidige en toekomstige leiers van openbare tegniese en beroepsgerigte onderwys-en-opleidingskolleges in Suid-Afrika te ontwikkel. Deur interaktiewe kwalitatiewe analise, ’n interpretatiewe metodologie wat sy basis in stelselsteorie het (Northcutt & McCoy, 2004) en wat ’n interpretatiewe benadering toepas, is daar gepoog om deur middel van fokusgroep- en individuele onderhoude vas te stel wat leiers in die sektor glo in so ’n kurrikulumraamwerk ingesluit moet word, sodat die mandaat van die Witskrif (RSA, 2014) uitgeoefen kan word.
KerkoCite.ItemAlsoKnownAs: 2129771:HQTXPUGS 2317526:DKF7G2VI UTI-CACA454E-39E3-3CEB-BAB8-A2EFFDF58548
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:T; F:curriculum; F:leadership; T:TVET; publicImportV1; ⛔ No DOI found

Le renforcement de la formation technique et l’industrialisation en Afrique subsaharienne : le cas du Gabon - Moussone, Emmanuel; Metougue Nang, Prosper (Marché et organisations, 2018)
The objective of this article is to analyze the relationship between the technical training, the skills and the setting up or development of various industries in a developing country by focussing on Gabon. The issues addressed are diverse and varied and more particularly, they relate to the contribution of technical training to the progress of industry and techniques, to the conditions of and needs for economic and social development and finally to innovation, a thread by which all those elements are interconnected. The study shows that the post-colonial economic processes of income and cooperation set up since the independences did not allow for a long time to further on the one hand true skills transfers and one the other hand the setting up of industries. Now, in the face of the current changes in the international environment, the technical training appears as a sufficient condition for acquiring skills essential to the appropriation of innovations and the setting up of industries.
KerkoCite.ItemAlsoKnownAs: 10.3917/maorg.032.0153 10/gf62xr 2129771:HRRLBPVW 2317526:IEVXZ7GJ 2317526:ZHSJXMW3 UTI-26D9E3E9-03B0-3044-ABFC-35627CE2E7BE
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; -RRQv:f2-H-fr; A:Sub-Saharan Africa; C:Gabon; CA:AandC; CL:en; CL:fr; CLL:fr; CLS:en; CT:A; CT:C; CT:D; CT:T; D:developing nation; T:Training; publicImportV1

La Tablet en la escuela: Revisión bibliográfica en Scopus - Rodríguez, María Montserrat Castro; Suárez, Óscar Mallón (Hamut\' ay, 2019)
KerkoCite.ItemAlsoKnownAs: 10.21503/hamu.v6i1.1579 10/gf62gd 2129771:6WIRJVSN 2129771:NY65TXXB 2129771:TCZDYJM9 2129771:VC8RK2UT
Keywords: _C:Australia AUS; _C:China CHN; _C:Costa Rica CRI; _C:Ghana GHA; _C:Guatemala GTM; _C:India IND; _C:Norway NOR; _C:Spain ESP; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; literature / systematic review

La recherche sur les competences techniques et professionnelles permettant l'insertion - etat des lieux, contraintes et perspectives dans trois pays de l'afrique de l'ouest - Azoh, François-Joseph; Weyer, Frédérique; Carton, Michel (NORRAG; ROCARE, 2012)
[FRGMNT] On assiste en Afrique à un regain d'intérêt pour la question du développement des compétences techniques et professionnelles (DCTP). L'existence de données et d'analyses fiables sur ce thème représente néanmoins un préalable indispensable à la définition et à la …[...]… CAP Certificat d'Aptitude Professionnelle CBL Competency Based Learning CBT Competency Based Training CCI Chambre de Commerce et d'Industrie CEBNF Centre d'Education de Base Non Formelle CEPE Certificat d'Etude Primaire Elémentaire … [...]… COTVET Council for Technical and Vocational Education and Training CPAF Centre Permanent d'Alphabétisation Fonctionnelle … NACVET National Coordinating Committee on Technical and Vocational Education and Training … [...]Page 1. LA RECHERCHE SUR LES COMPETENCES TECHNIQUES ET PROFESSIONNELLES PERMETTANT L'INSERTION ETAT DES LIEUX, CONTRAINTES ET PERSPECTIVES DANS TROIS PAYS DE L'AFRIQUE DE L'OUEST (Burkina Faso, Côte d'Ivoire et Ghana) …
KerkoCite.ItemAlsoKnownAs: 2129771:RSBEIDQR 2317526:AVQL6L32 2317526:JLIAVL84
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQv:f2-H-fr; A:Africa; A:West Africa; C:Burkina Faso; C:Ivory Coast; CA:AandC; CC:Burkina Faso; CC:Ghana; CC:Ivory Coast; CL:en; CL:fr; CLL:fr; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:pay; Q:certificate; T:Ausbildung; T:TVET; _C:Ghana GHA; publicImportV1

La formation professionnelle en secteur informel - ou Comment dynamiser l’économie des pays en développement? Les conclusions d’une enquête terrain dans sept pays africains. - Walther, Richard; Filipiak, Ewa (Agence Française de Développmement, 2007)
KerkoCite.ItemAlsoKnownAs: 2129771:2RLDNXMH 2317526:DEESIG58
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQv:f2-H-fr; C:Angola; C:Benin; C:Cameroun; C:Ethiopia; C:Morocco; C:Senegal; CLL:fr; publicImportV1

L’EFTP en Afrique subsaharienne: où en est-on? - Ginestié, Jacques; Huot-Marchand, Hervé; Delahaies, Laetitia (Éducation technologique, Formation professionnelle et égalité des chances, 2012)
The adoption of the Millennium Development Goals (MDGs) and the importance attached to Education for all (EFA) mark an important turning point in the elaboration of a common initiative, which aims to improve living conditions of people worldwide. Its ambition is to eliminate misery and to increase wealth. The means to achieve this goal focus essentially on education, which has become a goal in itself: reduce illiteracy, ensure global access to basic schooling and promote equal opportunities for all. Through education other objectives can be targeted, such as promoting poverty reduction through gainful employment, gender equality, and sustainable development and partnerships for development. This paper aims to present the situation in subSaharan Africa (SSA) since the end of the 1990s and the international focus on these great programs.
KerkoCite.ItemAlsoKnownAs: 2129771:SZZY8H6R 2317526:5UCZSLLA 2317526:G7T7NRYJ
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; -RRQv:f2-H-fr; AA:SSA; C:Central African Republic; C:Gabon; C:Ivory Coast; C:Senegal; C:Tunisia; CLL:fr; publicImportV1; ⛔ No DOI found

Knowledge Production in the Knowledge Economy: Higher Education Institutions and the Application of Innovations in ICT for Capacity Development in Africa - Evoh, CJ; Mugimu, Christopher; Chavula, Hopestone (2014)
[FRGMNT] … 16.7 101.6 34.1 6 6.1 0 20 40 60 80 100 120 Pre-primary Primary secondary TVET Tertiary Fig. 1. Education Access in Sub-Saharan Africa (% GER), 2011. Sources: Nsapato, Limbani (2012). Knowledge Production in the Knowledge Economy 295 Page 12 … [...]… RESEARCH METHODOLOGY Data for the study was gathered through qualitative research method, and theory-driven multiple case study approach was adopted (Yin, 2004) to examine the higher education system in Kenya and Uganda (East Africa) … [...]… Data for the study was gathered through qualitative research method, and theory-driven multiple case study approach was adopted (Yin, 2004) to examine the higher education system in Kenya and Uganda (East Africa) … 120 Pre-primary Primary secondary TVET Tertiary Fig …
KerkoCite.ItemAlsoKnownAs: 2129771:VZPVMDHI 2317526:52LF3UGR
Keywords: -FullBiblioUHMLgen; -RRQ:LOW; A:Africa; A:East Africa; A:Sub-Saharan Africa; C:Kenya; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; P:economy; P:measurement; P:production; Q:ICT; Q:higher education; R:case study; R:qualitative; R:research method; T:TVET; _C:Uganda UGA; publicImportV1; ⛔ No DOI found

Keyword inventory - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoé; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
EdTechHub.Source: 2405685:LSEETV6K KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:LSEETV6K
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; _C:Abkhazia XABKH; _C:Afghanistan AFG; _C:Albania ALB; _C:Algeria DZA; _C:Andorra AND; _C:Angola AGO; _C:Antigua and Barbuda ATG; _C:Argentina ARG; _C:Armenia ARM; _C:Artsakh XARTH; _C:Australia AUS; _C:Austria AUT; _C:Azerbaijan AZE; _C:Bahamas BHS; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Barbados BRB; _C:Belarus BLR; _C:Belgium BEL; _C:Belize BLZ; _C:Benin BEN; _C:Bhutan BTN; _C:Bolivia BOL; _C:Bosnia and Herzegovina BIH; _C:Botswana BWA; _C:Brazil BRA; _C:Brunei Darussalam BRN; _C:Bulgaria BGR; _C:Burkina Faso BFA; _C:Burundi BDI; _C:Cambodia KHM; _C:Cameroon CMR; _C:Canada CAN; _C:Cape Verde CPV; _C:Catalan Republic XCATA; _C:Central African Republic CAF; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:Comoros COM; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Congo; Republic COG; _C:Costa Rica CRI; _C:Croatia HRV; _C:Cuba CUB; _C:Cyprus CYP; _C:Czech Republic CZE; _C:Denmark DNK; _C:Djibouti DJI; _C:Dominica DMA; _C:Dominican Republic DOM; _C:Ecuador ECU; _C:Egypt EGY; _C:El Salvador SLV; _C:Equatorial Guinea GNQ; _C:Eritrea ERI; _C:Estonia EST; _C:Ethiopia ETH; _C:Federated States of Micronesia FSM; _C:Fiji FJI; _C:Finland FIN; _C:France FRA; _C:Gabon GAB; _C:Gambia GMB; _C:Georgia GEO; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Grenada GRD; _C:Guatemala GTM; _C:Guinea GIN; _C:Guinea-Bissau GNB; _C:Guyana GUY; _C:Haiti HTI; _C:Holy See VAT; _C:Honduras HND; _C:Hungary HUN; _C:Iceland ISL; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Ivory Coast CIV; _C:Jamaica JAM; _C:Japan JPN; _C:Jordan JOR; _C:Kazakhstan KAZ; _C:Kenya KEN; _C:Kiribati KIR; _C:Korea XKOR

Kenya National Qualifications Framework Act Nº 22 - Government of Kenya (2014)
AN ACT of Parliament to establish the Kenya National Qualifications Authority; to provide for the development of a Kenya Qualifications Framework and for connected purposes
UA-c7caea3d-31e5-4518-894a-f2a923cf3c88 KerkoCite.ItemAlsoKnownAs: 2129771:YYI2DH67 2317526:L8PU5BJQ
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; Qualification Framework; publicImportV1

Junior Secondary I, III, III Mathematics (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745246 2129771:IULPJ2QQ
Keywords: SSEIP; _C:Sierra Leone SLE

Junior Secondary I, II, III English (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745244 2129771:PS5RG5JA
Keywords: SSEIP; _C:Sierra Leone SLE

Jika iMfundo: a South African study of ‘turning education around’through improved curriculum coverage - Pillay, Venitha (Professional Development in Education, 2020)
Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2018.1550101 2129771:BVYHJ2A6 2129771:NX2LQYTG
Keywords: _C:Australia AUS; _C:Cameroon CMR; _C:Ethiopia ETH; _C:South Africa ZAF; _C:Tanzania TZA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

It takes a village to raise a teacher: the Learning Assistant programme in Sierra Leone - Crisp, Martin; Safford, Kimberly; Wolfenden, Freda (The Open University and Plan International, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:4ZWNMP4P 2129771:I3GR9GBM 2129771:L8VCNB4Z 2405685:I76Z2SKV 2486141:RP5DXILU 2601447:DGAXJQFN 4556019:F5RJQZKR
Keywords: _C:Sierra Leone SLE

Is there learning continuity during the COVID-19 pandemic? Six Lessons - McBurnie, Chris; Haßler, Björn (2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3930934 2129771:A4N8WK7U
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; ___duplicate_item; _r:ImportedToMyEducationEvidence

Is indoor environmental quality in my school classroom safe? - Warwocki, Pawel (Open Development & Education, 2023)
How can we monitor indoor environmental quality without access to sophisticated measurement instruments? This blog highlights simple methods for checking classroom environmental quality. The methods cannot replace the processes of taking actual measurements and monitoring, or ensure that classrooms meet code requirements; they will, however, help identify particular problems and indicate actions that can be taken to avoid them. The end of the blog includes a table of the actions described and a simple survey that can be used with schoolchildren. An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10079928 ZenodoArchiveConcept: 10079927 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1028 2129771:F6PT9SPQ
Keywords: _r:AddedByMyEducationEvidence

Is farmer-to-farmer extension effective? The impact of training on technology adoption and rice farming productivity in Tanzania - Nakano, Yuko; Tsusaka, Takuji W.; Aida, Takeshi; Pede, Valerien O. (World Development, 2018)
Abstract Agricultural training is a potentially effective method to diffuse relevant new technologies to increase productivity and alleviate rural poverty in Sub-Saharan Africa (SSA). However, since it is prohibitively expensive to provide direct training to all the farmers in SSA, it is critically important to examine the extent to which technologies taught to a small number of farmers disseminate to non-trained farmers. This paper investigates the technology dissemination pathways among smallholder rice producers within a rural irrigation scheme in Tanzania. As an innovative feature, we compare the performance of three categories of farmers: key farmers, who receive intensive pre-season training at a local training center; intermediate farmers, who are trained by the key farmers; and other ordinary farmers. By collecting and analyzing a unique five-year household-level panel data set, we estimate difference-in-differences models to assess how the gap in performance evolve as the technologies spill over from the trained farmers to the ordinary farmers. To disentangle the technology spillover process, we also examine the extent to which social and geographical network with the key and intermediate farmers influences the adoption of technologies by the ordinary farmers, by incorporating social relationship variables into spatial econometric models. We found that the ordinary farmers who were a relative or residential neighbor of a key or intermediate farmer were more likely to adopt new technologies than those who were not. As a result, while the key farmers’ technology adoption rates rose immediately after the training, those of the non-trained ordinary farmers caught up belatedly. As the technologies disseminated, the paddy yield of the key farmers increased from 3.1 to 5.3 tons per hectare, while the yield of the ordinary farmers increased from 2.6 to 3.7 tons per hectare. Our results suggest the effectiveness and practical potential of farmer-to-farmer extension programs for smallholders in SSA as a cost effective alternative to the conventional farmer training approach.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2017.12.013 10/gf62mx 2129771:WC9P2ZP8 2317526:95UDVN5X
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CCZ:Tanzania; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:learning; P:agricultural; P:economy; P:measurement; P:social; P:technology; R:impact; T:Training; T:trainee; Z:Agricultural training; Z:Rice cultivation; Z:Social learning; Z:Sub-Saharan Africa; Z:Technology adoption; publicImportV1

Investigating the Barriers to Teachers’ Professional Development in an EFL Context - Soodmand Afshar, Hassan; Ghasemi, Shabnam (Journal of Modern Research in English Language Studies, 2020)
Publisher: Imam Khomeini International University KerkoCite.ItemAlsoKnownAs: 2129771:S37LDJFA
Keywords: _C:China CHN; _C:Iran IRN; _C:Israel ISR; _C:Lesotho LSO; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Introduction to Professional Development (Tutors) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
EdTechHub.ItemAlsoKnownAs: 2129771:5TJPNZXE
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Introduction to Professional Development (Coordinators) - Haßler, Björn (Transforming Teacher Education and Learning, Ministry of Education (Ghana), 2015)
EdTechHub.ItemAlsoKnownAs: 2129771:BTAVK4XM
Keywords: Author:Haßler; Author:OpenDevEd; _r:ImportedToMyEducationEvidence

Introducing the next iteration of our sensor box - Haßler, Björn; Bablok, Bernhard (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10456801 ZenodoArchiveConcept: 10456800 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1064 2129771:FNTQ646H
Keywords: _r:AddedByMyEducationEvidence

International Handbook of Education for the Changing World of Work: Bridging Academic and Vocational Learning - Maclean, Rupert; Wilson, David (Springer Science & Business Media, 2009)
The aim of this Handbook is to review the developments that have occurred in Technical and vocational education and training (TVET) and that may help improve the field. The Handbook provides information on TVET models that occur in different parts of the world; reflects best and innovative practice; and, wherever possible, uses case studies as examples. The 220 authors are representative of the various regions of the world and major international organisations involved in TVET. This volume presents the work of established researchers as well as the work of promising young researchers. Intended as the universally-accepted resource for the field, the Handbook provides a comprehensive coverage of cutting edge developments in research, policy and practice in TVET within a single source. It will assist those involved in TVET at any level in making informed decisions and further advance and improve the field and to bridge the gap between vocational and academic education in the 21st century.
KerkoCite.ItemAlsoKnownAs: 2129771:A8GV4XU8 2317526:PQDLDLV5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:SSA; A:West Africa; C:South Africa; CLL:en; Education / Adult & Continuing Education; Education / Counseling / Career Development; Education / Vocational; _C:Ghana GHA; publicImportV1

Interactive apps promote learning of basic mathematics in children with special educational needs and disabilities - Pitchford, Nicola J.; Kamchedzera, Elizabeth; Hubber, Paula J.; Chigeda, Antonie L. (Frontiers in psychology, 2018)
00000 KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2018.00262 10/gc7b8q 2129771:CI5TENAJ 2129771:CJ2M5WC2
Keywords: _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Malawi MWI; _C:Spain ESP; _C:United Kingdom GBR; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Interactive apps prevent gender discrepancies in early grade mathematics in a low-income country in Sub-Sahara Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1111/desc.12864 10/gf62gt 2129771:DMDYK6Z2 2129771:VXRGS3KV
Keywords: _C:Belgium BEL; _C:France FRA; _C:Kenya KEN; _C:Malawi MWI; _C:Myanmar MMR; _C:Netherlands NLD; _C:Seychelles SYC; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Integrating new technology in the language classroom: innovative teacher identities - Valentyn, Gail (Stellenbosch: Stellenbosch University, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:48JWYMGW
Keywords: _C:Australia AUS; _C:China CHN; _C:Estonia EST; _C:Finland FIN; _C:Mauritius MUS; _C:Namibia NAM; _C:New Zealand NZL; _C:Nigeria NGA; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Integrated strategic planning framework for teacher education and development in South Africa, 2011-2025 - Government of South Africa (Department of Basic Education, 2011)
KerkoCite.ItemAlsoKnownAs: 2129771:33373HWY 2317526:GEB5KEP4
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; Education; Education and state; Teachers; Training of; publicImportV1

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:AJ3VZ7A3 2129771:AXTJCXSX 2339240:XCXZB356 2405685:67AH3BDQ 2405685:FJHBE4VN
Keywords: _C:Sierra Leone SLE

Informing the scale-up of Kenya's nursing workforce: A mixed methods study of factors affecting pre-service training capacity and production - Appiagyei, Ashley A.; Kiriinya, Rose N.; Gross, Jessica M.; Wambua, David N.; Oywer, Elizabeth O.; Kamenju, Andrew K.; Higgins, Melinda K.; Riley, Patricia L.; Rogers, Martha F. (Human Resources for Health, 2014)
© 2014 Appiagyei et al.; licensee BioMed Central Ltd. Background: Given the global nursing shortage and investments to scale-up the workforce, this study evaluated trends in annual student nurse enrolment, pre-service attrition between enrolment and registration, and factors that influence nurse production in Kenya.Methods: This study used a mixed methods approach with data from the Regulatory Human Resources Information System (tracks initial student enrolment through registration) and the Kenya Health Workforce Information System (tracks deployment and demographic information on licensed nurses) for the quantitative analyses and qualitative data from key informant interviews with nurse training institution educators and/or administrators. Trends in annual student nurse enrolment from 1999 to 2010 were analyzed using regulatory and demographic data. To assess pre-service attrition between training enrolment and registration with the nursing council, data for a cohort that enrolled in training from 1999 to 2004 and completed training by 2010 was analyzed. Multivariate logistic regression was used to test for factors that significantly affected attrition. To assess the capacity of nurse training institutions for scale-up, qualitative data was obtained through key informant interviews.Results: From 1999 to 2010, 23,350 students enrolled in nurse training in Kenya. While annual new student enrolment doubled between 1999 (1,493) and 2010 (3,030), training institutions reported challenges in their capacity to accommodate the increased numbers. Key factors identified by the nursing faculty included congestion at clinical placement sites, limited clinical mentorship by qualified nurses, challenges with faculty recruitment and retention, and inadequate student housing, transportation and classroom space. Pre-service attrition among the cohort that enrolled between 1999 and 2004 and completed training by 2010 was found to be low (6%).Conclusion: To scale-up the nursing workforce in Kenya, concurrent investments in expanding the number of student nurse clinical placement sites, utilizing alternate forms of skills training, hiring more faculty and clinical instructors, and expanding the dormitory and classroom space to accommodate new students are needed to ensure that increases in student enrolment are not at the cost of quality nursing education. Student attrition does not appear to be a concern in Kenya compared to other African countries (10 to 40%).
KerkoCite.ItemAlsoKnownAs: 10.1186/1478-4491-12-47 10/f6sjbd 2129771:STXD3RRB 2317526:S85ZAYJD
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CCZ:Kenya; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:health; P:logistics; P:nurse; P:production; P:services; R:interview; R:mixed method; R:qualitative; R:quantitative; R:regression; T:Training; Z:Nursing workforce; Z:Scale-up; Z:Training; __C:filed:1; publicImportV1

Information and communication technology: The pivot of teaching and learning of skills in electrical and electronics technology programme in Nigeria - Chukwuedo (International Journal of Vocational and Technical Education, 2013)
The polymorphous nature of teaching and learning has contributed to the quest for skills delivery and acquisition at any place and pace. Teaching and learning of skills in electrical and electronics programme cannot be restricted to the traditional classroom settings, but should adopt favourable and acceptable technological dynamism. The inadequacy in the supply of facilities and qualified manpower perhaps has contributed to the need for skills delivery and acquisition in electrical and electronics programme through other technological means. One of such means found achievable is information and communication technologies (ICTs). This paper therefore reviewed ICTs as the pivot of globalizing teaching and learning of skills in electrical and electronics technology programme. The paper identified some of the skills in this programme, and ICTs that can be used to teach and learn the skills, by both normal and impaired teachers and learners. The findings from the survey questioning revealed that learners unavoidably support their teaching-learning situation with ICTs. It was therefore concluded that ICTs are pivot of teaching and learning of electrical and electronic skills.
KerkoCite.ItemAlsoKnownAs: 2129771:5MJMBBBF 2317526:Z8TBHDAA
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:teaching; P:electro; P:technology; Q:ICT; Q:distance learning; T:Educação profissionalizante; T:TVET; publicImportV1

Information and Communication Technologies in Library and Information Science Education in Kenya - Minishi-Majanja, Mabel K.; Ocholla, Dennis N. (Education for Information, 2003)
Information and Communication Technologies (ICTs) have become central to education and training in Library and Information Science/Service (LIS) because of the great influence of these technologies on the professional world. This study on Kenya is part of a larger doctoral research project that aims to map and audit the types, nature and diffusion of ICTs in LIS education and training programmes in Africa. The findings indicate that all LIS schools in Kenya have embraced the use of ICTs, but there are major variations in terms of application. All but one LIS School offers a wide range of relevant ICT courses, many of them as core modules. However, not all of them offer, or are able to offer, practical hands-on experience for their students. In teaching and learning, only a few LIS schools use ICTs to deliver lectures, the majority still favouring age-old methods of face-to-face classroom teaching. In research, the lack of ICT facilities has resulted in partial and minimal use of ICTs, especially since academic staff have to pay (individually, from private funds) to access the Internet. For the same reasons electronic publishing of research results on the Internet is low. In terms of academic administration, most LIS schools have computerised but most activities still are conducted offline due to networking inadequacies. The study recommends that Kenyan LIS schools should increase the use of ICTs in teaching and learning to foster greater effectiveness. Kenyan LIS schools should strive to provide online and distance education in order to open more learning opportunities for the nation. (Contains 5 tables and 1 footnote.)
KerkoCite.ItemAlsoKnownAs: 2129771:W26XGJ5W 2317526:7SLJ32G9 LOCAL-PQ-61845047
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; F:assessment; F:attitude; F:curriculum; F:learning; F:offline; F:pay; F:teaching; P:administration; P:electro; P:nature; P:services; P:technology; Q:ICT; Q:distance education; R:evaluation; R:questionnaire; SpecialTopic:Library; T:Classroom teaching; T:Training; Z:Administrator Attitudes; Z:Curriculum Evaluation; Z:Deans; Z:Educational Assessment; Z:Educational Development; Z:Educational Indicators; Z:Foreign Countries; Z:Information Science Education; Z:Information Technology; Z:Institutional Characteristics; Z:Questionnaires; Z:Technology Integration; Z:Technology Uses in Education; Z:Use Studies; publicImportV1; ❓ Multiple DOI

InfoInternet for Education in the Global South: A Study of Applications Enabled by Free Information-only Internet Access in Technologically Disadvantaged Areas (authors' version) - Johansen, Johanna; Johansen, Christian; Noll, Josef (arXiv preprint arXiv:1808.09496, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:LTN7QU6X
Keywords: _C:Bangladesh BGD; _C:Congo; Democratic Republic COD; _C:Congo; Republic COG; _C:Finland FIN; _C:Germany DEU; _C:India IND; _C:Namibia NAM; _C:Nigeria NGA; _C:Norway NOR; _C:Peru PER; _C:Tanzania TZA; _C:Thailand THA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Influence of Mobile Learning Training on Pre-Service Social Studies Teachers' Technology and Mobile Phone Self-Efficacies - Adedoja, Gloria; Oluwadara, Abimbade (Journal of Education and Practice, 2016)
Current instructional deliveries favour the use of mobile technology because of its inherent potentials and benefits such as portability, ease of use cost and others. Despite these benefits, many teachers especially in Sub-Saharan Africa still prefer the conventional method and use mobile phones for social engagements such as texting, chatting, callings and others. Though, these teachers use mobile phones for these social activities, using it for instruction is somewhat problematic for them without adequate training on its pedagogical implications. This is also because there are dearth of trainings in this area. Some factors that could however affect this type of specialised training include Technology Self-efficacy, Mobile Phone Self-efficacy, attitude, age and others. The sample of this present study was 101 pre-service social studies teachers in two Universities in Nigeria. The influence of the Mobile learning training on Technology/Mobile Phone Self-efficacies was explored. The results indicated that the pre-service social studies teachers have high Technology/Mobile Phone Self-efficacies after exposure to the training.
KerkoCite.ItemAlsoKnownAs: 2129771:6PDEGCPL 2317526:QMB7LST9 2405685:2B3XKEGJ 2534378:GD8S4UHN 2534378:KAL73UF6 2534378:SDN92DUR
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; Age Differences; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; ERIC; Current Index to Journals in Education (CIJE); Electronic Learning; F:attitude; F:learning; F:pedagogy; Foreign Countries; Higher Education; Instructional Effectiveness; Likert Scales; Nigeria; P:electro; P:services; P:social; P:teachers; P:technology; Postsecondary Education; Predictor Variables; Preservice Teachers; Pretests Posttests; Q:mobile learning; Questionnaires; R:questionnaire; Self Efficacy; Social Studies; Student Teacher Attitudes; T:Training; Technological Literacy; Technology Education; Z:Age Differences; Z:Electronic Learning; Z:Foreign Countries; Z:Instructional Effectiveness; Z:Likert Scales; Z:Predictor Variables; Z:Preservice Teachers; Z:Pretests Posttests; Z:Questionnaires; Z:Self Efficacy; Z:Social Studies; Z:Student Teacher Attitudes; Z:Technological Literacy; Z:Technology Education; __:import:01; __:match:final; __:matched; __:study_id:2096188; __C:filed:1; ___working_potential_duplicate; __finaldtb; publicImportV1; ⛔ No DOI found

Inequitable Dispersion: Mapping the Distribution of Highly Qualified Teachers in St. Louis Metropolitan Elementary Schools - Schultz, Lyndsie Marie (Education Policy Analysis Archives, 2014)
The No Child Left Behind (NCLB) Act of 2001 required all schools, including those located in historically disadvantaged areas, to employ highly qualified teachers. Schools in areas with higher levels of poverty and students of color have historically employed a higher percentage of less qualified teachers (Clotfelter, Ladd, & Vidgor, 2005, 2006; Hill & Lubienski, 2007; Lankford, Loeb, & Wyckoff, 2002). This study examines the distribution, location, and exceptions to highly qualified teachers in St. Louis metropolitan elementary schools. Using Geographic Information Systems (GIS), this study demonstrates how the distribution of highly qualified teachers remains relevant to urban education policy discussions.
Publisher: Colleges of Education at Arizona State University and the University of South Florida
Keywords: Educational Legislation; Elementary School Teachers; Elementary Schools; Federal Legislation; Lebanon_event_2021; Minority Group Students; Poverty; Predictor Variables; Socioeconomic Status; Teacher Certification; Teacher Effectiveness; Teacher Qualifications; Urban Education; Urban Schools; _C:Argentina ARG; _C:Bolivia BOL; _C:Brazil BRA; _C:Chad TCD; _C:Chile CHL; _C:China CHN; _C:Colombia COL; _C:India IND; _C:Mexico MEX; _C:Peru PER; _C:Portugal PRT; _C:Spain ESP; _C:United States USA; _C:Venezuela VEN; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Industrial training in Ghana: perceptions of the undergraduate construction student - Ayarkwa, J; Adinyira, E; Agyekum, K (2011)
The recent oil discovery and processing in Ghana is expected to result in growth of infrastructural development and increased chances of construction graduates to secure jobs. Universities hold the responsibility of producing graduates with sufficient background and excellent qualification to meet the expectations of the construction industry. Although universities‘ curricula have provisions for industrial training (IT), such programmes have not made the expected impact and need quick redress. This paper assesses the perceptions of undergraduate construction students of the College of Architecture and Planning of the Kwame Nkrumah University of Science and Technology (KNUST), Kumasi, Ghana, on IT, and identifies challenges and possible measures to overcome such challenges. A structured questionnaire survey of 185 final year Building Technology and Architecture students was conducted. Data obtained were analyzed based on mean scores of factors evaluated and also t-test to assess the significance of the differences between students‘ performance before and after undertaking IT. Students are of the view that IT exposes them to real work environment and increase their job prospects among others. Students‘ satisfaction level with their performance on personal attitude, communication and work attitude significantly improved after undergoing IT. They are, however, not satisfied with their departments‘ involvement, particularly, with regards to placement and monitoring. Stressful placement processes and financial strain on students are some of the challenges identified. Educational institutions are to collaborate with industry to secure suitable placement for all students and to monitor IT activities in order to enhance the effectiveness of training programmes.
KerkoCite.ItemAlsoKnownAs: 2129771:2GWSGUHU 2317526:QC26FE86
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:construction; P:environment; Q:educational technology; T:TVET; T:Training; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Indigenisation of the School Curriculum: Connecting Classroom and Community Experiences - Mwanza, Christine; Changwe, Robert (Multidisciplinary Journal of Language and Social Sciences Education (2664-083X, Online ISSN: Print ISSN: 2616-4736), 2021)
Keywords: ⛔ No DOI found

Independent Reporting Mechanism (IRM): Sierra Leone Design Report 2019–2021 - Field, Tracey-Lynn (Open Government Partnership, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:FGADC62Q 2339240:8XF8TYGA 2405685:YMJMKLLJ
Keywords: _C:Sierra Leone SLE

Increasing health worker capacity through distance learning: a comprehensive review of programmes in Tanzania - Nartker, AJ; Stevens, L (Human Resources for Health, 2010)
KerkoCite.ItemAlsoKnownAs: 10.1186/1478-4491-8-30 10/cjvg5z 2129771:FM2TGKY8 2317526:2P6XH38Y
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:motivation; P:health; Q:distance learning; T:Training; T:career; T:continuing education; publicImportV1

Inclusiveness in the Vocational Education Policy and Legal Frameworks of Kenya and Tanzania - Malle, Abebe Yehualawork (Journal of Education and Learning, 2016)
This study examines the status of inclusiveness in the education and training policies of Ethiopia in comparison to those of selected East African countries. The focus is on vocational education in terms of the special educational and training needs of students with disabilities. Focus group discussions and interviews conducted in Kenya and Tanzania, relevant policy document analysis and the findings of Article 1 of the study were used as primary sources for the research. A total of 18 representatives of DPOs from Kenya and Tanzania participated in two sessions of focus group discussions, and 15 high-profile figures and experts from concerned government bodies of these study countries were interviewed. Most of the study participants agreed that the issue of disability was not adequately addressed in the education and training policies or the legal and implementation instruments of the study countries. The participants also proposed valuable recommendations.
KerkoCite.ItemAlsoKnownAs: 2129771:ELDA7AXH 2317526:WJTYUD3U
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Ethiopia; C:Kenya; C:Tanzania; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:disability; F:inclusion; F:policy; P:measurement; R:focus groups; R:interview; T:TVET; T:Training; T:training needs; Z:Comparative Education; Z:Disabilities; Z:Educational Legislation; Z:Educational Needs; Z:Educational Policy; Z:Focus Groups; Z:Foreign Countries; Z:Inclusion; Z:Interviews; Z:Special Education; Z:Specialists; Z:Vocational Education; publicImportV1; ⛔ No DOI found

Inclusion of GIS in student teacher training and its significance in higher education in southern African countries - Mzuza, Maureen Kapute; Westhuizen, Christo Van der (International Research in Geographical and Environmental Education, 2020)
Studies have been carried out on the use of geographical information systems (GIS) in teacher training, especially in the developed countries. In southern African countries, nevertheless, the scenario is different because GIS education appears to be a rather new field of study. This study therefore used systematic review to collect data. This method assists in finding and understanding the outcomes of other research conducted within the same field of study. The results reveal that only three countries (South Africa, Botswana and Malawi) teach GIS at their teacher-training universities and secondary schools. In Lesotho, GIS are only taught in secondary schools. In other countries, such as Zambia, Namibia and Zimbabwe, GIS are not taught at all at teacher-training universities and secondary schools but only at universities or departments that do not train teachers. There is no inclusion of GIS at the universities in Angola, Mozambique, Swaziland and Lesotho. Countries that use GIS have demonstrated that the course helps with decision-making, critical thinking and inquiry-based and learner-centred learning, which have the ability to improve the quality of education. Educators and policy-makers are encouraged to reinforce the inclusion of GIS and use of relevant pedagogical skills in teacher-training universities.
Publisher: Routledge _eprint: https://doi.org/10.1080/10382046.2019.1684660
Keywords: Southern Africa; _C:Angola AGO; _C:Botswana BWA; _C:Canada CAN; _C:Finland FIN; _C:India IND; _C:Italy ITA; _C:Kenya KEN; _C:Lesotho LSO; _C:Malawi MWI; _C:Malaysia MYS; _C:Mozambique MOZ; _C:Namibia NAM; _C:Netherlands NLD; _C:Portugal PRT; _C:Rwanda RWA; _C:South Africa ZAF; _C:Tanzania TZA; _C:Turkey TUR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1; geographical information systems (GIS); geography; motivation tool; technology

Inclusion in Practice: An explanatory study of how patterns of classroom discourse shape processes of educational inclusion in Tanzanian secondary school classrooms - Walker, Lisa Beth (University of Cambridge, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:MK7VDX9J 2129771:PHE2UR36
Keywords: _C:Albania ALB; _C:Australia AUS; _C:Austria AUT; _C:Botswana BWA; _C:Brunei Darussalam BRN; _C:Germany DEU; _C:India IND; _C:Israel ISR; _C:Jordan JOR; _C:Kenya KEN; _C:Lesotho LSO; _C:Malaysia MYS; _C:Malta MLT; _C:Morocco MAR; _C:Mozambique MOZ; _C:Netherlands NLD; _C:Peru PER; _C:Russian Federation RUS; _C:Seychelles SYC; _C:South Africa ZAF; _C:Syrian Arab Republic SYR; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

In-Service Training Needs in an African Context: A Study of Headteacher and Teacher Perspectives in the Gucha District of Kenya - Onderi, Henry; Croll, Paul (Journal of in‐service education, 2008)
Improving the quality of teaching is an educational priority in Kenya, as in many developing countries. The present paper considers various aspects on in-service education, including views on the effectiveness of in-service, teacher and headteacher priorities in determining in-service needs and the constraints on providing in-service courses. These issues are examined though an empirical study of 30 secondary headteachers and 109 teachers in a district of Kenya. The results show a strong felt need for in-service provision together with a firm belief in the efficacy of in-service in raising pupil achievement. Headteachers had a stronger belief in the need for in-service for their teachers than did the teachers themselves. The priorities of both headteachers and teachers were dominated by the external pressures of the schools, in particular the pressures for curriculum innovation and examination success. The resource constraints on supporting attendance at in-service courses were the major problems facing headteachers. The results reflect the difficulties that responding to an externally driven in-service agenda creates in a context of scarce resources. (Contains 6 tables.)
KerkoCite.ItemAlsoKnownAs: 10.1080/13674580801950832 10/d94hch 2129771:64AUDAL8 2317526:RYK8LPLC
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:T; D:developing country; F:achievement; F:attitude; F:curriculum; F:teaching; P:measurement; P:services; P:teacher education; P:teachers; T:TVET; T:work-based learning; Z:Academic Achievement; Z:Administrator Attitudes; Z:Educational Innovation; Z:Educational Needs; Z:Faculty Development; Z:Foreign Countries; Z:Inservice Teacher Education; Z:Principals; Z:Secondary School Teachers; Z:Secondary Schools; Z:Teacher Attitudes; Z:Teacher Influence; Z:Vocational Education; publicImportV1

Improving the teaching of English as a first additional language in South Africa. - Cilliers, Jacobus; Fleisch, Brahm; Kotze, Janeli; Mohohlwane, Nompumelelo; Taylor, Stephen; Thulare, Tshegofatso (American Economic Association, 2020)
We experimentally compare on-site with virtual coaching of South African teachers. After three years, on-site coaching improved students’ English oral language and reading proficiency by 0.31 and 0.13 SD, respectively. Virtual coaching improved English oral language proficiency (0.12 SD), had no impact on English reading proficiency, and an unintended negative effect on home language literacy. Classroom observations show that on-site coaching improved teaching practice and that virtual coaching led to larger crowding-out of home language teaching time. Implementation and survey data suggest that the use of technology did not preclude effectiveness, but rather that in-person contact enabled more accountability and support.
Trial registration: 10.1257/rct.5148-1.0 KerkoCite.ItemAlsoKnownAs: 2129771:8M4KYKZ8 2486141:VVJ6LX89
Keywords: C:South Africa; __C:filed:1

Improving Secondary School Teacher Quality in Sub-Saharan Africa - Bainton, Dave; Barrett, Angeline Mbogo; Tikly, Leon (University of Bristol, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:X5Z7RU4N 2405685:CLHEDE9L
Keywords: C:sub-Saharan Africa; _C:Benin BEN; _C:Botswana BWA; _C:Burundi BDI; _C:Cameroon CMR; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Congo; Republic COG; _C:Ethiopia ETH; _C:Gambia GMB; _C:Ghana GHA; _C:India IND; _C:Ivory Coast CIV; _C:Kenya KEN; _C:Malawi MWI; _C:Mali MLI; _C:Mozambique MOZ; _C:Namibia NAM; _C:Nigeria NGA; _C:Pakistan PAK; _C:Philippines PHL; _C:Rwanda RWA; _C:South Africa ZAF; _C:South Sudan SSD; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Improving School Work in Challenging Context: Practitioners’ Views following a Participatory Action Research Project from Eritrea - Idris, Khalid Mohammed; Asfaha, Yonas Mesfun (Nordic Journal of Comparative and International Education (NJCIE), 2019)
KerkoCite.ItemAlsoKnownAs: 10.7577/njcie.3039 2129771:JFFXBPYK 2129771:URC8U36C
Keywords: _C:China CHN; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Ghana GHA; _C:Namibia NAM; _C:Nigeria NGA; _C:Saudi Arabia SAU; _C:Senegal SEN; _C:South Africa ZAF; _C:Sudan SDN; _C:Tanzania TZA; _C:Turkey TUR; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Improving Motivation in Arabic Language Arts Classrooms Through Technology Integration - Chamout, Rima (Walden University, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:WRYY9UFL
Keywords: _C:Algeria DZA; _C:China CHN; _C:Croatia HRV; _C:France FRA; _C:Indonesia IDN; _C:Japan JPN; _C:Jordan JOR; _C:Kurdistan XKRDN; _C:Lebanon LBN; _C:Malaysia MYS; _C:Nigeria NGA; _C:Oman OMN; _C:Pakistan PAK; _C:Saudi Arabia SAU; _C:Spain ESP; _C:State of Palestine PSE; _C:Sudan SDN; _C:Switzerland CHE; _C:Syrian Arab Republic SYR; _C:Turkey TUR; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Improving micro-planningin education througha Geographical Information SystemStudies on Ethiopia and Palestine - Attfield, Ian; Tamiru, Mathewos; Parolin, Bruno; De Grauwe, Anton (2002)
KerkoCite.ItemAlsoKnownAs: 2129771:ALELB33F
Keywords: _C:Argentina ARG; _C:Australia AUS; _C:Cambodia KHM; _C:Chile CHL; _C:Denmark DNK; _C:Egypt EGY; _C:Eritrea ERI; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Iceland ISL; _C:India IND; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Japan JPN; _C:Jordan JOR; _C:Malaysia MYS; _C:Namibia NAM; _C:Nepal NPL; _C:Norway NOR; _C:South Africa ZAF; _C:State of Palestine PSE; _C:Sweden SWE; _C:Switzerland CHE; _C:Tunisia TUN; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Improving learning through classroom experience in Tanzania - Pattni, Ravina; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi; Proctor, Jamie; Forbes, Catriona; Atherton, Paul; Haßler, Björn (Laterite, Fab Inc, Open Development & Education, 2023)
This conference paper was delivered at UKFIET 2023 (Oxford). IT was a joint presentation between Laterite, Fab Inc, and Open Development & Education, as well as FCDO.
ZenodoArchiveID: 10044115 ZenodoArchiveConcept: 10044114 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1025 2129771:ICBNFIUW 2129771:JNMJ2AAW 2129771:U5GXRKUD
Keywords: _r:AddedByMyEducationEvidence

Improving adult learning and professional development in a post-conflict area: The case of Cambodia - Berkvens, Jan; Kalyanpur, Maya; Kuiper, Wilmad; Akker, Jan (International Journal of Educational Development, 2012)
All over the world, international development organizations try to increase professional capacity of local staff. These attempts are thought to fail because of financial constraints, but this is just part of the story. Professional development and adult learning theories approach learning from a western perspective, while many developing societies are organized according to non-western models. This article describes research conducted in the Cambodian Ministry of Education, focusing on how adult learning theory could be applied in order to improve learning and support transfer. When local experience and the cultural influence on learning are acknowledged, learning outcomes are found to improve.Highlights► Professional development activities should be adapted to local culture. ► Extra attention should be paid to creating trust and a safe learning environment. ► Acknowledging local expertise increases ownership and professionalism. ► Time is a crucial factor for understanding the influence of local culture on adult learning. ► Staff motivation and support of superiors are key factors in successful professional learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2011.03.008 2129771:KWUU9EMN
Keywords: _C:Cambodia KHM; _C:Ghana GHA; _C:Laos LAO; _C:Netherlands NLD; _C:Thailand THA; _C:United States USA; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1

Implementing large-scale instructional technology in Kenya: Changing instructional practice and developing accountability in a national education system - Piper, Benjamin; Oyanga, Arbogast; Mejia, Jessica; Pouezevara, Sarah (International Journal of Education and Development using Information and Communication Technology, 2017)
Previous large-scale education technology interventions have shown only modest impacts on student achievement. Building on results from an earlier randomized controlled trial of three different applications of information and communication technologies (ICTs) on primary education in Kenya, the Tusome Early Grade Reading Activity developed the National Tablets Program. The National Tablets Program is integrated into the Tusome activity by providing tablets to each of more than 1,200 instructional coaches in the country to use when they visit teachers. This enables a national database of classroom instructional quality, which is used by the education system to monitor overall education quality. The tools provided on the tablets are designed to help coaches increase the quality of their instructional support to teachers, and deepen the shallow accountability structures in Kenya’s education system. Using results of a national survey, we investigated the ability of the National Tablets Program to increase the number of classroom observations done by coaches and to improve student learning outcomes. Survey results showed high levels of tablet program utilization, increased accountability, and improvements in learning outcomes. We share recommendations regarding large-scale ICT interventions and literacy programs.
KerkoCite.ItemAlsoKnownAs: 2129771:U4THKEF5 2405685:7L6V38N5
Keywords: C:Kenya; _C:Brazil BRA; _C:Catalan Republic XCATA; _C:Ghana GHA; _C:Guinea GIN; _C:Honduras HND; _C:India IND; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Malawi MWI; _C:Niger NER; _C:Peru PER; _C:Portugal PRT; _C:Tanzania TZA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Implementation of the Free Education Policy in Primary Schools in Kafue District: Is It a Compromise on Quality of Education in Zambia? - Mwanza, Christine; Silukuni, Darious (European Journal of Education Studies, 2020)

Implementation of the competency-based curriculum by teachers of History in selected Secondary Schools in Lusaka district, Zambia - Kabombwe, Yvonne Malambo; Mulenga, Innocent Mutale (Yesterday and today, 2019)
Publisher: The South African Society for History Teaching (SASHT)

Implementation of learner support services in distance teacher education programmes in selected public colleges of education in Zambia - Jere, Getrude; ManchishI, Peter Chomba; Mulenga, Innocent Mutale (The Zambia Journal of Distance Education (Online ISSN 2789-052X), 2021)
Keywords: ⛔ No DOI found

Impacts of Pre-Service Training and Coaching on Kindergarten Quality and Student Learning Outcomes in Ghana - Wolf, Sharon (Studies in Educational Evaluation, 2018)
Using a randomized-control trial, this study evaluates a program designed to support Ghanaian kindergarten student-teachers during pre-service training through mentorship and in-classroom training. Several potential barriers to improved teaching quality and learning outcomes are examined. Findings show that the program improved knowledge and implementation of the national curriculum for individuals both when they were student-teachers and, the following year, when they became newly qualified teachers (NQTs). There were mixed impacts on professional well-being, increasing personal accomplishment and motivation but decreasing job satisfaction for NQTs. There were mixed impacts on teaching quality, with increases in child-led learning but decreases in some other aspects of quality. There were no impacts on NQTs’ student learning outcomes. The findings highlight system level challenges with both the posting of NQTs and the absence of support in their first teaching year. Implications for global early childhood education policy and teacher education are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.stueduc.2018.05.001 10/gf62pq 2129771:SM5UVAZ4 2317526:ISEA45I5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CCZ:Ghana; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:curriculum; F:learning; F:motivation; F:outcomes; F:policy; F:teaching; P:measurement; P:services; P:teacher education; P:teacher training; P:teachers; R:impact; R:trial; T:Training; Z:early childhood education; Z:kindergarten; Z:pre-service training; Z:sub-Saharan Africa; Z:teacher training; _C:Ghana GHA; publicImportV1

ILCE: Trialling environmental sensors in Tanzanian Schools – First pilot - Hassler, Bjoern; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8402851 ZenodoArchiveConcept: 8402850 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1019 2129771:IT8RD5H2
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

ILCE: Trialling environmental sensors in Tanzanian Schools – First pilot - Hassler, Bjoern; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8402855 ZenodoArchiveConcept: 8402854 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1020 2129771:HHH8MWN3
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

ILCE: Conducting surveys in Tanzanian Schools – Second pilot - Haßler, Björn; Villavicencio Peralta, Xuzel; Toyinbo, Oluyemi (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8402861 ZenodoArchiveConcept: 8402860 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1021 2129771:EASK7UAW
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

“If I can be a helper, one day I be a boss”–A case study of informal apprenticeship in Lusaka - Ryan, S (2015)
Despite recent high levels of economic growth, many young people in Zambia are trapped by poverty, unemployment or underemployment, and lack of access to skills development opportunities. Vocational training institutions cannot accommodate the vast numbers of school leavers every year, and often charge fees that are prohibitive to young people from poorer families. Young people remain significantly overrepresented in Zambia’s unemployment statistics. For those that do manage to secure work, it is predominantly in the informal economy, which currently accommodates over 90 of employed Zambians. Zambia faces a clear challenge to translate the economic gains of the past few years into improved livelihood conditions and decent work outcomes. With over 46 per cent of the population being under the age of 15, there is an urgent need for programs that provide young people in particular with skills development and employment opportunities. In this climate, informal apprenticeships may offer young people access to both affordable training and future employment. Informal apprenticeship, as defined by the International Labour Organization (ILO), is a written or oral training agreement under which a master craftsperson (MC) provides an apprentice (a young person) with training in all skills relevant to a trade. An apprentice gains tacit skills by working alongside a master craftsperson in a micro or small enterprise in the informal economy. Informal apprenticeships are anchored in the norms and traditions of a society, which shape the obligations and incentives for MCs to train others, and for apprentices to seek this kind of training. Costs and benefits are shared between the apprentice and master craftsperson (ILO, 2012). This study seeks to identify the norms and characteristics of informal apprenticeship in Zambia’s capital city, Lusaka. The study aims to provide guidance on how informal apprenticeships in Zambia can be supported and strengthened within the ILO’s mandate to improve the quality of apprenticeships within the informal economy. The study also aims to contribute to ILO’s body of knowledge on informal apprenticeship, describing both the local specificities of informal apprenticeship in urban Zambia, and how the training relates to ILO’s broader findings on informal apprenticeship in Africa. This study found that training within the informal economy is widely undertaken in the Lusaka region. However, the informal institutional framework for apprenticeships in Lusaka’s informal economy is currently less well established, compared to informal apprenticeships in West Africa. Written contracts were found to be non-existent, and verbal training agreements were considerably undefined. There is no specific term used for apprentices within the informal economy – young people join businesses as othandiza (helpers), but this term may apply both to those in an apprenticeship role, and casual workers brought in for temporary work. This study also determined a variety of training arrangements within the informal economy including fluid models of group-based learning, whereby a young person may learn from several experienced craftspeople in a ‘cluster’ of selfemployed operators. Despite these issues, vast numbers of Zambian young people still gain skills through working and learning in informal economy enterprises. The majority of apprentices reported that they join businesses with the key objective of acquiring all relevant trade skills - training within an informal enterprise was also found to be the primary source of skills development for MCs. While the lack of clear norms surrounding informal apprenticeship may be seen as problematic, many MCs and apprentices felt that the flexibility of terms supported, rather than hindered the apprentice - for instance, by the apprentice being able to progress quickly through the learning process. Incentive and obligation operate as strong binding mechanisms for both MCs and apprentices to complete the training in the absence of fixed institutional frameworks. Furthermore, the fluid nature of Zambian informal apprenticeships may mean that any future targeted interventions may be incorporated more easily. There is currently an enabling institutional environment for upgrading informal apprenticeship in Zambia. With the 2011 election of the Patriotic Front (PF) party to government, there is a renewed focus on the issues of youth, job creation, skills training, self-employment opportunities and the quality of jobs. The PF government has stated that they seek to involve youths in national development by ‘expanding educational facilities and vocational training to absorb all school leavers’, ‘collaborating with industry to provide learnership/apprenticeship practical training’, and ‘facilitating access to finance and to markets’ for young people (The Patriotic Front, 2011). Considering informal apprenticeship as a mode of vocational training in Zambia would clearly support government’s aim of creating a vocational training system capable of absorbing all school leavers. Recognition of informal training is further supported by reforms in TEVET policy, which call for a greater focus on training within and for the informal sector, and seek to diversify the modes in which training is delivered. Key interventions are required to upgrade informal apprenticeship to a robust mode of vocational training leading to gainful and decent employment for young people in Zambia. This report argues that TEVET policy needs to become more responsive to the informal economy, with the Apprenticeship Act revitalized, trade testing promoted more effectively, and informally acquired skills recognized. The quality of training needs to be improved, such as through providing MCs with skills development opportunities, introducing competency assessment measures, and strengthening training agreements. Decent work outcomes also need to be strengthened through supporting trade associations, providing greater access to finance for MCs and graduating apprentices, improving health and safety outcomes, and creating greater links between the formal and informal training and employment sectors.
KerkoCite.ItemAlsoKnownAs: 2129771:28YFYBHE 2317526:AESRQWBS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; A:West Africa; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:learning; F:policy; HDR25; P:economy; R:case study; T:Ausbildung; T:Formal apprenticeship; T:Lehrlingsausbildung; T:TVET; T:Training; publicImportV1; ⛔ No DOI found

Identifying and prioritizing strategies to strengthen climate resilience of education systems - Ryan, Benjamin; Garner, Shelby; Flynnn, Rachael (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912284 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1128 ZenodoArchiveConcept: 10912283
Keywords: Coming soon; _r:AddedByMyEducationEvidence

ICT and the Education of Refugees - Lewis, Kent; Thacker, Simon (2016)
00000 KerkoCite.ItemAlsoKnownAs: 10.1596/26522 10/gdm2tq 2129771:2C83JMHH
Keywords: _C:Afghanistan AFG; _C:Algeria DZA; _C:Armenia ARM; _C:Australia AUS; _C:Canada CAN; _C:Chile CHL; _C:Congo XCO; _C:Costa Rica CRI; _C:Egypt EGY; _C:Ethiopia ETH; _C:France FRA; _C:Germany DEU; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Iraq IRQ; _C:Jordan JOR; _C:Kenya KEN; _C:Korea XKOR; _C:Kuwait KWT; _C:Lebanon LBN; _C:Libya LBY; _C:Luxembourg LUX; _C:Malawi MWI; _C:Malaysia MYS; _C:Morocco MAR; _C:Netherlands NLD; _C:Norway NOR; _C:Oman OMN; _C:Pakistan PAK; _C:Philippines PHL; _C:Qatar QAT; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:South Sudan SSD; _C:Spain ESP; _C:State of Palestine PSE; _C:Sudan SDN; _C:Sweden SWE; _C:Syrian Arab Republic SYR; _C:Thailand THA; _C:Turkey TUR; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Yemen YEM; __C:filed:1; __C:scheme:1

Hur lärare kan arbeta med problemlösningsuppgifter - Findelius Jämsén, Isabelle; Nilsson, Frida (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:7NBBFIVQ 2129771:8BTH37ZQ
Keywords: _C:Australia AUS; _C:Greece GRC; _C:Sweden SWE; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Human Resources for Health Challenges in Nigeria and Nurse Migration - Salami, Bukola; Dada, Foluke O.; Adelakun, Folake E. (Policy, Politics, and Nursing Practice, 2016)
© 2016, © The Author(s) 2016. The emigration of sub-Saharan African health professionals to developed Western nations is an aspect of increasing global mobility. This article focuses on the human resources for health challenges in Nigeria and the emigration of nurses from Nigeria as the country faces mounting human resources for health challenges. Human resources for health issues in Nigeria contribute to poor population health in the country, alongside threats from terrorism, infectious disease outbreaks, and political corruption. Health inequities within Nigeria mirror the geographical disparities in human resources for health distribution and are worsened by the emigration of Nigerian nurses to developed countries such as the United States and the United Kingdom. Nigerian nurses are motivated to emigrate to work in healthier work environments, improve their economic prospects, and advance their careers. Like other migrant African nurses, they experience barriers to integration, including racism and discrimination, in receiving countries. We explore the factors and processes that shape this migration. Given the forces of globalization, source countries and destination countries must implement policies to more responsibly manage migration of nurses. This can be done by implementing measures to retain nurses, promote the return migration of expatriate nurses, and ensure the integration of migrant nurses upon arrival in destination countries.
KerkoCite.ItemAlsoKnownAs: 10.1177/1527154416656942 10/gf62zt 2129771:L9QF72FB 2317526:S78FFQ3Q
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:policy; P:economy; P:environment; P:health; P:health professionals; P:nurse; T:career; T:trainee; Z:foreign-trained nurses; Z:human resources for health; Z:immigrant nurses; Z:internationally educated nurses; Z:migration; publicImportV1

Human Resource Development (HRD) through Technical and Vocational Education and Training (TVET) during Independence Days in Kenya - Mosoti, Z (International Journal of Social and Policy Issues, 2011)
I have traced the history and evolution of HRD through IVET during independence days. I relied on Kenya's NDPs and the education commissions appointed by political leaderships (Kenya's two past presidents) to look at the development and processes of education and ways that have been suggested to improve education. I have discussed these through the NDPs and the commissions appointed by the presidents of the time. The information has been presented using a chronological, thematic and, again chronological method. Additional information includes changes in curriculum during the same period. The first part considers the period from independence in 1963 to 1987 and the second part 1988 to 2005.
KerkoCite.ItemAlsoKnownAs: 2129771:K9LJWRZB 2317526:RTA2RDLL UTI-4BE1C78C-9730-3BB9-80B7-D07E9D344652
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; Q:degree; T:TVET; T:Training; publicImportV1; ⛔ No DOI found

How to Improve Teaching Practice? Experimental Comparison of Centralized Training and In-classroom Coaching - Cilliers, Jacobus; Fleisch, Brahm; Prinsloo, Cas; Taylor, Stephen (Research on Improving Systems of Education (RISE), 2018)
We experimentally compare two modes of in-service professional development for South African public primary school teachers. In both programs teachers received the same learning material and daily lesson plans, aligned to the ofﬁcial literacy curriculum. Pupils exposed to two years of the program improved their reading proﬁciency by 0.12 standard deviations if their teachers received centralized Training, compared to 0.24 if their teachers received in-class Coaching. Classroom observations reveal that teachers were more likely to split pupils into smaller reading groups, which enabled individualized attention and more opportunities to practice reading. Results vary by class size and baseline pupil reading proﬁciency.
shortDOI: 10/ghgnff KerkoCite.ItemAlsoKnownAs: 10.35489/BSG-RISE-WP_2018/024 10/ghgnff 2129771:8TR54IFM 2405685:WYIY3SSM
Keywords: C: South Africa; _C:South Africa ZAF; _C:United States USA; __C:filed:1; __C:scheme:1

How to build an IoT device with low-power sleep - Haßler, Björn (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 7881014 ZenodoArchiveConcept: 7881013 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1011 2129771:3SCPTDDX 2129771:HUZFX6PG
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707884 10.5281/zenodo.4707888 2129771:E6F3I5MG 2129771:S4SM32SK 2339240:6XDHWICN 2405685:7FQR6GZK 2405685:E2KWWHCK 2405685:LND4UENT 2405685:Y22H6PQD
Keywords: _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _zenodoETH

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, A; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.
KerkoCite.ItemAlsoKnownAs: 2129771:AT8FP8ZI 2405685:AVDJP4T3 4042040:AJHHQGBH
Keywords: _C:Sierra Leone SLE

How can Sierra Leone’s education response after Ebola help with the COVID-19 response? - Bangay, Colin (The Education and Development Forum (UKFIET), 2020)
This blog is written by Colin Bangay, Senior Education Adviser, Department for International Development (DFID). It aims to look at some practical and sensible lessons from the education response in Sierra Leone during the Ebola outbreak, to help others as they face closures of education systems. This blog was originally published on the Global Partnership […]
KerkoCite.ItemAlsoKnownAs: 2129771:C5HFDS3J 2339240:D5Q8A77B 2405685:PK7UUFGK
Keywords: _C:Sierra Leone SLE

How Can Micro and Small Enterprises in Sub-Saharan Africa Become More Productive? The Impacts of Experimental Basic Managerial Training - Mano, Yukichi; Iddrisu, Alhassan; Yoshino, Yutaka; Sonobe, Tetsushi (World Development, 2012)
Summary The vast majority of micro and small enterprises (MSEs) in developing countries are located in industrial clusters, and the majority of such clusters have yet to see their growth take off. The performance of MSE clusters is especially low in Sub-Saharan Africa. While existing studies often attribute the poor performance to factors outside firms, problems within firms are seldom scrutinized. In fact, entrepreneurs in these clusters are unfamiliar with standard business practices. Based on a randomized experiment in Ghana, this study demonstrates that basic-level management training improves business practices and performance.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2011.09.013 10/cxgkj2 2129771:JQM5BFMC 2317526:68LWWGVE
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; AA:Africa; CA:AandC; CCZ:Ghana; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:R; CT:T; D:developing country; F:standards; R:impact; T:Training; Z:industrial development; Z:management training; Z:randomized experiment; Z:survival clusters; _C:Ghana GHA; publicImportV1

Hospitality and Tourism Education in Uganda: An Integrative Analysis of Students' Motivations and Industry Perceptions - Tukamushaba, Eddy Kurobuza; Xiao, Honggen (Journal of Teaching in Travel & Tourism, 2012)
This article presents an integrative analysis of students' motivations in choosing hospitality and tourism programs as well as industry perceptions of graduates' qualifications for employment in Uganda, A mixed-method approach is used for data collection, analysis, and reporting. Quantitatively, the study replicates a motivational scale of choosing educational programs and identifies six factors that collectively explain about 60% of the variance in students choosing hospitality and tourism programs in this African developing economy. Industry perceptions of graduates' qualifications for employment are reported on the basis of qualitative interviews. Implications of the study are discussed in light of curriculum and program refinement to better prepare future graduates for the industry.
KerkoCite.ItemAlsoKnownAs: 10.1080/15313220.2012.729457 10/gf62kz 2129771:Z4QMF3PS 2317526:28LGQ7QE
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CCZ:Uganda; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:curriculum; F:motivation; F:qualification; P:economy; P:tourism; R:interview; R:qualitative; R:quantitative; T:career; Z:career choice; Z:employer perception; Z:hospitality and tourism education; Z:study motivation; _C:Uganda UGA; publicImportV1

Higher Education Students' Ownership and Usage of Smart Phones and Tablets: The Case of Kwame Nkrumah University of Science and Technology (KNUST). - Essel, Harry Barton; Nunoo, Francis Kofi Nimo; Tachie-Menson, Akosua; Amankwa, John Opuni (International Journal of Educational Technology, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:DXG3ZX4S
Keywords: _C:Australia AUS; _C:Ghana GHA; _C:Ireland IRL; _C:Nigeria NGA; _C:Spain ESP; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ⛔ No DOI found

High School Teacher Perceptions of Blended Learning - Raymond, Stephen (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:ITZPK2IN
Keywords: _C:France FRA; _C:Greece GRC; _C:Kuwait KWT; _C:Malaysia MYS; _C:Namibia NAM; _C:Tanzania TZA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Harnessing technical and vocational education and training and entrepreneurship education to address unemployment in Lusaka province, Zambia. - Mubanga, Phillip; Hock, Oo Yu; Karim, Asif Mahbub; Senteri, Zulkifli; Mulenga, Innocent Mutale; Preckler, Miriam (2019)
Publisher: Scientific Research Publishing

Harmonisation of curricula and qualifications in higher education in africa: challenges and prospects. - Chishimba, P. Chanda; Kalimaposo, Kalisto; Mulenga, Innocent Mutale (2013)
Publisher: Zambia Journal of Education
Keywords: ⛔ No DOI found

Handbook of comparative studies on community colleges and global counterparts - Latiner Raby, Rosalind (Springer Berlin Heidelberg, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:9XBP698I 2249382:EP2B5LEI 2317526:ULGLVBDG UA-959dc1ce-edef-4780-a442-bd4e9bdec895
Keywords: C:South Africa

Guidelines for Registration of Training Providers - Government of Kenya (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:74AGI8EH 2317526:R5RUMKJQ
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Kenya; publicImportV1

Guidelines for licensing and regulating private schools - Government of Uganda (2013)
UA-7f7feb58-efb3-4047-b1b6-14c51747534d KerkoCite.ItemAlsoKnownAs: 2129771:968D6A4X 2317526:AP3KURJ7
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; publicImportV1

Guidelines for Establishment and Operation of Production Unit in Technical College - Government of Nigeria (2006)
KerkoCite.ItemAlsoKnownAs: 2129771:G5YIKFHX 2317526:Q8UPWPZS
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Nigeria; publicImportV1

Guidelines and Procedures for the Establishment of Private Technical and Technological Institutions - Government of Nigeria (2014)
KerkoCite.ItemAlsoKnownAs: 2129771:8WBLVZR9 2317526:GRWQEZKP
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Nigeria; publicImportV1

Guide: Technical specifications for applying local white paint on schools’ roofs - Regime Projects Tanzania; Open Development & Education (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10666717 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1071 ZenodoArchiveConcept: 10666716
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

Guide: Roof paint, shading, and sound insulation - Regime Projects Tanzania; Open Development & Education (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10666750 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1072 ZenodoArchiveConcept: 10666749
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions
Library Catalog: www.mobileconnectivityindex.com KerkoCite.ItemAlsoKnownAs: 2129771:L7MHP2UX 2405685:AGNKXIPC
Keywords: _C:Sierra Leone SLE

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2129771:V823UWZQ 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Government of Sierra Leone Education Data Hub - Directorate of Science, Technology and Innovation (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:TWXIHHM2 2339240:8BAXTEYI 2405685:46EQS5JF
Keywords: _C:Sierra Leone SLE

Governance and Change in Educational Policy Systems in Technical Vocational Education - Oluwafemi, CO; Martins, OR; Adebiaye, HO (2015)
From time immemorial, people have been controlled (ruled) by others in order to maintain law and order. This process is what is called governance. Governance is the act of exercising power and making decisions for a group of people by a selected few granted the authority to do so. Different human era called for different ‘curricular’ of teaching since it is believed that the needs of the society are one of the major determinants of the content of the curriculum. The authorities at each of such times only help to articulate the curriculum and provide the environment for teaching and learning to take place. In this pursuit, the Nigerian government has not been an exception. Over the years, the Governments have brought in one change or the other to the educational sector all with the utmost aim of making the nation better through her educational processes. This paper through the methodology of literature review and the authors’ observations focuses on some of the changes brought into the sector particularly in Technical Vocational Education. It looked at how these changes have benefited or otherwise affected the country and makes suggestions based on the findings.
KerkoCite.ItemAlsoKnownAs: 2129771:XWDKZE4R 2317526:ZYPADVAW
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Central Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:policy; P:administration; Q:distance learning; T:TVET; publicImportV1; ⛔ No DOI found

Globalization, Mass Education and Technical and Vocational Education and Training - Galguera, MP (2018)
This book assesses the influence of the international organization UNESCO on the development of national Technical and Vocational Education and Training (TVET) systems in the Southern African Community Region (SADC), focusing particularly on Botswana and Namibia. Designed around UNESCO’s Better Education for Africa’s Rise (BEAR) project, the study is an excellent example of applied policy research. Analysis is from the perspective of key stakeholders including UNESCO headquarters and field offices, Ministries of Education and of Labor, employers and employees, education and training institutions, international partners and more. Both qualitative and quantitative evidence are used to provide a comparative overview, and the author also reveals the current state of data on skills. Readers will discover common goals and challenges across the nations but also a common lack of action to measure the impact and influence that UNESCO’s programs have had at a national level, prior to this study. Were the newly implemented educational policies successful or not? If the public policies failed, why was that? These chapters shed light on such questions and how UNESCO's contribution influenced the national development processes, in the context of globalization processes and trends of global mass education. The book has much to offer for both scholars and those working in UN agencies or national governments who seek to develop education systems and better link them to the world of work.
KerkoCite.ItemAlsoKnownAs: 2129771:HHSFUZBU 2317526:HKNVDPCL
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; A:West Africa; C:Namibia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:qualification; P:construction; P:economy; Q:ODEL; Q:open learning; T:Educação profissionalizante; T:TVET; publicImportV1

Global economic crisis: A challenge to the entrepreneurship development of technical vocational education and training in oil and gas sector of the Nigerian Economy - Wodi, SW (International Journal of Academic Research in Business and Social Sciences, 2012)
The paper attempts to evaluate the Global economic crisis and the challenges to entrepreneurship development of technical vocational education and training in oil and Gas sector of the Nigerian economy. Effects of the global melt down in the economies of developed countries of the world and its chain-link action has gradually enveloped the entire world economy. This development impacted negatively on the Nigerian economy coupled with the Niger delta crisis that has drastically affected oil and gas production and development of new fields with its attendant consequences. Accordingly, vocational and technical education institutions that undertake training of technicians in such enterprise as welders, electricians, pipe fitters including safety experts were affected as a result of global melt down, constraining the oil and gas companies from engaging the services of Technical Vocational Education and Training Professionals (TVET) in the energy sector.
KerkoCite.ItemAlsoKnownAs: 2129771:WV2ZQM7U 2317526:6SUVI26U UTI-621EF8ED-FC0B-37B7-8B86-05C15BA2D5E4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:economy; T:TVET; publicImportV1; ⛔ No DOI found

“Give courage to the ladies”: Expansive apprenticeship for women in rural Malawi - Safford, K.; Cooper, D.; Wolfenden, F.; Chitsulo, J. (Journal of Vocational Education & Training, 2013)
Apprenticeship in developed and industrialised nations is increasingly understood and practised as learning which connects workplace activity and formal study. The concept of 'expansive apprenticeship' defines frameworks for workforce development where participants acquire knowledge and skills which will help them in the future as well as in their current roles; 'restrictive' apprenticeships limit opportunities for wider, lifelong learning. In developing world economies, apprenticeships are a traditional route to learning and employment, but tend to reflect a restrictive approach characterised by narrowly defined roles and weak educational outcomes. This paper examines the apprenticeship opportunities in a large scale Access to Teaching Scholarship in Malawi. The programme's study materials and support structures are designed to move participants from restrictive to expansive contexts for learning and to develop hybrid roles as students, community workers and apprentice teachers. The authors examine data from the first cohort of participants and consider the extent to which the Scholarship offers an innovative model of expansive apprenticeship to address barriers to female continuing education and chronic teacher shortages in Sub-Saharan Africa. © 2013 Copyright The Vocational Aspect of Education Ltd.
KerkoCite.ItemAlsoKnownAs: 10.1080/13636820.2012.755213 10/gf62pr 2129771:W7A3AETF 2317526:J9QU3SAQ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Malawi; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:T; D:developing world; F:access; F:gender; F:learning; F:motivation; F:outcomes; F:teaching; F:women; P:economy; P:measurement; P:teacher education; P:teacher training; P:teachers; Q:certificate; Q:distance education; Q:lifelong learning; T:Lehrlingsausbildung; T:TVET; T:Training; T:apprentice; T:career; T:continuing education; T:workplace education; Z:Access to Education; Z:Adult Education; Z:Apprenticeships; Z:Barriers; Z:Career aspirations; Z:Continuing Education; Z:Distance Education; Z:Distance education; Z:Donors and NGOs; Z:Economic Development; Z:Elementary Schools; Z:Female empowerment; Z:Females; Z:Foreign Countries; Z:Gender Issues; Z:Mentors; Z:Rural Areas; Z:Teacher Certification; Z:Teacher Education; Z:Teacher Shortage; Z:Teacher education; Z:Teacher motivation; Z:VET and development; Z:VET and economic development; Z:Vocational Education; Z:Vocational education and training; Z:Women Faculty; Z:Workplace Learning; Z:adult learning; Z:gender and learning; Z:learning in life &; Z:philosophy of VET; Z:teacher training; Z:training; Z:vocational education &; Z:work transitions; Z:workplace learning; publicImportV1

GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G. C.; Nyadimo, E. (Survey Review, 2013)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision...
Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 10.1179/003962611X13117748892155 2129771:D7LGKELW 2129771:EG8QF9R9
Keywords: _C:Ethiopia ETH; _C:France FRA; _C:India IND; _C:Ireland IRL; _C:Kenya KEN; _C:State of Palestine PSE; _C:Thailand THA; _C:Uganda UGA; __C:filed:1; __C:scheme:1

Getting girls back into school: strategies for successfully re-enrolling girls in Ghana and Sierra Leone - Belfield, Sophie; Mathur, Meenu; Caine, Ellie (FCDO - GEC, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:7PSBTMG4 2339240:GMMKRGS8 2405685:79GPUNG4
Keywords: _C:Sierra Leone SLE

Gestaltungsorientierung als Entwicklungsstrategie zur Beförderung der beruflichen Fortbildung – dargestellt und untersucht am Beispiel des Projektes VET-Net - Haseloff, Gesine (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:U972YMBU 2317526:CP2DPGD3 UA-7a56c9f3-ad17-469f-b082-d4f037a697d4
Keywords: -FullBiblioUHMLgen; -GeneralCitations; C:Mozambique; C:South Africa; publicImportV1; ⛔ No DOI found

GENERAL MATHEMATICS OR MATHEMATICS (CORE) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745446 2129771:J5DMLP64
Keywords: SSEIP; _C:Sierra Leone SLE

General and Further Education and Training Quality Assurance Act Nº58 - Government of South Africa (2001)
UA-1a6bde11-123e-41f7-957c-aaee9859b58f KerkoCite.ItemAlsoKnownAs: 2129771:SP966LAJ 2317526:MUJYGBFC
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; Quality Assurance; publicImportV1

Gender Strategy for the Education and Training Sector - Government of Ethiopia (2014)
UA-46cd01a7-d8a9-492d-8b98-a24cd842a26c KerkoCite.ItemAlsoKnownAs: 2129771:7JH29QYT 2317526:PMC5SD9Y
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Ethiopia; gender; inclusion; publicImportV1

Gender Issues in Technical and Vocational Education and Training - Gaidzanwa, RB (2008)
This paper argues that post primary education in Africa is uneven, biased by gender, location, class and region, resulting in the illiteracy of the majority of girls and women in Africa. A minority of African adolescents undertakes secondary schooling. The majority have little foundation for building on technical, vocational education and training, making technical, vocational education and training the preserve of a few, usually elite students. The rest of adolescents drop out of school and join the informal sector or work on family farms, enterprises and domestic domains with little systematic training. Girls and poor boys start working as early as age five and their schooling has to be undertaken together with unpaid family labour. Boys’ mobility allows them to earn better incomes while girls usually marry early, fall pregnant and have children, resulting in their occupational immobility. Educated adolescents acquire skilled and better-paid jobs with bright career prospects while poorly educated and illiterate adolescents secure poorly paid, easy entry easy exit jobs usually in the informal sector. The global sex industry has emerged a source of employment for young female adolescents who may be trafficked or recruited voluntarily for sex work in Europe, Australia, the United States and Canada. HIV and AIDS are threats to adolescents especially in Southern Africa where they may head households after being orphaned. Orphaned and other poor and vulnerable adolescents are at risk of infection with HIV, dropping out of school, entering the labour force too early and falling sick with overwork in poor quality jobs with meager wages. The paper argues for provision of good quality formal and non-formal primary and some secondary and TVET for adolescents in Africa, especially for girls and poor boys in countries where barriers to schooling are high. The paper cites specific types of TVET which have been implemented in various countries, suggesting that secondary schooling, both formal and informal, be placed on a continuum and restructured to incorporated both formal and non-formal education, be made more accessible to poor, female, vulnerable and other adolescents and enable all students to choose any route to education and to ensure that there is equivalence, comparability and satisfactory quality in all types of education. The content of such TVET must suit the interests and life situations of the adolescents to make it relevant, effective and appropriate for generating decent levels of income and livelihoods for different types of adolescents.
KerkoCite.ItemAlsoKnownAs: 2129771:CWR9J8Z4 2317526:6GINJEJR
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:gender; F:girl; F:pay; F:women; P:culture; P:nature; Q:distance learning; Q:primary education; T:Educação profissionalizante; T:TVET; T:vocational school; _C:Ghana GHA; publicImportV1

Gender in Education Policy - Government of Uganda (2016)
UA-9e3445e4-27e0-4bb3-8fc9-87582a923f5c KerkoCite.ItemAlsoKnownAs: 2129771:SB7VVPSG 2317526:AVECW5AI
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; publicImportV1

Further Education and Training Act nº16, 2006 - Government of South Africa (2006)
Also known as Continuing Education and Training Act.
UA-12d0a561-668e-4da9-9506-2693c36aeb96 KerkoCite.ItemAlsoKnownAs: 2129771:3HJSUHG7 2317526:H2K8DC4E
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:South Africa; publicImportV1

Fundamentals of the development of Vocational Education and Further Education of VET pedagogues in Sub-Saharan Africa - Eicker, Friedhelm (2017)
For many years, the University of Rostock/Technical Education has supported three universities from Mozambique, Ethiopia and South Africa in their effort to establish a modern educational and further educational programme for VET pedagogues. A Further Education network was established in the first steps. If more German universities support it, this network can expand to various other Sub-Saharan African countries. This still poses the essential question which scientific approach will be the basic position. Furthermore the question is how the Further Education network of universities, vocational schools and other VET institutions should be developed locally in Sub-Saharan Africa. A constructivist approach, which is positioned between academic discipline and vocational science, will be proposed here. In the first place, university lecturers and selected teachers will be able to acquire shaping competence. A “Train the Trainer Further Education System” will be proposed.
KerkoCite.ItemAlsoKnownAs: 2129771:DZPPNXYY 2317526:TBLBB8G9 UTI-7B87897D-3120-3B03-9C28-4B8DC3719BA5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Ethiopia; C:Mozambique; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:pedagogy; T:TVET; T:in-service TVET; publicImportV1; ⛔ No DOI found

From counting women to ensuring women count: A qualitative study of university and early career experiences of women secondary school teachers in Addis Ababa, Ethiopia from a capabilities perspective - Abay, Negar Ashtari (2016)
At the heart of this study is a concern with moving from counting women—from a quantitative focus on gender parity—to having women count—ensuring conditions exist that allow women teachers to fully participate in quality teaching and the positive transformation of the teaching profession. Women comprise less than 20% of secondary school teachers in Ethiopia (MoE, 2014), reflecting similar patterns of under-representation elsewhere in Sub-Saharan Africa. This study uses in-depth interviews and field observations over a period of 15 months in Addis Ababa to shed light on why many women in Ethiopia who enter university do not make it into secondary school teaching and why many of those who enter teaching, in urban areas where most teachers are concentrated, do not stay in the profession. Drawing on a capabilities perspective, the study goes further to examine the cumulative disadvantage—in terms of well-being and agency—that women experience during the process of their university (undergraduate and teacher) training and in their early years of working in urban secondary schools, as well as the ways in which women contend with disadvantage. This study shows that such disadvantage and the responses to it have implications not only for whether women enter and stay in teaching but also for how they engage in their work. Utilizing the rich qualitative data collected and the analysis afforded by using the capability approach, the study concludes by recommending how different actors, including government, universities and schools, can foster institutional conditions of possibility (Walker, 2006a) and educational arrangements that enhance rather than limit full and equal participation in the teaching profession. Foregrounded throughout this study are the voices and experiences of young women, offering a perspective which disrupts the presumed norm of the single male teacher and highlights some of the limits of gender-neutral teacher policies.
KerkoCite.ItemAlsoKnownAs: 2129771:Z4ISYM3H 2317526:5S7STSEQ LOCAL-PQ-1873007472
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Ethiopia; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:gender; F:policy; F:teaching; F:women; P:measurement; P:school teacher; P:teacher education; P:teachers; Q:higher education; R:interview; R:observation; R:qualitative; R:quantitative; T:Ausbildung; T:career; Z:Higher education; Z:Teacher education; publicImportV1; ⛔ No DOI found

Four Ways Technology Has Negatively Changed Education - Alhumaid, Khadija (Journal of Educational and Social Research, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:BDVMUL5N
Keywords: _C:Bulgaria BGR; _C:Canada CAN; _C:China CHN; _C:Egypt EGY; _C:Iran IRN; _C:Poland POL; _C:Romania ROU; _C:Saudi Arabia SAU; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ❓ Multiple DOI

Forging New Partnerships: Lessons from the Dissemination of Agricultural Training Videos in Benin - Okry, Florent; Van Mele, Paul; Houinsou, Felix (The Journal of Agricultural Education and Extension, 2014)
Purpose: This article evaluates the dissemination and use of rice training videos by radio stations, farmers, farmer associations and extension services in Benin. It pays attention to positive deviants and process innovation within a 'hands-off experiment'. Design/methodology/approach: Using questionnaires and checklists we interviewed leaders of radio stations, extension services of nine municipalities and organized focus discussions with 13 farmer associations. Interviews focused on the processes of video dissemination/acquirement and the use and usefulness of the video. Findings: The commercial radio of Glazoué developed persuasive adverts and sold most of the 240 VCDs to farmers and extension services, whereas the community radios distributed most VCDs free of charge. About 20% of all the VCDs were sold, suggesting that farmers are eager to invest in acquiring knowledge. Extension services acquired the rice videos in various ways, indicating the need to inject videos via multiple pathways into the agricultural innovation system. Watching the farmer-to-farmer videos during staff meetings gave extension agents more confidence to interact with farmers. Practical implications: Videos do not need to be distributed to all farmer associations in the same village, as dissemination may take place between different associations. Farmers appreciate watching videos with their families if they are available in their local language. When suitable language versions are not available, group viewing is more appropriate. Originality/value: The farmer-to-farmer rice videos have created a momentum in Benin and across Africa, especially in the current context of rapid changes in the agricultural systems. The newly established non-governmental organization Access Agriculture aims at further supporting video-mediated learning in developing countries. [PUBLICATION ABSTRACT]
KerkoCite.ItemAlsoKnownAs: 10.1080/1389224x.2013.783495 10/gf62k7 2129771:HKPGFNHX 2317526:3SKW69JC
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Benin; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:developing country; F:access; F:learning; F:pay; P:agricultural; P:agriculture; P:media; P:service industry; P:technology; R:focus groups; R:interview; R:questionnaire; T:Ausbildung; T:Training; publicImportV1

Findings from a Mobile Tablet Project Implementation in Rural South Africa. - Herselman, Marlien; Botha, Adele; Dlamini, Sifiso; Marais, Mario; Mahwai, Nare (International Association for Development of the Information Society, 2019)
Publisher: ERIC KerkoCite.ItemAlsoKnownAs: 2129771:9RD2NSUC
Keywords: _C:Japan JPN; _C:South Africa ZAF; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Features of iPad language applications for speech-language therapy with children - Heyman, Nikki (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:3ZM4YRJR 2129771:4CY5A3GY
Keywords: _C:Australia AUS; _C:Austria AUT; _C:Canada CAN; _C:India IND; _C:Japan JPN; _C:New Zealand NZL; _C:Portugal PRT; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Switzerland CHE; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Feasibility of training Zambian nurse–midwives to perform postplacental and postpartum insertions of intrauterine devices - Prager, Sarah; Gupta, Pratima; Chilambwe, Jully; Vwalika, Bellington; Neukom, Josselyn; Siamwanza, Nomsa; Eber, Maxine; Blumenthal, Paul D. (International Journal of Gynecology & Obstetrics, 2012)
Abstract ObjectiveTo explore the feasibility of competency-based training of Zambian nurse–midwives in postplacental and postpartum intrauterine device (PPIUD) insertion and to estimate learning curves for this procedure. MethodsA pilot service-delivery project was conducted, involving 9 nurse–midwives who participated in a 10-day PPIUD insertion training course at the University Teaching Hospital, Lusaka, Zambia. US and Zambian clinicians taught the didactic and practical curriculum. Checklists were used for standardization and a pelvic model was developed to achieve PPIUD insertion competency in the classroom before moving to clinical practice. Patients were recruited during prenatal visits, in early labor, and postpartum. Informed, voluntary consent was obtained. All clinical PPIUD insertions were supervised or performed by experienced trainers. ResultsAll 9 nurse–midwives achieved competency on the pelvic model after 3 attempts. During the training period, 38 PPIUDs were inserted in postpartum women; no complications occurred. By the end of training, 4 of the nurse–midwives were deemed competent to independently insert PPIUDs. On average, 4 PPIUD insertions were needed to achieve clinical competency. ConclusionsConcentrated, competency-based training in PPIUD insertion is feasible in an African setting. Replication of such training could increase the popularity and prevalence of PPIUD use among African women.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijgo.2012.01.013 10/f2hgm7 2129771:PV67NDUD 2317526:22IE8B28
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:curriculum; F:learning; F:pedagogy; F:standards; F:teaching; F:women; P:nurse; P:services; T:Training; T:competency-based training; T:trainee; Z:Competency-based training; Z:Contraception; Z:Family planning; Z:Postpartum intrauterine device; Z:Postplacental intrauterine device; Z:Training model; publicImportV1

Faculty productivity in Zambian higher education in the face of internationalization: Unpacking research, publication and citation at the University of Zambia - Masaiti, Gift Masaiti; Mwila, Kennedy; Kulyambanino, Cecilia; Njobvu, Tommie (Scholarship of Teaching and Learning in the South, 2021)
Keywords: ❓ Multiple DOI

Factors Related to Teacher Absenteeism in Sierra Leone: Literature Review - Vijil, Alejandra; Bellinger, Amy; Godwin, Katie; Haßler, Björn; McBurnie, Chris (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 2129771:XLDCZECC 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Factors Influencing The Adoption Of Flexible Teaching Approaches In Technical Training Institutions In Kenya - Tiony, AK; Ferej, A; Kitainge, K (2016)
The goal of training in technical training institutions is to produce highly skilled graduates with competencies to handle various challenges in technology oriented fields. The continuing need to improve the quality of education in Technical Vocational Education and Training (TVET) is ever present. Therefore, effective teaching at these institutions is important to enhance quality of its graduates. This paper highlights the factors influencing the adoption of flexible approaches to teaching in technical training institutions in Kenya. Two specific objectives; establish how the syllabus content influences the adoption of flexible approaches to teaching; evaluate how institutional factors influence the adoption flexible approaches to teaching. The study was guided by a conceptual framework developed by the author. This study was conducted through descriptive research design. Data were collected from seven technical training colleges in Western Kenya. The method of data collection was through open and closed-ended structured questionnaires, and interview schedules. Collected data were coded in SPSS 17.0, (2008) and analysed using descriptive statistics. The study established that institutional managers had no authority to develop their own courses tailor made to suit specific needs in the market. The teaching resources that influence the adoption of flexible learning and teaching were also found to be unavailable in classrooms. Most institutions however had put in place strategic objectives to improve the quality of learning and teaching. Outputs from this study are expected to enhance the adoption of flexible learning in technical training institutions. In light of the findings of the study, it was recommended that the government of Kenya should establish a clear policy aimed at greater adaptability to flexibility. Institutions need to be granted authority to develop or reorganise syllabi for provision of industry specific solutions while being regulated to meet set international standards.
KerkoCite.ItemAlsoKnownAs: 2129771:WGXD2WGI 2317526:SV2CLWAI
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:inclusion; F:teaching approach; Q:ICT; Q:e-learning; Q:flexible; T:TVET; publicImportV1; ⛔ No DOI found

Factors influencing female undergraduate students' acceptance of, and motivation to, use tablet computers for learning - Alomary, Azza (University of Southampton, 2017)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:ES7QIDR4 2129771:LNWZCWZC
Keywords: _C:Australia AUS; _C:Belgium BEL; _C:Botswana BWA; _C:Brazil BRA; _C:Canada CAN; _C:China CHN; _C:Cuba CUB; _C:Ecuador ECU; _C:Egypt EGY; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Japan JPN; _C:Jordan JOR; _C:Korea; Republic KOR; _C:Lebanon LBN; _C:Libya LBY; _C:Malaysia MYS; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Philippines PHL; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Turkey TUR; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Factors affecting youth entrepreneurship development within Kibera, Kenya: The perspective of entrepreneurship education - Sambo, Wise (Problems and Perspectives in Management, 2016)
© Wise Sambo, 2016. All over the world there has been an increased interest in entrepreneurship education and the society in general. Kenya was among the first countries in Africa to introduce aspects of entrepreneurship education in its education and training systems. Entrepreneurship and business creation are a growing alternative for young people in different economies whose age group often faces a labor market with double digit unemployment rates. This study seeks to investigate and report on the factors affecting youth entrepreneurship development with specific reference to entrepreneurship education in Kibera, a district of Kenya. Two objectives are identified, namely (i) to determine the government's provision and access to the entrepreneurship education and training among the Kenyan youth, and (ii) to determine whether there is a relationship between the level of education, training and development of youth entrepreneurship. A sample of three hundred entrepreneurs (aged 18-35) within the Kibera district in Kenya is drawn to participate in this study. Structured survey questionnaires are used to collect primary data from business owners in the Kibera district. Findings revealed a strong positive correlation between the provision of entrepreneurship education and development of youth entrepreneurship and the level of education has a very weak positive correlation to youth entrepreneurship development. This study concludes with recommendations on how youth entrepreneurship can be improved in Kibera and the rest of Kenya. A total of 300 questionnaires were administered via emails with a total response rate of 83.3% (250) returned for analysis.
KerkoCite.ItemAlsoKnownAs: 10.21511/ppm.14(2-2).2016.09 2129771:9CEXBYJS 2129771:S2TWSBPJ 2317526:9UTQC4YM 2317526:P3X659PV
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:access; P:economy; R:questionnaire; R:survey; T:Training; T:entrepreneurship education; Z:Entrepreneurship education; Z:Kibera; Z:Unemployment; Z:Youth entrepreneurship; publicImportV1; ❓ Multiple DOI

Exploring the mismatch between teacher demand-supply in sub-Saharan Africa: Ghana as case study - Ntim, , S. (Mediterranean Center of Social and Educational Research, 2013)
This study presents an analysis of the factors affecting the supply and demand of school teachers in Ghana. The findings suggest that the major pull causing the mismatch in teacher supply-demand equation can be summed up under: a) economic demand, b) demographic factors and c) market forces. Sixty percent of those sampled constituting 162 of the respondents were of the view that there was a significant correlation between remuneration and supply while the other 40% (108) not attributing it to remuneration per se, nevertheless saw a link between supply and other economic issues such as end of service benefit. Ninety five percent of respondents were of the view that teacher upgrading in higher market premium courses in institutions of higher learning exacerbate teacher attrition into other better paid jobs: an indication of non-incentives pulling teachers from the teaching profession. The objective of the study is to contribute to advocacy on teacher issues, especially increased resources as well as innovative funding for the employment of sufficient number of teachers.
KerkoCite.ItemAlsoKnownAs: 10.5901/mjss.2013.v4n1p273 2129771:UFJXNNYW 2317526:G97GX7S6
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:incentives; F:learning; F:motivation; F:remuneration; F:teaching; P:economy; P:services; P:teacher education; P:teachers; Q:higher education; R:case study; T:career; Z:Higher education; Z:Teacher career; Z:Teacher deployment; Z:Teacher education; Z:Teacher motivation; _C:Ghana GHA; publicImportV1; ⚠️ Invalid DOI

Exploring technical vocational education and training systems in emerging markets: A case study on Ghana - Alagaraja, Meera; Arthur-Mensah, Nana (European Journal of Training and Development, 2013)
Purpose - The purpose of this study was to explore trends and changes in technical vocational education and training (TVET) in emerging economies as a national human resource development (NHRD) approach and its practical applications using Ghana as an example. Design/methodology/approach - A case study approach was used to develop an in-depth analysis of TVET practices in Ghana. The study utilizes a targeted review of literature, analysis of government documents and interviews with key informants as illustrative sources of evidence for developing the case study. Findings - TVET has been identified as a major contributor to skills development in Ghana. Capitalizing on the potential of TVET requires addressing the challenges of increasing employer participation in TVET, improving TVET curriculum to enhance student's employability and reflect labor market needs. Additionally, informal TVET plays a major role in skills development therefore it is recognized as part of the TVET planning process. Research limitations/implications - Data for this research were gathered from key informant interviews and archival records. Additional methods such as observations would further enhance this study. Further research of trends in Ghana to validate implications drawn from this research is recommended. Practical implications - This research provides an overview for HRD professionals to understand the potential of TVET as an approach to human capital development within emerging markets. This is because developing comprehensive plans that address national and employer needs regarding talent acquisition, development and retention will re-emerge as a critical objective for TVET system as nations compete in the global market place. Originality/value - This study provides a unique perspective of current TVET practices in Ghana and its implications for human resource development (HRD). Furthermore, it adds to the small but growing literature on HRD in Ghana and in the African context.
KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-04-2013-0037 10/gfc4m2 2129771:KWC5DXAK 2317526:BX9DKE3Z
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:emerging economies; F:curriculum; P:economy; P:human resources manager; P:measurement; R:case study; R:interview; R:observation; T:TVET; Z:Case studies; Z:Economic development; Z:Economic growth; Z:Emerging markets; Z:Globalization; Z:Human capital; Z:Human resource management; Z:Theory; Z:Workforce; _C:Ghana GHA; __C:filed:1; publicImportV1

Exploring selected theories applicable to educational disciplines and social sciences research. - Nkhata, Bentry; Mkandawire, Sitwe Benson; Nachiyunde, Kabunga; Phiri-Nalube, Patricia; Kaani, Bestern; Mulenga, Innocent Mutale; Phiri, Chidongo; Chileshe, Bernard; Sichula, Noah Kenny; Sikayomya, Patrick (2019)
Publisher: International Journal of Humanities Social Sciences and Education (IJHSSE)
Keywords: ⛔ No DOI found

Exploring first-year students’ experiences of using Moodle in learning an accounting undergraduate module at a South African University - Cele, Siyabonga Alpheos (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:P5CDJ2SU
Keywords: _C:Australia AUS; _C:Georgia GEO; _C:Greece GRC; _C:India IND; _C:Korea XKOR; _C:Malawi MWI; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Poland POL; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Exploring Business Studies teachers’ perspectives on teaching Grade 12 learners for Entrepreneurship. - Dube, Zinhle Thabisile Angeline (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:9R4Z7MW4
Keywords: _C:Australia AUS; _C:Botswana BWA; _C:China CHN; _C:Finland FIN; _C:India IND; _C:Kenya KEN; _C:Mozambique MOZ; _C:New Zealand NZL; _C:Nigeria NGA; _C:Norway NOR; _C:Portugal PRT; _C:Serbia SRB; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:United States USA; __C:filed:1; __C:scheme:1

Exploring Blended Learning for Science Teacher Professional Development in an African Context - Boitshwarelo, Bopelo (The International Review of Research in Open and Distributed Learning, 2009)
This paper explores a case of teacher professional development in Botswana, where a blended learning solution was attempted. The analysis of the implementation environment reveals deficiencies in policy, schools (workplaces), and training providers. The paper concludes with three recommendations: 1) Schools should support on-going teacher learning in the workplace and should manage ICT resources for use by both teachers and students; 2) Government should support participatory and localised learning and institutionalise ICT access and use; and 3) Training providers should use blended methods and should model good ICT practices. The author also notes that change is needed in the culture of teaching and learning so that ongoing, situated, participatory, and collaborative approaches are accepted. Finally, collaboration between the training providers and the schools is necessary as is a change in beliefs about the use of ICTs in education.
KerkoCite.ItemAlsoKnownAs: 10.19173/irrodl.v10i4.687 2129771:8BY4IISL 2405685:RP3KMTVU 2405685:THJLBADH 2534378:5C3ILQ5H 2534378:LSG5BCAP 2534378:PTQCJYNQ
Keywords: C:Botswana; _C:Botswana BWA; _C:Cuba CUB; _C:Senegal SEN; _C:South Africa ZAF; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ___working_potential_duplicate

Evidence-based approaches to improving teachers’ skills, in schools serving poor and marginalised communities - Power, Tom; Hedges, C; McCormick, R; Rahman, S (Commonwealth of Learning (COL), 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:7WRQ3XAW 2129771:GAUBXL6M 2339240:6ETY8HWG 2405685:26U2C9E5 2405685:FV3V5JDR 2405685:U22CW5TA 2534378:3GHKQTE7
Keywords: C:Poor and marginalised communities; _C:Bangladesh BGD; _C:France FRA; _C:India IND; _C:Jordan JOR; _C:Malawi MWI; _C:Sierra Leone SLE; _C:State of Palestine PSE; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Evaluation of the vocational education orientation programme (VEOP) at a university in South Africa - Jacobs, L; Wet, C De (The International Review of Research in Open and Distributed Learning, 2013)
To address the training needs of Further Education and Training college (FETC) lecturers, and in the absence of a full professional education qualification, several higher education institutions, FETCs, and other bodies in South Africa formed an alliance to develop a short programme towards a possible future full qualification. In 2010 a Vocational Education Orientation Programme (VEOP) was piloted. In line with the responsibility for quality assurance, and the need to inform further developments in the training of FETC lecturers, the aim of this research was to evaluate the VEOP presented by the University of the Free State (UFS). To reach the stated aim, a two phase evaluative study was undertaken (1) to assess the individual modules, and (2) to holistically investigate the quality of the programme. Two questionnaires were used to gather data. The first set of data was collected at the completion of each of the six modules. For the second phase of the study, 48 lecturer-students were randomly selected more than a year after completion of the VEOP. The study identified a number of strengths and weaknesses of the VEOP. The results emphasise the need to carefully select tutors and train them to have an understanding of the FETC milieu, rethink the methodology employed in the education training of FETC lecturers, and redesign the modules’ contents to better reflect the FETC sector. The need to enhance student support and improve administration is also highlighted by the study. The results of the study may inform the development of a full qualification for FETC lecturers.
KerkoCite.ItemAlsoKnownAs: 10.19173/irrodl.v14i4.1568 10/gf623n 2129771:ZEMMK3KE 2317526:MEYCNUIZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; P:media; Q:distance education; Q:open education; Q:open learning; R:evaluation; T:Ausbildung; T:TVET; publicImportV1

Evaluation of artisan training in metal silo construction for grain storage in Africa: Impact on uptake, entrepreneurship and income - Ndegwa, M.K.; de Groote, Hugo; Gitonga, Z.M. (International Journal of Educational Development, 2015)
This study assesses the impact of training sheet metal workers in Kenya on their uptake of learned skills and their income. Fifty-eight artisans trained in the construction of metal silos for hermetic grain storage were compared to a random sample of 123 untrained artisans. Results show that two-thirds of the trained artisans were making the silos, half of these in their own workshops and half as employees. The probability of using the skills learned declined with age but increased with previous experience in technical work. The training did not significantly increase the income of employed artisans, but increased the annual income of those who made the silos in their own workshops by KSh315,173 (about US$3,600). The overall impact could be improved by better targeting of trainees, by using apprenticeships as an alternative mode of training, and by encouraging entrepreneurship through business training and provision of credit.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2015.04.012 10/f7q8g8 2129771:5AI7LX8E 2317526:FI7GMN2J
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:artist; P:construction; P:metal; R:evaluation; R:impact; T:Lehrlingsausbildung; T:TVET; T:Training; T:trainee; Z:Adult education; Z:Benefits of education; Z:Employment skills; Z:Engineering education; Z:Intervention evaluation; Z:Vocational education and training; publicImportV1

Evaluating the impact of a tablet-based intervention on the mathematics attainment, receptive language and approaches to learning of preschool children - Walton, Jodie M. (University of Nottingham, 2018)
EdTechHub.ItemAlsoKnownAs: 2129771:W2LIJBJV
Keywords: _C:Australia AUS; _C:Brazil BRA; _C:China CHN; _C:France FRA; _C:India IND; _C:Ireland IRL; _C:Japan JPN; _C:Jordan JOR; _C:Korea; Republic KOR; _C:Malawi MWI; _C:Mexico MEX; _C:Netherlands NLD; _C:Singapore SGP; _C:Spain ESP; _C:Sudan SDN; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; __C:filed:1; __C:scheme:1

Evaluating and improving the quality of education - Part 6: How we inspect. A guide to external evaluation - Government of Uganda (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:V5NC2VCC 2317526:BTCJ68NK
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; National Standards; publicImportV1

ETSSP 2015-2020 - Education & Training Sector Strategic Plan - Government of Botswana (2015)
KerkoCite.ItemAlsoKnownAs: 2129771:MBJNYRR6 2317526:N36I6HE7
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; publicImportV1

Establishment of a VET-system with focus on Further Education: presentation of ideas on the motivation and establishment of a Further Education system, especially in universities in sub-Saharan Africa - Shindi, Alpheas (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:984CL23D 2317526:9CDMM8C3 UA-67F644AB-F6A3-435E-B209-9C76AE2F5F67
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Namibia; CLL:en; publicImportV1; ⛔ No DOI found

Equitable access to health professional training in Uganda: A cross sectional study - Galukande, M.; Maling, S.; Kabakyenga, J.; Nshaho, J.; Oboke, H.; Oonge, B.; Muyenje, H.; Katumba-Sentongo, G.; Mayanja-Kizza, H.; Sewankambo, N. K. (Annals of Global Health, 2018)
© 2018 The Author(s). Objective: We set out to assess inequalities to access health professional education, and the impact of an education improvement program supported by MEPI (Medical Education Partnership Initiative). Inequalities in the higher education system in sub-Saharan Africa remain despite some transformative policies and affirmative action. Methods: We reviewed enrollment data from four universities for the period 2001–2014 for various health professional training programs, and conducted group discussions through an iterative process with selected stakeholders, and including a group of education experts. Two time periods, 2001–2010 and 2011–2014, were considered. In 2010–11, the MEPI education program began. Gender ratios, regional representation, secondary schools, and the number of admissions by university and year were analysed. We used SPSS version 17 software to analyse these data with level of significance p < 0.05. We collated qualitative data along predetermined and emerging themes. Results: The overall male-to-female ratio among the student population was 2.3:1. In total, there were 7,023 admissions, 4,403 between 2001–2010 (440 per annum) and 2,620 between 2011–2014 (655 per annum) with p = 0.018. There were no significant increases in admissions in the central and western regions over the two time periods, 1,708 to 849 and 1,113 to 867 respectively, both p = 0.713 and p = 0.253. We propose improving the university admission criteria and increasing enrollment to health professions training schools. Conclusion: There were significant inequalities for higher education training in Uganda by gender, regional representation and school attended. Modifying the admission criteria and increasing enrollment may reduce these inequalities.
KerkoCite.ItemAlsoKnownAs: 10.29024/aogh.7 10/gd4gt8 2129771:FSHRTJ7F 2317526:K42YI764
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:Improvement; F:access; F:equity; F:gender; F:policy; P:health; P:media; Q:higher education; R:impact; R:iterative; R:qualitative; T:Ausbildung; T:Educação Profissional Técnica de Nível Médio; T:Fortbildung; _C:Uganda UGA; publicImportV1

Entrepreneurship training and skills development in Africa: Evidence from Koforidua Technical University, Ghana - Dzisi, Smile; Odoom, Franklin Dodzi; Gligah, Bernice (International Journal of Economics and Business Research, 2018)
Copyright © 2018 Inderscience Enterprises Ltd. The significant role entrepreneurial training plays in the success of entrepreneurs has been touted in the literature. This paper explores the idea of practical entrepreneurship training and skills development among African students. The primary objective is to establish the extent to which acquisition of practical entrepreneurial training in addition to the students’ course of study is beneficial to them. The findings revealed that practical entrepreneurial training is new to students in Ghana. The few students who are exposed to practical entrepreneurial training have acquired entrepreneurial skills and knowledge, and this enabled them to set up their own businesses. The findings of this study have implications on growth and development of the economies Africa by creating new and innovative jobs to subsequently and significantly decrease unemployment. The study recommends that tertiary institutions should have entrepreneurial centre for practical sessions.
KerkoCite.ItemAlsoKnownAs: 10.1504/ijebr.2018.092154 10/gf62nw 2129771:99834DNJ 2317526:YQJTXMQD
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; CA:AandC; CCZ:Ghana; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:economy; T:Training; Z:Education; Z:Entrepreneurial skills; Z:Entrepreneurs; Z:Innovation; Z:Practical sessions; Z:Students; Z:Training; _C:Ghana GHA; publicImportV1

Entrepreneurship Education in Sub-Saharan Africa: Results of a Case Study in Senegal - Garcia-Rodriguez, Francisco J; Gil-Soto, Esperanza; Ruiz-Rosa, Ines; Sene, Papa Mamour (2017)
The number of entrepreneurship education programs has grown worldwide in the last two decades. This has helped consolidate a fruitful line of research focusing on measuring the impact that these programs have on participating students' entrepreneurship potential. However, to date, these programs have almost exclusively centered on more developed countries. The present work, on the contrary, analyses the impact of an entrepreneurship promotion program carried out for a period of three years in the socioeconomic and cultural context of a less developed country: Senegal. Specifically, the program was aimed at students on different degree programs at the University of Gaston Berger. Theoretical approaches of effectuation and bricolage were applied and students' enterprise potential was tested ex ante and ex post. The results show that students had a significant improvement in their entrepreneurial potential, thus reflecting the effectiveness of entrepreneurship education in these contexts.
KerkoCite.ItemAlsoKnownAs: 2129771:BLNBLAL2 2317526:RSJYRBT8
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Senegal; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing country; D:less developed country; F:Improvement; F:attitude; P:culture; Q:degree; R:case study; R:impact; T:entrepreneurship education; Z:Attitudes; Z:Developing countries–LDCs; Z:Entrepreneurs; Z:Students; publicImportV1; ⛔ No DOI found

Entrepreneurship education in Ghana – the case of the KNUST entrepreneurship clinic - Nyadu-Addo, Ralph; Mensah, Mavis Serwah Benneh (Journal of Small Business and Enterprise Development, 2018)
© 2018, Emerald Publishing Limited. Purpose: Entrepreneurship education thrives on the pillars of experiential education. Using the case of the Kwame Nkrumah University of Science and Technology in Ghana, the purpose of this paper is to examine the entrepreneurship clinic (EC) as a viable pedagogy for the promotion of experiential education in entrepreneurship. Design/methodology/approach: The paper relies on insider action research to analyse, within Joplin’s five-step model, the case of the EC at the Kwame Nkrumah University of Science and Technology (KNUST), Ghana. Findings: The analysis showed that the KNUST clinic comprises five main activities including preparation, orientation, selection and matching, coaching and monitoring and evaluation. In relation to Joplin’s five-step model, the first three stages of the clinic provide focus for the clinic while the remaining two stages – coaching and monitoring and evaluation – entail activities that are geared towards action, support, feedback and debrief. Through the clinic, thousands of tertiary students have been trained in entrepreneurship and new venture creation; some selected participants have been coached while others have had the opportunity to qualify for business incubation. Research limitations/implications: Although the paper discusses some achievements of the clinic in relation to enrolment and fundraising, it does not assess the impact of the clinic on the entrepreneurial competencies, intentions and initiatives of participants, hence, these issues are recommended for future research. Practical implications: The paper demonstrates that it is feasible to implement the EC methodology, irrespective of the cost and time implications that are often associated with experiential educational methodologies. However, support from university management, funding raising from internal and external sources and technical support from industry and government agencies are key to the sustainability of clinics. Originality/value: The paper adds novelty to the entrepreneurship education literature by bringing to the fore how a university in an emerging African economy is implementing and managing the EC pedagogy.
KerkoCite.ItemAlsoKnownAs: 10.1108/jsbed-02-2017-0062 10/gf62p2 2129771:8T5MIJXW 2317526:3JJTGLIK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:achievement; F:pedagogy; P:economy; P:measurement; P:technology; R:evaluation; R:impact; T:entrepreneurship education; T:trainee; Z:Clinic; Z:Development; Z:Education; Z:Entrepreneurship; Z:Experiential; _C:Ghana GHA; publicImportV1

Entrepreneurial skills in technical vocational education and training as a strategic approach for achieving youth empowerment in Nigeria - Maigida, JF; Saba, TM (International Journal of Humanities and Social Science, 2013)
Entrepreneurial studies are inter-displinary training that focuses on the tools needed to start a new business or vocation. Because Nigeria is fast becoming a predominantly youthful society with high rate of unemployment requires training the youth in entrepreneurial skills in Technical Vocational Education and Training to tackle the unemployment which has reached alarming proportions. This is because the youth represents a tremendous potentials development of human capital which the society cannot afford to neglect. Young people’s situation and future prospects are of vital concern to all. Many youth face high unemployment, joblessness and difficulties in getting a firm foothold into the labour market. These have led to problem of unemployment especially among youth leaving various educational institutions. The youth graduate from school without the needed skills or competencies that would enable them function in today’s emerging society. Therefore, this paper examined how entrepreneurial skills in Technical Vocational Education and Training (TVET) can be used as a strategic approach for achieving youth empowerment in Nigeria.
KerkoCite.ItemAlsoKnownAs: 2129771:Y7937GDQ 2317526:7XMIRUEB UTI-07487CB8-9983-3320-9CBB-FF1466B43253
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:assessment; P:measurement; T:Ausbildung; T:TVET; publicImportV1; ⛔ No DOI found

English WAEC BECE Exam Syllabus - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745440 2129771:9CGPKHNL
Keywords: SSEIP; _C:Sierra Leone SLE

English teacher education curriculum designing: A mixed methods analysis of the programme at the University of Zambia - Mulenga, Innocent (The University of Zambia, 2015)

English, Senior Secondary School, Year 4, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745270 2129771:YQAQHCT5
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745314 2129771:TTQUN6KS
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 2 MS0723, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745416 2129771:SWBWTWVJ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745268 2129771:GPGD72GN
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745312 2129771:QHHSU9NQ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 1 MS0723, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745414 2129771:VJSMAI3B
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745338 2129771:EUYTPL2S
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 4, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745336 2129771:XK55XTGP
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745266 2129771:AV2NB6EN
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745310 2129771:UPQGVIH4
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 3 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745412 2129771:QSC9IPFB
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745264 2129771:XBWQ52NV
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745308 2129771:7KPSBKY2
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 2 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745410 2129771:LYBP3EDA
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745262 2129771:IAEEYT7S
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745306 2129771:RZFA8PW6
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 1 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745408 2129771:LNRM3ZQ7
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745334 2129771:L3443FQQ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745332 2129771:DA83SCEZ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 3, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745330 2129771:E5A9TX45
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745260 2129771:CJNKIJM2
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745304 2129771:QWQRVB4D
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 3 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745406 2129771:WS8ESCBJ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745258 2129771:DH37LZV8
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745302 2129771:9278HNXV
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 2 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745404 2129771:QRSTYN48
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745254 2129771:783FMDXJ
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745300 2129771:DRCH92CA
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 1 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745400 2129771:MDNPN76N
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745328 2129771:LHS9ECTN
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745326 2129771:C7WZE3RD
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 2, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745324 2129771:H8L2G74C
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 3 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745252 2129771:CMNJVMIT
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 3, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745298 2129771:6L7F3BQH
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 3 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745398 2129771:GNETPRAG
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 2 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745250 2129771:MJSI2Z37
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 2, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745296 2129771:AUK67RFP
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 2 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745396 2129771:IEDAA2RI
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 1 SeniorSecondarySchool, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745248 2129771:BWQR74K7
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 1, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745294 2129771:E744KZ2M
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 1 MS0722, teachers guide - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745394 2129771:K2L9VFAS
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745320 2129771:2NNACSQS
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745318 2129771:KZZN77XR
Keywords: SSEIP; _C:Sierra Leone SLE

English, Senior Secondary School, Year 1, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745316 2129771:IS8TDI66
Keywords: SSEIP; _C:Sierra Leone SLE

ENGLISH LANGUAGE - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745444 2129771:YMZCQS7A
Keywords: SSEIP; _C:Sierra Leone SLE

English in Action: a new approach to continuing professional development through the use of mediated video, peer support and low-cost mobile phones in Bangladesh - Woodward, Clare; Griffiths, Malcolm; Solly, Mike (Innovations In The Continuing Professional Development Of English Language Teachers, 2014)
KerkoCite.ItemAlsoKnownAs: 2129771:PR4JTY27 2405685:VLPHGQ5H
Keywords: C:Bangladesh; _C:Afghanistan AFG; _C:Argentina ARG; _C:Australia AUS; _C:Bahrain BHR; _C:Bangladesh BGD; _C:Brazil BRA; _C:Bulgaria BGR; _C:Cameroon CMR; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Croatia HRV; _C:Czech Republic CZE; _C:Djibouti DJI; _C:Dominican Republic DOM; _C:Ethiopia ETH; _C:France FRA; _C:Germany DEU; _C:Greece GRC; _C:Hungary HUN; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Italy ITA; _C:Japan JPN; _C:Kazakhstan KAZ; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Lithuania LTU; _C:Malaysia MYS; _C:Mali MLI; _C:Mexico MEX; _C:Mongolia MNG; _C:Montenegro MNE; _C:Namibia NAM; _C:Oman OMN; _C:Pakistan PAK; _C:Poland POL; _C:Romania ROU; _C:Russian Federation RUS; _C:Saudi Arabia SAU; _C:Serbia SRB; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:Syrian Arab Republic SYR; _C:Thailand THA; _C:Turkey TUR; _C:Ukraine UKR; _C:United Arab Emirates ARE; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Uzbekistan UZB; _C:Yemen YEM; __C:filed:1; __C:scheme:1

English, Class 09, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745171 2129771:EBAN9SQS
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 09, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745210 2129771:4ASWZUTB
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 09, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745208 2129771:KA36LRQ3
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 09, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745167 2129771:PK9PIWNE
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 09, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745206 2129771:3XU8A8MP
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 08, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745165 2129771:9267C68M
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 08, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745204 2129771:5QMDNWP5
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 08, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745163 2129771:VPU8AYJJ
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 08, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745202 2129771:6JURBC9X
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 08, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745161 2129771:UPPTLQPS
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 08, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745200 2129771:RKBEBC6H
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 07, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745159 2129771:V964FYNF
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 07, Term 03 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745198 2129771:8EFDHYE8
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 07, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745157 2129771:2EQ3NSCV
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 07, Term 02 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745196 2129771:E79AJ9JW
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 07, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745155 2129771:MMG8UDG5
Keywords: SSEIP; _C:Sierra Leone SLE

English Class 07, Term 01 Full, pupil handbook - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745194 2129771:QT9TV93W
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 06, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745084 2129771:A6LIC8N2
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 06, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745082 2129771:VX6HPQGI
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 06, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745080 2129771:ERJNSG3A
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 05, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745078 2129771:9Z9CJZX9
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 05, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745076 2129771:BGYEPP5W
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 05, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745074 2129771:AAQQSV3B
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 04, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745072 2129771:F2379T65
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 04, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745070 2129771:6CDIDFID
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 04, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745068 2129771:P7KQJGK2
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 03, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745066 2129771:H3ZN6RK2
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 03, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745064 2129771:XJACEB2W
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 03, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745062 2129771:TDT9WIVH
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 02, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745060 2129771:YTWV4LZW
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 02, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745058 2129771:HXBDJXR9
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 02, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745056 2129771:I5NR3LPR
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 01, Term 03, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745054 2129771:JDSF535N
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 01, Term 02, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745052 2129771:ZKWKD3KC
Keywords: SSEIP; _C:Sierra Leone SLE

English, Class 01, Term 01, lesson plan - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745050 2129771:AMU6VMDD
Keywords: SSEIP; _C:Sierra Leone SLE

Empowering Individuals to Empower the Nation Nigeria - Sharehu, A; Achor, E (National Association for Science, Humanities & Education Research Journal, 2014)
This paper examined strategies of empowering individuals to empower the nation with focus on Technical and Vocational Education Training (TVET), Entrepreneurship Education (EE) and Information Communication Technology (ICT). It is established that from history TVE was not given its prominent place and that may have accounted for the slow and lagging nature of advancement in TVE. Consequently, future progress will be determined by the level of empowerment given to individuals in schools which is predicated upon level of empowerment of TVE teachers themselves. A number of strategies were identified as possible options for empowering learners and youths in Nigeria. Some of them include combining TVE with academic work till end of secondary education, vocationalisation, and work experience programmes (eg SIWES, youth apprenticeship and school based experience) and adjusting to effects of advance technology among others. With government’s political will and schools and teachers prepared for change, much could be achieved in empowering the nation.
KerkoCite.ItemAlsoKnownAs: 2129771:7WQEPFKI 2317526:YBZRX3IR
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:Q; CT:T; Q:ICT; T:TVET; T:apprenticeship training; T:entrepreneurship education; publicImportV1; ⛔ No DOI found

Employers' perceptions regarding the quality of technical education and training in Southern Africa : a case of the Botswana Technical Education Programme - Odora, RJ (2011)
KerkoCite.ItemAlsoKnownAs: 2129771:SHVTNY2L 2317526:83BN2WMC LOCAL-jolis:1045432917
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Botswana; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; T:TVET; publicImportV1; ⛔ No DOI found

Employability Skills in TVET Curriculum in Nigeria Federal Universities of Technology - Ismail, Sarimah; Mohammed, Dahiru Sale (Procedia - Social and Behavioral Sciences, 2015)
In the 21st century, employability skill is the most required skill besides technical knowledge in an attempt to compete for employment and sustain job at the industrial global market. However, Nigerian TVET graduates are not equipped with the employability skills needed by the industries and as a result, they are not ready to enter into workforce. This concept paper is written to discuss how the curriculum of one of TVET programmes at the Federal Universities of Technology in Nigeria, which is Electrical Technology Education has contributed to this issue. Analytical review on Electrical Technology Education programme curriculum showed that the curriculum gave less attention to practice based courses that provide skills of the programme than theory based courses and no course in the programme curriculum that directly teaches good attitudes and traits. As a result, there is lack of incorporation of employability skills such as Problem solving and decision making, Lifelong learning and Competencies amongst the graduates. Other issues discussed are the need of employability skills in TVET curriculum of Nigeria, employability skills, Electrical Technology Education in Nigeria, and the analysis of Electrical Technology Education curriculum in Nigeria The last part of this paper is recommendation for the curriculum of Electrical Technology Education to be designed with equal number of theory and practice courses by giving emphasize on all eleven generic skills, good traits and attitudes.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2015.08.111 10/gf62zv 2129771:YWWJS6SA 2317526:NFVGKN6Q
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; Analysis; C:Nigeria; CC:Nigeria; CLL:en; Electrical Technology Education; curriculum; employability skills; integrations; needs; publicImportV1

EMIS | Education Management Information System - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
Library Catalog: mbsse.gov.sl KerkoCite.ItemAlsoKnownAs: 2129771:VHB75LAY 2405685:WDHKTX4J

Effects of Three Categories of Manpower on Undergraduate Students' Learning Outcomes in Technical Education and Their Implications for the Curriculum Implementation - Alade, Ibiwumi Abiodun (JISTE, 2015)
The implementation of technical education curriculum has been besieged with dearth of qualified teaching personnel over the years in Nigeria and some other African countries. Similarly, the available higher institutions where vocational and technical education experts are prepared have not been able to meet this demand of the manpower. This calls for possible intervention strategies which could perhaps address this lingering problem. It is on this observation that this study examines the effects of three categories of manpower on undergraduate students' learning outcomes in technical education and their implications for the curriculum implementation. The pretest, posttest control group, quasi experimental research design with a 4x3x2 factorial matrix was adopted for the study. Sixty technical education undergraduate students from a Nigerian university were purposively sampled for the study. Seven null hypotheses are generated and tested at 0.05 level of significance. Three research instruments were developed, validated, and used for data collection. Data collected were analyzed using Analysis of Covariance (ANCOVA) while Scheffe's post-hoc test was used to explain significant main and interaction effects respectively. Results showed that there is significant main effect of treatment on students' learning outcomes in technical education (F[subscript 3], 57 = 132.314; P<0.05). The students taught by vocational educator performed best in basic vocational knowledge acquisition (X = 16.38) while those taught by literate artisans had the highest means score on vocational skills acquisition (x = 42.82), then those taught by higher technician group had a mean score of x = 38.27 in vocational skills acquisition, while the control group performed least (x = 31.60). It was concluded that the three categories of manpower are effective at enhancing students' learning outcomes in technical education in various dimensions. To this end, it was recommended that literate artisans should be integrated to the teaching of vocational skills in the tertiary institutions.
KerkoCite.ItemAlsoKnownAs: 2129771:7LAZ9RCB 2317526:5S7Q7V45
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:curriculum; F:gender; F:learning; F:outcomes; F:teaching; P:artist; P:measurement; P:technician; R:observation; R:research design; T:TVET; T:vocational skills; Z:Academic Ability; Z:Control Groups; Z:Curriculum Implementation; Z:Data Collection; Z:Foreign Countries; Z:Gender Differences; Z:Hypothesis Testing; Z:Job Skills; Z:Labor Force; Z:Outcomes of Education; Z:Pretests Posttests; Z:Quasiexperimental Design; Z:Statistical Analysis; Z:Technical Education; Z:Undergraduate Students; Z:Vocational Education; __C:filed:1; publicImportV1; ⛔ No DOI found

Effectiveness of Technical and Vocational Education and Training (TVET) Insights from Ethiopia's reform - Baraki, Atakilt Hagos; van Kemenade, Everard (TQM, 2013)
Purpose - This paper provides an overview on the technical and vocational education and training (TVET) program components/mechanisms and their overall effect on learning outcomes in a developing country context. Design/methodology/approach - Using secondary data, this descriptive case study integrates the realistic evaluation framework of Pawson and Tilley (1997) with Total Quality Management (TQM) frameworks. Findings - Ethiopia's TVET system adopts/adapts international best practices. Following the implementation of the 2008 TVET strategy, the proportion of formal TVET graduates who were recognized as competent by the assessment and certification system increased from 17.42 percent in 2009/2010 to 40.23 percent in 2011/2012. Nevertheless, there is regional variation. Research limitations/implications - Outcome-based TVET reforms that are based on TQM frameworks could improve learning outcome achievements in developing countries by enhancing awareness, coordination, integration, flexibility, participation, empowerment, accountability and a quality culture. Nevertheless, this research is limited by lack of longitudinal data on competency test results. There is also a need for further investigation into the practice of TQM and the sources of differences in internal effectiveness across TVET institutions. Practical implications - Our description of the Ethiopian reform experience, which is based on international best experience, could better inform policy makers and practitioners in TVETelsewhere in Africa. Originality/value - A realistic evaluation of TVET programs, the articulation of the mechanisms, especially based on TQM, that affect TVET effectiveness would add some insight into the literature. The evidence we have provided from the Ethiopian case is also fresh. © Emerald Group Publishing Limited.
KerkoCite.ItemAlsoKnownAs: 10.1108/tqm-11-2012-0099 10/gf62pf 2129771:XWCMFHMK 2317526:PUQ8JVC2
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing country; F:achievement; F:assessment; F:learning; F:outcomes; F:policy; P:culture; P:mechanic; Q:certificate; R:case study; R:evaluation; T:TVET; Z:Developing countries; Z:Ethiopia; Z:Internal effectiveness; Z:Realistic evaluation; Z:TVET quality; Z:TVET reform; Z:Total quality management; __C:filed:1; publicImportV1

Effectiveness and viability of revenue diversification in sub-saharan africa’s higher education: examining Zambia’s public universities. - Masaiti, Gift (2015)
Publisher: International Journal of Humanities Social Sciences and Education
Keywords: ⛔ No DOI found

Effective teaching and learning of large cohorts in institutions of higher learning in Zambia: Challenges and opportunities - Haßler, Björn; Shemi, Alice (2017)
KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1033 2129771:6SW7NKWT
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _bjoern_cv; _comingsoon; _r:AddedByMyEducationEvidence

Effect of Flipped Classroom Strategy on The Performance of Prospective Teachers of Khyber Pakhtunkhwa - Minaz, Maksal (Northern University Nowshera, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:JJ33TDMP
Keywords: _C:Australia AUS; _C:Belgium BEL; _C:Canada CAN; _C:China CHN; _C:Egypt EGY; _C:Finland FIN; _C:Greece GRC; _C:India IND; _C:Netherlands NLD; _C:Pakistan PAK; _C:Saudi Arabia SAU; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Educational Technology Topic Guide - Power, Tom (2014)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:8WY3UUCX 2129771:CM5HB782 2129771:U82KRZAA 257089:BQNAW6PN 261495:H7X3RNJG
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Chile CHL; _C:Congo XCO; _C:Egypt EGY; _C:Ethiopia ETH; _C:Ghana GHA; _C:Guinea GIN; _C:Haiti HTI; _C:India IND; _C:Jamaica JAM; _C:Jordan JOR; _C:Kenya KEN; _C:Korea XKOR; _C:Malawi MWI; _C:Mali MLI; _C:Mozambique MOZ; _C:Myanmar MMR; _C:Namibia NAM; _C:Nepal NPL; _C:Nigeria NGA; _C:Oman OMN; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Qatar QAT; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:Somalia SOM; _C:South Africa ZAF; _C:South Sudan SSD; _C:State of Palestine PSE; _C:Sudan SDN; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Education Workforce Supply and Needs in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:23HCCGWI 2129771:6QUWDNYH 2129771:8MNC2N4I 2129771:NVEG4QQ7 2129771:X4L45EA5 2339240:2KB28MDX 2405685:52ZGRDGR 2405685:8MIWRFD2 2486141:SXAGH5JI 2601447:ZQXDP3AD 4556019:J9ZYVZC6
Keywords: _C:Canada CAN; _C:Chile CHL; _C:Finland FIN; _C:Ghana GHA; _C:Korea; Republic KOR; _C:Malawi MWI; _C:Nigeria NGA; _C:Peru PER; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Viet Nam VNM; __C:filed:1; __C:scheme:1; _yl:c; ⛔ No DOI found

Education Workforce Spatial Analysis in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:352YTJXA 2129771:B6HL4K8H 2129771:IDUHPLI9 2129771:KY2Y4AEB 2129771:PDLNHLL4 2129771:RZJA4ZWV 2339240:Q42KZNBD 2339240:V7GZZAMR 2405685:2HRVB9KF 2405685:B5LNLGZL 2405685:FS263PV6 2486141:JNVMUL8V 2601447:VTLIFB9A 4042040:ZQNXW7RV
Keywords: _C:India IND; _C:Sierra Leone SLE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Education Workforce Recruitment and Matching in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:CW55SAM3 2129771:SLC5ADTU 2339240:8YVNU64V 2405685:KZBP674C
Keywords: _C:Bangladesh BGD; _C:Ethiopia ETH; _C:France FRA; _C:Gambia GMB; _C:Ghana GHA; _C:India IND; _C:Malawi MWI; _C:Mexico MEX; _C:Sierra Leone SLE; _C:Tanzania TZA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Education Workforce Management in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:2U4XHCEW 2129771:4JVXKYSH 2129771:8GWCPEXT 2129771:C4BFMJUQ 2339240:28FQ3DS8 2405685:QEWLRFDX 2601447:YEE5ED32
Keywords: _C:Australia AUS; _C:Chile CHL; _C:China CHN; _C:Eritrea ERI; _C:France FRA; _C:Gambia GMB; _C:Iceland ISL; _C:India IND; _C:Italy ITA; _C:Kenya KEN; _C:Lebanon LBN; _C:Lesotho LSO; _C:Mozambique MOZ; _C:Netherlands NLD; _C:Nigeria NGA; _C:Pakistan PAK; _C:Senegal SEN; _C:Sierra Leone SLE; _C:Tanzania TZA; _C:Togo TGO; _C:Uganda UGA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Education Workforce Costed Options Paper - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:BSJCUVG2
Keywords: _C:Sierra Leone SLE; __C:filed:1; __C:scheme:1

Education Statistics Annual Abstract - Government of Ethiopia (2011)
KerkoCite.ItemAlsoKnownAs: 2129771:9UCN9LNT 2317526:RAVWXKPC
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Ethiopia; publicImportV1

Education Standards Officers Supervision Roles of Curriculum Implementation in Choma District in Zambia: What do Teachers Think? - Mooya, Eugine; Mulenga, Innocent Mutale (Multidisciplinary Journal of Language and Social Sciences Education (2664-083X, Online ISSN: Print ISSN: 2616-4736), 2021)
Keywords: ⛔ No DOI found

Education service transformation in Sierra Leone: Where policy meets the people | Blog | Global Partnership for Education - Sengeh, David Moinina (2020)
As GPE prepares to launch a new five-year strategic plan responding to partner countries’ demands for transformative change, GPE Board Member and Minister of Basic and Senior Secondary Education David Moinina Sengeh shares learnings from his first year of office on what transforming education means to the people of Sierra Leone.
KerkoCite.ItemAlsoKnownAs: 2129771:EFIQDYW2 2339240:DE8NBSA7 2405685:TJT9ZI8V
Keywords: _C:Sierra Leone SLE

Education service transformation in Sierra Leone: Where policy meets the people - Sengeh, David (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:GWGDR5N4 2339240:Y5AL4GBH 2405685:CL5T3HVF
Keywords: _C:Sierra Leone SLE

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:QDLHI3WH 2339240:AIISD4KD 2405685:DFHS5ZVL
Keywords: _C:Sierra Leone SLE

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:4PRIBRQ2 2405685:24PRFKEK

Education Needs Assessment Report - Sierra Leone - Plan International (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:TU5FBQUH 2405685:FPBLY982 2486141:T8M7TVMD
Keywords: _C:Sierra Leone SLE

Education in Zambia at fifty years of independence and beyond: history, current status and contemporary issues. - Masaiti, Gift (Unza Press, 2018)

Education in Emergencies Endline Evaluation Report – Sierra Leone - Sankoh, Didan; Cowan, Emma (Girls' Education Challenge, UK Aid, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:TCAM9TMU 2405685:G2I2A3Y5
Keywords: _C:Sierra Leone SLE

Education ICT assemblage: encounters of discourses, emotions, affects, subjects, and their productive forces - Lameu, Paula Cristina (University of Birmingham, 2017)
EdTechHub.ItemAlsoKnownAs: 2129771:F87U5UCI
Keywords: _C:Australia AUS; _C:Brazil BRA; _C:Canada CAN; _C:China CHN; _C:Korea; Republic KOR; _C:New Zealand NZL; _C:South Africa ZAF; _C:Spain ESP; _C:Sudan SDN; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

Education for sustainable development in Africa: a critique of regional agendas - Tikly, Leon (Asia Pacific Education Review, 2019)
KerkoCite.ItemAlsoKnownAs: 10.1007/s12564-019-09600-5 2129771:9REQDVU6

Education Coverage in Sierra Leone - GRID3 (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:982SWX54
Keywords: _C:Luxembourg LUX; _C:Sierra Leone SLE; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

Education continuity during the Coronavirus crisis: Sierra Leone and Liberia Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Rising Academy Network, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:BQT46MPC 2339240:YUCXSRDK 2405685:U7GMEU2U
Keywords: _C:Sierra Leone SLE

Education Consortium - Sierra Leone Secondary Education Improvement Programme (SSEIP) [zip] - SSEIP (2020)
ZIP file for Education Consortium - Sierra Leone Secondary Education Improvement Programme (SSEIP).
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3743296 10.5281/zenodo.3743296 2129771:KQEE3GAS
Keywords: SSEIP; _C:Sierra Leone SLE

Education buildings: resilience to global climate change and avoidance of inequalities - Wargocki, Pawel (Open Development & Education, 2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912097 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1126 ZenodoArchiveConcept: 10912096
Keywords: _r:AddedByMyEducationEvidence

Education as currently provided in Zambia. - Masaiti, Gift (UNZA Press, 2018)

Education and climate change – What retrofits could make classroom environments more conducive to learning? - Toyinbo, Oluyemi; Villavicencio, Xuzel (Open Development & Education, 2023)
An output of the Open Development & Education, https://.opendeved.net/
ZenodoArchiveID: 8392534 ZenodoArchiveConcept: 8392533 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0297 10.53832/opendeved.1014 2129771:WSD6C5HV
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgnd3 previousDOI: 10.5281/zenodo.3903213 shortDOI: 10/ghgnd3 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3903213 10.5281/zenodo.3903213 10.53832/edtechhub.0038 10/ghgnd3 2129771:YRBISV4P 2339240:NJVI79X2 2339240:VJKBU72Y 2405685:C5MWWQI2 2405685:D25NXEFY
Keywords: C:Sierra Leone; LP: English; _C:Sierra Leone SLE; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech for learning in emergencies and displaced settings - Tauson, Michaelle; Stannard, Luke (London: Save the Children UK, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:76WWBGAL 2129771:DL685ZJZ 2129771:QFUWKQGI
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:Belgium BEL; _C:Botswana BWA; _C:Brazil BRA; _C:China CHN; _C:Egypt EGY; _C:Ethiopia ETH; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Holy See VAT; _C:Honduras HND; _C:India IND; _C:Indonesia IDN; _C:Israel ISR; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Malawi MWI; _C:Mexico MEX; _C:Namibia NAM; _C:Nepal NPL; _C:Nigeria NGA; _C:Oman OMN; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Qatar QAT; _C:Seychelles SYC; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:South Sudan SSD; _C:Sri Lanka LKA; _C:State of Palestine PSE; _C:Sudan SDN; _C:Syrian Arab Republic SYR; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United States USA; _C:Uruguay URY; _C:Yemen YEM; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2129771:VN6G6ARB 2405685:K5BJUBRE 2405685:U6G7C62D
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Ebola, Education And Innovation In Sierra Leone - Berry, Chris (DFID bloggers, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:WE6ZTJGI 2339240:Y4SENBBT 2405685:CYLG6GK7 2405685:DD7BMIBU
Keywords: _C:Sierra Leone SLE; ___working_potential_duplicate

Earthquake and Its Impacts on Education: Aftermath Nepal Quake 2015 - Basnet, Bal Krishna (European Educational Researcher, 2020)
Although earthquakes themselves do not kill people, they highlight the critical importance of physical infrastructure resilience, safety measures and preparedness for natural disasters. Earthquakes are one of several environmental crises that can be categorized as a natural hazard/disaster. This study uses the qualitative method of research. The semi-structured interview with follow up questions among the educational actors like students, head/teachers, officials from the district education office and the local NGO staff working in the field of education before and immediately after the earthquake. The content analyses of curriculum of secondary level and textbooks of grade IX and X as well as field visit/observation were carried out during the study. The result and the conclusion of this study show that following the 2015 earthquake, the preparation of emergency bags helped children and their families gather essential items in a ready-to-go bag specifically designed for disaster situations. Simulation activities in schools helped prepare students for future disasters, and there were also many initiatives to reduce student and teacher trauma following the 2015 quake, including the development of a credited 5-hour teacher professional development (TPD) counselling programme. The inclusion of school disaster risk reduction (DRR) education in the curriculum and textbooks containing information on earthquakes, their cause, effects and preventive measures have now been disseminated in many languages including Nepali and English.
Publisher: The European Educational Researcher KerkoCite.ItemAlsoKnownAs: 10.31757/euer.332 2129771:Y49STNFM
Keywords: Administrator Attitudes; Content Analysis; Counseling Services; Emergency Programs; Faculty Development; Foreign Countries; Futures (of Society); Grade 10; Grade 9; Multilingualism; Natural Disasters; Nongovernmental Organizations; Prevention; Program Descriptions; Resilience (Psychology); Risk; Safety; Secondary School Curriculum; Simulation; Student Attitudes; Teacher Attitudes; Textbooks; Trauma; _C:Bangladesh BGD; _C:Cambodia KHM; _C:Chile CHL; _C:China CHN; _C:Egypt EGY; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Japan JPN; _C:Malaysia MYS; _C:Maldives MDV; _C:Nepal NPL; _C:Norway NOR; _C:Pakistan PAK; _C:Philippines PHL; _C:Sri Lanka LKA; _C:Switzerland CHE; _C:United States USA; __C:filed:1; __C:scheme:1

E-Learning in nursing education in Rwanda: benefits and challenges. An exploration of participants' perspectives - Harerimana, A; Mtshali, NG; Hewing, H (Journal of Nursing and Health Science, 2016)
E-learning is a commonplace in nursing and healthcare professional education, and generally the importance of Information and Communication Technology (ICT) and the Internet in tertiary education is recognized. The entry visa for e-learning is a computer and an Internet connection [1]. The aim of this paper is to analyse the utilisation of e-learning in selected nursing campus in Rwanda. A convergence parallel mixed method was use as recommended by Creswell[2]. For quantitative survey, a total of 275 participants responded to the questionnaires, and for qualitative approach, a total number of 40 participants were purposively selected. Quantitative data was analysed using SPSS 23, and for qualitative data, thematic analysis was used. The finding from this study indicated that participants were ready and eager to embrace e-learning in nursing education due to a number of benefits they reported such e-learning being a student centred approach, being a blended learning method, and fast track for the production of nursing workforce taking into consideration the history of Rwanda. However it was found that a number of challenges were hindering a proper implementation such as: resource constraints, insufficient teachers and students training in ICT, language barrier, lack of policies regarding e-learning, resistance to change, issues related to Moodle accessibility.
KerkoCite.ItemAlsoKnownAs: 2129771:ZR2CG5P7 2317526:5J65FI2H
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Central Africa; C:Rwanda; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:nurse; Q:e-learning; T:Training; T:continuing education; publicImportV1; ⛔ No DOI found

E-Learning for Teacher Training in Tanzania - Baker, D; Bliss, A; Chung, R (2013)
Rural Tanzania is struggling to provide an adequate number of qualified teachers to keep up with increased primary and secondary school enrollment rates. Teachers enter classrooms with minimal teaching experience and education, sometimes having never studied the subject they are teaching. As a result of this under-qualification, teachers struggle in critical topics such as math, science, and English, exacerbating the trend of low academic performance. A lack of well-qualified teachers means the country is producing students whose education is cut short, as they are not passing national exams for graduation. This result is a great disappointment and an unacceptable outcome for students who represent years of investment and hope for the future. Primary and secondary school teachers must have sufficient knowledge and skills in the classroom. Teacher training will need to employ a variety of tools, among them education of and with Information and Communications Technologies (ICTs). This project has two components. First, it provides a landscape review of national and international policies and initiatives that affect education in Tanzania, clarifying how Asante Africa’s programs can best fit into the country’s established systems. Second, it identifies best practices for using e-learning ICTs to train teachers and improve the country’s education system. The report identifies four prospective e-learning models, and recommends that Asante Africa consider aspects of two: mobile learning and massive open online courses (MOOCs). Through our model evaluation, we found that these two models ranked best for Tanzania in effectiveness, cost, rural feasibility, scalability, and sustainability. Once a delivery method is in place and Asante Africa ensures technical support for the teachers utilizing the training materials, Asante Africa can strategize a plan for content and curriculum that leverages its Khan Academy videos. By implementing the recommended ICTs for learning and teacher training, Asante Africa will deliver increased access of quality training to teachers in the rural districts of Tanzania, improving the academic environment and performance of students throughout the country.
KerkoCite.ItemAlsoKnownAs: 2129771:I53KBPC4 2317526:2QHUGPLF
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; F:learning; F:ministry; P:teacher training; Q:e-learning; Q:mobile learning; T:TVET; publicImportV1; ⛔ No DOI found

Dynamic Effect of Rapid Urbanization on City Logistics: Literature Gleened Lessons for Developing Countries - Mwamba, Evans; Masaiti, Gift; Simui, Francis (Journal of City and Development, 2021)
Keywords: ⛔ No DOI found

DSTI | Home - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:KZXDSHQF 2405685:T64PHUNV

Driving the process or driven by the process? The transformation of Nkrumah college of education into Nkrumah university college. - Cheyeka, Austin; Mulenga, Innocent Mutale; Masaiti, Gift (2010)
Publisher: ZANGO-Journal of Contemporary Issues
Keywords: ⛔ No DOI found

Donor Organizations and the Principles for Digital Development: A Landscape Assessment and Gap Analysis - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Digital Impact Alliance, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: <this> EdTechHub.Source: 2129771:I2CG3TP3 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Australia AUS; _C:Belgium BEL; _C:Cambodia KHM; _C:Canada CAN; _C:China CHN; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:Jordan JOR; _C:Kenya KEN; _C:Liberia LBR; _C:Norway NOR; _C:Philippines PHL; _C:Portugal PRT; _C:Rwanda RWA; _C:Spain ESP; _C:Sweden SWE; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:c; docs.opendeved.net

Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke (International Journal of Educational Development, 2016)
In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers’ level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls’ education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2015.09.008 2129771:24DRB739 2129771:QXGQZQLQ 2405685:YPUYEULY
Keywords: Girls’ education; Mothers’ education; School attendance; Sierra Leone; _C:Sierra Leone SLE

Document de Travail - La formation en secteur informel: Note de problématique - Walther, Richard (Agence Française de Développement, 2006)
KerkoCite.ItemAlsoKnownAs: 2129771:9XLP2DNC 2317526:N4U8VVCW
Keywords: -FullBiblioUHMLgen; -GeneralCitations; -RRQ:H:final; -RRQ:U:final; C:Benin; C:Cameroon; C:Morocco; C:Senegal; C:South Africa; CLL:fr; publicImportV1

Do youth employment programs improve labor market outcomes? A systematic review - Kluve, Jochen; Puerto, Susana; Robalino, David A.; Romero, Jose Manuel; Rother, Friederike; Stöterau, Jonathan; Weidenkaff, Felix; Witte, Marc (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This study reviews the evidence on the labor market impact of youth employment programs. We analyze the effectiveness of interventions, and factors that influence program performance including country context, target beneficiaries, program design, implementation, and evaluation type. We identify 113 impact evaluations covering a wide range of methodologies, interventions, and countries. The meta-analysis synthesizes the evidence based on 2,259 effect sizes (Standardized Mean Differences) and the statistical significance of 3,105 impact estimates (Positive and Statistically Significant). Just more than one-third of youth employment program evaluations worldwide show a significant positive impact on labor market outcomes - either employment rates or earnings. In general, programs have been more successful in middle- and low-income countries; this may be because programs' investments are especially helpful for the most vulnerable population groups that they target. We conjecture that recent programs might have benefited from innovations in design and implementation. In middle-low income countries, skills training and entrepreneurship programs have had a higher impact. In high-income countries, the role of intervention type is less decisive - much depends on context and how services are chosen and delivered, a result that holds across country types. We find evidence that programs integrating multiple interventions more likely succeed because they respond better to different needs of beneficiaries. Results also point to the importance of profiling and follow-up systems in determining program performance, as well as to incentive systems for services provider
KerkoCite.ItemAlsoKnownAs: 2129771:B58KPPYI 2317526:2F7UE67W
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Ethiopia; C:Kenya; C:Liberia; C:Malawi; C:South Africa; CLL:en; Employment; _C:Uganda UGA; publicImportV1

'Distance learning' or 'learning at a distance'? Case study of an education initiative to deliver an in‐service bachelors degree in Zambia - Smith, CJ (Innovations in Education and Teaching International, 2010)
In 1998, as part of what was then Zambia’s Department of Technical Education and Vocational Training’s (DTEVT) human resources capacity building initiative, under the Ministry of Science, Technology and Vocational Training (MSTVT), donor funding was secured to provide degree-level training for key teachers and managers within the technical education and vocational education and training (TEVET) system. However, the lack of degree-level courses designed for TEVET personnel at both of Zambia’s universities prevented progress. This situation has disadvantaged TEVET staff and for years has limited their professional development. To address this, a pilot project involving a British Higher Education Institution delivering a degree programme, in-country and in-service (part-time), was proposed by senior DTEVT staff. Some seven years after the commencement of this programme and with three cohorts having successfully been completed, this paper examines some of the key issues in delivery of the programme over the years and reflects on significant events that have influenced the programme’s development and are likely to continue to impact on its future direction. Keywords: blended learning; distance learning; e-learning; international development; professional development; TVET (technical and vocational education and training)
KerkoCite.ItemAlsoKnownAs: 10.1080/14703291003718950 10/bcfqp9 2129771:XXF7GLXP 2317526:AFAZ37Q6
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Zambia; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; P:service industry; Q:degree; Q:distance learning; Q:open learning; R:case study; T:TVET; publicImportV1

Disability in and Around Urban Areas of Sierra Leone - Trani, Jean-Francois; Bah, Osman; Bailey, Nicki; Browne, Joyce; Groce, Nora; Kett, Maria (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:HBY77CAK 2129771:QHDCLY92 2405685:FSQFJ72I
Keywords: _C:Sierra Leone SLE

Directory of Accredited Programmes Offered in Polytechnics, Technical and Vocational Institutions - Government of Nigeria (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:J5VZIWBX 2317526:ZLQF4KYM
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Nigeria; TVET Provider; publicImportV1

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, K.; Thi Mai, T. (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.
KerkoCite.ItemAlsoKnownAs: 2129771:8RLHW9WQ 2129771:QWF5JY27 2129771:WNSMNZQR 2339240:PP5768J6 2339240:TGTJZWCC 2405685:EPMH5GMB 2405685:EY9VEBRN 2405685:KXNLTUXL 2405685:NUSFD2XU 2405685:PLIT3YBG 2405685:TIEFATQQ 4803016:S4RTD2LL
Keywords: _C:Sierra Leone SLE

Digital neocolonialism and massive open online courses (MOOCs): colonial pasts and neoliberal futures - Adam, Taskeen (Learning, Media and Technology, 2019)
Through evaluating dominant MOOC platforms created by Western universities, I argue that MOOCs on such platforms tend to embed Western-centric epistemologies and propagate this without questioning their global relevance. Consequently, such MOOCs can be detrimental when educating diverse and complex participants as they erode local and indigenous knowledge systems. Arguing that the digital divide is an exacerbation of historical inequalities, I draw parallels between colonial education, specifically across Sub-Saharan Africa, and ‘digital neocolonialism’ through Western MOOC platforms. I analyse similarities in ideology, assumptions, and methods of control. Highlighting evolving forms of coloniality, I include contemporary problems created by neoliberal techno-capitalist agendas, such as the commodification of education. Balance is needed between the opportunities offered through MOOCs and the harms they cause through overshadowing marginalised knowledges and framing disruptive technologies as the saviour. While recommending solutions for inclusion of marginalised voices, further problems such as adverse incorporation are raised.
KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2019.1640740 2129771:GICLIPT3 4804264:5D2NHMP4
Keywords: Author:OpenDevEd; Decolonising education; _C:Canada CAN; _C:China CHN; _C:Cuba CUB; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Iran IRN; _C:Italy ITA; _C:Jordan JOR; _C:Korea; Democratic People's Republic PRK; _C:Mexico MEX; _C:Nigeria NGA; _C:Somalia SOM; _C:South Africa ZAF; _C:Spain ESP; _C:Sudan SDN; _C:Syrian Arab Republic SYR; _C:Thailand THA; _C:Tonga TON; _C:Turkey TUR; __C:filed:1; __C:scheme:1; decolonising technology; digital neocolonialism; epistemic injustice; neoliberal education

Digital Literacy Among Teachers: Identifying Digital Divide Among Interactive Whiteboard Users in Public High Schools - Oatis, Tammy (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:RYULW4BI
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:Brazil BRA; _C:Canada CAN; _C:China CHN; _C:Georgia GEO; _C:Greece GRC; _C:Jordan JOR; _C:Korea; Republic KOR; _C:Netherlands NLD; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:South Africa ZAF; _C:Spain ESP; _C:Thailand THA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Digital Earth Partnership: Climate, Environment & Education in Tanzania – Gaps & Policy implications - Anderson, Edward (2024)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10912243 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1127 ZenodoArchiveConcept: 10912242
Keywords: Coming soon; _r:AddedByMyEducationEvidence

Die richtigen Mitarbeiter finden: Berufsbildung und HR-Management - Bauer, Annette; Kühnrich, Heinz-Joachim (Praxishandbuch Wirtschaft in Afrika, 2017)
Qualifizierte Fachkräfte stellen einen wichtigen Faktor für die Eintrittsentscheidung in einen Markt dar. Eine der am häufigsten genannten Hemmnisse für eine Investition in Afrika, ist deren Mangel. Vor allem für deutsche Unternehmen ist es wichtig mit ausgebildetem Personal die höhere Produktivität und Lebensdauer ihrer Produkte und Maschinen zu erreichen, um den meist höheren Investitionskosten im Marktvergleich Rechnung zu tragen und einen kosten- und zeiteffizienten After Sales Service anbieten zu können. Doch in vielen Ländern Afrikas ist diese Voraussetzung von qualifizierten Fachkräften noch nicht geschaffen. Folgendes Kapitel gibt einen Überblick über den wachsenden Bedarf an Fachkräften, die aktuelle Situation in der Berufsbildung, sowie Lösungsansätze zur Reduzierung der Lücke zwischen Angebot und Nachfrage an Fachkräften aus Sicht eines deutschen Anbieters für Aus- und Weiterbildungslösungen in Afrika.
KerkoCite.ItemAlsoKnownAs: 2129771:X864VGAL 2317526:G4L3I4Y4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; A:West Africa; C:Rwanda; CA:AandC; CL:de; CL:en; CLL:de; CLS:en; CT:A; CT:C; CT:P; CT:T; P:agriculture; T:Ausbildung; T:TVET; T:in-service TVET; publicImportV1

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)
Abstract Background and Introduction: This research describes the planning, design, implementation and evaluation of a (Continuous Professional Development & Learning) CPDL-based programme for schools in Sierra Leone, a low-income country with low educational standards. Aims: The research aimed to: (i) assess evidence of EducAid schools’ effectiveness; (ii) identify features of EducAid practice that government schools might adopt; (iii) design a CPDL programme for Sierra Leonean teachers; (iv) report the programme’s impact on students’ progress; (v) explore the possibility of programme delivery by local and largely untrained teachers; (vi) throw light on aspects of the programme that participants saw as strengths and weaknesses. Design and Methods: Within an innovative quasi-experimental design, an impact evaluation drew on data from five intervention and ten comparison schools, and a process evaluation drew on data on information from programme participants and the trainers. The impact evaluation was based on public exam results, literacy test scores and attendance data collected pre- and post-CPDL. Process data included information from lesson observations, semi-structured interviews, focus groups and a post-intervention evaluation workshop. Results: The impact evaluation showed larger improvements in student attendance and literacy test results in the intervention schools than in the comparison schools. The process evaluation identified challenges in embedding changes in pedagogic practice, and in data collection. However, it also identified consistent evidence of improvements in student behaviour. These were supported by head teachers and community groups and were seen as a necessary but not sufficient condition for the literacy score improvements. Discussion and Conclusions: Discussion focuses on how far the six aims were met and on how the research adds to understanding of CPDL and school improvement in a low-income country. The impossibility of randomisation in sample selection prevents any strong causal claims for the CPDL’s impact. The possibility of a larger scale roll-out is considered, subject to changes in the programme suggested by the process evaluation.
KerkoCite.ItemAlsoKnownAs: 2129771:3MNXK5A7 2129771:PAVJ5PN8 2129771:WNVH5866 2405685:55RYBL9Q 2405685:MWXU3IUJ 2601447:C789A8YJ 4556019:SYQXDHHM
Keywords: Must-read; _C:Sierra Leone SLE

Development of social studies learners’ textbooks for secondary schools in Zambia. - Musilekwa, Sianga; Mulenga, Innocent Mutale (2019)
Publisher: Journal of Education and Practice
Keywords: ⛔ No DOI found

Development of an emergency nursing training curriculum in Ghana - Bell, Sue Anne; Oteng, Rockefeller; Redman, Richard; Lapham, Jeremy; Bam, Victoria; Dzomecku, Veronica; Yakubu, Jamila; Tagoe, Nadia; Donkor, Peter (International Emergency Nursing, 2014)
Abstract The formal provision of emergency health care is a developing specialty in many sub-Saharan African countries, including Ghana. While emergency medicine training programs for physicians are on the rise, there are few established training programs for emergency nurses. The results of a unique collaboration are described between a university in the United States, a Ghanaian university and a Ghanaian teaching hospital that has developed an emergency nursing diploma program. The expected outcomes of this training program include: (a) an innovative, interdisciplinary, team-based clinical training model, (b) a unique and low-resource emergency nursing curriculum and (c) a comprehensive and sustainable training program to increase in-country retention of nurses.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ienj.2014.02.002 10/f6vv27 2129771:UFJJIVJS 2317526:5WYR796J
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CCZ:Ghana; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:curriculum; F:outcomes; F:teaching; P:health; P:media; P:nurse; Q:diploma; T:Training; Z:Curriculum; Z:Emergency Nursing; Z:Sub-Saharan Africa; Z:Training; _C:Ghana GHA; __C:filed:1; publicImportV1

Developing teacher-led professional learning in a Tanzanian secondary school: a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Manawatū, New Zealand - Mwakabenga, Rehema Japhet (Massey University, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:EJLIILMC 2129771:NIA5JA3I 2129771:ULPHVD3Y
Keywords: _C:Australia AUS; _C:Belgium BEL; _C:Bhutan BTN; _C:Botswana BWA; _C:Cambodia KHM; _C:Canada CAN; _C:Central African Republic CAF; _C:China CHN; _C:Czech Republic CZE; _C:Egypt EGY; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:Iceland ISL; _C:India IND; _C:Iran IRN; _C:Ireland IRL; _C:Israel ISR; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Korea XKOR; _C:Korea; Republic KOR; _C:Lithuania LTU; _C:Malawi MWI; _C:Malaysia MYS; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Russian Federation RUS; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

Developing learning diaries for action research on healthcare management in Ghana, Tanzania and Uganda - Mshelia, Comfort; Lê, Gillian; Mirzoev, Tolib; Amon, Samuel; Kessy, Ambrose; Baine, Sebastian Olikira; Huss, Reinhard (Action Research, 2016)
© 2016, © The Author(s) 2016. Action research (AR) can be an effective form of ‘on the job’ training. However, it is critical that AR cycles can be appropriately recorded in order to contribute to reflection and learning. One form of recording is for coresearchers to keep a diary. We found no previous literature describing the use of diaries in AR in sub-Saharan Africa. We therefore use this paper to reflect on how diaries were used by district health management teams in the PERFORM project. We share five lessons from our experience. First, it is important to foster ownership of the diary by the people who are responsible for filling it in. Second, the purpose of keeping a diary needs to be clear and shared between researchers and practitioners from the very beginning. Third, diaries should be allowed to evolve. Fourth, it is a challenge for busy practitioners to record the reflection and learning processes that they go through. Last, diaries on their own are not sufficient to capture reflection and learning. In conclusion, there is no best way for practitioners to keep a diary; rather the focus should be on ensuring that an AR recording process (whether diary or otherwise) is locally owned and complements the specific practice setting.
KerkoCite.ItemAlsoKnownAs: 10.1177/1476750315626780 10/gf62p7 2129771:XUXFIEJA 2317526:M5KRBYFV
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CCZ:Ghana; CCZ:Tanzania; CCZ:Uganda; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:learning; P:health; T:Training; Z:Diaries; Z:action research; Z:district health management teams; _C:Ghana GHA; _C:Uganda UGA; publicImportV1

Developing inclusive pre-service and in-service teacher education : Insights from Zanzibar primary school teachers - Juma, Said; Lehtomäki, Elina; Naukkarinen, Aimo (International Journal of Whole Schooling, 2017)
Developing inclusive teacher education to improve learning and schooling for all children is attracting increasing interest worldwide. This study examined teachers’ insights into the development of inclusive teacher education by drawing on collaborative action research conducted by 20 primary school teachers in Zanzibar, Tanzania. The data were collected through semi-structured interviews and self-reflective journals kept by the teachers and the first author. The qualitative thematic content analysis revealed: (1) the need to embed inclusive education and action research into pre-service and in-service teacher education curricula and (2) both school-based organisational learning and school–community and school–university collaborations may foster collaborative school cultures and inclusive inservice teacher education. The study discusses the role of teachers’ voices in informing teacher education development for educational equity and inclusion.
KerkoCite.ItemAlsoKnownAs: 2129771:2T3354QE 2129771:V42L3ESP
Keywords: _C:Australia AUS; _C:Canada CAN; _C:Central African Republic CAF; _C:Finland FIN; _C:India IND; _C:Japan JPN; _C:Namibia NAM; _C:North Macedonia MKD; _C:Pakistan PAK; _C:South Africa ZAF; _C:Tanzania TZA; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Developing Inclusive Education Policy in Sierra Leone: A Research Informed Approach - Rose, R.; Garner, P.; Farrow, B. (Inclusion, Equity and Access for Individuals with Disabilities., 2019)
https://doi.org/10.100/ 978-981-13-5962-0_21 KerkoCite.ItemAlsoKnownAs: 2129771:B3K7GRXA 2405685:AMF2AQAE
Keywords: _C:Sierra Leone SLE

Developing inclusive education policy and practice in Zanzibar : collaborative action research - Juma, Said (Jyväskylä studies in education, psychology and social research, 2018)
This doctoral dissertation, which consists of three interrelated sub-studies and an overarching summary, explores the inclusive education development process in Zanzibar, Tanzania. The purpose of the research is to contribute to the development of inclusive policies and practices in order to increase the presence, participation and achievement of all learners. The overarching research question investigated in this research was as follows: How is inclusive education developed in Zanzibar, and how can it be better integrated into the education system? This question was divided into six sub-questions. Each of the three interrelated sub-studies in this dissertation focused on specific sub-questions. The data included several documents related to inclusive education development; interviews conducted with 20 teachers from two primary schools; these teachers’ reflective diaries, which were kept during their action research projects, and the researcher’s reflective diary. The data were analysed using qualitative content analysis and thematic analysis. The findings revealed that Zanzibar has taken several measures to make its education system more inclusive. These measures include acknowledging inclusive education in its 2006 education policy, drafting an inclusive education policy, introducing a re-entry policy for school girls who become pregnant, increasing the number of years of compulsory education from 10 to 12, removing school fees for both primary and secondary schools, providing in-service teacher training for inclusive education, recruiting inclusive education and life skills advisors and resource teachers, and introducing inclusive education courses in teacher training colleges. It is also worth noting that the teachers in this research experienced collaborative action research as valuable in developing their inclusive practices, despite the challenges they encounter in the course of conducting their projects. Despite its advantages, collaborative action research demands additional time from the teachers beyond their teaching responsibilities. The research participants found the teacher resource centres to be key in enhancing their professional development. This research shows the need to review the teaching methods and materials used in schools. Reforms in teacher education curricula are also needed in response to increasingly diverse learning needs and educational changes. In addition, this research emphasises the integration of inclusive education and collaborative action research into teacher education so that all teachers can teach inclusively. Both school-based organisational learning and school–community and school–university collaborations can foster collaborative school cultures and inclusive teacher education.
KerkoCite.ItemAlsoKnownAs: 2129771:5SMNLRN4 2129771:95RCWSF9 2129771:HE6NVBQE
Keywords: _C:Argentina ARG; _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Cambodia KHM; _C:Canada CAN; _C:Central African Republic CAF; _C:China CHN; _C:Finland FIN; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Ireland IRL; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Lesotho LSO; _C:Malawi MWI; _C:Malaysia MYS; _C:Mexico MEX; _C:Mongolia MNG; _C:Namibia NAM; _C:Nepal NPL; _C:New Zealand NZL; _C:North Macedonia MKD; _C:Norway NOR; _C:Oman OMN; _C:Pakistan PAK; _C:Russian Federation RUS; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Developing an emergency nursing short course in Tanzania - Cunningham, C.; Brysiewicz, P.; Sepeku, A.; White, L.; Murray, B.; Lobue, N.; Sawe, H. (African Journal of Emergency Medicine, 2017)
Abstract Nurses are the largest group of healthcare workers in Africa. By adequately equipping nurses to identify, intervene and care for emergency conditions, emergency healthcare systems can be strengthened. To address this need, a nursing working group was formed within the African Federation for Emergency Medicine (AFEM). The aim of this international emergency nursing group was to develop a guiding document to help improve emergency nursing skills within Africa. Using this guiding document, a group of Tanzanian clinical nurse trainers was selected to develop a context specific short course. They used this guiding document as a foundation to improve skill development. The pilot course was well received and has since expanded to training in five regions within the United Republic of Tanzania. The clinical nurse trainers leading the course, are supported by a mentorship programme with competent educators within a global emergency nursing infrastructure. This course, a combination of local knowledge, formal mentorship programs, and international nursing support, demonstrates that investing in the improvement of emergency nursing skills can have high impact results with low-cost. This will ultimately improve emergency care on the continent.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.afjem.2017.08.002 10/gf62kh 2129771:PC2NVHDL 2317526:PYL5L8JH
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:Improvement; P:health; P:media; P:nurse; R:impact; T:Training; T:trainee; publicImportV1

Developing a systemic approach to teacher education in sub-Saharan Africa: emerging lessons from Kenya, Tanzania and Uganda - Hardman, Frank; Ackers, Jim; Abrishamian, Niki; O’Sullivan, Margo (Compare: A Journal of Comparative and International Education, 2011)
While many countries in Eastern and Southern Africa are on track for meeting the Education for All targets, there is a growing recognition of the need to improve the quality of basic education and that a focus on pedagogy and its training implications needs to be at the heart of this commitment. By drawing on three East African countries, Kenya, Tanzania and Uganda, which are at different stages of development with regard to the reforming of teacher education, this paper explores the challenges and the lessons learned from each of the countries with regard to the development and strengthening of pre- and in-service training. The tension between quality, breadth and cost-effectiveness is explored together with a broader discussion of key principles to be taken into account when enhancing teacher education in the region as a whole.
00073 KerkoCite.ItemAlsoKnownAs: 10.1080/03057925.2011.581014 10/gftr63 2129771:HFSLX6UE 2129771:NCXUKWK4 2129771:Q5IYQCTD 2317526:JIARV2LH 2339240:7KFNHLPK 2405685:J57J3RGT 2405685:QWHDI7ZH 2534378:L9VFMLYK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; A:Sub-Saharan Africa; C:Kenya; C:Kenya / Uganda / Tanzania; C:Tanzania; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:Improvement; F:ministry; F:pedagogy; F:policy; F:teaching; P:teacher education; P:teachers; Q:distance education; Q:open learning; R:survey; T:TVET; T:Training; T:work-based learning; Z:Cost Effectiveness; Z:Educational Change; Z:Educational Development; Z:Educational Improvement; Z:Educational Policy; Z:Educational Quality; Z:Equal Education; Z:Foreign Countries; Z:Systems Approach; Z:Teacher Education; _C:Botswana BWA; _C:Brunei Darussalam BRN; _C:Ghana GHA; _C:Ireland IRL; _C:Kenya KEN; _C:Myanmar MMR; _C:Nigeria NGA; _C:Peru PER; _C:Rwanda RWA; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; ___working_potential_duplicate; publicImportV1

Der Flipped Classroom als Motor für Open Educational Resources? - Buchner, Josef; Höfler, Elke (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2019)
KerkoCite.ItemAlsoKnownAs: 10.21240/mpaed/34/2020.01.24.X 2129771:42UAQMBY
Keywords: _C:Austria AUT; _C:South Africa ZAF; __C:filed:1; __C:scheme:1

Curriculum re-engineering and development in Zambia: the sociology of education in the face of globalisation. - Simamuna, Mubita Likando; Mulenga, Innocent Mutale (The University of Zambia Press, 2017)

Curriculum Implementation Strategies of Education Standards Officers in Choma District of Zambia: A Critique of their Effectiveness - Mulenga, Innocent Mutale; Mooya, Eugine (Zambian Journal of Educational Management, Administration and Leadership (ZJEMAL)(ISSN-Print: 2706-7416, Online: 2709-1864), 2021)
Keywords: ⛔ No DOI found

Curriculum Implementation Strategies of Education Standards Officers in Choma District of Zambia: A Critique of their Effectiveness - Mulenga, Innocent Mutale; Mooya, Eugine (2021)
Effective curriculum implementation by teachers is recognised as a lynchpin for achieving educational goals of any education system that leads to improved learner outcomes. In this article, authors make a critique of the effectiveness of Education Standards Officers’ (ESOs) curriculum implementation strategies that were used to support teachers’ effective teaching and learning in Choma district of Zambia. They set the arguement by riding on the six premises of Fullan’s curriculum implementation model against the contemporary backdrop and knowledge that ESOs monitoring and evaluation roles are critical to effective curriculum implementation in schools. In this qualitative study, researchers identified and critiqued strategies that were employed by ESOs in the contemporary milieu of Choma district. Using interview guides and focus group discussions guides, data was collected from head teachers and teachers in five, public secondary schools. Additionally, interview guides were also used to collect information from ESOs themselves. Findings pointed to the fact that curriculum implementation strategies such as formation of subject associations, follow-up visits and the recommendations from ESOs and the use of common schemes of work in schools did not yield desired results in terms of supporting teachers to improve their teaching based on what ESOs identified as areas of need during their school visits. In fact, it was also noted that ESOs missed a golden opportunity to practice clinical supervision and to make lesson demonstrations as they interacted with teachers. Arising from the factors which led to this scenario, researchers make two main recommendations. They first and foremost suggest that the Ministry of Education needs to provide sufficient funding to aspects of curriculum implementation at both the district and school levels. Researchers also recommend that ESOs should consult teachers and their administrators as they come up with curriculum implementation strategies in order to have them aligned with the realities of the schools.
Keywords: ⛔ No DOI found

Curriculum Implementation in Zambia: Best Practices of Bridging the Gap between the Intended and the Achieved School Curriculum - Changwe, Robert; Mwanza, Christine (International Journal of Research and Innovation in Social Science, 2022)

Curriculum design in contemporary teacher education: what makes job analysis a vital preliminary ingredient?. - Mulenga, Innocent Mutale (2015)
Publisher: International Journal of Humanities Social Sciences and Education (IJHSSE)
Keywords: ⛔ No DOI found

Curriculum and training needs of mid-level health workers in Africa: A situational review from Kenya, Nigeria, South Africa and Uganda - Couper, Ian; Couper, Ian; Ray, Sunanda; Ray, Sunanda; Blaauw, Duane; Ng'Wena, Gideon; Muchiri, Lucy; Oyungu, Eren; Omigbodun, Akinyinka; Omigbodun, Akinyinka; Morhason-Bello, Imran; Ibingira, Charles; et al. (BMC Health Services Research, 2018)
© 2018 The Author(s). Background: Africa's health systems rely on services provided by mid-level health workers (MLWs). Investment in their training is worthwhile since they are more likely to be retained in underserved areas, require shorter training courses and are less dependent on technology and investigations in their clinical practice than physicians. Their training programs and curricula need up-dating to be relevant to their practice and to reflect advances in health professional education. This study was conducted to review the training and curricula of MLWs in Kenya, Nigeria, South Africa and Uganda, to ascertain areas for improvement. Methods: Key informants from professional associations, regulatory bodies, training institutions, labour organisations and government ministries were interviewed in each country. Policy documents and training curricula were reviewed for relevant content. Feedback was provided through stakeholder and participant meetings and comments recorded. 421 District managers and 975 MLWs from urban and rural government district health facilities completed self-administered questionnaires regarding MLW training and performance. Results: Qualitative data indicated commonalities in scope of practice and in training programs across the four countries, with a focus on basic diagnosis and medical treatment. Older programs tended to be more didactic in their training approach and were often lacking in resources. Significant concerns regarding skills gaps and quality of training were raised. Nevertheless, quantitative data showed that most MLWs felt their basic training was adequate for the work they do. MLWs and district managers indicated that training methods needed updating with additional skills offered. MLWs wanted their training to include more problem-solving approaches and practical procedures that could be life-saving. Conclusions: MLWs are essential frontline workers in health services, not just a stop-gap. In Kenya, Nigeria and Uganda, their important role is appreciated by health service managers. At the same time, significant deficiencies in training program content and educational methodologies exist in these countries, whereas programs in South Africa appear to have benefited from their more recent origin. Improvements to training and curricula, based on international educational developments as well as the local burden of disease, will enable them to function with greater effectiveness and contribute to better quality care and outcomes.
KerkoCite.ItemAlsoKnownAs: 10.1186/s12913-018-3362-9 10/gdw4tb 2129771:6QH2RT5L 2317526:KXPW6NSD
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; C:Kenya; C:Nigeria; C:South Africa; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:Improvement; F:curriculum; F:ministry; F:outcomes; F:pedagogy; F:policy; P:health; P:media; P:services; P:technology; R:interview; R:qualitative; R:quantitative; R:questionnaire; T:TVET; T:Training; T:training needs; Z:Curricula; Z:Educational models; Z:Healthcare providers; Z:Healthcare workers; Z:Mid-level workers; Z:Primary healthcare; Z:Quality of healthcare; _C:Uganda UGA; publicImportV1

Cultivating Dynamic Educators: Case Studies in Teacher Behavior Change in Africa and Asia - Pouezevara, Sarah (RTI Press, 2018)
KerkoCite.ItemAlsoKnownAs: 10.3768/rtipress.2018.bk.0022.1809 2129771:69X6P654
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:Belgium BEL; _C:Brazil BRA; _C:Cambodia KHM; _C:Canada CAN; _C:Congo XCO; _C:Cuba CUB; _C:Ethiopia ETH; _C:France FRA; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Haiti HTI; _C:Honduras HND; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Jamaica JAM; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Korea; Republic KOR; _C:Liberia LBR; _C:Madagascar MDG; _C:Malawi MWI; _C:Malaysia MYS; _C:Maldives MDV; _C:Mali MLI; _C:Morocco MAR; _C:Namibia NAM; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Panama PAN; _C:Papua New Guinea PNG; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Singapore SGP; _C:Somalia SOM; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Sudan SDN; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Tuvalu TUV; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Viet Nam VNM; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

Cross-country comparison of TVET systems, practices and policies, and employability of youth in Sub-Saharan Africa - Oketch, Moses (2017)
In recent years, organisations such as the African Development Bank (AfDB), and several African governments have conceded that TVET may have a positive impact on harnessing the youth dividend. There has been some progress in some countries, but there is still insufficient understanding of the place of TVET and youth skills development. The criticisms of TVET in the past, and attitudes toward it, coupled with a period of neglect by governments and donors have all resulted in insufficient understanding of the positive effects TVET can have on the youth and on economic development compared to other regions of the world that have had clearly developed agenda for youth skills development through further colleges, community colleges, or apprenticeships.
KerkoCite.ItemAlsoKnownAs: 2129771:6I2JU3NY 2317526:R76QDY82
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; A:Africa; C:Botswana; C:Kenya; CLL:en; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Critical knowledge, skills and qualifications for accelerated and sustainable development in Africa - Ndoye, M; Walther, R (2012)
The major challenge of the 2012 ADEA Triennale will be to help African countries design and develop suitable and effective education and training systems that can help move the continent away from the struggle for subsistence and the spiral of poverty towards a process of sustainable transformation that reconciles economic growth with the pursuit of equity and the conservation of natural resources. In short, the aim is to enable Africa to “run while others walk”, while avoiding causing the same damage others caused when they were running. To achieve such a goal, the Synthesis Report recommends that a number of prerequisites should be met before the required reforms can be possible. They will succeed only if they look back at Africa’s past identity in order to take greater control over future choices, if they are based on a common vision of the future determined with all concerned stakeholders, and if they make education, training and employment central to current and future policies. The report then discusses the unprecedented efforts of public and private, African and international officials and stakeholders in order to formulate appropriate, concrete responses to the challenge of the Triennale, which is to “promote critical knowledge, skills and qualifications for Africa’s sustainable development”. These responses, categorized by sub-theme, may be summed up as follows. Sub-theme 1: building a common core of skills for all The education system should give people of all ages access to a common core of basic skills (cognitive, communication and learning-to-learn skills, personal and social development skills, etc.) to enable them to control their human, social and economic environment and develop responsible and active African citizenship. Sub-theme 2: mass development of technical and vocational skills Massive investment to raise training and qualification levels is urgently required in order to wage an effective war against unemployment and massive underemployment of youth and the low productivity of a largely informal economy. It is also necessary to invest in high-level qualifications in order to support and, if possible, anticipate changes and technological innovation and promote the badly-needed industrialization of the African economy. Sub-theme 3: building knowledge and innovation-based economies and societies in Africa R&D, knowledge and innovation have become the key drivers of output, economic competitiveness and development generally. Africa needs to catch up in this respect and, to this end, it must build its scientific development on indigenous African knowledge, use science and technology to strengthen education and exploit the current surge in information and communication technology as a driver of development. All this will be possible only if all African countries work towards the adoption of a continental pact for sustainable development.
KerkoCite.ItemAlsoKnownAs: 2129771:UD7XFDU6 2317526:NBSBQZMH
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; A:Africa; A:Central Africa; C:Burkina Faso; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:qualification; Q:lifelong learning; T:Ausbildung; T:Lehrlingsausbildung; T:TVET; T:journeyman; T:vocational skills; publicImportV1; ⛔ No DOI found

COVID-19 Education Emergency Response Plan - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:TK93PBJQ 2405685:XV46GE39

COVID-19 and the Digital Transformation of Education: What We Are Learning in South Africa - Mhlanga, David; Moloi, Tankiso (2020)
The study sought to gauge the impact of COVID-19 pandemic in unleashing digital transformation in the education sector in South Africa. In order to gauge the impact, the study tracked the rate at which the 4IR tools were used by various institutions during the COVID-19 lockdown. Data were obtained from secondary sources, mainly newspaper articles, magazines and peer-reviewed journals. The findings are that, in South Africa, during the lockdown, a variety of 4IR tools were unleashed from primary education to higher and tertiary education where educational activities switched to remote learning (online learning). These observations point to the fact that South Africa generally has, some pockets of excellence to drive the education sector into the 4IR, which has the potential to increase access. Access to education, particularly at a higher education level, has always been a challenge due to a limited number of spaces available. Much as this pandemic has brought with it massive human suffering across the globe, there is an opportunity to assess successes and failures of deployed technologies, costs associated with them, and scaling these technologies to improve access.
Publisher: Preprints KerkoCite.ItemAlsoKnownAs: 10.20944/preprints202004.0195.v1 2129771:XL2TPA77
Keywords: __C:filed:1

COVID-19 and the Digital Transformation of Education: What Are We Learning on 4IR in South Africa? - Mhlanga, David; Moloi, Tankiso (Education Sciences, 2020)
The study sought to assess the influence of the COVID-19 pandemic in motivating digital transformation in the education sector in South Africa. The study was premised on the fact that learning in South Africa and the rest of the world came to a standstill due to the lockdown necessitated by COVID-19. To assess the impact, the study tracked the rate at which the Fourth Industrial Revolution (4IR) tools were used by various institutions during the COVID-19 lockdown. Data were obtained from secondary sources. The findings are that, in South Africa, during the lockdown, a variety of 4IR tools were unleashed from primary education to higher and tertiary education where educational activities switched to remote (online) learning. These observations reflect that South Africa generally has some pockets of excellence to drive the education sector into the 4IR, which has the potential to increase access. Access to education, particularly at a higher education level, has always been a challenge due to a limited number of spaces available. Much as this pandemic has brought with it massive human suffering across the globe, it has presented an opportunity to assess successes and failures of deployed technologies, costs associated with them, and scaling these technologies to improve access.
Publisher: MDPI KerkoCite.ItemAlsoKnownAs: 10.3390/educsci10070180 2129771:FZ72LCBN 2129771:KGMAPFPF
Keywords: 4IR; COVID-19; South Africa; __C:filed:1; digital transformation; education

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:5BLVEY7N 2339240:746WTJF3 2405685:HNVAP5QB
Keywords: _C:Sierra Leone SLE; dode_eth-src-eth

COTVET Act nº 718, 2006 - The Council for Technical and Vocational Education and Training Act - Government of Ghana (2006)
KerkoCite.ItemAlsoKnownAs: 2129771:77QFAKGT 2317526:RW9FWN7C
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Ghana; publicImportV1

CORONAVIRUS: OP-ED: Why it can’t be education as usual - Collective, Bua-lit (Daily Maverick, 2020)
In this time of the Covid-19 pandemic and school closures, we need to plan and strategise creatively so that ALL South African children – not just those with access to digital devices, data, and network coverage – can continue to learn.
Library Catalog: www.dailymaverick.co.za KerkoCite.ItemAlsoKnownAs: 2129771:TRCDE88E

Continuous Teacher Learning Circles in Learner-Centered Pedagogy: A Case Study in the Democratic Republic of the Congo - Lund, Jennifer Anne (2020)
This dissertation explores how continuous teacher learning circles (TLCs) support the implementation of a learner-centered pedagogy in grades 5-10 at a school in a long-term refugee community located in the Democratic Republic of the Congo (DRC). Learner-centered pedagogy has gained notice as a means to improve educational outcomes in sub-Saharan Africa (Vavrus & Bartlett, 2012). Learner-centered pedagogy may be defined as education rooted in the interests of students, their prior knowledge, and pedagogy based on student inquiry with the goal of solving real-world problems (Dewey, 1916). TLCs are increasingly used by international educational development organizations, including in the DRC (Frisoli, 2014; Inter-Agency Network for Education in Emergencies, 2015). Focusing on sustained teacher and student learning, one U.S. non-profit has worked since 2011 to co-create learner-centered modules based on locally identified assets and problems. This qualitative case study seeks to illuminate how teacher learning and well-being are supported through the TLCs and what teachers and staff understand about learner-centered pedagogy as a teaching and learning paradigm in the context. Drawing from Kanu's (2005) precept that pedagogical ideas crossing borders are continually reinterpreted and reinvented, this study takes a closer look at how indigenous practices may influence or mediate teacher learning. By using Lave and Wenger’s (1991) concept of communities of practice as the principal theoretical framework, the study relied on data from onsite individual interviews, focus groups, classroom observations, and TLC observations as well as archival documents such as lesson plans, teacher reflections, and transcripts of cross-cultural Skype conversations between Congolese and American staff. Findings suggest that the TLCs viii help teachers gain confidence in learner-centered teaching tools that support safe, inclusive, and engaging classrooms while offering a supportive space to voice problems and receive feedback from peers as they engage in planning and implementing the innovative curriculum. Findings also highlight the need for increased teacher autonomy in lesson planning. Implications of these findings encourage future research to determine whether it is feasible for learner-centered pedagogy and TLCs to be operationalized and sustained over time in other similar settings.
KerkoCite.ItemAlsoKnownAs: 2129771:HKKSKFMH
Keywords: _C:Algeria DZA; _C:Angola AGO; _C:Azerbaijan AZE; _C:Belgium BEL; _C:Botswana BWA; _C:Cambodia KHM; _C:Canada CAN; _C:China CHN; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Congo; Republic COG; _C:Ethiopia ETH; _C:France FRA; _C:Gambia GMB; _C:Greece GRC; _C:Guinea GIN; _C:Italy ITA; _C:Japan JPN; _C:Malawi MWI; _C:Mali MLI; _C:Mexico MEX; _C:Namibia NAM; _C:Pakistan PAK; _C:Rwanda RWA; _C:Serbia SRB; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Sudan SDN; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Continuous professional development in Sierra Leone: Scoping Phase Overview - McBurnie, Chris; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4774318 2129771:YE8VL5V7 2405685:EKMQD8WQ
Keywords: Author:OpenDevEd; _C:Sierra Leone SLE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Continuing technology professional development: A technology learning preferences instrument to support teacher educators’ workplace learning - Maurice Schols, B. A. (Roehampton University, 2015)
KerkoCite.ItemAlsoKnownAs: 2129771:FUGDS44Y
Keywords: _C:Australia AUS; _C:Belgium BEL; _C:Canada CAN; _C:China CHN; _C:Cuba CUB; _C:France FRA; _C:Georgia GEO; _C:Germany DEU; _C:Greece GRC; _C:Ireland IRL; _C:Luxembourg LUX; _C:Netherlands NLD; _C:New Zealand NZL; _C:Portugal PRT; _C:Spain ESP; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Context-driven entrepreneurial education in vocational schools - Sandirasegarane, S; Sutermaster, S; Gill, A (International Journal for Research in Vocational Education and Training, 2016)
Vocational Education and Training (VET) is offered throughout the world to students of various educational backgrounds and career aspirations in an effort to create a skilled workforce. The structure of VET varies greatly across different fields and countries with high-growth, low-growth, and transitional economies. However, a common critique of many vocational institutions is that they focus on skills training without addressing related business systems. Thus, students may not understand the business strategies related to their field, which stifles job readiness and entrepreneurial potential. To counter this, a more context-driven and integrated entrepreneurial approach is proposed for VET. Benefits, disadvantages, and exemplars of various types of vocational and entrepreneurial programs are evaluated to determine how their strengths might be leveraged. Such integrated entrepreneurial and vocational training would more suitably address context-specific market needs via both practical and transferrable skills, thus helping to reduce unemployment, particularly among youth in sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 10.13152/IJRVET.3.2.3 10.13152/ijrvet.3.2.3 2129771:ECRXUQXI 2129771:HXBEX8S3 2317526:5KPNRHLP 2317526:I4TIDQ6U
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; C:Botswana; C:Guinea; C:Kenya; C:Mozambique; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:achievement; T:Lehrlingsausbildung; T:TVET; T:dual TVET; T:vocational school; _C:Uganda UGA; publicImportV1

Construction craft skills requirements in sub-Saharan Africa: A focus on Zambia - Muya, Mundia; Price, Andrew D.f.; Edum-Fotwe, Francis T. (Engineering, Construction and Architectural Management, 2006)
Purpose – As the development agenda for sub-Sahara Africa (SSA) gains momentum, it has become necessary to refocus attention on effective and sustainable human resource development strategies for the construction sector in the region that include craft skills. Aims to provide insight into the availability and quality of construction craft skills in Zambia, and the SSA region in general. Design/methodology/approach – Using Zambia as a country case study, results of a survey that was designed to assess the construction industry's perceptions of the quality and availability of construction craft skills in Zambia are presented. The surveyed contractors' support for the introduction of a sector-specific training levy in Zambia was also investigated and is reported. Findings – Findings point to both poor quality and shortage of construction craft skills in Zambia. Results suggest that construction sector-specific training levy would be the most viable, sustainable and industry-wide supported option for supplementing government funding in the training of construction craft skills in Zambia, and probably in the SSA region. Research limitations/implications – The survey was exploratory in nature and depth, and SSA is a vast and diverse region. The results of the case study may not correctly reflect construction skills exigencies across the whole SSA region. Originality/value – The results provide information and advice for both policy makers and contractors concerned with construction crafts skills issues in Zambia, and SSA in general. © 2006, Emerald Group Publishing Limited
KerkoCite.ItemAlsoKnownAs: 10.1108/09699980610669660 10/bzvww9 2129771:4BWX6MG3 2317526:HR9BPMJT
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Zambia; CA:AandC; CCZ:Zambia; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:policy; P:construction; P:crafts; P:nature; R:case study; R:survey; T:Training; Z:Construction industry; Z:Skills; Z:Sub Saharan Africa; Z:Training; publicImportV1

Connecting the Dots: Digitizing Teaching and Learning in Rural Schools in Uganda - Aduno, Freda (2019)
Publisher: Commonwealth of Learning (COL) KerkoCite.ItemAlsoKnownAs: 2129771:9WRJZIP6
Keywords: _C:Malaysia MYS; _C:Uganda UGA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Conducting surveys in Tanzanian schools – Second pilot - Villavicencio, Xuzel; Haßler, Björn; Toyinbo, Oluyemi (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10257420 ZenodoArchiveConcept: 10257419 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1036 2129771:EZ9EFDFS
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Conceptualization of competency based curricula in pre-service nursing and midwifery education: A grounded theory approach - Muraraneza, Claudine; Mtshali, Gloria Ntombifikile (Nurse Education in Practice, 2018)
In health professional education, the competency-based curriculum concept has been an important driver of reform in the training of competent graduates for the 21st century. In African countries, although there has been implementing it in pre-service nursing and midwifery education and the literature reports a lack of understanding of what is it on the part of the implementers. This article explores the meaning of competency based curriculum in pre-service nursing and midwifery education in Rwanda. A grounded theory approach, following Corbin and Strauss, was used. Following ethical clearance by the university ethical committee, data was collected from 17 participants through in-depth individual interviews of staff. Four categories emerged: (a) transformation, (b) tool for primary health care philosophy, (c) technological approach to education, (d) and modular system. Competency-based curriculum is confirmed as an appropriate educational tool in producing competent graduates for today and the future.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.nepr.2017.09.018 10/gc8bbc 2129771:QM52498T 2317526:4INW3TVV DOI-10.1016/j.nepr.2017.09.018
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Rwanda; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:curriculum; F:leadership; F:learning; P:health; P:health professionals; P:media; P:nurse; P:services; P:technology; R:grounded theory; R:interview; R:qualitative; T:TVET; T:Training; Z:Approaches; Z:Clinical competence; Z:Competency based learning; Z:Core curriculum; Z:Curriculum; Z:Curriculum development; Z:Data collection; Z:Education reform; Z:Grounded theory; Z:Health professionals; Z:Leadership; Z:Learning; Z:Meaning; Z:Medical education; Z:Medical ethics; Z:Midwifery; Z:Midwifery education; Z:Nursing; Z:Nursing education; Z:Primary health care; Z:Professional competence; Z:Qualitative research; Z:Students; Z:Transformation; publicImportV1

Conceptualization and Definition of a Curriculum - Mulenga, Innocent Mutale (Journal of Lexicography and Terminology (Online ISSN 2664-0899. Print ISSN 2517-9306)., 2018)
Keywords: ⛔ No DOI found

Computer literacy among practical arts teachers in swaziland vocational schools - Hlophe, Zanele F.; Mindebele, CBS (Journal of Vocational Education and Training, 2001)
This article reports findings of a study conducted in Swaziland to determine computer literacy skills of teachers of agriculture, commerce, home economics and technical studies in 16 pilot vocational schools. These teachers are expected to teach the new vocationalised curriculum of the four subjects. Findings revealed that the teachers lacked the basic computer knowledge and skills needed in the newly vocationalised curriculum that was to be mounted in the year 2000 with the financial assistance (loan) from the African Development Bank. However, the teachers indicated a strong interest in taking computer technology courses. © 2001 Taylor & Francis Group, LLC.
KerkoCite.ItemAlsoKnownAs: 10.1080/13636820100200161 10/cxxtx9 2129771:3GU7567E 2317526:VP54IRPY
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:eSwatini; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:curriculum; P:agriculture; P:economy; P:services; P:teachers; P:technology; Q:educational technology; T:TVET; T:Training; T:vocational school; publicImportV1

Competence and TVET Innovation in Sub-Saharan Africa: The Case of Rwanda - van Halsema, Wybe (Competence-based Vocational and Professional Education: Bridging the Worlds of Work and Education, 2017)
In many African countries, technical and vocational education and training (TVET) is considered a means to stimulate strategic economic growth. In order to render TVET more in line with market demands, governments increasingly promote the competence-based education (CBE) approach. In this chapter, the Central African country Rwanda is studied as an exemplary case for sub-Saharan Africa in how they apply CBE. Through competence-based curriculum development and teacher training, a centralised form of workforce planning is envisaged that would shape the TVET reform in the Central African country.In Rwanda, the Belgian Technical Cooperation (BTC) follows a systems approach to implement CBE in TVET. Having done so over the past 4 years, it becomes apparent that in the transitional phases of the systems, there is much ‘transitional noise’ that hampers implementation. This fact challenges the centralist view on CBE and its scope for national workforce planning. However, some positive features emerge from CBE implementation in that it stimulates practical learning and creativity in TVET.It is argued that by adapting the concept of competence to a more decentralised, intrinsic and generic form of TVET, a more capable, innovative and employable workforce can be formed. Government should thereby not just focus on formal employment but follow a diversified and inclusive approach of TVET for youth employment in all segments of the economy.
KerkoCite.ItemAlsoKnownAs: 2129771:TAF5U3YI 2317526:X95943S2 LOCAL-WOS:000398946600027
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Rwanda; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; Competence Development; Competency Statement; Informal Sector; Master Trainer; Pilot School; T:TVET; publicImportV1

COL in the Commonwealth: Sierra Leone - Commonwealth of Learning (2020)
KerkoCite.ItemAlsoKnownAs: 2129771:8KSADXRZ 2405685:I3SFDGVA
Keywords: _C:Sierra Leone SLE

Climate-resilient school buildings - Villavicencio, Xuzel; Hassler, Bjoern (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
ZenodoArchiveID: 10203951 ZenodoArchiveConcept: 10203950 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1031 2129771:FVMXNR7R
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Classroom dialogue and digital technologies: A scoping review - Major, L.; Warwick, P.; Rasmussen, I.; Ludvigsen, S.; Cook, V. (Education and Information Technologies, 2018)
This article presents a systematic scoping review of the literature focusing on interactions between classroom dialogue and digital technology. The first review of its type in this area, it both maps extant research and, through a process of thematic synthesis, investigates the role of technology in supporting classroom dialogue. In total, 72 studies (published 2000–2016) are analysed to establish the characteristics of existing evidence and to identify themes. The central intention is to enable researchers and others to access an extensive base of studies, thematically analysed, when developing insights and interpretations in a rapidly changing field of study. The discussion illustrates the interconnectedness of key themes, placing the studies in a methodological and theoretical context and examining challenges for the future.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-018-9701-y 10/gdm2tx 2129771:FDF826ZS 2129771:J9CF7AAC
Keywords: _C:Australia AUS; _C:Denmark DNK; _C:Finland FIN; _C:France FRA; _C:Greece GRC; _C:Israel ISR; _C:Korea XKOR; _C:Mexico MEX; _C:Netherlands NLD; _C:New Zealand NZL; _C:Norway NOR; _C:Singapore SGP; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; literature / systematic review

Class V + Class VI (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745153 2129771:8VUWYYJK 2129771:PFS92B3V
Keywords: SSEIP; _C:Sierra Leone SLE

Class III + Class IV (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745151 2129771:BX8FXSGM
Keywords: SSEIP; _C:Sierra Leone SLE

Class I + Class II (Accelerated Teaching Syllabi) - SSEIP (Zenodo, 2020)
This resource was produced by the Sierra Leone Secondary Education Improvement Programme (SSEIP).You can view and search all related records in the collection for Sierra Leone Secondary Education Improvement Programme. A full list of files is available here: full list. A zip file with all resources is available here: https://zenodo.org/record/3743296 (10.5281/zenodo.3743296).The document available under Creative Commons Attribution 4.0, https://creativecommons.org/licenses/by/4.0/.The document was uploaded by the EdTech Hub, https://edtechhub.org. For more information, see https://edtechhub.org/oer.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3745149 2129771:FCPVSMQ2
Keywords: SSEIP; _C:Sierra Leone SLE

Civic education teaching resources and teacher preparedness for secondary school competency-based curriculum in Lusaka, Zambia - Mulenga, Innocent Mutale; Ng’andu, Moonga (East African Journal of Education and Social Sciences (EAJESS), 2022)

China's cooperation in education and training with Kenya: A different model? - King, Kenneth (International Journal of Educational Development, 2010)
Abstract This is the first detailed study of the character and particularity of China's rapidly growing education and training cooperation with Kenya. Set against the 50-year history of Kenya's engagement with China, it pays special attention to the human resources targets of the Forum for China–Africa Cooperation (FOCAC) from 2000. It argues that the growing popularity of China as a destination for both short- and long-term training for Kenyans, and the increasing interest by Kenyans in learning Chinese, cannot be separated from the wider involvement of China in Kenya's infrastructure development, the growth of Chinese business and foreign direct investment, and Chinese migration to East Africa.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2010.03.014 10/fczrfd 2129771:N3FZ3A25 2317526:ZNRL39CJ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:learning; F:pay; T:Training; Z:African training in China; Z:China's education targets; Z:China–Africa; Z:China–Kenya; Z:Chinese aid; Z:Confucius Institutes; Z:Forum for China–Africa Cooperation; publicImportV1

Children's Work and Apprenticeship - Lancy, DF (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:BQL6WTEL 2317526:L8VWPZD5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Central Africa; A:East Africa; C:Burkina Faso; C:Guinea; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:learning; P:crafts; R:survey; T:Formal apprenticeship; T:Lehrlingsausbildung; publicImportV1

Characteristics of micro, small and medium enterprises in Ghana: Gender and implications for economic growth - Asare, Roland; Akuffobea, Mavis; Quaye, Wilhelmina; Atta-Antwi, Kwasi (African Journal of Science, Technology, Innovation and Development, 2015)
© 2015 African Journal of Science, Technology, Innovation and Development. This paper sought to investigate the characteristics of MSMEs and to suggest ways of improving performance, particularly tackling constraints faced by women and youth entrepreneurs in Ghana. A total of 4 433 MSME operators were interviewed in all the ten regions of Ghana using a structured questionnaire. The study revealed that apprenticeship was the most common form of training received by the MSME operators interviewed. Disaggregating data by gender, it was observed that more men had received training in their business operations than women. Close to 90% of the MSMEs were under sole proprietorship. There was significant correlation between gender and scale of enterprises, with increasing numbers of men as scale of operations increased. Women, who dominated the agro-processing, agro-industrial and services sectors, were constrained by ineffective marketing strategies, lack of capital, inadequate equipment and machinery, lack of improved technology, inadequate training and low skill development. Marketing strategies employed by the majority of women were limited, mostly patronising markets within their respective districts of business operations. The study recommended support for women to access sizeable business credit with flexible payment plans, tailor-made skill development training and improved access to institutional markets with quality and well-packaged products.
KerkoCite.ItemAlsoKnownAs: 10.1080/20421338.2014.979651 10/gd9bc3 2129771:9V7XC358 2317526:Q8Q2KP2R LOCAL-SCOPUS_ID:85006409797
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:access; F:gender; F:payment; F:women; P:economy; P:media; P:services; P:technology; Q:flexible; R:interview; R:questionnaire; T:Lehrlingsausbildung; T:Training; Z:Businesses; Z:Constraints; Z:Development; Z:Gender; Z:Practices; _C:Ghana GHA; __C:filed:1; publicImportV1

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Haßler, Björn; Chuang, Rachel (EdTech Hub, 2020)
EdTechHub.Source: 2405685:R9VVKUH5 EdTechHub.Source: 2405685:R9VVKUH5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3873462 2129771:237CSM4W 2129771:IGN2QCEN 2129771:RMWSKUI5 2129771:TAFSP89V 2339240:4P99D7MN 2339240:5P9STQIK 2339240:K3RVT7JU 2339240:WP59YJ57 2405685:3TKLS2TH 2405685:BHY8AJBY 2405685:I62EYSDT 2405685:R9VVKUH5 2486141:IX4B74H9 10.5281/zenodo.3873462
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _C:Australia AUS; _C:Bangladesh BGD; _C:Benin BEN; _C:Botswana BWA; _C:Brazil BRA; _C:Burundi BDI; _C:China CHN; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Malawi MWI; _C:Myanmar MMR; _C:New Zealand NZL; _C:Niger NER; _C:Nigeria NGA; _C:Pakistan PAK; _C:Paraguay PRY; _C:Portugal PRT; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Spain ESP; _C:Sri Lanka LKA; _C:State of Palestine PSE; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _forthcoming; _r:ImportedToMyEducationEvidence; _yl:h; _zenodoODE; docs.opendeved.net

Chapter 9: INVEST Africa - Isaacs, Shafika (Using ICTs and Blended Learning in Transforming TVET, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:WVV3BNC3 2317526:SVVD5ZKB
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Kenya; C:Zambia; CA:AandC; CLL:en; publicImportV1

Chapter 12: Considerations in Costing ODL and ICTs in TVET - Hoosen, S; Butcher, N (Using ICTs and Blended Learning in Transforming TVET, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:NTRZ8NZ5 2249382:CNYM4R76 2317526:IQCV5LKH
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Botswana; C:Namibia; C:South Africa; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:Q; CT:T; Q:OER; T:TVET; publicImportV1

Changing pedagogical practice in Kenyan primary schools: the impact of school‐based training - Hardman, Frank; Abd‐Kadir, Jan; Agg, Catherine; Migwi, James; Ndambuku, Jacinta; Smith, Fay (Comparative Education, 2009)
This study reports on an investigation into the impact of a national, school‐based teacher development programme on learning and teaching in Kenyan primary schools. Building on a national baseline study (n=102), 144 video‐recorded lessons, covering the teaching of English, maths and science at Standards 3 and 6, were analysed to investigate whole‐class teaching and group‐based learning. Interviews were also conducted with school management committees, head teachers, teachers and pupils to elicit their views on the impact of the school‐based training programme on learning and teaching. The study found that compared to the earlier baseline, teachers were more interactive with the pupils in their whole‐class teaching and greater use was being made of group work. Lesson plans, teaching resources and flexible classroom layouts were also much more in evidence. However, the greatest impact on classroom practice was seen in the classrooms of those teachers who had undergone the most systematic in‐service training. The wider implications of the findings for improving the quality of classroom learning in Kenyan primary classrooms are considered.
00083 KerkoCite.ItemAlsoKnownAs: 10.1080/03050060802661402 10/d4pwg6 2129771:QUUGMC69 2129771:TUTLCRRE 2405685:YDTY3JCV 261495:A32BNMRX
Keywords: C:Kenya; _C:Botswana BWA; _C:Brunei Darussalam BRN; _C:Ghana GHA; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:Nigeria NGA; _C:South Africa ZAF; _C:Tanzania TZA; __C:filed:1; __C:scheme:1

Changing classroom practice using a school-based professional development approach to introducing digital resources in Zambia - Haßler, Björn; Hennessy, S.; Lubasi, B. (Itupale Online Journal of African Studies, 2011)
KerkoCite.ItemAlsoKnownAs: 2129771:97RP78VU 2129771:AIM8NQRH 261495:CF6Z9BP2
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _r:ImportedToMyEducationEvidence; _yl:b; ⛔ No DOI found

Challenges of Using Icibemba in the Learning of Initial Literacy in Selected Primary Schools in Serenje District of Zambia: An Analysis of Views of Teachers and Learners - Chibesakunda, Mwimba; Mulenga, Innocent Mutale (Multidisciplinary Journal of Language and Social Sciences Education (2664-083X, Online ISSN: Print ISSN: 2616-4736), 2019)
The purpose of this study was to establish views and investigate challenges faced by teachers and learners in the use of Icibemba in teaching initial literacy in primary schools in Serenje district. A descriptive research design supported by qualitative data collection techniques was employed. A purposive sampling procedure was used to select all the participants giving the study a sample size of 56 comprising of 40 grade four learners and 16 of their teachers sampled from 10 primary schools. Researchers decided to have more learners in this study since they were the direct beneficiaries of the curriculum. And thus the need to have a wider view from them. This was also done so as to have enough participants from each school. Data was collected through interviews, focus group discussions and classroom observations of literacy lessons. Lesson observation was used to get first hand information on the learning experiences and helped the researchers to triangulate with what participants expressed during interviews and focus group discussions. Focus group discussions and interviews enabled participants to provide their detailed views of the exact situation learners and teachers encountered. Thematic analysis was used to analyze all the data. It involved organizing data through use of open, axial and selective coding before presenting the emerging themes. The findings revealed that although the Ministry of General Education zoned Serenje district under Icibemba instead of Icilala in teaching initial literacy, learners’ performance was low because the language used in school was unfamiliar to learners. Additionally, findings also showed that there was a lack of teacher’s guide books and learners’ text books to use in teaching initial literacy hence teacher’s delivery of lessons was negatively affected. Researchers concluded that learners performed poorly in literacy due to the fact that the zoned language was unfamiliar to learners in that area where it was used as a medium of teaching literacy. It is therefore recommended that the Ministry of General Education through the Curriclum Development Center should develop and produce and distribute learning materials for the teaching of literacy in grades one to four. Furthermore, lessons for literacy should be taught using concrete and real teaching and learning resources that can enhance learning. Additionally, there is a need to start thinking about the possibility of rezoning the whole country.
Number: 1 KerkoCite.ItemAlsoKnownAs: 2129771:856UQLBM 2129771:NU87YDL4 2129771:SUQ28UP5 2129771:SXYWSC5C
Keywords: Familiar language; Initial literacy; Language of Instruction; Local language; ⛔ No DOI found

Challenges of Technical Vocational Teacher Education and Teaching in Nigeria: The Need for Intervention - Kennedy, George W; Udoetuk, Udeme S (2017)
This paper reviews the critical roles of Technical Vocational teacher education and teaching in Nigeria. The paper establishes a nexus between quality Technical Vocational teacher education and national development. Critical challenges to Technical Vocational teacher education programmes and the teaching profession in Nigeria are identified to include over-crowded classes for teacher’s trainees, inequity in urban/rural deployment of teachers, poor funding and inadequate facilities, low quality Information and Communication technology (ICT) compliance and non-professionalization of teaching in Nigeria. Recommendations which include, a standard class, equity in urban/rural deployment of teachers, training/or retraining of Technical Vocational teacher in qualitative Information and Communication technology (ICT), Technical Vocational teacher mandatory membership in professional organisation, periodic attendance and active participation at conferences, seminars and workshop were made.
Keywords: _C:China CHN; _C:India IND; _C:Japan JPN; _C:Nigeria NGA; _C:Turkey TUR; _C:United States USA; __C:filed:1; __C:scheme:1

Challenges of Curtin-AVU-AAU Distance Learning Program in Ethiopia: A Case Study - Belwal, Rakesh; Dawit Ayalew Kassa; Medhanie Gaim Asgedom (MERLOT Journal of Online Learning and Teaching, 2010)
Distance education programs are emerging globally in the form of joint ventures among higher educational institutions. This paper describes the research undertaken to explore one such joint venture program in business between Australian and African universities. This study utilizes both primary and secondary data gathered through a review of the literature, consultations with program administrators, interviews with faculty members, direct observations, and questionnaires administered to sample students. This case study explores factors affecting the program. Using quantitative and qualitative analytical tools, this study discusses the outcomes of the analyses to facilitate experiential learning. It finds that for students originating mainly from remote regions of Ethiopia, distance learning can offer good opportunities of receiving cost-effective, quality-education on their doorsteps. This experience could contribute immensely to the extension of such programs to other regions of the country. Although the joint venture reveals the potential of coordinated educational efforts, internal weaknesses and inefficiencies need serious attention to ensure the success of such initiatives in the future.
KerkoCite.ItemAlsoKnownAs: 2129771:9ZJBUJR4 2317526:4T9GN28B
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:outcomes; P:technology; Q:distance learning; Q:higher education; R:case study; R:interview; R:observation; R:qualitative; R:quantitative; R:questionnaire; T:distance learning program; Z:Alliances; Z:Distance learning; Z:Education reform; Z:Market entry; Z:Qualitative research; Z:Technological change; __C:filed:1; publicImportV1; ⛔ No DOI found

Challenges in the training of teachers through open and distance learning: Implications for quality - Mubika, KA; Bukaliya, R (Asian Journal of Social Sciences & Humanities, 2013)
This study aimed at establishing the challenges that may have affected the training of teachers through ODL at the Zimbabwe Open University. The study was carried out in order to put in place a model that may be implemented to improve the quality teacher training programme. The study adopted the case study design for the gathering the in-depth perceptions held by the given population. Questionnaires, telephone interviews and documentary analysis were adopted for data collection. The population of the study consisted of the National Programme Leader, Regional Programme Coordinators and graduate diploma students and their former school heads. Thirty-three members of the population constituted the sample for this study. Among other findings, results of the study show that while the training of teachers was a very viable undertaking at ZOU, existing collaboration between the schools and the training institution was very informal. Teaching practice faced numerous problems such as inadequate funding and unavailability of teaching practice vehicles. The study recommended that there be collaboration among all the stakeholders. There is also need for the setting up of a Teaching Practice Department which should be fully equipped with to enable the smooth flow of teaching practice supervisory activities.
KerkoCite.ItemAlsoKnownAs: 2129771:7Y69A25Z 2317526:936H4XCC UTI-BCF2239B-F7FC-3E8D-A3BE-8B8B5C6D7A5D
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:teachers; Q:ODEL; T:Lehrlingsausbildung; T:Training; publicImportV1; ⛔ No DOI found

Challenges in the Informal Construction Artisan Training System in the Ghanaian Construction Industry - Damasah, SK (College of Art and Built Environment, 2016)
This research sought to find out the challenges confronting the informal artisan training system in the Ghanaian construction industry and provide available opportunities to help improve the system. The study was limited to two regions namely Greater Accra and Volta regions of Ghana. In all, two hundred and thirty-three (233) artisans comprising of one hundred and thirteen (113) apprentices and one hundred and twenty (120) master artisans were used for the study. Questionnaires were the main research instrument but personal observation was also used by the researcher. The sample of three hundred (300) was used in the data analysis. Qualitative research approach was used, employing the descriptive approach. Data from the field was analysed using percentages. From the findings, it was realized that two main modes of skill acquisition were in play pertaining to the informal sector, these are the traditional method (75%) and the attachment method (25%). Another finding was that, one shortcoming of the informal system appears to be a lack of consistency and adequate content in the training that apprentice receive. The study concludes that there is little external motivation or capability for the system’s trainees to progress in performance or in improving their methods. More than 55% of the master artisans apply experimentation or trial and error in their work. It is recommended that, it will be essential to involve the master artisans in a reform process including efforts to provide them with opportunities to upgrade their own knowledge of construction skills.
KerkoCite.ItemAlsoKnownAs: 2129771:9ZD86LA7 2317526:C4X3KFCN UTI-44D05C99-3FFA-30A1-91F8-C18A23CBCCA7
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:T; P:artist; P:construction; T:Formal apprenticeship; T:Training; _C:Ghana GHA; publicImportV1

Challenges facing technical and vocational education in Ghana - Amedorme, SK; Fiagbe, YAK (International Journal of Scientific & Technology Research, 2013)
Abstract : Technical and vocational education and training (TVET) in Ghana is facing a number of challenges. The problems ranging from the limited number of technical institutes available in the country, lack of facilities and materials for training students, inadequate technical teachers or facilitators, limited number of training institutions for technical teachers and difficulty in career progression to the negative public attitudes and perceptions towards technical and vocational education and training in Ghana. In this paper, these challenges confronting TVET and the pertinent issues are discussed with the aim of recommending ways of addressing them.
KerkoCite.ItemAlsoKnownAs: 2129771:UZEN6WB2 2317526:GCVCK6TS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; T:TVET; T:training needs; _C:Ghana GHA; __C:filed:1; publicImportV1; ⛔ No DOI found

Challenges and Prospects of Information Communication Technology (ICT) in Teaching Technical Education towards Globalisation - Olabiyi, OS (Effects of Information Capitalism and Globalization on Teaching and Learning, 2014)
The relevance of Information and Communication Technologies (ICTs) in the field of Technical Vocational Education and Training (TVET) cannot be overemphasised in the knowledge-based and globalised society. The world of works is in as continuous a state of change as ICT itself, thus posing more challenges to the workers in the 21st century and the institutions responsible for their preparation. Therefore, this chapter discusses the challenges and prospects of ICT in teaching TVE towards globalisation. The chapter points out clearly the meaning, philosophy, and objectives of TVET, concept and types of ICT, the need for effective utilisation of ICTs and its role in TVET, the challenges and solutions to the effective utilisation of ICTs in TVET, and the prospect of using ICT in teaching TVET. The chapter concludes by suggesting solutions for proper planning, management, and effective utilisation of ICTs resources in TVET.
KerkoCite.ItemAlsoKnownAs: 2129771:VI7QUHLL 2317526:2R3T6FAS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:teaching; P:technology; Q:ICT; T:TVET; publicImportV1

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Björn; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2015.1092466 10.1080/1475939x.2015.1092466 10/gfv5xz 2129771:5VQYH38X 2129771:AMZ6ZM6C 2129771:J9GHN7C4 2129771:L2HUHYLN 2129771:Z6IRJ6Y4 2129771:ZCU7ZNTG 257089:GN2B3JX9 261495:HSFJGS9C
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Bangladesh BGD; _C:France FRA; _C:Japan JPN; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:Pakistan PAK; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _yl:b

Career challenges in construction craft training in technical vocational education and training in Ghana - Yangben, PN; Seniwoliba, JA (2014)
The study examined the challenges of the Pilot Training Centre (PTC) at the National Vocational Training Institute (NVTI) at Kokomlemle, a suburb of Accra in the training of tradesmen for the construction industry. A descriptive survey design was used for the study. The population consists of tutors, current students and past students of the PTC/NVTI and contractors within the Accra Metropolis. The sample comprised ten tutors, fifteen past students, one hundred and ten currents and ten contractors were randomly selected from the PTC and contractors. A set of questionnaire was prepared and used for collecting data for the study. The data were analyzed using the descriptive statistics from the Statistical Package for Social Scientist (SPSS 16 version).For many years, technical and vocational education in Africa has been considered as a career path for the less academically endowed. This perception has been fuelled by the low academic requirements for admission into TVET programmes and the limited prospects for further education and professional development. Worse of all, the impression is sometimes created by governments that the primary objective of the vocational education track is to keep dropouts from the basic and senior high school system off the streets, rather than project this type of training as an effective strategy to train skilled workers for the employment market. However, 84.3% of the respondents refuted the assertion and only 15.7% supported the assertion. Based on these findings on the career challenges TVET trainees face, it was recommended that training institutions should be well resourced by the collective efforts of government and all other stakeholders so that training programmes can achieve their set objectives. Training providers should liaise with those in the industry so that in-service training activities could be organized which would enrich students with the right skills for the job market. There should be a clear cut for technical students climbing the academic ladder without bottlenecks.
KerkoCite.ItemAlsoKnownAs: 2129771:3G4FCKWH 2317526:6SPWM8TL UTI-BB8248E6-3B00-36D8-B42C-02FDB191916A
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:construction; P:crafts; P:nature; Q:masters; T:Educação profissionalizante; T:TVET; T:Training; T:career; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

Capacity Building For Entrepreneurship Education: The Challenge For The Developing Nations - Eze, John F.; Nwali, Anthony C. (American Journal of Business Education (AJBE), 2012)
Number: 4 KerkoCite.ItemAlsoKnownAs: 10.19030/ajbe.v5i4.7117 10/gf62m8 2129771:3N36VEHG 2129771:9HU76LE7 2317526:7ISBHD6T 2317526:H2PQ8BHW
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Nigeria; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:T; Capacity Building; D:developing country; D:developing nation; D:developing world; Economic Development; Entrepreneurship; Entrepreneurship Education; F:curriculum; F:inclusion; F:learning; F:policy; P:economy; P:service industry; P:social; Q:certificate; Q:degree; Q:diploma; Q:higher education; T:Ausbildung; T:entrepreneurship education; Z:Business education; Z:Business schools; Z:Curriculum development; Z:Developing countries–LDCs; Z:Economic development; Z:Entrepreneurship; Z:Higher education; Z:Studies; publicImportV1

Building mental health workforce capacity through training and retention of psychiatrists in Zimbabwe - Abas, Melanie A.; Nhiwatiwa, Sekai M.; Mangezi, Walter; Jack, Helen; Piette, Angharad; Cowan, Frances M.; Barley, Elizabeth; Chingono, Alfred; Iversen, Amy; Chibanda, Dixon; Barley, Elizabeth; Barley, Elizabeth; et al. (International Review of Psychiatry, 2014)
Despite the need to improve the quantity and quality of psychiatry training in sub-Saharan Africa (SSA), very little is known about the experiences of psychiatric trainees in the region. This is the first study examining psychiatric trainees in a low-income country in SSA. It was carried out as part of the needs assessment for a unique Medical Education Partnership Initiative (MEPI) programme to find African solutions for medical shortages in Africa. We approached all doctors who had trained in post-graduate psychiatry in Zimbabwe in 2010 and conducted in-depth qualitative interviews with all except one (n = 6). We analysed the data using constant comparison and thematic analysis. Trainees described the apprenticeship model as the programme's primary strength, through providing clinical exposure and role models. Programme weaknesses included shortages in information sources, trainee salaries, trainers, public health education, and in the mental health service. Most respondents were, however, eager to continue practising psychiatry in Zimbabwe, motivated by family ties, national commitment and helping vulnerable, stigmatized individuals. Respondents called for sub-speciality training and for infrastructure and training to do research. Resources need to be made available for psychiatric trainees in more SSA settings to develop public health competencies. However, investment in psychiatry training programmes must balance service provision with trainees' educational needs. Directing investment towards needs identified by trainees may be a cost-effective, context-sensitive way to increase retention and learning outcomes. © 2014 Institute of Psychiatry.
KerkoCite.ItemAlsoKnownAs: 10.3109/09540261.2014.924487 10/gf62pv 2129771:S37KJPZJ 2317526:H7G6FTSU
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Zimbabwe; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:low-income country; F:assessment; F:learning; F:outcomes; F:salary; P:health; P:measurement; P:media; P:services; R:interview; R:qualitative; T:Lehrlingsausbildung; T:Training; T:trainee; _C:Canada CAN; _C:Ghana GHA; _C:Mexico MEX; _C:Nicaragua NIC; _C:South Africa ZAF; _C:United Kingdom GBR; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; publicImportV1

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (2020)
EdTechHub.Source: 2405685:6W2UWE89 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 2129771:2MD2QL8K 2405685:6W2UWE89 2339240:7QEJ68RG
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _C:Afghanistan AFG; _C:Bhutan BTN; _C:Gambia GMB; _C:Ghana GHA; _C:Malawi MWI; _C:Nepal NPL; _C:Nigeria NGA; _C:Pakistan PAK; _C:Rwanda RWA; _C:Somalia SOM; _C:South Sudan SSD; _C:Sudan SDN; _C:Uganda UGA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Building capacity for professional development: the development of teachers as facilitators in Ghana - Perry, Emily; Bevins, Stuart (Professional Development in Education, 2018)
In low- and middle-income countries, cascade models of teacher professional development are often used as routes to educational reform. In these models, external agents deliver professional development, which is then disseminated by in-country facilitators. However, little is known about how to support facilitators of professional development, particularly in low- and middle-income countries. In this study, we report on a model of capacity building for professional development in Ghana. In the context of a large-scale programme of science teacher professional development, a group of Ghanaian teachers gradually assumed responsibility for professional development facilitation, working alongside experienced facilitators from the UK. Using interviews focussed on a storyline technique, we explore the experiences of the Ghanaian teachers as they reflected on their roles. We found the teachers’ epistemological beliefs about teaching were coherent with those of the programme and suggest that this may be an important factor in the success of cascade models of professional development. The teachers gained self-confidence and improved their knowledge and skills of teaching and of professional development facilitation. We propose that this is useful learning for all facilitators and that the model described here is one which is potentially useful for capacity building in other contexts.
KerkoCite.ItemAlsoKnownAs: 10.1080/19415257.2018.1474489 10/gf62g8 2129771:ZSW9GMBF
Keywords: CPD; Ghana; Professional development; _C:Benin BEN; _C:Ghana GHA; _C:India IND; _C:Kenya KEN; _C:Lesotho LSO; _C:Netherlands NLD; _C:Nigeria NGA; _C:Singapore SGP; _C:Somalia SOM; _C:Somaliland XSMLD; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; capacity building; facilitation; professional learning; science education

BTVET Act - Business, Technical, Vocational Education Act and Training Act - Government of Uganda (2008)
UA-3bb9182e-8e45-4a62-accc-6e180fb22c9f KerkoCite.ItemAlsoKnownAs: 2129771:3TVXXDG8 2317526:EL3XYKS7
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Uganda; publicImportV1

Bridging the Bandwidth Gap: Open Educational Resources and the Digital Divide - Haßler, Björn; Jackson, Alan McNeil (IEEE Transactions on Learning Technologies, 2010)
http://doi.ieeecomputersociety.org/10.1109/TLT.2010.8
00008 EdTechHub.Copy: 2405685:VCQFS2J9 KerkoCite.ItemAlsoKnownAs: 10.1109/tlt.2010.8 10/dxgcg5 2129771:9ZBX559Q 2129771:AL3P4CV5 2129771:WU5VWEPS 2405685:VCQFS2J9 257089:2XRARJMC
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; _C:Brazil BRA; _C:Guatemala GTM; _C:Mexico MEX; _C:Pakistan PAK; _C:Rwanda RWA; _C:Sudan SDN; _C:United States USA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence

BQA Act - Botswana Qualifications Authority Act Nº 24 - Government of Botswana (2013)
KerkoCite.ItemAlsoKnownAs: 2129771:7Y8WZPDB 2317526:6ISIESAH
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; publicImportV1

BNVQF - Botswana National Vocational Qualifications Framework - Government of Botswana (2005)
KerkoCite.ItemAlsoKnownAs: 2129771:LRZ92HFH 2317526:TGGR3UEF
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CC:Botswana; Qualification Framework; publicImportV1

Blended learning vid lärares professionella lärande - Nilsson, Malin (2017)
KerkoCite.ItemAlsoKnownAs: 2129771:XYDS49VP
Keywords: _C:Canada CAN; _C:Finland FIN; _C:New Zealand NZL; _C:Portugal PRT; _C:Tanzania TZA; _C:United Kingdom GBR; _C:Viet Nam VNM; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; ⛔ No DOI found

Blended learning methods in introduction to teaching and sociology of education courses at a university of education - Ololube, Nwachukwu Prince (Advancing technology and educational development through blended learning in emerging economies, 2014)
KerkoCite.ItemAlsoKnownAs: 2129771:TFI2MYEF
Keywords: _C:Nigeria NGA; __C:filed:1; __C:scheme:1

Blended Learning in the Vocational Education and Training System in Tanzania: Understanding Vocational Educators' Perceptions - Machumu, HJ; Zhu, C; Sesabo, JK (International Journal of Multicultural and Multireligious Understanding, 2016)
In a constructivist world of teaching and learning, opportunities to acquire and develop the knowledge and practical skills necessary to design, establish, and deploy blended learning in vocational education and training (VET) programs delivery is a labour-market-driven. The paper examines VET educator’s pleas about the need for the design, adoption and deployment of blended learning in VET programs delivery in Tanzania. A single case study design with an in-depth interview and focus group discussion was conducted with 15 VET educators in three VET colleges in both Morogoro and Dar es Salaam regions. Snowball and purposive sampling were used to obtain sample respondents. For the data analysis, content analysis was employed to condense data obtained from interviews and focus group discussion. It was found that continuous professional development, institutional arrangements, and support should be provided online to facilitate the design, adoption and use of blended learning in VET. We recommend that locally designed blended learning should be relevant to the environment of both students and teachers. In reality, the interplay between blended learning, imparting knowledge and practical skills remain the key focus of future research.
KerkoCite.ItemAlsoKnownAs: 10.18415/ijmmu.v3i2.46 10/gf623b 2129771:FVP787HA 2317526:7SSXUQBF UTI-5C942F65-1513-3AC4-8993-CBC0906C370B
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:learning; F:teaching; HDR25; P:technology; Q:e-learning; Q:mobile learning; Q:open education; T:Ausbildung; T:TVET; publicImportV1

Between Social Justice and Decolonisation: Exploring South African MOOC designers’ conceptualisations and approaches to addressing injustices [presentation, O-143] - Adam, Taskeen (OER20, 2020)
As social justice and decolonisation discussions fill the physical and virtual corridors of university spaces in South Africa, educators, and in this case, MOOC designers, are inevitably influenced by them. They are prompted to reflect on such topics, whether in agreement or with scepticism. Provoked by one interviewee’s comment that ‘you could decolonise and still have an enormous amount of injustice’, this paper investigates how South African MOOC designers conceptualise justices, and how they attempt to address these injustices in and through their MOOCs. As terminology from these discourses at times misconstrued MOOC designers’ opinions, an analytical framework was created to shift focus to addressing injustices, namely: material injustices, cultural-epistemic injustices, and political/geopolitical injustices. These Dimensions of Human Injustice were used to analyse semi-structured interviews with 27 MOOC South African designers. It was found that they formed opinions based on the aforementioned discourses, which impacted their engagement with injustice in their designs. Those who stressed cultural-epistemic injustices, focused on relevance, inclusive processes and the geopolitics of knowledge production. Those who stressed material injustices, focused on socio-economic disparities, infrastructural inequalities and the need to tackle these systemic problems at a societal level. Through highlighting MOOC designers’ attempts at addressing injustices, it is envisioned this will lead to more multi-dimensional, justice-oriented approaches to MOOC design that better enable learners. Additionally, efforts by South African MOOC designers, highlighted in this paper, can be seen as a guide for the MOOC space in general to take greater strides in creating MOOCs in more justice-oriented ways.
KerkoCite.ItemAlsoKnownAs: 2129771:NW9VFE68
Keywords: Author:OpenDevEd

Between Social Justice and Decolonisation: Exploring South African MOOC Designers’ Conceptualisations and Approaches to Addressing Injustices [journal article] - Adam, Taskeen (Journal of Interactive Media in Education, 2020)
As social justice and decolonisation discussions fill the physical and virtual corridors of universities in South Africa, educators, and in this case, MOOC designers, are inevitably influenced by them. They are prompted to reflect on such topics, whether in agreement or with scepticism. Provoked by one interviewee’s comment that ‘you could decolonise and still have an enormous amount of injustice’, this paper investigates how South African MOOC designers conceptualise (in)justice, and how they attempt to address these injustices in and through their MOOCs. As notions such as ‘social justice’ and ‘decolonisation’ have multiple meanings and connotations, a framework was created to unpack the ‘Dimensions of Human Injustice’ namely, material, cultural-epistemic, and political/geopolitical injustices. These dimensions of injustice were used to analyse semi-structured interviews with 27 South African MOOC designers. MOOC designers who stressed cultural-epistemic injustices, focused on relevance, inclusive processes and the geopolitics of knowledge production. Those who stressed material injustices, focused on socio-economic disparities, infrastructural inequalities and the need to tackle these systemic problems at a societal level. Through illustrating that MOOC designers attempt to address injustices based on their different conceptualisations of (in)justice, this study argues that a multi-pronged approach to tackling the various dimensions of injustice perpetuated in and through MOOCs can lead to more holistic justice-oriented MOOCs that better enable learners. Additionally, justice-oriented efforts by South African MOOC designers, highlighted in this paper, can be seen as a guide for the MOOC space in general to take greater strides in creating MOOCs in more justice-oriented ways.
Number: 1 Publisher: Ubiquity Press EdTechHub.Source: <this> EdTechHub.Source: 2129771:TMULW29L KerkoCite.ItemAlsoKnownAs: 10.5334/jime.557 2129771:AYIPTCYC 2129771:TMULW29L 2405685:UBRAD3MS 2447227:5ZYAXQAX
Keywords: Author:OpenDevEd; MOOC designers; _C:Albania ALB; _C:South Africa ZAF; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; cultural-epistemic injustice; decolonisation; docs.opendeved.net; geopolitical injustice; material injustice; social justice

Benefits of using ISSB in school buildings - Nambatya, Mauricia (Open Development & Education, 2023)
An output of the Open Development & Education, https://opendeved.net/
CallNumber: opendeved.1034 ZenodoArchiveID: 10257225 ZenodoArchiveConcept: 10257224 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1034 2129771:3KUTI3BB
Keywords: _r:AddedByMyEducationEvidence

Baseline Study for Distance Technical and Professional Education in Mozambique - Romiszowski, A (2015)
This baseline study has been undertaken to describe and analyse the current situation with respect to TVET, in order to evaluate the needs and the viability of employing open and distance Learning (ODL), and in particular eLearning in a flexible and blended approach. The main focus of the study is directed to that part of the system that is under the responsibility of the National Directorate for Technical and Professional Education (DINET) – namely the pre-tertiary level public-sector TVET institutions. These institutions are classified into three levels, equivalent to the subdivisions of the general education system: elementary, basic and medium, the last being equivalent to high school – the 11th and 12th grades. Elementary level courses are offered in 36 technical schools, 28 offer basic level courses and 19 offer courses at the medium level, a total of 85.
KerkoCite.ItemAlsoKnownAs: 2129771:EI9BPEQX 2317526:UK28UYUK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Mozambique; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:manufacture; P:teachers; P:technology; Q:ICT; Q:ODEL; Q:distance education; Q:open education; T:Ausbildung; T:Educação Profissional Técnica de Nível Médio; T:TVET; T:competency-based training; T:professional and vocational education; T:trainee; publicImportV1

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (2020)
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Ghana GHA; _C:Guinea GIN; _C:India IND; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Zambia ZMB; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _publish; _r:ImportedToMyEducationEvidence; _yl:g; _zenodoETH; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (2020)
EdTechHub.Source: 2405685:DS66UGW4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:DS66UGW4 2405685:IS587WTH
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Bolivia BOL; _C:Congo XCO; _C:Congo; Democratic Republic COD; _C:Ghana GHA; _C:Guinea GIN; _C:India IND; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Mozambique MOZ; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Sri Lanka LKA; _C:Zambia ZMB; _EdTechHub_Output; __C:filed:1; __C:scheme:1; _cover:v1; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Availability and usage of information communication technology facilities in secondary schools in Zambia - Nsama, Peggy; Masaiti, Gift; Akakandelwa, Akakandelwa (Zambian Journal of Educational Management, Administration and Leadership (ZJEMAL)(ISSN-Print: 2706-7416, Online: 2709-1864), 2020)
Keywords: ⛔ No DOI found

Availability, Access and Utilization of E-Resources among Pre-Service Teacher Trainees by Distance - Olaniran, Sunday O.; Duma, M. A. N.; Nzima, D. R.; Kumar, V; Murthy, S; Kinshuk (IEEE 8TH International Conference on Technology for Education, 2016)
The study investigated accessibility to and utilization of electronic resources among pre-service teachers in the National Open University of Nigeria (NOUN). Survey research design was used to carry out the study. Two hundred and thirty eighty (238) undergraduate students studying to obtain Bachelor of Education (B. Ed.) by distance were purposively sampled from Ibadan Study Centre of the institution. The results from the survey revealed that electronic resources in different forms like radio broadcast, e-journals, e-books, and CD-ROM, among others, are available and accessible to the pre-service teacher trainees by distance. However, limited internet connectivity and inadequate access to electricity were shown as major factors constraining most of the participants from accessing and utilizing the available electronic resources. The study recommends for the distance learning providers in developing nations to partner with telecommunication firms and internet service providers with a view to providing constant and affordable internet services to their learners, especially those that are studying to become classroom teachers.
KerkoCite.ItemAlsoKnownAs: 10.1109/T4E.2016.55 2129771:NRBGSNFD 2317526:YD6P9NHZ
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; C:Nigeria; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing nation; F:access; P:electro; P:service industry; P:teachers; Q:ICT; Q:distance learning; Q:e-learning; R:research design; R:survey; T:trainee; Z:E-Learning; Z:E-Resources; Z:ICT; Z:ODL; Z:Pre-Service Teachers; publicImportV1; ⚠️ Invalid DOI

Automatic Teacher Modeling from Live Classroom Audio - Donnelly, Patrick J.; Blanchard, Nathan; Samei, Borhan; Olney, Andrew M.; Sun, Xiaoyi; Ward, Brooke; Kelly, Sean; Nystran, Martin; D'Mello, Sidney K. (Proceedings of the 2016 Conference on User Modeling Adaptation and Personalization, 2016)
We investigate automatic analysis of teachers' instructional strategies from audio recordings collected in live classrooms. We collected a data set of teacher audio and human-coded instructional activities (e.g., lecture, question and answer, group work) in 76 middle school literature, language arts, and civics classes from eleven teachers across six schools. We automatically segment teacher audio to analyze speech vs. rest patterns, generate automatic transcripts of the teachers' speech to extract natural language features, and compute low-level acoustic features. We train supervised machine learning models to identify occurrences of five key instructional segments (Question & Answer, Procedures and Directions, Supervised Seatwork, Small Group Work, and Lecture) that collectively comprise 76% of the data. Models are validated independently of teacher in order to increase generalizability to new teachers from the same sample. We were able to identify the five instructional segments above chance levels with F1 scores ranging from 0.64 to 0.78. We discuss key findings in the context of teacher modeling for formative assessment and professional development.
KerkoCite.ItemAlsoKnownAs: 2129771:MWMRUTL7 2129771:P5U3LFX7
Keywords: _C:Canada CAN; _C:Congo; Republic COG; _C:United States USA; __C:filed:1; __C:scheme:1; automatic feedback; classroom discourse; dialogic instruction; educational data mining; speech recognition

Assessment of Perceived Ease of Use and Instructional Use of ICT by Lecturers in Technical Training Institutions in Kenya - Agufana, PB; Too, JK; Mukwa, CW (African Journal of Education, Science and Technology, 2018)
In the past ten years, Information Communication Technology (ICT) has become an essential part of our learning and development in education. The rapid development of these new technologies coupled with the worldwide challenge to educate all children has led to a global reform and development of teacher education and motivated educational Institutions to redesign and restructure their teaching methods to enable students equip themselves for the future. The main purpose of this study therefore was to explore the relationship between Perceived Ease of Use and instructional use of ICT by Lecturers in Technical Training Institutions in Kenya. The study adopted the quantitative research design. A sample size of 629 respondents was drawn from a total population of 2909 Lecturers in Technical Training Institutions in Kenya. Data were collected using questionnaires. The quantitative data obtained from the administrated questionnaires were analyzed using descriptive statistics. The findings indicated that use of ICT by lecturers’ is perceived to greatly improve instruction. The study recommends that lecturers be encouraged to use ICT for instructional purposes because it greatly improves the passage of instruction.
KerkoCite.ItemAlsoKnownAs: 2129771:89J6L33G 2317526:ZRG8DS9N
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Kenya; C:Rwanda; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:assessment; F:attitude; P:culture; P:school teacher; Q:ICT; Q:lifelong learning; Q:open learning; T:TVET; __C:filed:1; publicImportV1; ⛔ No DOI found

Assessment of perceived attributes and instructional use of information communication technology by lecturers in technical training institutions in Kenya - Agufana, PB (Moi University, 2015)
In the past ten years, Information Communication Technology (ICT) has become an essential part of our learning and development in education. Today it is no longer an option to learn the basic skills of ICT but rather a prerequisite for academic qualifications. The rapid development of these new technologies coupled with the worldwide challenge to educate all children has led to a global reform and development of teacher education and motivated educational institutions to redesign and restructure their teaching methods to enable students equip themselves for the future. The main purpose of this study therefore was to explore the relationship between Perceived Attributes and instructional use of ICT by Lecturers in Technical Training institutions in Kenya. The specific objectives of this study were, to establish the relationship between Perceived Attributes (ease of use, usefulness, cultural relevance, and government policy) and instructional use of ICT. The study adopted the quantitative research design. A sample size of 629 respondents was drawn from a total population of 2909 Lecturers in Technical Training institutions in Kenya. The sampling frame was obtained from a list provided by the Ministry of Education Science and Technology 2013. Data was collected using questionnaires. Piloting of the research tools was conducted and the sample obtained was subjected to the Cronbach‟s alpha. The quantitative data obtained from the administrated questionnaires was analyzed using descriptive statistics and inferential statistics. The study determined that ICT use has created a new platform for instruction. The findings also indicated that use of ICT by lecturers‟ greatly improved instruction. The study found out that; use of ICT improved ones relationship with others, and was fashionable. The study further found out that ICT policies enhanced use of ICT. The study concludes that perceived attributes are critical in instructional use of ICT. The study recommends that higher education qualifications are to be preferred for lecturers as it enables skilled use of available ICT technology. The study recommends the provision of Cisco Networking Academy Programme to provide more ICT exposure to students and staff. The study recommends that lecturers be encouraged to use ICT to access current and upto date information resources. The study recommends that the government should operationalize, the ICT lecturers competencies framework to enable lecturers have policy direction when planning for competence training. Lecturers are encouraged to use ICT for instructional purposes because it is the trend in modern communication, and has globalized the world. Lastly, the study recommends use of ICT for instruction as it greatly improves the instruction.
KerkoCite.ItemAlsoKnownAs: 2129771:XJCD389Q 2317526:SSQE8UDY
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:East Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:assessment; P:media; P:school teacher; P:technology; Q:ICT; R:survey; T:TVET; publicImportV1

Assessing the Impact of Training on Lowland Rice Productivity in an African Setting: Evidence from Uganda - Kijima, Yoko; Ito, Yukinori; Otsuka, Keijiro (World Development, 2012)
Summary This study attempts to assess the impacts of a training program on the adoption of improved cultivation practices, the productivity of rice farming, and the income and profit from rice production by using ex-post non-experimental data in Uganda. We found that participation in the training program increased the adoption of the improved cultivation practices. Furthermore, the profit from rice production was also found to have increased by the training program. These findings support the hypothesis that one of the major constraints on the growth in productivity of rice farming in sub-Saharan Africa is the absence of effective extension systems.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.worlddev.2012.04.008 10/gf62mn 2129771:6TCK7VHB 2317526:VYZHZQWE
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; CA:AandC; CCZ:Uganda; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:production; P:technology; R:impact; T:Training; Z:diffusion of technology; Z:improved cultivation practices; Z:lowland rice; Z:yield enhancement; _C:Uganda UGA; publicImportV1

Assessing the impact of the trauma team training program in Tanzania - Bergman, Simon; Deckelbaum, Dan; Lett, Ronald; Haas, Barbara; Demyttenaere, Sebastian; Munthali, Victoria; Mbembati, Naboth; Museru, Lawrence; Razek, Tarek; Razek, Tarek (Journal of Trauma - Injury, Infection and Critical Care, 2008)
BACKGROUND:: In sub-Saharan Africa, injury is responsible for more deaths and disability-adjusted life years than AIDS and malaria combined. The trauma team training (TTT) program is a low-cost course designed to teach a multidisciplinary team approach to trauma evaluation and resuscitation. The purpose of this study was to assess the impact of TTT on trauma knowledge and performance of Tanzanian physicians and nurses; and to demonstrate the validity of a questionnaire assessing trauma knowledge. METHODS:: This is a prospective study of physicians and nurses from Dar es Salaam undergoing TTT (n ≤ 20). Subjects received a precourse test and, after the course, an alternate postcourse test. The equivalence and construct validity of these 15-item multiple-choice questionnaires was previously demonstrated. After the course, subjects were divided into four teams and underwent a multiple injuries simulation, which was scored with a trauma resuscitation simulation assessment checklist. A satisfaction questionnaire was then administered. Test data are expressed as median score (interquartile ratio) and were analyzed with the Wilcoxon's signed rank test. RESULTS:: After the TTT course, subjects improved their scores from 9 (5-12) to 13 (9-13), p ≤ 0.0004. Team performance scores for the simulation were all >80%. Seventy-five percent of subjects were very satisfied with TTT and 90% would strongly recommend it to others and would agree to teach future courses. CONCLUSIONS:: After completion of TTT, there was a significant improvement in trauma resuscitation knowledge, based on results from a validated questionnaire. Trauma team performance was excellent when assessed with a novel trauma simulation assessment tool. Participants were very supportive of the course. © 2008 by Lippincott Williams & Wilkins.
KerkoCite.ItemAlsoKnownAs: 10.1097/ta.0b013e318184a9fe 10/bzcnz5 2129771:4RXGG6YM 2317526:3CVSJFSZ
Keywords: -FullBiblioUHMLgen; -RRQ:M:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CCZ:Tanzania; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:Improvement; F:assessment; F:disability; P:media; P:nurse; R:evaluation; R:impact; R:questionnaire; T:Training; Z:Education; Z:Team assessment; Z:Trauma team training; __C:filed:1; publicImportV1

Artisan training and employment outcomes in Tanzania - Bennell, Paul; Mukyanuzi, Faustin; Kasogela, Maurice; Mutashubirwa, Francis; Klim, Mikkel (Compare: A Journal of Comparative and International Education, 2006)
Studies have shown that artisan training courses in Africa are not cost-effective, and do not improve quality of life. The studies on artisanship education and their effects are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1080/03057920500382358 10/cq4xfd 2129771:7QPDWE5E 2317526:YYFGAN4J
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Tanzania; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:outcomes; P:artist; P:crafts; Survey; T:Training; Z:Craftsmen; Z:Feasibility studies; Z:Occupational training; Z:Quality of life; __C:filed:1; publicImportV1

Are Our Children Learning? The Status of Remote-learning among School-going Children in Kenya during the Covid-19 Crisis. - Uwezo Kenya (Uwezo, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:KP6KAY6P 2129771:KS33VZJD 2129771:LRBK4LWS 2405685:ZEM2E9VL
Keywords: _COVID-Continuity-Blogpost-01; _COVID_DEAA-List

Appropriateness and adequacy of teaching and learning resources and students’ industrial attachment in public colleges of technical and vocational education in Zambia. - Mulenga, Innocent Mutale; Chileshe, Edward King (2020)
Publisher: East African Journal of Education and Social Sciences

Apprenticeship Strategies Among Dii Potters from Cameroon, West Africa - Wallaert, H (2008)
KerkoCite.ItemAlsoKnownAs: 2129771:WYDEVZ8A 2317526:94N5NTT3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:West Africa; C:Cameroon; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:T; T:Lehrlingsausbildung; T:apprentice; publicImportV1

Analysis of factors affecting pupil performance in Malawi’s primary schools based on SACMEQ survey results - Mulera, David Mc W.J.; Ndala, Ken Kaziputa; Nyirongo, Richard (International Journal of Educational Development, 2017)
The paper employs techniques of multilevel modelling and geographical information systems (GIS) on Malawi’s SACMEQ1 I, II and III data to identify factors aﬀecting pupil performance in primary education of Malawi. The study reveals that in some districts pupils performed much better than others. Whilst in majority of cases the achievement levels of pupils were closely associated with the levels of inputs and services, there were some districts that did not demonstrate a positive correlation. The analysis further shows that pupils’ low socioeconomic status, high pupil-teacher ratios and the more time head teachers spent in teaching other than on school management were more signiﬁcant factors that negatively aﬀected pupil performance.
Keywords: _C:Botswana BWA; _C:Colombia COL; _C:Kenya KEN; _C:Laos LAO; _C:Malawi MWI; _C:Mozambique MOZ; _C:Namibia NAM; _C:South Africa ZAF; _C:Thailand THA; _C:Uganda UGA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

An investigation of appropriate new technologies to support interactive teaching in Zambian schools (ANTSIT). A joint report from Aptivate and the Centre for Commonwealth Education (University of Cambridge). Final Report to DfID. - Haßler, Björn; Hennessy, S.; Lord, T.; Cross, A.; Jackson, A.; Simpson, M. (Aptivate and University of Cambridge, 2011)
0007 EdTechHub.Copy: 2405685:3TABTBW7 KerkoCite.ItemAlsoKnownAs: 2129771:KZZRYUI2 2129771:QTDNPHWH 2129771:Y9FGADHH 2129771:ZATDIRKP 2405685:3TABTBW7 257089:5JDHV98J 261495:6J76DW54
Keywords: Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; __C:filed:1; _r:ImportedToMyEducationEvidence; _yl:a; ⛔ No DOI found

An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (The EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:BGLPB3AG
Keywords: _C:Gambia GMB; _C:Jordan JOR; _C:Malawi MWI; _C:Portugal PRT; __C:filed:1; __C:scheme:1; _r:ImportedToMyEducationEvidence; _zenodoODE

An examination of training and development of middle level managers in emerging economies: Evidence from financial institutions in Ghana - Abugre, James B.; Adebola, Kester (International Journal of Organizational Analysis, 2015)
© 2015, Emerald Group Publishing Limited. Purpose – The purpose of this paper is to examine whether the training and development (T&D) of middle-level managers in the financial institutions of a sub-Saharan African country make any difference in the performances of the managers and the institutions in general. Design/methodology/approach – An empirical analysis of managers’ opinions based on a quantitative survey of 140 middle-level managers from four banking institutions in Ghana is conducted. Findings – Findings showed that there is a significant relationship between T&D of middle-level managers and their performance and, consequently, performance of the banks. The findings also showed that managers become savvier in personal initiatives and responsive to customer care leading to enhanced service delivery. The paper proposes that T&D should focus on the significant relationship between the outcomes and programme objectives of organisations in emerging economies if these organisations want to be counted in this competitive global world. Practical implications – The paper provides valuable information on the important role of middle-level managers as custodians of “tacit knowledge” that can turn around organisations, particularly in developing economies, if the needed T&D are given to them. Originality/value – Empirical literature on T&D and on middle-level managers’ development in developing countries is limited. The contribution of this paper identifies the roles that middle management can play in the performances of organisations and especially in emerging economies.
KerkoCite.ItemAlsoKnownAs: 10.1108/ijoa-10-2011-0521 10/gf62pz 2129771:LL6D3NE8 2317526:EEZJGX8G
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; CA:AandC; CCZ:Ghana; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:developing country; D:emerging economies; F:outcomes; P:economy; P:measurement; P:services; R:quantitative; R:survey; T:Training; Z:Banks; Z:Mid-level managers; Z:Performance; Z:Training and development; _C:Australia AUS; _C:China CHN; _C:Ghana GHA; _C:Greece GRC; _C:Japan JPN; _C:Kuwait KWT; _C:Nigeria NGA; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; publicImportV1

An Atlas of The Forty Colleges of Education in Ghana - Haßler, Björn; Akunor, J. T.; Nyamador, E. S. (2017)
EdTechHub.Source: <this> EdTechHub.Source: 2129771:F7ZRYUZX KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911076 2129771:F7ZRYUZX 2129771:U3IVX9WX 2405685:SKFNBK29
Keywords: Author:Haßler; Author:OpenDevEd; _C:Ghana GHA; _C:Mexico MEX; _C:Zambia ZMB; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence

An assessment of employability skills among technical and vocational education students in Nigeria - Idris, A; Rajuddin, MR (Archives Des Science, 2012)
The research was conducted to investigate the level of importance as well as the competence among the students of technical and vocational education in terms of employability skills in Nigeria. There are 233 final year students that constituted the sample for the study in Kano State. The respondents were picked from mechanical, electronic, electrical installation and automobile departments in technical colleges in the state. The data was collected using questionnaire which was adapted from Employability skills for Australian small and medium sized enterprises. The analysis was done using descriptive statistics such as mean and standard deviation. The findings of the study showed that all the respondents perceived the employability skills components as high and rated their competency as low. A significant difference was found among the students in terms of their ages while no significant difference was found between the respondents in the area of competency. The study concludes that there is still an opportunity for technical and vocational institution in Nigeria to focus and redouble efforts towards equipping the students’ employability skills. Quality education and training enhances productivity, therefore, students of technical and vocational education in Nigeria need a better education that will help in accomplish the national goals.
KerkoCite.ItemAlsoKnownAs: 2129771:7DIXQXFQ 2317526:DGLU6N9H
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Central Africa; A:West Africa; C:Nigeria; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:assessment; F:women; T:TVET; publicImportV1; ⛔ No DOI found

An analysis of pre-service family planning teaching in clinical and nursing education in Tanzania - Muganyizi, Projestine S; Ishengoma, Joyce; Kanama, Joseph; Kikumbih, Nassoro; Mwanga, Feddy; Killian, Richard; McGinn, Erin (BMC medical education, 2014)
Doc number: 142 Abstract Background: Promoting family planning (FP) is a key strategy for health, economic and population growth. Sub-Saharan Africa, with one of the lowest contraceptive prevalence and highest fertility rates globally, contributes half of the global maternal deaths. Improving the quality of FP services, including enhancing pre-service FP teaching, has the potential to improve contraceptive prevalence. In efforts to improve the quality of FP services in Tanzania, including provider skills, this study sought to identify gaps in pre-service FP teaching and suggest opportunities for strengthening the training. Methods: Data were collected from all medical schools and a representative sample of pre-service nursing, Assistant Medical Officer (AMO), Clinical Officer (CO) and assistant CO schools in mainland Tanzania. Teachers responsible for FP teaching at the schools were interviewed using a semi-structured questionnaire. Observations on availability of teaching resources and other evidence of FP teaching and evaluation were documented. Relevant approved teaching documents were assessed for their suitability as competency-based FP teaching tools against predefined criteria. Quantitative data were analyzed using EPI Info 6 and qualitative data were manually analyzed using content analysis. Results: A total of 35 pre-service schools were evaluated for FP teaching including 30 technical education and five degree offering schools. Of the assessed 11 pre-service curricula, only one met the criteria for suitability of FP teaching. FP teaching was typically theoretical with only 22.9% of all the schools having systems in place to produce graduates who could skillfully provide FP methods. Across schools, the target skills were the same level of competence and skewed toward short acting methods of contraception. Only 23.3% (n = 7) of schools had skills laboratories, 76% (n = 22) were either physically connected or linked to FP clinics. None of the degree providing schools practiced FP at its own teaching hospital. Teachers were concerned with poor practical exposure and lack of teaching material. Conclusions: Pre-service FP teaching in Tanzania is theoretical, poorly guided, and skewed toward short acting methods; a majority of the schools are unable to produce competent FP service providers. Pre-service FP training should be strengthened with more focus on practical skills. Promoting family planning (FP) is a key strategy for health, economic and population growth. Sub-Saharan Africa, with one of the lowest contraceptive prevalence and highest fertility rates globally, contributes half of the global maternal deaths. Improving the quality of FP services, including enhancing pre-service FP teaching, has the potential to improve contraceptive prevalence. In efforts to improve the quality of FP services in Tanzania, including provider skills, this study sought to identify gaps in pre-service FP teaching and suggest opportunities for strengthening the training. Data were collected from all medical schools and a representative sample of pre-service nursing, Assistant Medical Officer (AMO), Clinical Officer (CO) and assistant CO schools in mainland Tanzania. Teachers responsible for FP teaching at the schools were interviewed using a semi-structured questionnaire. Observations on availability of teaching resources and other evidence of FP teaching and evaluation were documented. Relevant approved teaching documents were assessed for their suitability as competency-based FP teaching tools against predefined criteria. Quantitative data were analyzed using EPI Info 6 and qualitative data were manually analyzed using content analysis. A total of 35 pre-service schools were evaluated for FP teaching including 30 technical education and five degree offering schools. Of the assessed 11 pre-service curricula, only one met the criteria for suitability of FP teaching. FP teaching was typically theoretical with only 22.9% of all the schools having systems in place to produce graduates who could skillfully provide FP methods. Across schools, the target skills were the same level of competence and skewed toward short acting methods of contraception. Only 23.3% (n = 7) of schools had skills laboratories, 76% (n = 22) were either physically connected or linked to FP clinics. None of the degree providing schools practiced FP at its own teaching hospital. Teachers were concerned with poor practical exposure and lack of teaching material. Pre-service FP teaching in Tanzania is theoretical, poorly guided, and skewed toward short acting methods; a majority of the schools are unable to produce competent FP service providers. Pre-service FP training should be strengthened with more focus on practical skills.
KerkoCite.ItemAlsoKnownAs: 10.1186/1472-6920-14-142 10/f6bm6p 2129771:L3TWRW5G 2317526:I5R28FG3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Tanzania; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:teaching; P:economy; P:health; P:media; P:medical officers; P:nurse; P:service industry; P:services; P:teachers; Q:degree; R:evaluation; R:interview; R:observation; R:qualitative; R:quantitative; R:questionnaire; T:Ausbildung; T:TVET; publicImportV1

AMREF's Stand Up For African Mothers Campaign: Training Midwives to Reduce Maternal Mortality in Africa - Cabridens, M; Tolve, S (The Journal of Field Actions: Field Actions Science Reports, 2012)
Abstract. AMREF is the African Medical and Research Foundation, a uniquely African organization, created in 1957 which runs 145 health programmes a year to help around 7 million people in Africa. Headquartered in Nairobi and with offices around the world, AMREF ensures access to health care for the most vulnerable and marginalized people in Africa, with a focus on women and children. AMREF works within the communities, and works with and for women as they are the heart of the communities. Indeed, by focusing on midwives training in the Stand Up For African Mothers campaign, AMREF is able to talk about the key role of women and mothers for a healthy Africa and the needs of health workers to reduce mortality rates for mothers but also for children. Keywords. Health care, Africa, women, children, poverty, social work, midwifes, pregnancy.
KerkoCite.ItemAlsoKnownAs: 2129771:6PYYPYX6 2317526:Y2FGVEU7 UTI-1A7853B5-3161-3827-A9DE-182958302341
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:West Africa; C:Ethiopia; C:South Sudan; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:Q; CT:T; Q:ICT; Q:e-learning; T:Ausbildung; T:TVET; T:Training; _C:Uganda UGA; publicImportV1; ⛔ No DOI found

Ambientes online na profissionalização de professores em Cabo Verde: um projeto de investigação ação - Mendonça, Adriana (Universidade do Minho, 2014)
A introdução de ambientes online nas práticas docentes no ensino superior, tem-se afigurado numa necessidade um pouco por todo o mundo. Nesta investigação apresenta-se uma dessas iniciativas desenvolvidas na universidade de Cabo Verde (Uni-CV), no Departamento de Ciências Sociais e Humanas (DCSH). A Uni-CV conta com oito anos de existência, encontrando-se ainda na caminhada para a inclusão digital, a par do que ocorre no arquipélago cabo-verdiano. Mesmo com limitações, luta-se para alcançar os desafios da infoinclusão, nomeadamente através de programas como o Mundu Novu. É com esta preocupação que se trabalhou com estudantes finalistas em Ciências da Educação – Percurso de Desenvolvimento Pessoal e Social - futuros docentes da disciplina, do ensino secundário, de Formação Pessoal e Social/Educação para os Direitos Humanos e Cidadania. Isto para vivenciarem na sua formação inicial uma experiência inovadora, no período de estágio pedagógico, que enriquecesse a sua vivência e contribuísse para ampliar a sua visão sobre o potencial pedagógico dos ambientes online. Assim, a preocupação central da investigação foi perceber que desafios coloca a integração dos ambientes online nos processos de profissionalização dos docentes do Ensino Secundário em Cabo Verde, bem como compreender o espaço dos ambientes online nesse processo. Para tal, propôs-se compreender como é que as orientações legais e representações dos sujeitos estão a ser compreendidas pela Uni-CV, procurando-se simultaneamente contribuir com a organização de conteúdos formativos destinados aos estagiários e seus orientadores, de forma a contribuir para o aprofundamento das suas competências e simultaneamente criar um referencial indicativo de áreas prioritárias de formação em contexto de profissionalização para os professores de ensino secundário em Cabo Verde. Neste sentido levou-se a cabo um projeto de investigação ação, de natureza descritiva, com caráter eminentemente qualitativo, no âmbito do qual se concebeu e se implementou o b-curso: SuperVisão de estágio. Para a realização, com sucesso, desta investigação, foi necessário recorrer a diversas técnicas de recolha de dados em distintos momentos do processo, designadamente questionários, entrevistas (semi estruturadas e informais na modalidade individual e em focus group), observações participante e não participante, conversas e observações informais. Procedeu-se à análise estatística e de conteúdo com recurso ao Nvivo10 e ao Statistical Package for the Social Sciences (SPSS) garantindo uma triangulação destes que permitiu inferir da vontade dos parte dos participantes em ganharem destrezas no uso das Tecnologias de Informação e Comunicação (TIC) e na exploração dos ambientes online, revelando-se altamente motivados para a formação nos domínios, por eles, identificados como prioritários, a saber: TIC e ambientes online, planificação em educação, designadamente formulação de objetivos e competências em educação, estratégias e recursos pedagógicas. Tais domínios são percecionados como meio de desenvolvimento das competências científicas, técnicas e transversais no seu processo de profissionalização. Foi possível aferir, a partir dos resultados de investigação, que houve um considerável aumento do acesso à Internet pelos participantes. A par disso, também se verificou que a Uni-CV não dispõe, ainda, de condições técnicas e tecnológicas ideais para o desenvolvimento deste tipo de ações, com recurso a ambientes online. Porém, o recurso à Moodle no estágio pedagógico garantiu mais autonomia e flexibilidade ao estagiário, bem como ajudou-o na partilha quer de informações, quer de ansiedades, pelo que destacaram como atividades preferenciais, fóruns, o acesso a informações em diversos formatos, livro interativo e glossários. Como principais ganhos identificou-se o maior acesso a conteúdos específicos para trabalho na disciplina dinamizada pelos estagiários, bem como o feedback imediato facultado pela docente/investigadora e alguns colegas de estágio. As principais limitações relacionam-se com a duração do estágio (apenas quatro meses), o que limitou, nas atividades online, o envolvimento dos estagiários e seus orientadores, impossibilitando inclusivamente a participação destes últimos, bem como a evolução reflexiva na prática pedagógica. A estas dificuldades acresce a dificuldade de resposta da Uni-CV em facultar as condições ideais para que este b-curso decorresse com menos pressão. Apesar das dificuldades vivenciadas, entende-se que esta experiência contribuiu para que estes estagiários saíssem muito mais enriquecidos da sua formação académica inicial, pois, ainda que por pouco tempo, tiveram a possibilidade de “mergulharem no mundo digital”, de uma forma em que não o poderiam fazer sem que esta experiência ocorresse. Estes futuros professores interiorizam a necessidade de integração das TIC e dos ambientes online nas suas rotinas diárias e a necessária aprendizagem destas nas suas aprendizagens profissionais na perspetiva de formação ao longo da vida. Foi possível comprovar que, não obstante as dificuldades, é possível realizar uma prática pedagógica mediada por ambientes online na Uni-CV, desde que profissionais e gestores estejam cientes do seu potencial e procurem desenvolver as condições ideais para a sua exploração e desenvolvimento na Instituição, procurando envolver todas as forças ativas de modo a reunir sinergias e contribuir para o seu sucesso. A infoinclusão assumiria, aqui, um papel relevante na prossecução dos objetivos dos participantes neste processo da prática pedagógica, tornando-o ainda mais desafiador, para uns e para outros no âmbito das políticas e práticas da profissionalização docente em Cabo Verde.
KerkoCite.ItemAlsoKnownAs: 2129771:R9BYMURD 2317526:ARB3PRT4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Cape Verde; CLL:pt; publicImportV1

Alternatives towards achieving Education For All (EFA): a case of the informal sector business institute (ISBI), Nairobi, Kenya - Momanyi, C (2015)
In 1948 the United Nations declared that everyone has a right to education in the universal declaration of human rights. Education for All (EFA) is an international initiative first launched in Jomtien, Thailand, in 1990 to bring the benefits of education to “every citizen in every society’. To realize this aim, governments, civil society groups, and development agencies such as UNESCO and the World Bank have joined hands to achieve the EFA goals. Kenya is signatory to education for all initiative. Achieving the Education for All goals is critical for simultaneously attaining all 8 Millennium Development Goals (MDGs). The EFA strategies include the establishment of a policy on the re-entry of school-age mothers into the education system and the establishment of a non-formal education unit in the Ministry of Education Science and Technology. The recent implementation of free primary and secondary education is an effort by the government of Kenya to attain Universal primary Education (UPE) and the final attainment of EFA and MDGs. There are many suggestions both at the local and international levels on how to achieve this goal. Non-formal education and Technical and vocational education are some of the alternatives towards EFA, they lead participants to acquire practical skills in a particular occupation. Non formal education is flexible as more people who are out of the formal education system acquire skills. Strathmore Educational Trust (SET), a Public Charitable Trust incorporated in Kenya, established to promote educational initiatives started the Informal Sector Business Institute (ISBI) in 2004; a Non-formal education initiative to train jua kali artisans in ICT and business skills. Since its inception, more than 10,000 people have been trained in various skills. Data collected from artisans who have undergone the ISBI training showed that the artisans trained at ISBI are better than those form the same area that have not undergone the same training.
KerkoCite.ItemAlsoKnownAs: 2129771:5AMSN3QY 2317526:EIWGGY2S
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; C:Kenya; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:access; HDR25; Q:community education; Q:degree; Q:open learning; Q:secondary education; T:Educação profissionalizante; T:Lehrlingsausbildung; T:TVET; T:continuing education; T:work-based learning; publicImportV1

Alignment of higher professional education with the needs of the local labour market: the case of Ghana - Gondwe, Mtinkheni; Walenkamp, Jos (2011)
KerkoCite.ItemAlsoKnownAs: 2129771:EG3DK3SW 2249382:PHA6F7KQ 2317526:AF48W9NJ
Keywords: GS_en; _C:Ghana GHA; ⛔ No DOI found

Affordances and Constraints of Implementing Lesson Study for Teachers’ Professional Development: A Review - KIHWELE, JIMMY (African Journal of Teacher Education, 2020)
KerkoCite.ItemAlsoKnownAs: 10.21083/ajote.v9i0.5731 2129771:ZX8WS6TF
Keywords: _C:Australia AUS; _C:Canada CAN; _C:China CHN; _C:Ethiopia ETH; _C:Ghana GHA; _C:Indonesia IDN; _C:Ireland IRL; _C:Japan JPN; _C:Laos LAO; _C:Malawi MWI; _C:Netherlands NLD; _C:Pakistan PAK; _C:Rwanda RWA; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Thailand THA; _C:Turkey TUR; _C:Uganda UGA; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

Advancing Data-driven Decision-making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
zotzenLib.CopiedFrom: 2486141:UIV8NJ9M KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2129771:IPKSMS3Z 2129771:Q85KZGW8 2129771:U8L38F6S 2405685:MPRD5RKR 2486141:UIV8NJ9M 4556019:IGJQDXZM
Keywords: Author:OpenDevEd; _C:Sierra Leone SLE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Advances in clinical education: a model for infectious disease training for mid-level practitioners in Uganda - Miceli, Antonina; Sebuyira, Lydia Mpanga; Crozier, Ian; Cooke, Molly; Naikoba, Sarah; Omwangangye, Aquilla Priscilla; Rayko-Farrar, Lisa; Ronald, Allan; Tumwebaze, Margaret; Willis, Kelly S.; Weaver, Marcia R. (International Journal of Infectious Diseases, 2012)
Summary Advances in health professional education have been slow to materialize in many developing countries over the past half-century, contributing to a widening gap in quality of care compared to developed countries. Recent calls for reform in global health professional education have stressed, among other priorities, the need for approaches that strengthen clinical reasoning skills. While the development of these skills is critical to enhance health systems, little research has been carried out on the effectiveness of applying these strategies in the context of severe human resource shortages and complex disease presentations. Integrated Infectious Disease Capacity Building Evaluation (IDCAP) based at the Infectious Diseases Institute at Makerere University created a training program using current best practices in clinical education to support the development of complex reasoning skills among clinicians in rural Uganda. Over a period of 9 months, the program integrated classroom and clinic-based training approaches and measured indicators of success with particular reference to common infectious diseases. This article describes in detail the IDCAP approach to integrating advances in health professional education theory in the context of an overburdened, inadequately resourced primary health care system; results from the evaluation are expected in 2012.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijid.2012.07.003 10/f2fz47 2129771:Q9VBXXDP 2317526:RNKFJVNL
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AAZ:Africa South of the Sahara; CA:AandC; CL:de; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:P; CT:R; CT:T; D:developing country; P:health; P:media; P:nurse; R:evaluation; T:TVET; T:Training; T:work-based learning; Z:Clinical competence; Z:Education; distance; Z:Education; medical; continuing; Z:Education; nursing; continuing; Z:In-service training; _C:Uganda UGA; publicImportV1

Achieving teaching quality in sub-Saharan Africa: Empirical results from cascade training - Lange, Sarah; Benavot, Aaron (Springer VS, Wiesbaden, 2016)
© Springer Fachmedien Wiesbaden 2016. Sarah Lange examines the effectiveness of cascade training, which constitutes a cost-effective training model in teacher training. In development cooperation countries, teaching quality is expected to improve with teacher professional development; for this purpose, she explores the effectiveness of training multipliers in schools in Cameroon. This research question is analysed with a design, which encompasses a questionnaire survey provided to teachers, students and principals as well as a teacher video survey and a student achievement test. The empirical results show the effects of cascade training on the learner-oriented teaching practice, if the trained teachers are supported in their role as change agents. Among the conditions for the conceptual quality and the implementation of cascade training, the continuity of school-based professional development is particularly emphasized in light of the results.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-658-14683-2 10/gfw34w 2129771:EUDVDL6V 2129771:PRAA33FP 2317526:99594LBY 2317526:R5572EY6
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Cameroon; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:achievement; F:teaching; P:measurement; P:teacher training; P:teachers; R:questionnaire; R:survey; T:Training; T:trainee; publicImportV1; type:book

Access and use of clinical informatics among medical doctors in selected teaching hospitals in Nigeria and South Africa - Owolabi, Kehinde Aboyami (University of Zululand, 2017)
KerkoCite.ItemAlsoKnownAs: 2129771:UT98R4VX
Keywords: _C:Angola AGO; _C:Australia AUS; _C:Austria AUT; _C:Belgium BEL; _C:Benin BEN; _C:Bhutan BTN; _C:Bosnia and Herzegovina BIH; _C:Botswana BWA; _C:Brazil BRA; _C:Burkina Faso BFA; _C:Canada CAN; _C:China CHN; _C:Colombia COL; _C:Congo XCO; _C:Cuba CUB; _C:Denmark DNK; _C:Egypt EGY; _C:Ethiopia ETH; _C:Finland FIN; _C:France FRA; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:India IND; _C:Indonesia IDN; _C:Iran IRN; _C:Ireland IRL; _C:Japan JPN; _C:Jordan JOR; _C:Kenya KEN; _C:Korea XKOR; _C:Kuwait KWT; _C:Liberia LBR; _C:Malawi MWI; _C:Malaysia MYS; _C:Mali MLI; _C:Mexico MEX; _C:Morocco MAR; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Philippines PHL; _C:Portugal PRT; _C:Qatar QAT; _C:Romania ROU; _C:Saudi Arabia SAU; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Switzerland CHE; _C:Tanzania TZA; _C:Thailand THA; _C:Togo TGO; _C:Tunisia TUN; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; _C:eSwatini SWZ; __C:filed:1; __C:scheme:1

ACADEMIC USE OF MOBILE TECHNOLOGY BY STUDENT ATHLETES AT A LARGE DIVISION I MIDWESTERN UNIVERSITY: A GROUNDED THEORY STUDY - Kraft, Nicole (2018)
00000 KerkoCite.ItemAlsoKnownAs: 2129771:5V26P7PE 2129771:97RJVUH6
Keywords: _C:Cyprus CYP; _C:Estonia EST; _C:Ireland IRL; _C:Italy ITA; _C:Kuwait KWT; _C:Netherlands NLD; _C:New Zealand NZL; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1

A transição escola-trabalho em Cabo Verde: os sentidos da formação profissional para os jovens de baixa renda - Andrade, Maria Odete dos Reis de; others (Universidade de São Paulo, 2009)
KerkoCite.ItemAlsoKnownAs: 2129771:WZYIC97I 2317526:WTKVWRR4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Cape Verde; CLL:pt; publicImportV1

A study on mobile devices used by individuals for formal learning - Mangu, Hohepa (2019)
KerkoCite.ItemAlsoKnownAs: 2129771:5EJPQTGS
Keywords: _C:Australia AUS; _C:China CHN; _C:Indonesia IDN; _C:Kuwait KWT; _C:New Zealand NZL; _C:Nigeria NGA; _C:Tanzania TZA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

A Study of Agricultural Technical and Vocational Education and Training (ATVET) in Developing Countries - Walker, K; Hofstetter, S (2016)
KerkoCite.ItemAlsoKnownAs: 2129771:JHIQJH3P 2317526:HMBJNTIK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; A:West Africa; C:Benin; C:Ethiopia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:R; CT:T; D:developing country; F:gender; F:women; P:agricultural; P:agriculture; P:production; R:case study; T:Ausbildung; T:TVET; T:informal VET; publicImportV1; ⛔ No DOI found

A Skills Gap Analysis for Private Sector Development in Sierra Leone 2012 Economic Sector Work - Mannah, Emmanuel; Ngadi Gibril, Yvonne (2012)
KerkoCite.ItemAlsoKnownAs: 2129771:VZ2VN2UA 2405685:RFM2MVCL
Keywords: _C:Sierra Leone SLE

A situational analysis on the teaching of governance issues in the primary and junior secondary school curriculum in Zambia. - Kalimaposo, Kalisto; Kandondo, S. Chileshe; Matafwali, Beatrice; Mulenga, Innocent Mutale; Muleya, Gistered; Chakufyali, Peggy Nsama (2012)
Publisher: Zambia Journal of Education
Keywords: ⛔ No DOI found

A school mental health literacy curriculum resource training approach: Effects on Tanzanian teachers' mental health knowledge, stigma and help-seeking efficacy - Kutcher, Stan; Wei, Yifeng; Gilberds, Heather; Ubuguyu, Omary; Njau, Tasiana; Brown, Adena; Sabuni, Norman; Magimba, Ayoub; Perkins, Kevin (International Journal of Mental Health Systems, 2016)
© 2016 The Author(s). Background: Mental health literacy (MHL) is foundational for mental health promotion, prevention, stigma reduction, and care; School supported information pertaining to MHL in sub-Saharan Africa is extremely limited, including in Tanzania. Successful application of a school MHL curriculum resource may be an effective way to increase teacher MHL and therefore help to improve mental health outcomes for students. Methods: Secondary school teachers in Tanzania were trained on the African Guide (AG) a school MHL curriculum resource culturally adapted from a Canadian MHL resource (The Guide) for use in Africa. Teacher training workshops on the classroom application of the AG were used to evaluate its impact on mental health literacy in a sample of Tanzanian Secondary school teachers. Pre-post training assessment of participant knowledge and attitudes was conducted. Help-seeking efficacy for teachers themselves and their interventions for students, friends, family members and peers were determined. Results: Paired t test (n = 37) results demonstrate highly significant improvements in teacher's overall knowledge (p < 0.001; d = 1.14), including mental health knowledge, (p < 0.001; d = 1.14) and curriculum specific knowledge (p < 0.01; d = 0.63). Teachers' stigma against mental illness decreased significantly following the training (p < 0.001; d = 0.61). Independent t tests comparing the paired sample against unpaired sample also demonstrated significant differences between the groups for teacher's overall knowledge (p < 0.001). Teachers also reported high rates (greater than 3/4 of the sample) of positive help-seeking efficacy for themselves as well as for their students, friends, family members and peers. As a result of the training, the number of students teachers identified for potential mental health care totaled over 200. Conclusions: These positive results, when taken together with other research, suggest that the use of a classroom-based resource (the AG) that integrates MHL into existing school curriculum through training teachers may be an effective and sustainable way to increase the MHL (improved knowledge, decreased stigma and positive help-seeking efficacy) of teachers in Tanzania. As this study replicated the results of a previous intervention in Malawi, consideration could be given to scaling up this intervention in both countries and applying this resource and approach in other countries in East Africa.
KerkoCite.ItemAlsoKnownAs: 10.1186/s13033-016-0082-6 10/gf62ks 2129771:NME6EHAD 2317526:CXCUPU8E
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; A:Sub-Saharan Africa; AA:Africa; C:Malawi; C:Tanzania; CA:AandC; CCZ:Tanzania; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:Improvement; F:assessment; F:attitude; F:curriculum; F:outcomes; P:culture; P:health; P:teachers; R:impact; T:Ausbildung; T:Lehrwerkstatt; T:Training; T:trainee; Z:Adolescents; Z:Knowledge; Z:Mental health; Z:Mental health literacy; Z:School-based intervention; Z:Stigma; Z:Teachers; _C:Canada CAN; _C:Malawi MWI; _C:South Africa ZAF; _C:Tanzania TZA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; publicImportV1

A Roadmap to Vocational Education and Training Systems Around the World - Eichhorst, Werner; Rodríguez-Planas, Núria; Schmidl, Ricarda; Zimmermann, Klaus F (Institute of Labor Economics (IZA), 2012)
With young people among the big losers of the recent financial crisis, vocational education and training (VET) is often seen as the silver bullet to the problem of youth joblessness. This paper provides a better understanding of VET around the world, dealing with three types of vocational systems: school-based education, a dual system in which school-based education is combined with firm-based training, and informal training. We first explore the motivation for these different types of training, before summarizing the institutional evidence, highlighting the key elements of each training system and discussing its main implementation strengths and challenges. We subsequently review the evidence on the effectiveness of VET versus general education and between the three VET systems. There are clear indications that VET is a valued alternative beyond the core of general education, while the dual system tends to be more effective than school-based VET. Informal training is effective, however relatively little is known of its relative strengths compared with other forms of vocational education.
KerkoCite.ItemAlsoKnownAs: 2129771:Z6HUUQJF 2317526:HFS4J5GC
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:Sub-Saharan Africa; C:Botswana; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:R; CT:T; P:social; Q:flexible; R:quantitative; T:Ausbildung; T:TVET; T:dual TVET; T:firm-based training; T:informal training; T:school-based VET; T:vocational school; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

A review of traditional Ghanaian and Western philosophies of adult education - Fordjor, P; Kotoh, A,; Kpeli, K Kumah (International Journal of Lifelong Education, 2003)
The primary objective of this article is to critically examine some aspects of the traditional Ghanaian and Western philosophies of adult education. It is a well-attested fact that many of the pre-colonial and early colonial writers about Africa portrayed Africa as a dark continent devoid of advanced centres of learning worthy of emulation by others. The old West African civilizations of Ghana, Mali and Songhai with advanced centres of learning at Timbuktu and Djenne in the 11th century seemed to have been completely ignored by these writers (Boahen 1967: 20, Davidson 1966b: 50). Even though many other writers including several missionaries, anthropologists and historians, depicted Africa in a rather positive and scientific manner (Davidson 1966b, Goody 1966), much of the negative image created long ago still exists and needs to be examined and corrected. The formal Western system of school education was introduced in Ghana more than a century ago. Despite this, about 60% of the adult population today makes its living as illiterate farmers, workers, apprentices or master craftsmen in the various traditional art and craft production centres. Consequently, traditional adult education continues to play an important role in the social and economic development of the country. Like the Western system of adult education the Ghanaian traditional education has sound philosophical foundations, which have helped to maintain political stability and social cohesion in the country over the years. Much is written about Western and eastern philosophies but there is a dearth of literature on philosophies of adult education from Africa. Given that Africa is the second largest continent on the globe and that adult education proliferates throughout the continent, the authors felt their investigation would make a significant contribution to a global understanding of the field. Additionally, there is an increasing need for African students to appreciate and re-establish confidence in their own culture. This review cannot cover all of Africa so the focus is on Ghana, one country in West Africa.
KerkoCite.ItemAlsoKnownAs: 10.1080/0260137032000055321 10/ctk58c 2129771:MUC9B2B7 2317526:ZSV69QYX UTI-AF2875F6-DE57-37C7-9363-E343430A2EF5
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:West Africa; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:Q; CT:T; P:measurement; Q:adult education; T:Lehrlingsausbildung; T:Training; T:apprentice; _C:Canada CAN; _C:Denmark DNK; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Mali MLI; _C:Nigeria NGA; _C:Tanzania TZA; _C:Trinidad and Tobago TTO; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; publicImportV1

A Review of Community Extension Approaches to Innovation for Improved Livelihoods in Ghana, Uganda and Malawi - Wellard, Kate; Rafanomezana, Jenny; Nyirenda, Mahara; Okotel, Misaki; Subbey, Vincent (The Journal of Agricultural Education and Extension, 2013)
Purpose: Farmer-to-farmer extension offers a potentially low-cost and wide-reach alternative in supporting agricultural innovation. Various approaches are being promoted but information on their impact and sustainability is sparse. This study examines experiences of Self Help Africa and partners in Ghana, Uganda and Malawi. It asks: What is good practice in community extension for agriculture? What has been the impact of community extension on food security for smallholder farmers? What is the potential for scale-up and policy influence? Design/methodology/approach: Findings are based on a three-country mixed methods study of 240 households, farmer groups and community, government and NGO extensionists. Findings: Models of good practice include: community selection of extensionists, a twin technical and community development focus, and mutual learning. Impact of community based extension approaches on uptake of technologies, food security and livelihoods of poor groups was found to be broadly positive. Practical implications: Community based approaches appear sustainable where: communities provide support for their extensionists; community extensionists have marketable skills; communities and extensionists are developing Community Based Organisations (CBOs); and linkages are maintained with research and extension bodies. Community based extension approaches are being scaled-up in Malawi and elsewhere. To achieve sustainable pro-poor impacts, support will be needed for continued technical and community development training and back-stopping for community extensionists, and evaluation of different approaches. Originality/value: The study provides important evidence that community extensionists can help facilitate innovation in sustainable agriculture and reach the poor in a cost-effective way. They should be seen by policy-makers as part of pluralistic demand-driven extension, complementing over-stretched extension services. (Contains 6 tables.)
KerkoCite.ItemAlsoKnownAs: 10.1080/1389224x.2012.714712 10/gf62k8 2129771:3TBPH3VN 2317526:63P23WRI
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Malawi; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:learning; F:policy; F:pro-poor; P:agricultural; P:agriculture; P:economy; P:measurement; P:services; P:technology; R:evaluation; R:impact; R:mixed method; T:Training; Z:Agricultural Occupations; Z:Agriculture; Z:Community Development; Z:Community Support; Z:Economically Disadvantaged; Z:Evidence; Z:Food; Z:Foreign Countries; Z:Innovation; Z:Poverty; Z:Rural Education; Z:Rural Extension; Z:Security (Psychology); Z:Sustainability; _C:Benin BEN; _C:Ghana GHA; _C:Malawi MWI; _C:Morocco MAR; _C:Norway NOR; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; publicImportV1

A Quality assessment of education and for Kenya's tour-operating sector - Mayaka, M; King, B (Current Issues in Tourism, 2002)
This study examines the provision of tourism education and training in Kenya in the context of Sub-Saharan Africa and developing countries. Specifically the paper examines the human resource skills needed by Kenya’s tour-operating sector and the extent to which current training provision is adequate. The approach used in the present study is a modified version of WTO’s Tourism Education and Quality (TEDQUAL) methodology. The results indicate considerable convergence between the perceptions of industry operators and education providers concerning quality gaps in the development of skills. A number of systemic training shortcomings are identified including curriculum deficiencies and the inadequate development and enhancement of workplace skills. In view of the resource constraints facing most developing countries, it is argued that tourism trainingandeducation should consciously address the needs of the locally-based industry and that such an approach should result in a more effective education and training system.
KerkoCite.ItemAlsoKnownAs: 10.1080/13683500208667911 10/dkhvf5 2129771:NHULUCSM 2317526:2ZMSW74Z
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; C:Kenya; CA:AandC; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:T; D:developing country; F:assessment; P:measurement; P:technology; P:tourism; T:Ausbildung; _C:Algeria DZA; _C:Australia AUS; _C:Canada CAN; _C:Congo XCO; _C:Egypt EGY; _C:France FRA; _C:Ghana GHA; _C:Indonesia IDN; _C:Japan JPN; _C:Kenya KEN; _C:Namibia NAM; _C:Netherlands NLD; _C:New Zealand NZL; _C:Nigeria NGA; _C:Singapore SGP; _C:United States USA; __C:filed:1; __C:scheme:1; publicImportV1

A pilot of the use of short message service (SMS) as a training tool for anaesthesia nurses - Duys, R.; Duma, S.; Dyer, R. (Southern African Journal of Anaesthesia and Analgesia, 2017)
© 2017 The Author(s). Background: Anaesthesia nurses form a critical part of the team providing perioperative care to patients, but no accredited training exists for them in South Africa. In this setting, short in-service training interventions are a pragmatic attempt at improving nurse performance and patient outcomes. Traditional didactic teaching formats have limitations, and mLearning (the use of mobile telephones to facilitate education) has proved equivalent or superior to traditional teaching methods in several settings. Despite very high levels of mobile phone ownership amongst healthcare workers in Africa, this form of educational delivery has not been tested in the hospital-based nursing population. Methods: A telephonic true/false pre-test was performed with 12 nurses of varying levels of training, to assess their preexisting knowledge of anaesthesia. A pre-learning package was then delivered to them in the form of daily SMSs for a month, covering relevant anaesthesia content. A telephonic post-intervention test was performed to assess whether anaesthesia theory knowledge had improved. Results: Median test scores out of 30 were compared using a Wilcoxon signed rank test and were statistically higher in the postintervention test: 25 (IQR 20-26) vs. 21 (IQR 20-21.25) (p = 0.018). Conclusions: The results demonstrate an association between a cheap and widely available educational vehicle, and an increase in nurse knowledge scores. The use of mobile telephones in medical education in limited-resource settings should be explored further.
KerkoCite.ItemAlsoKnownAs: 10.1080/22201181.2017.1317422 10/gf62mm 2129771:YCYHD7KA 2317526:3KQQLLLS
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:outcomes; F:pedagogy; F:teaching; F:teaching method; P:health; P:media; P:nurse; P:service industry; P:services; Q:e-learning; T:Ausbildung; T:Training; T:work-based learning; Z:Anaesthesia nurse; Z:Nurse education; Z:Short Message Service (SMS); Z:eLearning; Z:mLearning; _C:Australia AUS; _C:Iran IRN; _C:Ireland IRL; _C:Kenya KEN; _C:South Africa ZAF; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; publicImportV1

A Map of Mkushi District Health Centres - Iseje, Fatuma (2023)
This map is an accurate map of the Health Centres coming under the Ministry of Health, Mkushi District. The health centre locations were collected an validated over a period of approximately two years (2022-23).
ZenodoArchiveID: 10850926 ZenodoArchiveConcept: 10850925 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1118 2129771:5S8X4MGW
Keywords: _r:AddedByMyEducationEvidence

A longitudinal study of learning, progression, and personal growth in Sierra Leone - Johnson, David; Hsieh, Jenny (University of Oxford, 2019)
KerkoCite.ItemAlsoKnownAs: 2129771:TFER47AP 2405685:A2EVGSWW
Keywords: _C:Sierra Leone SLE

A incompatibilidade entre os atributos dos recursos educacionais abertos e as preferências dos usuários como barreira à difusão de inovação - Correa, Juliana Nelia do Nascimento (Universidade de São Paulo, 2019)
KerkoCite.ItemAlsoKnownAs: 10.11606/D.12.2019.tde-20122018-174850 2129771:67HFPAHX 2129771:ESYSVDIA 2129771:FISSENID 2129771:JDI67S4E 2129771:Z6EDAH7Q
Keywords: _C:Australia AUS; _C:Brazil BRA; _C:Canada CAN; _C:Chile CHL; _C:China CHN; _C:Germany DEU; _C:Iceland ISL; _C:India IND; _C:Ireland IRL; _C:Korea XKOR; _C:Luxembourg LUX; _C:Mauritius MUS; _C:Montenegro MNE; _C:Netherlands NLD; _C:Pakistan PAK; _C:Peru PER; _C:South Africa ZAF; _C:Spain ESP; _C:Sudan SDN; _C:Sweden SWE; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Venezuela VEN; _C:Zambia ZMB; __C:filed:1; __C:scheme:1

A global outlook to the interruption of education due to COVID-19 pandemic: Navigating in a time of uncertainty and crisis - Bozkurt, Aras; Jung, Insung; Xiao, Junhong; Vladimirschi, Viviane; Schuwer, Robert; Egorov, Gennady; Lambert, Sarah; Al-Freih, Maha; Pete, Judith; Don Olcott, Jr; Rodes, Virginia; Aranciaga, Ignacio; et al. (Asian Journal of Distance Education, 2020)
Number: 1 EdTechHub.Source: <this> EdTechHub.Source: 2129771:QXHI373Z EdTechHub.Source: <this> EdTechHub.Source: 2129771:QXHI373Z KerkoCite.ItemAlsoKnownAs: 2129771:QXHI373Z 2129771:R99FXCAA 2405685:CFE5CVWB
Keywords: Author:OpenDevEd; COVID-19; Coronavirus Pandemic; _C:Algeria DZA; _C:Argentina ARG; _C:Australia AUS; _C:Belize BLZ; _C:Brazil BRA; _C:Canada CAN; _C:China CHN; _C:Congo; Democratic Republic COD; _C:Egypt EGY; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:Greece GRC; _C:Guatemala GTM; _C:India IND; _C:Ireland IRL; _C:Italy ITA; _C:Japan JPN; _C:Kenya KEN; _C:Korea (Republic of) KOR; _C:Korea XKOR; _C:Mexico MEX; _C:Namibia NAM; _C:Netherlands NLD; _C:Peru PER; _C:Philippines PHL; _C:Romania ROU; _C:Russian Federation RUS; _C:Rwanda RWA; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:Somalia SOM; _C:South Africa ZAF; _C:Spain ESP; _C:Sweden SWE; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; __C:filed:1; __C:scheme:1; _genre:LR-literature_review; _r:ImportedToMyEducationEvidence; distance education; docs.opendeved.net; emergency remote education; online learning; ⛔ No DOI found

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (2020)
EdTechHub.Source: 2405685:JLEWADHF KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3756012 2129771:SB3DJ28L 2129771:XKGV4EYL 2339240:5FRH2GYG 2339240:97HNYI75 2405685:JLEWADHF 2405685:JTYIWEJY 2405685:SCDLVVC7 2486141:9MWJP6MS
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _C:Ghana GHA; _C:India IND; _C:Jordan JOR; _C:Malawi MWI; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _Not used in LR; _T:reviewed; __C:filed:1; __C:scheme:1; _bjoern_cv; _r:ImportedToMyEducationEvidence; _yl:i

A educação e aprendizagem de jovens e adultos na África Austral: visão geral de um estudo para cinco nações - Aitchison, John (Open Society Initiative for Southern Africa (OSISA), 2012)
A pesquisa para este relatório foi realizada em 2010 e 2011 em cinco países da África Austral e, em seguida, foi conferido e editado pelo professor John Aitchison, da Universidade de KwaZulu-Natal.
KerkoCite.ItemAlsoKnownAs: 2129771:Q4UV6D63 2317526:DKKQTBZ3
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; C:Angola; C:Lesotho; C:Mozambique; C:Namibia; C:Swaziland; CLL:pt; publicImportV1

A district level study on the deployment, allocation and utilisation of teachers between and within Malawi’s primary schools: an accountability and political settlements approach - Zubairi, Asma (University of Cambridge, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:CSX7CQWJ
Keywords: _C:Australia AUS; _C:Bangladesh BGD; _C:Botswana BWA; _C:Cambodia KHM; _C:Chile CHL; _C:China CHN; _C:Ethiopia ETH; _C:Gambia GMB; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Jamaica JAM; _C:Japan JPN; _C:Kenya KEN; _C:Lesotho LSO; _C:Liberia LBR; _C:Malawi MWI; _C:Mauritius MUS; _C:Mexico MEX; _C:Mozambique MOZ; _C:Namibia NAM; _C:Nepal NPL; _C:Niger NER; _C:Nigeria NGA; _C:Norway NOR; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:South Africa ZAF; _C:Tanzania TZA; _C:Turkey TUR; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1

A description of the self-perceived educational needs of emergency nurses in Durban, KwaZulu-Natal, South Africa - Dulandas, Reka; Brysiewicz, Petra (African Journal of Emergency Medicine, 2018)
© 2018 African Federation for Emergency Medicine Introduction: Emergency nurses are usually the first to interact with critically ill patients and victims of violence and injuries, and require advanced skills and knowledge to manage such patients. Inadequate training prevents nurses from providing optimal emergency care, and it is important to investigate if there are any skills and competencies lacking in these emergency nurses. We sought to describe the self-perceived educational needs of emergency nurses in Durban, South Africa. Methods: A descriptive quantitative survey was conducted with nurses working in four emergency centres (two state, and two privately funded hospitals) in Durban, South Africa. Results: The survey questionnaire was distributed with a response rate of 79% (n = 128). Almost half the respondents (48%, n = 61) scored less than the mean score of 29, thus indicating lower competency levels. The majority of respondents (67%, n = 85) perceived themselves as highly competent in basic skills (e.g. assess breathing, administer oxygen, assess circulation). Less than half the respondents (45%, n = 57) perceived themselves as highly competent in the intermediate skills (e.g. control haemorrhage, assist with endotracheal intubation, manage shock). A large number of respondents (46%, n = 59) perceived themselves as least competent in advanced skills (e.g. defibrillation/cardioversion, interpreting an echocardiogram [ECG]). The mean score obtained for educational need was 100, thus reflecting a high educational need, and more than half the respondents (62%, n = 79) scored higher than the mean score of 100 for educational needs. The lowest score was 41. Thirty percent (n = 38) of the respondents scored 117, indicating educational needs for all the competencies listed. Overall, 72% (n = 92) agreed that emergency education was a need. Discussion: The study emphasises the need for support systems for educational development of emergency nurses. Further training in specific skills and competencies may enhance emergency care provided. There is a growing need for ongoing educational development of emergency nurses in South Africa.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.afjem.2018.03.001 10/gf62nv 2129771:RG8A9AFE 2317526:PYTR6KRL
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CCZ:South Africa; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:P; CT:R; CT:T; P:media; P:nurse; R:quantitative; R:questionnaire; R:survey; T:Training; Z:Competency needs; Z:Educational needs; Z:Emergency nurses; _C:Australia AUS; _C:Botswana BWA; _C:Ghana GHA; _C:Pakistan PAK; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Thailand THA; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; publicImportV1

A Critical Review of Vocational Education and Training Research in 2012 and Suggestions for the Research Agenda - Mulder, Martin; Roelofs, Eline (2012)
This paper is a follow-up of the paper ECER-presented in 2012, ‘A Critical Review of Vocational Education and Training Research and Suggestions for the Research Agenda’ (Author & Co-author, 2012). This paper gave a description of research in the field of Vocational Education and Training (VET) in 2011. This new paper gives an overview of the field of VET research in 2012. In this article the VET research presented at the European Conference of Educational Research 2012 (Cádiz) is reviewed, as well as the articles of a number of VET research journals of publication year 2012. A total of 173 articles are reviewed and after a qualitative interpretation divided into seven different research themes. The conclusions of the review are quite similar to last year. 1. There is a lot of VET research and this research is quite diverse and fragmented. 2. The quality of the articles is not always very high, also because a lot of conference proceedings are included. 3. There are many important topics for further research.
KerkoCite.ItemAlsoKnownAs: 2129771:UQUK4HXG 2317526:FBJ74PAL 2317526:PCHAS6F4
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:South Africa; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:T; F:policy; P:social; T:TVET; _C:Ghana GHA; publicImportV1; ⛔ No DOI found

A Critical Review of Vocational Education and Training Research and Suggestions for the Research Agenda - Mulder, Martin; Roelofs, Eline (2011)
This paper gives a description of research in the field of Vocational Education and Training (VET). The field of VET research is quite scattered, so giving a full overview is hardly possible. Nevertheless, the VET research presented at the European Conference of Educational Research 2011 (Berlin) is reviewed, as well as the content of a number of VET research journals of publication year 2011. Research themes and topics are defined, and according to the categories the research is reviewed. The conclusions of the review are: 1. there is a large amount of research on VET which is quite diverse and fragmented; 2. much VET research lacks theoretical and empirical foundation; the dominant research methods are case and desk studies and explorative and analytical studies. There are hardly any experiments and intervention and design-based research studies; 3. there are various urgent topics for further research, which are elaborated in the paper.
KerkoCite.ItemAlsoKnownAs: 2129771:WHGWHSRH 2317526:QY3L2P53
Keywords: -FullBiblioUHMLgen; -GeneralCitations; CLL:en; _C:Australia AUS; _C:Austria AUT; _C:Canada CAN; _C:China CHN; _C:Czech Republic CZE; _C:Denmark DNK; _C:Finland FIN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:Indonesia IDN; _C:Italy ITA; _C:Latvia LVA; _C:Luxembourg LUX; _C:Netherlands NLD; _C:Saudi Arabia SAU; _C:Spain ESP; _C:Sweden SWE; _C:Switzerland CHE; _C:Turkey TUR; _C:Ukraine UKR; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; publicImportV1; ⛔ No DOI found

A continuum of teachers'e-learning practices - Sadeck, Osman (International Conference on e-Learning, 2016)
KerkoCite.ItemAlsoKnownAs: 2129771:NQYDJCXP
Keywords: _C:South Africa ZAF; _C:United States USA; __C:filed:1; __C:scheme:1; ⛔ No DOI found

A conceptual framework to understand teachers’ Professional Dispositions and Orientation towards tablet technology in secondary schools - Sackstein, Suzanne; Slonimsky, Lynne (South African Computer Journal, 2017)
00000 KerkoCite.ItemAlsoKnownAs: 10.18489/sacj.v29i2.469 10/gdm2tk 2129771:LQD4ETTP
Keywords: _C:Cuba CUB; _C:South Africa ZAF; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1

A conceptual framework for examining HRD and NHRD linkages and outcomes: Review of TVET literature - Kim, Sehoon; Kotamraju, Pradeep; Alagaraja, Meera (European Journal of Training and Development, 2014)
This paper aims to review technical vocational education and training (TVET) literature, identify different components of the TVET system and develop a conceptual framework that integrates human resource development (HRD) and national human resource development (NHRD) outcomes. The renewed focus on technical vocational education and training (TVET) is important for human resource development (HRD), as it expands current understanding of its role in economic development through workforce training. National human resource development (NHRD) perspectives recognize the role of TVET in linking regional and national economic development strategies. Furthermore, TVET’s focus on literacy education, poverty alleviation and inclusion of marginalized and vulnerable populations emphasizes social development outcomes that are critical for NHRD. Using this background, the integration of HRD and NHRD outcomes into one conceptual TVET framework for addressing workforce, economic and social development outcomes has been proposed.
KerkoCite.ItemAlsoKnownAs: 10.1108/ejtd-01-2013-0009 10/gf62qc 2129771:CSVKCHI6 2317526:JQWJZUQY
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; CLL:en; _C:Australia AUS; _C:Austria AUT; _C:Brazil BRA; _C:Canada CAN; _C:China CHN; _C:France FRA; _C:Germany DEU; _C:Ghana GHA; _C:Hungary HUN; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Israel ISR; _C:Kenya KEN; _C:Korea XKOR; _C:Netherlands NLD; _C:Pakistan PAK; _C:Russian Federation RUS; _C:Saudi Arabia SAU; _C:Singapore SGP; _C:South Africa ZAF; _C:Thailand THA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:filed:1; __C:scheme:1; publicImportV1

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission; Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 2129771:65LTW8QP 2129771:MVHKYSFP 2339240:9VRVIUE6 2405685:CFRE6D4Q 2405685:UU3R28HB
Keywords: _C:Sierra Leone SLE

A competency-based curriculum for Zambian primary and secondary schools: learning from theory and some countries around the world. - Mulenga, Innocent Mutale; Kabombwe, Yvonne Malambo (2019)
Publisher: International Journal of Education and Research KerkoCite.ItemAlsoKnownAs: 2129771:JGIJBCTW 2129771:XNAU5AEI
Keywords: ⛔ No DOI found

A comparative study of TVET in 5 African Countries with a specific focus on TVET Teacher Education - Papier, Joy (2017)
This article describes a five country (Cameroun, Egypt, Ghana, South Africa, Tanzania) study of ‘TVET Teacher Education in Africa’ that was commissioned in terms of an EU-South African collaboration in 2013. While the focus was on vocational teacher education, the contextual realities of each country‘s vocational systems was studied as this would impact on every aspect of vocational teacher development, for instance, what teachers would have to teach, who the students might be, how students would be expected to learn, available funding for Vocational Education and so on. Comparisons were therefore made over a range of elements that included the systems in place for vocational training, systems of vocational teacher education, and the modalities for training of VET teachers.
KerkoCite.ItemAlsoKnownAs: 2129771:8J6PBLVZ 2317526:6TNBGFXK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CLL:en; _C:Denmark DNK; _C:Egypt EGY; _C:Finland FIN; _C:Ghana GHA; _C:Ireland IRL; _C:Netherlands NLD; _C:South Africa ZAF; _C:Sweden SWE; _C:Tanzania TZA; __C:filed:1; __C:scheme:1; publicImportV1; ⛔ No DOI found

A Comparative Analysis of the Perceptions of Primary and Secondary School Teachers of Lesson Observation by Education Standards Officers in Zambia - Muzata, Kenneth Kapalu; Banja, Madalitso Khulupilika; Mulenga, Innocent Mutale; Njobvu, Tommie (Zambia Interdisciplinary Journal of Education (ZIJE) Online-ISSN 2710-0715, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:35PGW85A 2129771:PXEA7M4Y
Keywords: ⛔ No DOI found

A Comparative Analysis of Firm Based Training in East African Manufacturing Sector: Does Level of Education Matter? - Ndlovu, Tchaka; Kajiba, John; Aiko, Rose; Kessy, Flora; Mkenda, Beatrice K.; Kweka, Josaphat; Kabelwa, George (2006)
Using World Bank's (2003) firm-level Investment Climate Survey (ICS) data for Kenya, Tanzania and Uganda, this paper examines extent in which education and skill levels are important determinants of Firm-based Training (FBT) in the East African manufacturing sector. The findings show weak evidence on complementary hypothesis between education and FBT but one which differs significantly across (perhaps depending on educational and training capacity of) different countries. Although other determinants of FBT apply differently to specific countries, size and technology characteristics are common determinants across the three countries. Furthermore, firms that care about HIV epidemic train more as a means to abate the negative effects of the epidemic on their human resources. Since FBT has potential to contribute to skill development, the findings imply that enterprise training should receive similar policy emphasis as education in the bid to enhance human resource development for growth and poverty reduction.
Accepted: 2016-07-08T12:19:36Z KerkoCite.ItemAlsoKnownAs: 10/2905 2129771:3FAL2TJF 2129771:VZ78IMDZ 2317526:JNZAK2I3 2317526:NQXBAGZX
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; A:East Africa; A:Sub-Saharan Africa; C:Kenya; C:Tanzania; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:outcomes; F:policy; P:manufacture; P:measurement; P:technology; Q:degree; Q:distance learning; Q:tertiary education; R:impact; T:Ausbildung; T:Lehrlingsausbildung; T:TVET; T:firm-based training; _C:Ghana GHA; _C:Uganda UGA; publicImportV1; ⚠️ Invalid DOI; ⛔ No DOI found

6 Social choice and research capacity strengthening in Nigeria - Watts, Michael; Waziri, Nafisa; Akogun, Oladele (Social Choice, Agency, Inclusiveness and Capabilities, 2024)
Publisher: Cambridge University Press

4.5.A. Review of AfL and lesson pacing - Zimbabwe, OER4Schools (Open Development & Education, 2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722373 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1113 ZenodoArchiveConcept: 10722372
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4.4.A. Peer and self-assessment - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722359 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1112 ZenodoArchiveConcept: 10722358
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4.3.A. Formative feedback - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722355 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1111 ZenodoArchiveConcept: 10722354
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4.2.A. Learning objectives and success criteria - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722349 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1110 ZenodoArchiveConcept: 10722348
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4.1.B. Introduction to Assessment for Learning - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722347 ZenodoArchiveConcept: 10722346 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1109 2129771:WPP5H275
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4.1.A. Introduction to Assessment for Learning - OER in Education - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722338 ZenodoArchiveConcept: 10722337 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1108 2129771:8SJPX5R5
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

4. Assessment for learning and lesson pacing - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722321 ZenodoArchiveConcept: 10722320 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1107 2129771:W7VWDFQX
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

30 Years of Gender Inequality and Implications on Curriculum Design in Open and Distance Learning - Koseoglu, Suzan; Ozturk, Tugba; Ucar, Hasan; Karahan, Engin; Bozkurt, Aras (Journal of Interactive Media in Education, 2020)
Gender inequality is a pressing issue on a global scale, yet studies on this important issue have stayed on the margins of open and distance learning (ODL) literature. In this study, we critically analyse a batch of ODL literature that is focused on gender inequality in post-secondary and higher education contexts. We use Therborn’s social justice framework to inform and guide the study. This is a comprehensive social justice lens that sees inequality as “a life and death issue,” approaching empowerment as a central area of concern. Qualitative content analysis of 30 years of peer-reviewed literature reveals patriarchy and androcentrism as significant mechanisms that continue to produce gender inequality, in particular in women’s access to educational resources and formal learning opportunities. We highlight three themes that emerged in the content analysis: (1) ODL and equal opportunity; (2) Feminism and gender-sensitive curriculum design; and (3) Culturally relevant curriculum design. We critique views of access to technology-enabled education as an instrument for social justice, and provide a pedagogical model for an ODL curriculum centred on empowerment and agency, two concepts closely linked to existential inequality. We argue that such a curriculum is public service and requires a model of education that is based on participation and co-construction, and lies at the intersection of critical, feminist, and culturally relevant pedagogical practices.
Number: 1 Publisher: Ubiquity Press KerkoCite.ItemAlsoKnownAs: 10.5334/jime.553 2129771:KR3WWGKU 2447227:4E8PTHWF
Keywords: _C:Australia AUS; _C:Canada CAN; _C:China CHN; _C:Finland FIN; _C:Germany DEU; _C:Ghana GHA; _C:Guinea GIN; _C:Iceland ISL; _C:India IND; _C:Jordan JOR; _C:Korea; Republic KOR; _C:Malaysia MYS; _C:Mongolia MNG; _C:Nigeria NGA; _C:Pakistan PAK; _C:Papua New Guinea PNG; _C:Saudi Arabia SAU; _C:State of Palestine PSE; _C:Sweden SWE; _C:Tanzania TZA; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; distance education; gender inequality; gender studies; open and distance learning; social justice; women empowerment

3.6.A. Designing interactive lesson plans - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722301 ZenodoArchiveConcept: 10722300 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1106 2129771:WS3RSN5K
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3.5.A. Review of group work - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722293 ZenodoArchiveConcept: 10722292 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1105 2129771:QME7CZBK
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3.4.A. Talking points and effective group work - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722285 ZenodoArchiveConcept: 10722284 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1104 2129771:2RHUCKBQ
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3.3.A. Mixed pace group work with and without ICT - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722279 ZenodoArchiveConcept: 10722278 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1103 2129771:8RQD5DCX
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3.2.A. When to use group work and how to manage it - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722275 ZenodoArchiveConcept: 10722274 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1102 2129771:J28AW983
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3.1.A. Group work: Same task and different tasks group work - OER in Education - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722271 ZenodoArchiveConcept: 10722270 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1101 2129771:2QU4CXQC
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

3. Group work - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722239 ZenodoArchiveConcept: 10722238 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1100 2129771:RM723GSR
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

21st century learning in Zambia - iSchool.zm and OER4Schools.org - Cook, Peter (2014)
This video features http://ischool.zm and http://www.oer4schools.org. It was produced by Björn Haßler (http://bjohas.de), directed by Peter Cook, and camera by Rich Peart. The video was part-funded by ARM, and part-funded by OER4Schools.
KerkoCite.ItemAlsoKnownAs: 2129771:S8DGM9HE
Keywords: Author:Haßler; Author:OpenDevEd; _bjoern_cv; _r:ImportedToMyEducationEvidence

2020 Draft Framework for Curriculum Recovery Post COVID-19 - Department of Basic Education (Department of Basic Education, South Africa, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:3HJJ94KB

2.5.B. Engaging the community - Using applications - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722234 ZenodoArchiveConcept: 10722233 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1099 2129771:VDV45KW4
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.5.A. Engaging the community - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722229 ZenodoArchiveConcept: 10722228 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1098 2129771:G6IKVQBU
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.4.B. Concept mapping - Aligning OER II - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722224 ZenodoArchiveConcept: 10722223 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1097 2129771:A4J2RQAC
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.4.A. Concept mapping - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722208 ZenodoArchiveConcept: 10722207 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1096 2129771:T47NX2AQ
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.3.B. More on Question - Aligning OER - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722206 ZenodoArchiveConcept: 10722205 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1095 2129771:X8V8H6JA
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.3.A. More on questioning - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722199 ZenodoArchiveConcept: 10722198 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1093 2129771:HB65MV59
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.2.A. Questioning I - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722191 ZenodoArchiveConcept: 10722190 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1092 2129771:7AZRTNJV
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.1.B. Mid-morning - final day - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722186 ZenodoArchiveConcept: 10722185 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1091 2129771:8Z6ZUQMD
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2.1.A. Introduction to dialogue and effective questioning - Part A - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722178 ZenodoArchiveConcept: 10722177 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1090 2129771:EX33UASR
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

2. Whole class dialogue and effective questioning - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722150 ZenodoArchiveConcept: 10722149 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1089 2129771:IKCBTMZQ
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.4.B. ICTs in interactive teaching - Part B - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722143 ZenodoArchiveConcept: 10722142 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1088 2129771:INPQZED4
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.4.A. ICTs in interactive teaching - Part A - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10722137 ZenodoArchiveConcept: 10722136 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1087 2129771:XA72SREV
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.3.B. Activity Planning - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721987 ZenodoArchiveConcept: 10721986 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1086 2129771:ICXE636H
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.3.A. Activity planning and reflection - Part A - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721965 ZenodoArchiveConcept: 10721964 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1085 2129771:4EJG3AMP
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.2.B. Introduction to interactive teaching with ICT - Part B - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721929 ZenodoArchiveConcept: 10721928 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1084 2129771:2E8CR3HM
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.2.A. Introduction to interactive teaching with ICT - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721902 ZenodoArchiveConcept: 10721901 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1083 2129771:EC5R3DZ6
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.1.B. What is interactive teaching? - Part B - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721860 ZenodoArchiveConcept: 10721859 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1081 2129771:QRC9F3GI
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1.1.A. What is interactive teaching? - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721771 ZenodoArchiveConcept: 10721770 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1080 2129771:WMPVAPMX
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon

1. Introduction to interactive teaching and the use of ICT - OER4Schools Zimbabwe (2022)
This resource is an adaptation of the Zambian OER4Schools programme, available here: https://oer.opendeved.net/wiki/OER4Schools. The Zambian OER4Schools programme was adapted for use at Mpumeleo High School (Nkayi District, Zimbabwe) and Siachilaba School (Binga District, near Victoria Town, Zimbabwe).
ZenodoArchiveID: 10721898 ZenodoArchiveConcept: 10721897 KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.1082 2129771:5AER6D62
Keywords: _forthcoming; _r:AddedByMyEducationEvidence; coming soon